The biodiversity impacts of forestry and agricultural land grabs on Indigenous Peoples’ Lands - Jacqueline Choo; Luis R. Carrasco; David P. Edwards (Land Use Policy, 2027)

Genetic ancestry proportion influences risk of adverse events from tuberculosis treatment in Brazil - Jacqueline A. Piekos; Gustavo Amorim; Felipe Ridolfi; Marcelo Cordeiro-Santos; Afrânio L. Kritski; Marina C. Figueiredo; Bruno B. Andrade; Adalberto R. Santos; David W. Haas; Timothy R. Sterling; Valeria C. Rolla; Digna R. Velez Edwards; et al. (Human Genetics, 2026)
Tuberculosis (TB) treatment is highly effective, but response to therapy varies by geography and population subgroups. We assessed differences in TB treatment response in a representative and heterogeneous Brazilian population. We estimated genetic ancestry according to major genetic ancestry groups (African, European, and Amerindian) in the Regional Prospective Observational Research in Tuberculosis (RePORT)-Brazil cohort using ADMIXTURE software. RePORT-Brazil is an observational prospective cohort study of individuals with newly-diagnosed, culture-confirmed, pulmonary TB. Outcomes attributed to TB treatment included Grade 2 or higher adverse drug reaction (ADR), Grade 3 or higher ADR, hepatic ADR, and failure/recurrence. Genetic ancestry proportions were evaluated as predictors in univariate and multivariable logistic regression models for each outcome, and in stratified models for each genetic ancestry group. There were 930 pulmonary TB patients included in this study. In multivariable models we observed a decreased risk of Grade 2 + ADR when African ancestry proportion increased by 10% (Odds Ratio [OR] 0.41, 95% Confidence Interval [CI] 0.20–0.85) and an increased risk for Grade 2 + ADR with increasing European genetic ancestry (OR 2.33, 95% CI 1.14–4.76). In secondary analyses evaluating the interaction of HIV and genetic ancestry, we observed a statistically significant interaction between HIV and African genetic ancestry, but significantly decreased risk for Grade 2 + ADR with increasing African ancestry proportion. There were no associations with Amerindian genetic ancestry or for other treatment outcomes. In this Brazilian TB cohort, increased toxicity risk was associated with decreased African and increased European ancestry proportion.

The difference between perceived and measured particulate matter in high population density urban environments: A citizen co-creation approach - Kurt Calleja; David Paul Suda; Mark Anthony Caruana; Daniel Micallef; Edward Duca; Francesca Mizzi (Sustainable Cities and Society, 2026)

Beyond the dung heap: the reliability of spores of the ascomycete fungal genus Sporormiella (incl. Preussia) as a proxy indicator of dung and grazing animals - David L. Hawksworth; Patricia E.J. Wiltshire; K. Anupama; M.B. Govinda Rajulu; N. Thirunavukkarasu; S. Prasad; Kevin J. Edwards; T.S. Suryanarayanan (Review of Palaeobotany and Palynology, 2026)

Biome-scale spatial patterns of avian abundance reveal proactive conservation opportunities in North American grasslands - Caleb P. Roberts; Victoria M. Donovan; Samantha M. Cady; Brandon P.M. Edwards; Scott Morford; David Naugle; Rheinhardt Scholtz; Dirac Twidwell; Daniel R. Uden; Dillon Fogarty (Biological Conservation, 2026)

Insights on the heterogeneity of thermal transfer in the chalk aquifer using fibre-optic distributed temperature sensing - Katerina Kyrkou; Joseph Kelly; Adam Booth; Fleur Loveridge; David Boon; Edward Hough; Lawrence Scott; Matthew Jackson; Adrian Butler; Daniel Perez; Athena Chalari (Geothermics, 2026)

The modelled impact of low traffic neighbourhoods (LTNs) on air pollution: findings from 5 schemes in London - Haneen Khreis; Matthew Williams; Chetan Lad; Dave Fevyer; Anthony A. Laverty; David Jinks; Jamie Furlong; James Woodcock; Phil Edwards; Anna Goodman (Environmental Research, 2026)

Dracula under siege: Persistent demand for a threatened and range-restricted orchid taxa - Edicson Parra-Sánchez; Luis Baquero; Juan Camilo Ordóñez-Blanco; Karen Gil-Amaya; David P. Edwards; Oscar Morton (Biological Conservation, 2026)

Restoration of a Mid-Atlantic Coastal Bay Scallop Population (Argopecten irradians) - Richard A. Snyder; Rebecca T. Smith; Darian M. Kelley; Sean Fate; Robert J. Orth; Bowdoin Lusk; Christopher J. Patrick; Stacy A. Krueger-Hadfield; Jan McDowell; Fredrick C. Holbert; John C. Lewis; John P. Richardson; et al. (Estuaries and Coasts, 2026)
We have attempted to re-establish bay scallops to the Virginia, U.S.A. coastal bays and document the dynamics of the restoration effort. Bay scallops ( Argopecten irradians ) once flourished in the eelgrass ( Zostera marina ) of the Virginia coastal bays. Eelgrass wasting disease led to declines, and both eelgrass and scallops were completely lost after a 1933 hurricane. The Virginia Institute of Marine Science (VIMS) led a successful eelgrass restoration effort beginning in 1997, with eelgrass beds expanding at 204 ha per year since 2012 and covering over 4,800 ha in 2025. From 2009 to 2025, bay scallops were brought in from North Carolina, New York, and Florida to the VIMS Eastern Shore Laboratory (VIMS ESL) in Wachapreague, VA and used to raise bay scallops for restoration. Progeny were released to the eelgrass beds and held in spawning cages. Annual census data documented low and fluctuating scallop densities from 2012 to 2018. From 2019 to 2025, we have observed continued exponential growth with a current (2024–2025) specific growth rate of µ = 0.468 year − 1 and a population doubling time of 1.48 years. The carrying capacity of the system for the new Virginia bay scallop population remains unknown with the population still in the exponential growth phase. In 2025 the annual census documented an average density of 0.114 scallops m − 2 and maximum recorded local density within 50 m − 2 sampling stations of 0.52 scallops m − 2 . Aggregation within the population was anticipated as necessary for reproductive success and was observed in population data with increasing density.

Land sparing outperforms land sharing across an elevational gradient in tropical cattle-farming landscapes - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; James. J. Gilroy; David P. Edwards (Biological Conservation, 2026)

The Effects of Land‐Use Dynamics on Avian Phylogenetic Diversity Across Island Ecosystems - Halvina G. Saiya; David P. Edwards; Matthew J. Struebig; David J. I. Seaman; Robby Butarbutar; Nurul L. Winarni; Simon L. Mitchell; Jatna Supriatna; Rob W. Martin; Adi Karya; Robert P. Freckleton (Journal of Biogeography, 2026)
Aim To test whether forest extent and recent forest‐cover change are associated with avian phylogenetic diversity and community‐level evolutionary value across islands. Location Seven islands spanning Borneo and Wallacea in the Malay Archipelago. Taxon Terrestrial birds. Methods We sampled 1410 sites (2010–2022). We calculated phylogenetic diversity (PD), mean phylogenetic distance (MPD), mean nearest taxon distance (MNTD) and their standardised effect sizes (SES), as well as community‐level EDGE (Evolutionarily Distinct and Globally Endangered). Responses to (i) average forest proportion (250‐m radius) and (ii) recent forest‐cover change were analysed with spatial linear mixed‐effects. Results Observed PD showed a negative visual trend with increasing forest proportion, whereas SES PD declined. MPD showed only a weak positive visual trend with forest proportion, whereas SES MPD showed no clear response. Although observed MNTD appeared to increase in the binned visual summaries, both observed MNTD and SES MNTD showed significant negative associations with forest cover in the spatial models, indicating stronger nearest‐neighbour phylogenetic clustering in more forested sites. Effects of recent forest loss (2010–2022) on SES metrics were generally weak and inconsistent. Although PD also declined with decreasing rates of forest change, community‐level EDGE was higher where forest cover was greater, indicating higher average evolutionary distinctiveness and extinction risk. Main Conclusions In this archipelagic system, forest amount is a key correlate of phylogenetic structure and the retention of evolutionarily distinctive, high‐risk lineages. By contrast, recent forest‐cover change showed weaker and more context‐dependent associations. Conserving intact forests remains crucial for safeguarding the evolutionary legacy of island bird communities.

Biological Sex Is Binary and Rooted in Anisogamy - Tim Janicke; Göran Arnqvist; Pierre‐André Crochet; Patrice David; Philippe Jarne; Jussi Lehtonen; Thomas Lenormand; Edward H. Morrow; Geoff A. Parker; Paul A. Saunders; Jeanne Tonnabel; Frédéric Veyrunes; et al. (Ecology Letters, 2026)
The definition of biological sex has become a renewed focus of societal debate, fuelled by the conflation of biological principles with discussions of human gender diversity. Here, we argue that conceptual clarity critically depends on separating these domains. Drawing on evolutionary theory and empirical evidence, we maintain that biological sex is best defined as a binary classification of male and female reproductive strategies rooted in anisogamy, characterised by the production of two discrete gamete types of different sizes. We stress that gamete size constitutes the ultimate criterion for biological sex and that this definition applies consistently across sexual systems, from separate‐sexed species to hermaphrodites, irrespective of variation in karyotype, hormonal profile, somatic phenotype, or behaviour. Further, we emphasise that evolutionary insights offer a coherent explanation for recurring, though not universal, associations between biological sex and patterns of sex‐specific selection, sexual dimorphism and parental care. We conclude that the definition of biological sex as a binary classification based on gamete size is a powerful scientific framework compatible with the diversity of sexual phenotypes found in anisogamous organisms and distinct from the concept of human gender.

Lung function and inflammation in healthy young adults after 6.6 hours of 0.07 ppm ozone exposure - Edward R. Pennington; Jairus C. Pulczinski; Martin W. Case; Jacob S. Griffin; Neil E. Alexis; Ilona Jaspers; Carole Robinette; Ann Chelminski; Andrea Davis; Neena Miller; David B. Peden; Andrew J. Ghio; et al. (Environmental Research, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Fall Armyworm (Spodoptera Frugiperda) Management and Baby Corn Yield Under Organic, Conventional, and Integrated Farming Systems in Sub-humid Tropics - Martin Muriuki; Felix Matheri; David Bautze; Edward Karanja; Anne Kelly Kambura; Edwin Mwangi; Nancy Munyoki; Chrysantus Tanga; Milka Kiboi (Journal of Crop Health, 2026)

The Circular Economy has High Potential to Mitigate the Global Biodiversity Crisis - Jianan Xie; Yingtong Zhu; Chloe Yun Yi Tan; Cengiz Akandil; Joanna. L. Coleman; David P. Edwards; Wanggi Jaung; Kelvin S.-H. Peh; Linjun Xie; Shweta Yadav; L. Roman Carrasco (Circular Economy and Sustainability, 2026)

Strategic deep tillage of deep sand soils impacts the sorption and biological availability of trifluralin - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Michael T. Rose; Benedict Arthur; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2026)

Pathologic Description and Genetic Characterisation of Kudoa thunni From Yellowfin Tuna ( Thunnus albacares ) in the Caribbean Sea - Noor‐Ul Huda; Magali Duran; Jonnel Edwards; Cynthia Ware; Olando Harvey; Matt J. Griffin; David P. Marancik (Journal of Fish Diseases, 2026)
Yellowfin tuna ( Thunnus albacares ) is a valuable recreational and commercial species in Grenada and the Caribbean region. Myxozoans, specifically the monotypic Kudoidae family within the Order Multivalvulida, are marine parasitic organisms that can negatively impact fish health and marketability. On 8 September 2023, muscle fillets from a yellowfin tuna caught off the coast of Grenada and containing numerous white nodules were submitted for diagnostic evaluation. Gross examination of the muscle showed firm, spherical to ovoid, white polysporous cysts approx. 0.8–1.3 mm in diameter and approx. 10–20 cysts per 2 × 2 cm section of muscle. Cysts were sharply excised and assessed by wet mount cytology revealing a myriad of quadrate myxosporean parasites consistent with the genus Kudoa . Histopathologic examination demonstrated numerous, intracytoplasmic plasmodia with thick hyaline walls containing intact and necrotic myxospores. Parasites present outside of plasmodia were associated with myoliquifaction of the tissue. The case isolate was morphologically consistent with K. thunni and the partial 18S small subunit rDNA (SSU) and 28S large subunit rDNA (LSU) demonstrated high homology (SSU: 99.8%–100%; LSU: 99.5%–100%) to several K. thunni isolates, including those isolated from blackfin tuna ( T. atlanticus ) harvested near the Caribbean islands of St. Kitts and Nevis. This is the first report of K. thunni infecting yellowfin tuna in the Caribbean region and expands the epidemiologic, pathologic, and molecular record for this parasite.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Investigating the contributions of herbaceous vegetation biomass to soil accretion in Louisiana's coastal deltaic wetlands using airborne imaging spectroscopy - Daniel Jensen; Elena Solohin; Edward Castañeda-Moya; Marc Simard; David R. Thompson; Cathleen E. Jones; Alexandra Christensen; Andre Rovai; Andy Fontenot; Robert Twilley (Remote Sensing of Environment, 2026)

Phylogenetic diversity recovery along Atlantic Forest succession: The potential for conserving evolutionary history - Alex Josélio Pires Coelho; Carlos Mário Galván-Cisneros; Pedro Manuel Villa; Heitor Mancini Teixeira; Fabio Antônio Ribeiro Matos; Alice Cristina Rodrigues; Nayara Mesquita Mota; Fernando da Costa Britod Lacerda; Fábia Maria dos Santos Souza; Nathália Vieira Hissa Safar; Nathália Silva; Fabiana Bonani; et al. (Biological Conservation, 2026)

Dissection of local haplotype diversity at soybean rust loci reveals resistance-associated and context-dependent variation patterns in diverse germplasm - Shameela Mohamedikbal; Hawlader A. Al-Mamun; Jacob I. Marsh; Shriprabha R. Upadhyaya; Jacqueline Batley; David Edwards (Theoretical and Applied Genetics, 2026)
Key message Soybean rust-associated haplotypes around significant SNPs show variable effects across diverse accessions, while distinct soybean mosaic virus-resistant haplotypes were identified at the Rsv1 locus on chromosome 13. Abstract Soybean rust (SBR), caused by the fungal pathogen Phakopsora pachyrhizi, significantly affects soybean yield and quality globally. Here, we present an association and haplotype analysis of 2,815 phenotypically diverse soybean accessions to identify durable sources of genetic variation associated with SBR. We characterised allelic diversity and local haplotype effects at two important SBR loci on chromosomes 13 and 18 ( Rpp1 ). At these genomic regions, marker groups containing tightly linked single-nucleotide polymorphisms (SNPs) associated with reduced disease severity were identified. In accessions showing reddish-brown lesion, marker groups associated with increased disease severity include gene variants in Glyma.18G280400 and Glyma.18G280300, indicating potential for resistance improvement. Within the delimited genomic region on chromosome 13, which is reported to be associated with multiple soybean diseases, we also mapped resistance-specific haplotypes associated with soybean mosaic virus, including in the Rsv1 carrier PI 96983, identifying candidate genes that may contribute to resistance. Cross-population haplotype transfer analysis between reddish-brown and tan lesion accessions for SBR around all significant loci showed context dependence of variation patterns, with stable loci on chromosome 07, having gene variants for Glyma.07G261000 . These findings provide insights into the genetic architecture associated with soybean disease resistance and contribute to haplotype-based resistance breeding efforts; however, future functional validation of identified candidate causal alleles and genes is required. Our results also demonstrate the potential of local haplotyping with newer phenotypic data for SBR to identify linked causal alleles and individuals containing beneficial alleles, for breeding applications.

Accessing crop genetic diversity via pangenomics - Tessa R. MacNish; Venkataramana Kopalli; Silvia F. Zanini; Rod J. Snowdon; Agnieszka A. Golicz; David Edwards (Theoretical and Applied Genetics, 2026)
With the increasing accuracy and decreasing cost of sequencing technology, the extent of structural variation (SV) and its importance in crop species has become increasingly evident. SVs such as insertions, deletions, and inversions have been associated with genetic variation of agronomically important traits and the diversification of crop species. Pangenomes aim to capture the genetic diversity of a species, population or genus, by incorporating the genomes of multiple individuals. The additional genetic diversity represented by a pangenome compared to a single-genome reference can aid the association of variation with traits and support crop improvement. Genus-wide pangenomes representing related crop species as well as their wild relatives can be used to identify and introduce novel genetic variation associated with agronomically important traits into crops. Pangenomes can aid crop improvement through pangenome assisted breeding (PAB) and genome editing. PAB is an adaption of marker assisted breeding that associates pangenome-based markers, including single nucleotide polymorphisms (SNPs) and SVs, with a trait of interest. Genome editing can use CRISPR/cas9 or similar tools to introduce or change the expression of agronomically important SVs. Pan-epigenomics is an emerging field that can complement pangenomics studies by identifying epigenetic modifications such as DNA methylation, histone modifications, and chromatin accessibility, which play important roles in regulating gene expression and have been shown to contribute to intraspecific diversity and agronomically important traits. We highlight the advances of crop pangenomics and their use in crop breeding and improvement.

Regional Nasal Drug Deposition in Pediatric vs. Adult Models: In vitro Insights into User Technique and Breathing Patterns Sensitivity - Mohammad Hejazi; Xiomara Owen; David J. Edwards; Michael Hindle; Worth Longest; Theodore Schuman; Ross Walenga; Steven Chopski; Anubhav Kaviratna; Bryan Newman; Laleh Golshahi (Pharmaceutical Research, 2026)
Purpose Although in vitro studies recommended for establishing bioequivalence of locally acting nasal suspension products provide useful information regarding product performance, currently they are not designed to fully account for variability introduced by patient-specific factors such as administration technique and breathing patterns. This limitation, combined with ethical and practical challenges in conducting pediatric clinical trials, creates a knowledge gap in understanding age-related differences in nasal drug delivery. Methods Anatomically realistic in vitro nasal models representing an average child and adult, in terms of total drug delivery to the sites of intended action posterior to nasal valve, were used to investigate the sensitivity of regional nasal drug deposition to variations in administration parameters and breathing conditions. Three breathing conditions were evaluated: breath hold, gentle sniffing, and vigorous sniffing. Administration parameters were varied using a Box-Behnken experimental design. Results Results showed that for commercially available nasal sprays, breathing patterns did not significantly affect drug delivery in the adult model, but extreme conditions (no breathing vs. vigorous sniffing) caused significant differences in anterior deposition in the child model. Differences between gentle sniffing and the other conditions were not statistically significant. The sensitivity analysis revealed that in vitro drug deposition patterns differ between child and adult nasal cavities under identical user parameter variations, and variable importance differed across nasal cavity regions. Conclusions This study demonstrates the potential for targeted drug delivery by enabling the identification of the optimal administration parameters to achieve desired outcomes, such as enhanced drug deposition in specific nasal regions.

Prevalence of traded bird species in key biodiversity areas - Oscar Morton; Tom Lansley; Stuart H. M. Butchart; Graeme M. Buchanan; David P. Edwards (Conservation Biology, 2026)
The use and trade of biodiversity involve tens of thousands of species that are exploited at a range of scales, intensities, and degrees of sustainability. As a result, some are highly threatened. Key biodiversity areas (KBAs) are sites of significance for the persistence of biodiversity identified nationally based on standardized criteria. The degree to which biodiversity in KBAs is likely to be used and traded is not well understood. We undertook a fine‐scale assessment of the area of habitat (AOH) of traded species in KBAs. We used data on >16,000 KBAs and combined these with AOH maps for >10,000 bird species, a heavily traded and well‐documented indicator taxon. We subsequently mapped and quantified the distribution of traded species richness, extinction risk, and range‐size rarity in and adjacent to KBAs. Although less than half of all bird species are traded, we found that most bird species in KBAs were traded, and the richness of traded species was more than twice (119%) that of nontraded species. Traded species had comparable proportions of their AOH (22.5% on average) in KBAs as nontraded species (21.5%). Global hotspots of richness, extinction risk, and range rarity for traded species disproportionately occurred in KBAs, which had higher levels of extinction risk and range rarity for traded species than locations immediately outside KBAs. Of the 46 species that are likely threatened by unsustainable use and have the majority of their habitat falling within KBAs, we found that eight species had no habitat in designated protected areas. Reconciling sustainable use and the critical importance of KBAs for threatened species is essential. Our results suggest that for some species, there is an urgent need to protect key sites and ensure that any use and trade of species within them are sustainable.

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Integrated Immunogenicity Assessment of a Novel, First-in-Class TrenibotulinumtoxinE Across 5 Clinical Trials for Glabellar Lines - Steve Yoelin; Edward Lain; Marion Moers-Carpi; Michael Gold; David Wirta; Wayne Lam; Amy S. Weitzenfeld; Jie Shen; Mitalee Tamhane (Toxicon, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Delta-X: An airborne remote sensing framework to calibrate hydrodynamic and ecogeomorphic processes responsible for land building in coastal deltas - Marc Simard; Cathleen E. Jones; Robert R. Twilley; Edward Castañeda-Moya; Sergio Fagherazzi; Cédric G. Fichot; Michael P. Lamb; Paola Passalacqua; Tamlin M. Pavelsky; David R. Thompson; Saoussen Belhadj-aissa; Pradipta Biswas; et al. (Remote Sensing of Environment, 2026)

Perinatal environmental exposures, maternal mental health and cognitive outcomes in very preterm infants born in urban London - Zeyuan Sun; Kaili Liang; Andrew Lawrence; Marguerite Leoni; Serena J. Counsell; Paola Dazzan; A David Edwards; Chiara Nosarti (International Journal of Hygiene and Environmental Health, 2026)

Performance evaluation and methods comparison of transcriptomic-based approaches for the characterization of wastewater treatment effluent - Adam D. Biales; Morgan S. Hu; David C. Bencic; Mary Jean See; Susan T. Glassmeyer; Edward T. Furlong; Julia M. Stelman; Weichun Huang; Dana W. Kolpin; Marc A. Mills; Laura D. Brunelle; Angela L. Batt; et al. (Environmental Pollution, 2026)

Managing risks in reverse logistics supply chains of demolition waste: A systematic literature review - I.E. Illeperuma; M.K.C.S. Wijewickrama; David J. Edwards (Environmental Development, 2026)

Organic farming with smallholder input rates cannot close the yield gap in Central Kenya - David Bautze; Anouk Unternährer; Felix Matheri; Martin Muriuki; Edward Karanja; Milka Kiboi (Organic Agriculture, 2026)

Impact of cover cropping on root lesion nematodes (Pratylenchus spp.) and nematode communities in Narcissus fields - Vongai Chekanai; Roy Neilson; David Roberts; Simon G. Edwards; Matthew A. Back (Applied Soil Ecology, 2026)

Evaluating the stability of synthetic cathinones in liquid urine and dried urine spots: impact of pH and storage conditions - Stefania Boccuzzi; David Cowan; Paul I. Dargan; Edward Goucher; Vincenzo Abbate (Archives of Toxicology, 2026)
Synthetic cathinones comprise a class of new psychoactive substances associated with significant morbidity and mortality. Their detection in biological samples is complicated by their instability, which can compromise quantification or interpretation. This study evaluates the stability of five synthetic cathinones – 4-chloroethcathinone (4-CEC), 4-ethylmethcathinone (4-EMC), N-ethylhexedrone (NEH), methylenedioxypyrovalerone (MDPV) and 4-chloro-α-pyrrolidinopropiophenone (4-Cl-α-PPP) – in dried urine spots (DUS) and liquid urine at acidic (pH 5.98) and mildly basic (pH 7.63) conditions. Fortified samples were stored at room temperature (25 °C) and refrigerated (4 °C) for up to 14 days and analysed using the Thermo Fisher VeriSpray™ Paper Spray Ion Source coupled to a Thermo Fisher Altis™ Plus Triple Quadrupole Mass Spectrometer. Urinary pH was the critical determinant of stability. Under acidic conditions, 4-EMC, 4-Cl-α-PPP, and MDPV retained > 90% of their initial concentration by day 14 in both matrices. Conversely, under basic conditions, 4-CEC and NEH degraded rapidly at room temperature ( p

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Global, regional, and national burden of hepatocellular carcinoma and contribution of nine modifiable risk factors across 185 countries/territories in 2022 - Ping Li; Zhan Ding; Yuqi Feng; Xiangyu Ren; Yongyue Wei; Changfa Xia; Yitao Yang; Quanbo Yang; Zhe Wang; Xuehong Zhang; L.G. van der Geest; Herbert Yu; et al. (Science Bulletin, 2026)

Hormetic effects of chemical contaminants on animal development: Mechanisms, phenotypes, and ecological implications - Evgenios Agathokleous; Peter Pressman; Edward J. Calabrese; David Costantini; Raul Narciso C. Guedes; A. Wallace Hayes; Vittorio Calabrese (Environmental Pollution, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Persistent chemicals in particulate matter (PM) near a hazardous waste thermal treatment facility - Chuqi Guo; Martine E. Mathieu-Campbell; Thomas Blanchard; Lavrent Khachatryan; Md Abdullah Al-Mamun; Qingzhao Yu; Myron Lard; Oluwafeyikemi Ogunmusi; Brenda Vallee; Wilma Subra; Iriel Edwards; David Malone; et al. (Atmospheric Pollution Research, 2026)

Tree cover influences bird assemblage composition in a city within the cerrado biodiversity hotspot - Daniele Pereira Rodrigues; David P. Edwards; Ana Claudia Almeida; Mauricio Almeida-Gomes (Urban Ecosystems, 2026)

Ulvan long-term biostimulant effects on Arabidopsis thaliana seed treatment via medium supplementation - Shai Shefer; Edward Vitkin; Ruslana Rachal Palatnik; David Zilberman; Alexander Golberg (Journal of Applied Phycology, 2026)
This study investigates the long-term effects of ulvan, a sulfated polysaccharide extracted from the green seaweed Ulva , on the growth and yield of Arabidopsis thaliana . While previous studies have demonstrated the short-term biostimulant effects of ulvan, well characterised ulvan long-term impact on plant development and seed yield remains unclear. The effects of a well-characterized crude ulvan extract on early germination, photosynthetic efficiency, root and shoot development, and final seed yield were determined. The results indicate that ulvan application at the time of sowing significantly enhances root elongation, shoot area, and photosynthetic activity, ultimately leading to a 43% increase in seed yield, suggesting a role in modulating metabolic pathways. Proteomic analysis further reveals significant upregulation of stress-related and growth-associated proteins, suggesting ulvan role in modulating metabolic pathways. Additionally, a comparative analysis of ulvan extracted two years apart demonstrates its biochemical consistency, reinforcing its potential for agricultural applications. These findings highlight ulvan promise as a sustainable biostimulant capable of reducing dependency on synthetic fertilizers while improving crop performance. Further research is needed to explore its efficacy across different crops and environmental conditions to optimize its integration into sustainable agricultural practices.

Screening cyanobacteria with antiplatelet properties as potential sources of natural products for preventing and treating cardiovascular diseases - Patricia I. Gómez; David Flaig; Edwards Araya; Olivia Rosales; Javiera Acuña; Marcelo Alarcón (Journal of Applied Phycology, 2026)

Metabolic cost of external work: a novel CPET parameter optimises characterisation of exercise performance in obese individuals - Jennifer J. Rayner; Rebecca R. Chamley; Robert Barker Davies; Oliver O’Sullivan; Peter Ladlow; Alex N. Bennett; Edward D. Nicol; Oliver J. Rider; David A. Holdsworth (European Journal of Applied Physiology, 2026)
Purpose Both obesity and cardiorespiratory fitness are crucial determinants of symptoms and prognosis. However, interpreting the gold-standard cardiopulmonary exercise test (CPET) is complicated by increasing body size and varying body composition. We hypothesised that the ‘metabolic cost of external work’ (or oxygen uptake (ml/min)/workload (Watts); V̇O 2 /W), a body weight-independent determinant of endurance capacity, would reflect metabolic health more accurately than V̇O 2 alone. Methods A test cohort of 160 fit individuals underwent anthropomorphic and metabolic assessment, maximal bicycle ergometer CPET, and six-minute walk test (6MWT). V̇O 2 /W was calculated at VT1 and peak. The performance of V̇O 2 /W was validated in 62 older, less fit individuals, undergoing the same protocol. 24 obese volunteers were assigned a weight loss intervention, and the impact on V̇O 2 /W examined. Results In both test and validation cohort, V̇O 2 /W at VT1 and peak correlated with 6MWT distance, more strongly than standard CPET parameters. Including V̇O 2 /W improved the accuracy of predicting 6MWT distance. V̇O 2 /W correlated with BMI, insulin sensitivity and waist-to-hip ratio. Metabolic cost falls with weight loss, in parallel to metabolic and functional improvements, in contrast to other CPET parameters. Conclusion Metabolic cost is strongly associated with functional capacity and metabolic health across a range of body weight and fitness, outperforming standard CPET metrics. It is a simple measure which may improve our assessment of the extent to which exertional symptoms are determined by metabolic factors in an individual, and thereby target the most appropriate intervention to those who will benefit most. Graphical Abstract

National-scale river water quality in the Philippines: establishing baselines in a mineralised megadiverse nation - Emma Biles; Richard David Williams; Decibel Faustino-Eslava; Loucel Cui; Francis Ian Gonzalvo; Kim Bryan Cabrera; Manilyn Casa; Craig MacDonell; Maria Regina V. Regalado; Laura Quick; Justine Perry Domingo; Trevor Hoey; et al. (Science of The Total Environment, 2026)

Integrating innovative design strategies in advancing sustainable housing in Kenya - David Njuguna Mathu; Bernadette Mukhwana Wanjala; Edward Otieno Owino; Salome Wambui Richu (Land Use Policy, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Strong Variation in Land‐Use Change Impacts on Tropical Avian Phylogenetic Diversity Between Ecoregions Highlights the Need to Sample Large Spatial Scales - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Robert P. Freckleton; Torbjørn Haugaasen; James J. Gilroy; David P. Edwards (Global Change Biology, 2026)
Forest conversion for agriculture is a major cause of tropical biodiversity loss, but its impacts vary with spatial scale. Higher species turnover in forests than in farmland means that land‐use change causes greater biodiversity loss at broader than at local scales, yet broad‐scale assessments are scarce. Phylogenetic diversity is increasingly prioritised in conservation to protect evolutionary history under global change, yet how deforestation‐driven changes in phylogenetic diversity scale spatially and accumulate in regions of high species turnover remains unclear. We compiled a large field database from across 13 biogeographically diverse regions affected by deforestation for cattle farming, covering most of Colombia, a megadiverse tropical country. Using occupancy models, we estimated bird communities for 1547 (936 observed plus 611 never‐observed) species across ecoregions and nationally in both forest and pasture habitats to quantify changes in phylogenetic diversity metrics and determine whether these impacts are dependent on spatial scale. We found an average loss of 2300 Myr of phylogenetic diversity at the country scale, with most species negatively affected across the phylogeny. Although single regional‐scale relative loss was on average comparable to broader scales, there was high variability between regional units. The latter was especially critical when evaluating metrics of evolutionary distinctiveness, which are key indicators for biodiversity conservation planning. Such underestimation of national‐scale impacts highlights the importance of sampling across multiple regions. Immediate conservation action is needed to safeguard evolutionarily unique species and prevent phylogenetic homogenisation driven by agricultural expansion across spatial scales—a threat often underestimated due to assessments limited to single biogeographic regions.

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Pangenomics combined with artificial intelligence and precision breeding can accelerate crop improvement - Teng Li; Shameela Mohamedikbal; Mitchell Bestry; Jacqueline Batley; David Edwards (Current Opinion in Plant Biology, 2025)

Quest for Orthologs in the era of Data Deluge and AI: Challenges and Innovations in Orthology Prediction and Data Integration - Sina Majidian; Armin Hadziahmetovic; Felix Langschied; Stefano Pascarelli; Silvia Prieto-Baños; Jorge Rojas-Vargas; Lars Arvestad; Jitender Cheema; Salvatore Cosentino; Ingo Ebersberger; Elena Kuzmin; Yannis Nevers; et al. (Journal of Molecular Evolution, 2025)
The rapid advancement of DNA sequencing technologies and computational algorithms has led to an unprecedented surge in genomic data, driven by several large-scale sequencing projects worldwide. Orthology plays a crucial role in understanding evolutionary patterns of genes and their functions. At the last Quest for Orthologs meeting (Montréal, Canada—2024), we discussed recent advances in orthology inference, with a focus on the impact of artificial intelligence (AI), protein structures, RNA splicing isoforms, and protein domain evolution together with other evolutionary considerations. A long-standing challenge in the field is the functional annotation of paralogs, for which we present novel approaches. The meeting also emphasised strategies for integrating diverse genetic features into the concept of orthology, encouraging frameworks that account for elements like alternative splicing, domain organisation, and regulatory sequences. We discuss various applications of orthology and paralogy to environmental research, agriculture, and comparative genomics. Additionally, we report recent progress in orthology inference methodologies and resources. This work represents a collaborative synthesis of insights and innovations presented at the 8th Quest for Orthologs meeting, highlighting current progress while outlining future directions for orthology research.

Congener Conflict: Invasive Barred Owl Landscape Use Across the Range of the Northern Spotted Owl - Julianna M. A. Jenkins; Natalie M. Rugg; Raymond J. Davis; Scott A. Gremel; Aaron Henderson; Edward Henson; Mark Higley; Holly D. Horan; Christopher McCafferty; Thomas Munger; David Press; Suzanne Reffler; et al. (Journal of Biogeography, 2025)
Aim To map the probability of landscape use of invading barred owls ( Strix varia ) across the range of the threatened northern spotted owl ( S. Occidentallis Caurina ) in the Pacific Northwest, USA , identifying environmental drivers of barred owl landscape use to inform targeted management interventions. Location Forests of the Pacific Northwest, USA. Taxon Barred Owl ( Strix varia ). Methods We deployed 4081 autonomous recording units ( ARUs ) within 1027 randomly selected long‐term monitoring sites consisting of 5‐km 2 hexagons in 2023. We processed audio recordings using convolutional neural networks to detect vocalisations. We applied single‐season occupancy models at both ARU station and hexagon scales to estimate barred owl landscape use and assess associations with environmental variables. Using top models, we mapped barred owl landscape use across the full US range of the northern spotted owl, an umbrella species for conservation of the pacific northwest old‐growth forest community. Results Barred owls were widely detected, with naïve occupancy at 86.8% at the 5‐km 2 hexagon scale. We observed regional variation, with the highest landscape use in the Oregon Coast region and lower landscape use in California regions and the Washington Eastern Cascades. Landscape use was positively associated with mature forest characteristics at both broad and fine scales and negatively associated with elevation and climatic water deficit. Cumulative detection probability exceeded 90% after 2 weeks at the hexagon scale and 4 weeks at the station scale, providing guidance for future barred owl monitoring efforts. Main Conclusions Our study reveals extensive, but not ubiquitous, barred owl distribution across the range of the northern spotted owl. The findings offer a decision‐support framework for prioritising targeted management actions, particularly in regions with lower rates of barred owl landscape use. The integration of passive acoustic monitoring and AI‐based detection demonstrates a scalable approach for invasive species monitoring and conservation planning to meet management objectives in dynamic forest landscapes.

Transformations of particulate organic matter from the surface to the abyssal plain in the North Pacific as inferred from compound-specific stable isotope and microbial community analyses - Lee C. Miller; Hilary G. Close; Kalina C. Grabb; Christine L. Huffard; Fuyan Li; David M. Karl; Kenneth L. Smith; Edward F. DeLong; Claudia R. Benitez-Nelson; Jeffrey C. Drazen; Brian N. Popp (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Untargeted and targeted LC-MS metabolomic analyses of putative chemical defenses in Taenaris butterflies - Belkes N. Stambouli; Ella T. Vardeman; Edward J. Kennelly; David J. Lohman (Phytochemistry Letters, 2025)

Coupled micro-computed tomography and micromechanical experiment on the failure of discontinuous porphyry rock - Sarah Webster; Nicolas Francois; Edward Andò; Mark Knackstedt; David Beck; Mohammad Saadatfar (International Journal of Rock Mechanics and Mining Sciences, 2025)

Corrigendum to ‘Passive sampling, a practical method for wastewater-based surveillance of SARS-CoV-2’ [Environ. Res., 204 Part-B (2022) 112058] - Jemaneh Habtewold; David McCarthy; Edward McBean; Ilya Law; Larry Goodridge; Marc Habash; Heather M. Murphy (Environmental Research, 2025)

Sugarcane genotype by environment interaction (G × E) in clonal trials in the U.S. Texas Rio Grande Valley - James R. Todd; Orlando Coto Arbelo; Anna L. Hale; Yong-Bao Pan; Edwis O. Dufrene; David Verdun; Aliya Momotaz; Collins A. Kimbeng; Herman L. Waguespack; Andrew W. Scott; Edward Hernandez; Matthew Klostermann (Euphytica, 2025)

Dynamic of infectious aerosols generated by cough from patients with pulmonary tuberculosis - Taline Canto Tristão; Mariana Abou Mourad Ferreira; Pedro Sousa de Almeida Júnior; Luiz Guilherme Schmidt Castellani; Manuela Negrelli Brunetti; Edward C. Jones-López; Kevin P. Fennelly; Michael R. Barer; Carlos Henrique Fantecelle; Saulo Almeida Morellato; David Jamil Hadad; Jerrold J. Ellner; et al. (Journal of Aerosol Science, 2025)

The sex matters: sex-biased stimulatory responses to contaminants - Evgenios Agathokleous; Edward J. Calabrese; Giovanni Benelli; David Costantini; Raul Narciso C. Guedes (Environmental Pollution, 2025)

Decadal change in deep-ocean dissolved oxygen in the North Atlantic Ocean and North Pacific Ocean - Henry A. Ruhl; Christine L. Huffard; Monique Messié; Thomas P. Connolly; Thomas Soltwedel; Frank Wenzhöfer; Rodney J. Johnson; Nicholas R. Bates; Susan Hartman; Anita Flohr; Edward W. Mawji; David M. Karl; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Identification of new genomic loci for seed protein and oil content in the soybean pangenome using genome-wide association and haplotype analyses - Tri D. Vuong; Guangqi He; Haifei Hu; Babu Valliyodan; Dongho Lee; Philipp E. Bayer; William T. Schapaugh; Rene Hessel; David Edwards; Henry T. Nguyen (Theoretical and Applied Genetics, 2025)

The mite fauna (Arachnida: Acari) of Gough Island, South Atlantic Ocean: natural colonization, endemism and human introduction - David J. Marshall; Elizabeth A. Hugo-Coetzee; Louise Coetzee; Edward A. Ueckermann; Owen Seeman; Steven L. Chown (Polar Biology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Proximal hyperspectral imaging for early detection and disease development prediction of Septoria Leaf Blotch in wheat using spectral–temporal features - Zhongzhong Niu; Yikai Li; Jorge David Salgado Moncada; William Johnson; Edward B. Lang; Xuan Li; Jian Jin (Computers and Electronics in Agriculture, 2025)

Monitoring mangrove responses to seasonal changes, hurricane-induced disturbance, and recovery in the South Florida Everglades: A spatio-temporal analysis of decade-long (2013–2023) Landsat-8 observations - Selena Chavez; Shimon Wdowinski; David Lagomasino; Edward Castañeda-Moya (Remote Sensing Applications: Society and Environment, 2025)

Agricultural subsidies augmented tropical deforestation in the state of Campeche, Mexico - Edward A. Ellis; David Chacón Castillo; Irving Uriel Hernández Gómez; Sergio Madrid Zubirán; Sara María Cuervo Vega (Forest Policy and Economics, 2025)

Effectiveness of Key Biodiversity Areas in representing global avian diversity - Tom P. Lansley; Olivia Crowe; Stuart H. M. Butchart; David P. Edwards; Gavin H. Thomas (Conservation Biology, 2025)
Key Biodiversity Areas (KBAs) are the largest and most complete network of significant sites for the global persistence of biodiversity. Although important sites for birds worldwide have been relatively well assessed, a key question is how effectively the global KBA network represents avian diversity. We identified bird species, orders, habitats, and geographic regions that are underrepresented by KBAs. Area of Habitat (AOH) maps for 10,517 terrestrial bird species were cropped and masked by the extent of each KBA. Almost all species had at least one part of their seasonal distribution in one or more KBAs. Twenty‐nine species had no habitat overlap with KBAs, and 1900 species had 2 ). Terrestrial bird species of tropical forests were 12.8% better represented in KBAs than expected by chance, whereas boreal and temperate forest species were less well represented than expected by chance (74.4% and 25.1%, respectively). Among avian orders, Anseriformes and Charadriiformes were underrepresented in KBAs (29.0% and 17.9%, respectively), whereas Trogoniformes and Psittaciformes were better represented (16.2% and 6.9%, respectively) than expected by chance. Bird species for potential KBA identification include marsh antwren ( Formicivora paludicola ) and Tabar pitta ( Erythropitta splendida ). These are mainly due to recent changes in species’ taxonomy or their International Union for Conservation of Nature Red List category. Identifying poorly represented species and where they occur highlights shortfalls where expansion of the network could bring conservation benefits.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Reimagining species on the move across space and time - Alexa L. Fredston; Morgan W. Tingley; Montague H.C. Neate-Clegg; Luke J. Evans; Laura H. Antão; Natalie C. Ban; I-Ching Chen; Yi-Wen Chen; Lise Comte; David P. Edwards; Birgitta Evengard; Belen Fadrique; et al. (Trends in Ecology & Evolution, 2025)

Validation of a novel method to quantify local axilla sweating, SweatSENSE - Andrew McGill; Emmett Cullen Tinley; Stephanie E. Edwards; Andrew Jamieson; Jane Ford; Evie Winterton; Jacob Shardey; Rachel A. Hand; Spyridon Efstathiou; Alan M. Wemyss; Maria Grypioti; Gavin Kirby; et al. (Journal of Thermal Biology, 2025)

Interplay of surface oxygen content and pore water during thermal regeneration of granular activated carbons - Dilara Hatinoglu; Lauren Edwards; Plabon Islam Turzo; David Hanigan; Onur G. Apul (Journal of Hazardous Materials, 2025)

Rural Economy-wide Impacts of Kenya’s Home-Grown School Meals Program - Anubhab Gupta; Miki Khanh Doan; Heng Zhu; Edward Whitney; Mateusz Filipski; Ernesto Gonzalez-Estrada; David Ryckembusch; J. Edward Taylor (Food Policy, 2025)

Heat stress monitoring, modelling, and mitigation in a dairy cattle building in reading, UK: Impacts of current and projected heatwaves - Chunde Liu; Yiran Cao; Zhiwen Luo; Yiqing Liu; Christopher K. Reynolds; David Humphries; Chenyu Zhang; Edward A. Codling; Kareemah Chopra; Jonathan Amory; Zoe Barker (Building and Environment, 2025)

Comparison of NO2 diffusion tube measurement methods and related uncertainties - David Medland; Gabriel Garcia; Tom Gardiner; Nicholas A. Martin; Valerio Ferracci; Ashley Wilkins; David Fryer; Tom Holmes; Pete Edwards; Sebastian Diez; David Butterfield (Atmospheric Environment, 2025)

Integrating multi-omics and machine learning for disease resistance prediction in legumes - Shameela Mohamedikbal; Hawlader A. Al-Mamun; Mitchell S. Bestry; Jacqueline Batley; David Edwards (Theoretical and Applied Genetics, 2025)
Key message Multi-omics assisted prediction of disease resistance mechanisms using machine learning has the potential to accelerate the breeding of resistant legume varieties. Abstract Grain legumes, such as soybean ( Glycine max (L.) Merr.), chickpea ( Cicer arietinum L.), and lentil ( Lens culinaris Medik.) play an important role in combating micronutrient malnutrition in the growing human population. However, plant diseases significantly reduce grain yield, causing 10–40% losses in major food crops. The genetic mechanisms associated with disease resistance in legumes have been widely studied using genomic approaches. Multi-omics data encompassing various biological layers such as the transcriptome, epigenome, proteome, and metabolome, in addition to the genome, enables researchers to gain a deeper understanding of these complementary layers and their roles in complex legume-pathogen interactions. Genomic prediction, used to select the best genotypes with desirable traits for breeding, has largely relied on genome-wide markers and statistical approaches to estimate the breeding values of individuals. Integrating multi-omics data into genomic prediction can be achieved using machine learning models, which can capture nonlinear relationships prevalent in high-dimensional data better than traditional statistical methods. This integration may enable more accurate predictions and identification of resistance mechanisms for breeding resistant legumes. Despite its potential, multi-omics integration for disease resistance prediction in legumes has been largely unexplored. In this review, we explore omics studies focusing on disease resistance in legumes and discuss how machine learning models can integrate multi-omics data for disease resistance prediction. Such multi-omics assisted prediction has the potential to reduce the breeding cycle for developing disease-resistant legume varieties.

Interactive effects of crop types and nitrogen sources on N2O emissions in a cool humid climate - Joannie D’Amours; David E. Pelster; Martin H. Chantigny; Andrew C. VanderZaag; Erin L. Smith; Gilles Bélanger; Émilie Maillard; Marie-Élise Samson; Edward G. Gregorich; Denis A. Angers; Isabelle Royer; Marie-Noëlle Thivierge (Plant and Soil, 2025)
Aims Perennial forages in rotation with annual crops can improve agricultural resilience by increasing soil organic carbon. However, how nitrogen (N) sources interact with rotation diversity to influence soil nitrous oxide (N 2 O) emissions is not well understood. Methods During three snow-free seasons, N 2 O emissions, crop yields, and ancillary variables were measured at three experimental sites with contrasting soil textures (silty clay and sandy loam) in eastern Canada. Using a split-plot design, we compared a corn ( Zea mays L.)-soybean ( Glycine max [L.] Merr.)-corn rotation and a mixed perennial grass sward receiving N via: i) mineral fertilizer (MIN), ii) liquid dairy manure (LDM), and iii) inclusion of alfalfa ( Medicago sativa L.) to the perennial forages with no additional N (LEG). Results When summed across sites over all three years, cumulative N 2 O emissions were greater for LDM than MIN in annual crops (8.75 ± 1.63 and 5.15 ± 0.96 kg N 2 O-N ha –1 , respectively), but not in perennial grasses (2.95 ± 0.55 and 3.76 ± 0.70 kg N 2 O-N ha –1 , respectively). When comparing N sources within each crop type over the three years, MIN generated greater yields than LDM in annual and perennial crops, but lower yield-scaled N 2 O emissions than LDM in annual crops only. During forages post-seeding years, area- and yield-scaled N 2 O emissions induced by LDM and LEG were lower than MIN. Conclusion Our results suggest that for a cool humid climate using LDM or LEG in perennial forages and MIN on annual crops can reduce overall N 2 O emissions, while generating similar or lower yield-scaled emissions.

Production and immunogenicity of a plant-produced beak and feather disease virus vaccine in Japanese quails - Goodman Mulondo; Mélie L. R. Buyse; Kimberley Labuschagne; David Jarvis; Albertha van Zyl; Edward P. Rybicki; Inga I. Hitzeroth; Sandiswa Mbewana (Archives of Virology, 2025)
Beak and feather disease virus (BFDV), a single-stranded DNA virus, infects endangered psittacine species, including the South African Cape parrot. The disease is highly contagious and can be transmitted through contact with contaminated faeces, crop secretions, and feather and skin dander. To date, there is no vaccine or cure available for BFDV. The production of an effective vaccine depends on having a production platform and methods that are both easy to use and capable of yielding a significant amount of protein that will induce a sufficient immune response. Therefore, the aim of this study was to produce a plant-based BFDV vaccine candidate and to evaluate its ability to elicit an immune response in birds. Recombinant BFDV capsid protein (CP) was transiently expressed in Nicotiana benthamiana and purified using density gradient ultracentrifugation. Japanese quails were immunized with purified BFDV CP. Yolk-derived IgY was purified by water dilution and salt precipitation, and its specificity was verified by western blot analysis. The expression levels of the coat protein increased from non-detectable to an average accumulation of 1.58 mg/kg of fresh plant tissue biomass, and antibodies against BFDV CP were detected in both the blood and eggs of immunized quails, indicating that vaccination with BFDV CP successfully elicited a humoral immune response. This study demonstrates that heterologous expression in plants is a viable method for producing BFDV CP. To the best of our knowledge, this is the first study to show the antibody response to a plant-produced BFDV antigen in a quail model. Given that the presence of anti-CP antibodies in infected birds is associated with immunity, this system can potentially be used to produce a vaccine against BFDV.

Harmonizing nature’s timescales in ecosystem models - Vivienne P. Groner; Jacob Cook; C. David L. Orme; Priyanga Amarasekare; Edward Comyn-Platt; Taran Rallings; Jaideep Joshi; Robert M. Ewers (Trends in Ecology & Evolution, 2025)

Removal of vanadium(V) ions from acidic water using reusable manganese oxide sorbents - Peirou Li; Laura Newsome; Arthur Graf; Karen A. Hudson-Edwards; David Morgan; Richard Crane (Journal of Hazardous Materials, 2025)

Price shocks and associated policy responses stemming from the Russia-Ukraine War and other global crises: Evidence from six African countries - Emmanuel Mwakiwa; Ayala Wineman; Andrew Agyei-Holmes; Modou Gueye Fall; Lilian Kirimi; Zena Mpenda; Edward Mutandwa; Iredele Ogunbayo; David Tschirley (Global Food Security, 2025)

A novel physiologically-based pharmacokinetic model to estimate reduced CYP3A4 activity in cancer patients utilizing the neutrophil-to-lymphocyte ratio as an inflammatory marker - David E. Coutant; Jessica Rehmel; Donna M. Edwards; Stephen D. Hall (European Journal of Clinical Pharmacology, 2025)

Detecting patches of invasive shrubs using high-density airborne LiDAR data and spectral imagery - Dennis Heejoon Choi; Isaac S. Morton; Lindsay E. Darling; Jianmin Wang; Bina Thapa; Edward P.F. Price; David N. Zaya; Songlin Fei; Brady S. Hardiman (Urban Forestry & Urban Greening, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

A Review of Global Fisheries Performance - Frank Asche; Taryn M. Garlock; James L. Anderson; Ruth B. Pincinato; Christopher M. Anderson; Edward V. Camp; Jingjie Chu; Andreea L. Cojocaru; Hakan Eggert; Kai Lorenzen; David C. Love; Ragnar Tveteras (Fish and Fisheries, 2025)
Management of fisheries is complex as it combines environmental, economic and social objectives. The relative importance of these objectives is highly debated and the best approaches to achieving good outcomes are unclear. A lack of global and multi‐dimensional data has largely precluded reviews providing comparisons of performances across systems at a large scale. We review fisheries performance by analysing outcomes over 14 dimensions of environmental, economic and community performance using a unique global dataset for 145 fisheries collected with the Fishery Performance Indicators. The fisheries are ranked into three performance groups by an average of their environmental, economic and community scores: the 10% best fisheries, the 10% worst fisheries and the middle 80%. Furthermore, we investigate how four different types of management systems, catch shares, territorial use rights, limited entry and open access, are represented in the three performance groups. The best performing fisheries scored equally or better and the poorest performing fisheries scored equally or worse in environmental, economic and social dimensions. We found three different management systems to be represented among the best performing fisheries, indicating that no specific management system is best. Moreover, some management systems were represented in all three performance categories, indicating that fisheries characteristics or management designs are important elements of fishery performance. The worst performing fisheries were dominated by open access fisheries with no or very limited management.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Recycling of lignin-based biocomposites: Improving sustainability and enhancing material strength - Barney H. Miao; Daniel Woo; Darius Javan; Edward J. Garboczi; Robert J. Headrick; Andrew C. Lesh; Zhiye Li; David J. Loftus; Michael D. Lepech (Resources, Conservation and Recycling, 2025)

Can recovered road sweeping wastes provide a soil or soil amendment alternative? An investigation of temporal variability of physico-chemical parameters - Daniel Niepsch; Edward Randviir; Rebecca Murphy-Peers; Emma Coulthard; David Hackett; David McKendry; David Megson (Journal of Environmental Management, 2025)

How much deforestation in sub-Saharan Africa has been caused by mining? - Abdulkareem I. Ahmed; Mike R. Massam; Robert G. Bryant; David P. Edwards (Biological Conservation, 2025)

The combined effect of nitrogen source and silicate availability on the growth of the eicosapentaenoic acid-producing diatom Phaeodactylum tricornutum - Edwards Araya; David Flaig; Patricia I. Gómez (Journal of Applied Phycology, 2025)

Machine Learning Predicts Non-Preferred and Preferred Vertebrate Hosts of Tsetse Flies (Glossina spp.) Based on Skin Volatile Emission Profiles - Olabimpe Y. Orubuloye; David P. Tchouassi; Abdullahi A. Yusuf; Christian W. W. Pirk; Daniel K. Masiga; Edward Kariuki; Baldwyn Torto (Journal of Chemical Ecology, 2025)
Tsetse fly vectors of African trypanosomosis preferentially feed on certain vertebrates largely determined by olfactory cues they emit. Previously, we established that three skin-derived ketones including 6-methyl-5-hepten-2-one, acetophenone and geranyl acetone accounted for avoidance of zebra by tsetse flies. Here, we tested the hypothesis that these three ketones serve as biomarkers for tsetse flies to distinguish between non-preferred- and preferred-vertebrate hosts. We used coupled gas chromatography/mass spectrometry to analyze and compare the skin volatile emissions of two non-preferred- (waterbuck and zebra) and four preferred- (buffalo, donkey, horse, warthog) vertebrate hosts in two wildlife parks in Kenya. We detected a total of 96 volatile organic compounds (VOCs) in the skin emissions composed mainly of aldehydes, ketones, alcohols, phenols and alkanes, which varied with the vertebrate host. Using random forest analysis, we found a weak correlation between the three skin-odor repellent ketones and non-preferred and preferred vertebrate hosts. However, we found that the three repellent ketones plus skin background odors may be more sensitive chemical signals for tsetse flies to discriminate vertebrate hosts. These results contribute to understanding tsetse fly vertebrate host preferences in their natural habitat across geographic scales.

Can agricultural systems facing climate change benefit from a deeper understanding of invasive plant species? - Artur Nosalewicz; Ali A. Bajwa; Dana M. Blumenthal; David Edwards; Marcel G.C. França; Ülo Niinemets; Bruce A. Osborne; Lewis H. Ziska (Agriculture, Ecosystems & Environment, 2025)

Eddy dipole differentially influences particle‐associated and water column protistan community composition - Jennifer L. Beatty; Brittany P. Stewart; Lisa Y. Mesrop; Edward F. DeLong; David M. Karl; David A. Caron (Limnology and Oceanography, 2025)
Ocean eddies are mesoscale features that can extend > 100 km and maintain cohesiveness for months, impacting planktonic community structure and water column biogeochemical cycles. Standing stocks of protists in the water column and on sinking particles were investigated using microscopy, in situ imagery, and metabarcoding across an anticyclonic to cyclonic eddy dipole in the North Pacific Subtropical Gyre during July 2017. The water column was sampled from the surface to 500 m and particle interceptor traps were deployed at 150 m. Protistan assemblage composition varied substantially between sample type and analytical approach across the eddy dipole. Alveolates represented 63% of sequences from water samples. In contrast to water samples, rhizarian protists represented 79% of trap sequences obtained by metabarcoding of sediment trap material. Microscopy of trap material supported the important contribution of Rhizaria to sinking particles and revealed increased relative abundances of ciliates in the anticyclonic eddy and diatoms in the cyclonic eddy. In situ imagery confirmed the presence of relatively large Rhizaria that were not adequately assessed from water samples but contributed significantly to particle flux. Together, these data demonstrate differing perspectives of planktonic protistan community composition and contributions to sinking particles gained from the application of different sampling and analytic approaches. Our observations and analyses indicate a specific subset of the protistan community contributed disproportionately to organic matter downward export.

Day-ahead statistical forecasting of algal bloom risk to support reservoir release decisions in a highly engineered watershed - María Menchú-Maldonado; David Kaplan; Mauricio E. Arias; Eric Milbrandt; Elise Morrison; Edward Phlips; Natalie G. Nelson (Journal of Environmental Management, 2025)

The function of love: A signaling-to-alternatives account of the commitment device hypothesis - Benjamin Gelbart; Kathryn V. Walter; Daniel Conroy-Beam; Casey Estorque; David M. Buss; Kelly Asao; Agnieszka Sorokowska; Piotr Sorokowski; Toivo Aavik; Grace Akello; Mohammad Madallh Alhabahba; Charlotte Alm; et al. (Evolution and Human Behavior, 2025)

Dust transport pathways from The Great Basin - Ronald S. Treminio; Nicholas P. Webb; Saroj Dhital; Akasha Faist; Beth Newingham; Colby Brungard; David DuBois; Brandon L. Edwards; Emily Kachergis (Aeolian Research, 2025)

Resilience to Hurricanes Is High in Mangrove Blue Carbon Forests - David Reed; Selena Chavez; Edward Castañeda‐Moya; Steven F. Oberbauer; Tiffany Troxler; Sparkle Malone (Global Change Biology, 2025)
Mangrove forests are typically considered resilient to natural disturbances, likely caused by the evolutionary adaptation of species‐specific traits. These ecosystems play a vital role in the global carbon cycle and are responsible for an outsized contribution to carbon burial and enhanced sedimentation rates. Using eddy covariance data from two coastal mangrove forests in the Florida Coastal Everglades, we evaluated the impact hurricanes have on mangrove forest structure and function by measuring recovery to pre‐disturbance conditions following Hurricane Wilma in 2005 and Hurricane Irma in 2017. We determined the “recovery debt,” the deficit in ecosystem structure and function following a disturbance, using the leaf area index (LAI) and the net ecosystem exchange (NEE) of carbon dioxide (CO 2 ). Calculated as the cumulative deviation from pre‐disturbance conditions, the recovery debt incorporated the recapture of all the carbon lost due to the disturbance. In Everglades mangrove forests, LAI returned to pre‐disturbance levels within a year, and ecosystem respiration and maximum photosynthetic rates took much longer, resulting in an initial recovery debt of 178 g C m −2 at the tall forest with limited impacts at the scrub forest. At the landscape scale, the initial recovery debt was 0.40 Mt C, and in most coastal mangrove forests, all lost carbon was recovered within just 4 years. While high‐intensity storms could have prolonged impacts on the structure of subtropical forests, fast canopy recovery suggests these ecosystems will remain strong carbon sinks.

Fate of a toxic Microcystis aeruginosa bloom introduced into a subtropical estuary from a flow-managed canal and management implications - Edward J. Phlips; Susan Badylak; Eric C. Milbrandt; Benjamin Stelling; Mauricio Arias; Cassondra Armstrong; Thomas Behlmer; Amanda Chappel; Amanda Foss; David Kaplan; Leslie Landauer; Peter Landauer; et al. (Journal of Environmental Management, 2025)

Green solutions for treating groundwater polluted with nitrates, pesticides, antibiotics, and antibiotic resistance genes for drinking water production - Jessica Subirats; Edward J. Pastor-López; Joan Pascó; Marlene Mendoza; Miriam Guivernau; Belén Fernández; Rosa Trobajo; Marc Viñas; Carme Biel; David Sánchez; Jofre Herrero; Victor Matamoros (Journal of Environmental Management, 2025)

Colourful Brazilian anurans are preferentially targeted by wildlife trade - Joseph L. Werling; Oscar Morton; David P. Edwards (Biological Conservation, 2025)

Risk of mortality in Fusobacterium species bloodstream infection from a large Australian cohort - Adam G. Stewart; Felicity Edwards; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

The need for carbon finance schemes to tackle overexploitation of tropical forest wildlife - Caroline E. Milson; Jun Ying Lim; Daniel J. Ingram; David P. Edwards (Conservation Biology, 2025)
Defaunation of tropical forests, particularly from unsustainable hunting, has diminished populations of key seed dispersers for many tree species, driving shifts in forest community composition toward small‐fruited or wind‐dispersed trees with low wood density. Such shifts can reduce aboveground biomass, prompting calls for overexploitation to be included in bioeconomic policy, but a synthesis of existing literature for wildlife impacts on carbon stores is lacking. We evaluated the role of wildlife in tropical forest tree recruitment and found that it was critical to tropical forest carbon dynamics. The emerging financial value of ecosystem services provided by tropical forest fauna highlights the need for carbon‐based payments for ecosystem services schemes to include wildlife protection. We argue for three cost‐effective actions within carbon finance schemes that can facilitate wildlife protection: support land security opportunities for Indigenous peoples and local communities; provide support for local people to protect forest fauna from overexploitation; and focus on natural regeneration in restoration projects. Incorporating defaunation in carbon‐financing schemes more broadly requires an increased duration of carbon projects and an improved understanding of defaunation impacts on carbon stores and ecosystem‐level models. Without urgent action to halt wildlife losses and prevent empty forest syndrome, the crucial role of tropical forests in tackling climate change may be in jeopardy.

Light buckets and laser beams: mechanisms and applications of photobiomodulation (PBM) therapy - David W. Frankowski; Luigi Ferrucci; Praveen R. Arany; Dawn Bowers; Janis T. Eells; Francisco Gonzalez-Lima; Nicole L. Lohr; Brendan J. Quirk; Harry T. Whelan; Edward G. Lakatta (GeroScience, 2025)
Photobiomodulation (PBM) therapy, a non-thermal light therapy using nonionizing light sources, has shown therapeutic potential across diverse biological processes, including aging and age-associated diseases. In 2023, scientists from the National Institute on Aging (NIA) Intramural and Extramural programs convened a workshop on the topic of PBM to discuss various proposed mechanisms of PBM action, including the stimulation of mitochondrial cytochrome C oxidase, modulation of cell membrane transporters and receptors, and the activation of transforming growth factor-β1. They also reviewed potential therapeutic applications of PBM across a range of conditions, including cardiovascular disease, retinal disease, Parkinson’s disease, and cognitive impairment. Workshop participants largely agreed that PBM holds immense potential as a safe and effective therapeutic approach for a wide range of age-related diseases and cognitive decline. While further research is needed to fully elucidate its mechanisms and optimize treatment protocols, the findings presented at the NIA workshop provide strong evidence for the continued investigation and clinical translation of this promising, inexpensive, safe technology, to aging and age-associated diseases. Here, we review the research presented and discussion held at the meeting. In addition, the text has been updated, where applicable, with recent research findings that have been made since the meeting occurred.

Mercury deposition in central China from the Last Glacial Maximum to the early Holocene recorded in an accurately-dated stalagmite - Yanzhen Li; Liangcheng Tan; Simin Jin; Hai Xu; Lüfan Chen; David B. Kemp; Ashish Sinha; Le Ma; Chunju Huang; Lawrence R. Edwards; Hai Cheng (Science Bulletin, 2025)

Influence of regulated water discharges on phytoplankton composition and biomass in a subtropical canal - Susan Badylak; Edward J. Phlips; Eric C. Milbrandt; Elise S. Morrison; Benjamin D. Stelling; Shin-Ah Lee; Thomas A. Frankovich; David Kaplan (Journal of Environmental Management, 2025)

Emergency Department Patients Presenting after Oral versus Inhaled Cannabinoid use: A Retrospective Analysis - Tony Zitek; Christopher Raciti; Alvin Nguyen; Valentina Roa; Edward Lopez; Gregory Oliva; David A. Farcy (Journal of Medical Toxicology, 2025)

Revisiting the sustainability science research agenda - Mesfin Sahle; Shruti Ashish Lahoti; So-Young Lee; Katja Brundiers; Carena J. van Riper; Christian Pohl; Herlin Chien; Iris C. Bohnet; Noé Aguilar-Rivera; Peter Edwards; Prajal Pradhan; Tobias Plieninger; et al. (Sustainability Science, 2025)

Challenges to and importance of considering early and intermediate ontogenetic stages in mangrove forest recovery and restoration - Taylor M. Sloey; Sean P. Charles; Lin Xiong; Edward Castañeda-Moya; Erik S. Yando; David Lagomasino (Marine Pollution Bulletin, 2024)

Investigating the chemical space coverage of multiple chromatographic and ionization methods using non-targeted analysis on surface and drinking water collected using passive sampling - Angela L. Batt; Laura D. Brunelle; Natalia S. Quinete; Eva K. Stebel; Brian Ng; Piero Gardinali; Alex Chao; Anna K. Huba; Susan T. Glassmeyer; David A. Alvarez; Dana W. Kolpin; Edward T. Furlong; et al. (Science of The Total Environment, 2024)

Deployment-invariant probability of detection characterization for aerial LiDAR methane detection - Michael J. Thorpe; Aaron Kreitinger; Dominic T. Altamura; Cameron D. Dudiak; Bradley M. Conrad; David R. Tyner; Matthew R. Johnson; Jason K. Brasseur; Peter A. Roos; William M. Kunkel; Asa Carre-Burritt; Jerry Abate; et al. (Remote Sensing of Environment, 2024)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Recommendation for Clarifying FDA Policy in Evaluating “Sameness” of Higher Order Structure for Generic Peptide Therapeutics - Jessica A. Rogers-Crovak; Edward J. Delaney; David J. Detlefsen (The AAPS Journal, 2024)
Recognizing the approach of a dramatic expansion of peptide therapeutics reaching the marketplace in recent years, led by GLP-1 receptor agonists such as semaglutide and liraglutide, the Center for Drug Evaluation and Research (CDER) branch of the US Food and Drug Administration (FDA) issued a final guidance in 2021 that was intended to assist generic drug producers in meeting Abbreviated New Drug Application (ANDA) obligations to establish “sameness” of their active peptide drug relative to that produced by innovator companies. Research and a published report by FDA scientists on best practices followed, which promulgated the use of nuclear magnetic resonance (NMR) and principal component analysis (PCA) and established a quantitative standard by which “sameness” of higher order structure for the applicant’s peptide drug could be judged. A key requirement is that drug product samples be analyzed directly and non-invasively, a condition which in practice restricts sample modification to the addition of a small amount of deuterium oxide to allow signal lock and spectral data alignment (as required for NMR analysis). In the study described herein, data are presented to illustrate that 1) relatively small differences in sample pH can cause significant shifting of certain proton resonances, 2) that such resonance shifting is readily reversible and due to the degree of protonation of specific amino acid residues (rather than reflecting differences in higher order structure), and 3) that small differences in pH variability between sample cohorts can frequently cause failure to meet the quantitative benchmark established by the agency. Methodology is presented by which drug sample pHs can be aligned with minimal impact, and a recommendation is made that minor sample pH adjustments be allowed in assessing “sameness” of peptide drug higher order structure. Graphical Abstract

Milk production and viability of the various smallholder dairying models used in Zimbabwe - Takudzwa Mafigu; Blessed Masunda; Venancio Edward Imbayarwo-Chikosi; David Tinotenda Mbiriri; Pride Hodzi (Tropical Animal Health and Production, 2024)

Impact of endophyte-infected tall fescue seed consumption on endocrine changes associated with intake regulation and post-absorptive metabolism in growing steers - Mindy E. King; Hannah M. Herzing; Kyle R. McLeod; James L. Klotz; Andrew P. Foote; J. Lannett Edwards; David L. Harmon (Domestic Animal Endocrinology, 2024)

Manipulation of Farmed Wetlands Increases use by Migrating Shorebirds and Ducks - Dustin L. Toy; Michael J. Anteau; Aaron T. Pearse; Edward S. DeKeyser; David C. Roberts (Wetlands, 2024)
The Drift Prairie, in central North America, has been largely converted from grasslands to croplands, but still contains thousands of wetlands used by shorebirds and waterfowl during breeding and migration periods. Consequently, many of the remaining wetlands are situated within cropland where disturbance regimes (i.e., fire, grazing, and water-level dynamics), which occurred naturally prior to agricultural development, have been highly altered by landscape fragmentation from agriculture practices. Currently, smaller wetlands within crop fields are subject to disturbances stemming from agricultural practices (i.e., manipulations), such as burning, disking, harvesting, and mowing. We evaluated vegetation structure of idled (i.e., not recently manipulated by farming practices) and manipulated agricultural wetlands to investigate whether management method or resulting vegetation structure had greater influence on occurrence probabilities and densities of dabbling ducks and shorebirds during spring. All manipulation methods reduced vegetation heights compared to idled wetlands and most manipulations reduced the proportion of vegetation cover in inundated areas. Wetland manipulations generally increased shorebird occurrence compared to idled wetlands, whereas vegetation variables better explained duck occurrence probabilities. Duck occurrence peaked in wetlands with lower vegetation coverage (32%), and duck densities decreased as vegetation coverage increased beyond 10%. While more studies are needed to understand underlying mechanisms driving these outcomes, our results indicate that including periodic disturbances that reduce dense vegetation within wetlands in agricultural fields would increase their use by migrating and breeding shorebirds and dabbling ducks.

Moths are less attracted to light traps than they used to be - Ian Battles; Eric Burkness; Michael S. Crossley; Collin B. Edwards; Kristian Holmstrom; William Hutchison; Joseph Ingerson-Mahar; David Owens; Avalon C.S. Owens (Journal of Insect Conservation, 2024)
As evidence of global insect declines continues to mount, insect conservationists are becoming increasingly interested in modeling the demographic history of at-risk species from long-term survey data. However, certain entomological survey methods may be susceptible to temporal biases that will complicate these efforts. Entomological light traps, in particular, may catch fewer insects today than they once did due solely to increases in anthropogenic light pollution. Here we investigate this possibility by comparing the demographic histories of corn earworm moths ( Helicoverpa zea ) estimated from pairs of blacklight and pheromone traps monitored at the same farms. We find a stark decline in blacklight trap efficacy over 25 years of monitoring in Delaware, USA, mirrored over 10 years of monitoring in New Jersey, USA. While the precise causes of this decline remain a subject for discussion, the practical consequences are clear: insect conservationists cannot fully rely on long-term trends from entomological light traps.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

The glass from the arrabal of Arrixaca (Murcia, 12th-13th centuries) - David J. Govantes-Edwards; Almudena Velo; Alicia Hernández-Robles; José Ángel González-Ballesteros; Chloe Duckworth (Archaeological and Anthropological Sciences, 2024)
This article presents an assemblage of 36 glass samples excavated in the urban site of San Esteban, part of the arrabal of Arrixaca (Murcia) (in al-Andalus, an arrabal was a relatively dense urbanised area outside the city walls) in contexts securely dated to the 12th and early 13th century, spanning the rule of Ibn Mardanīš, and the early period of Almohad domination in the city. The samples were analysed by electron microprobe (EMPA) for major and minor elements and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) for trace elements. The results are examined within the context of glass production, circulation, and consumption in al-Andalus and the Islamicate Mediterranean more broadly. The results show that some of the glasses found in San Esteban-Arrixaca may have been imported from other Islamicate regions (Egypt and Mesopotamia), but that the vast majority can be related to previously recognised compositional Iberian glass groups. At the same time, the identification of several fragments of production waste and raw glass suggest that some glass-working facility may have existed in the vicinity of San Esteban-Arrixaca. The compositional evidence also indicates that recycling (including of imported glass objects) may have been a fairly common practice in Andalusi glassmaking, but it is suggested that some of the usual chemical markers of recycling may, in the case of al-Andalus and perhaps also elsewhere in the medieval Mediterranean, be the result of the cross-breeding of glass- and glaze-making activities.

Tracking aquatic animals for fisheries management in European waters - Aytaç Özgül; Kim Birnie‐Gauvin; David Abecasis; Josep Alós; Kim Aarestrup; Jan Reubens; Jon Bolland; Altan Lök; Jena E. Edwards; Polona Pengal; Marie Prchalová; Milan Říha; et al. (Fisheries Management and Ecology, 2024)
Acoustic telemetry (AT) has emerged as a valuable tool for monitoring aquatic animals in both European inland and marine waters over the past two decades. The European Tracking Network (ETN) initiative has played a pivotal role in promoting collaboration among AT researchers in Europe and has led to a significant increase in the number of tagged and observed aquatic animals in transboundary European waters. While AT benefits decision‐making and delivers essential data to management bodies, its potential for management decision‐making mechanisms has yet to be fully harnessed. We reviewed existing research, studies, and organisational initiatives related to aquatic animal tracking and their utility in fisheries management in European waters. We found that AT has already contributed to many aspects of fisheries management, such as improved understanding of stock dynamics, identification of critical habitats, assessment of migration routes, and evaluation of the effectiveness of conservation measures. However, broader utilisation of tracking technologies is needed. By leveraging the full potential of AT, managers can make more informed decisions to protect, restore, and sustainably manage European waters and creatures that live therein.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Proximity Labelling Confirms the Involvement of Papain-Like Cysteine Proteases and Chaperones in Cyclotide Biosynthesis - Meng-Han Lee; Mark A. Jackson; Fabian B. H. Rehm; Deborah S. Barkauskas; Wing L. Ho; Kuok Yap; David J. Craik; Edward K. Gilding (Plant Molecular Biology Reporter, 2024)
Cyclotides are disulfide-rich insecticidal peptides from plants that harbour a cyclic cystine knot motif that imparts them with high stability. Like most ribosomally encoded peptides, cyclotides are produced as precursor proteins that are subsequently processed to maturity through proteolytic activity. Although the final maturation of the prototypic cyclotide kalata B1 (kB1) is known to involve asparaginyl endopeptidases, the role of the in planta folding machinery is less well characterized, as is also the case for in planta N-terminal processing enzyme(s). Here, we used proximity labelling to identify proteins involved in the biosynthesis of kB1 in both a cyclotide-bearing plant species, Petunia × hybrida [Regel], and in Nicotiana benthamiana [Domin] that does not naturally produce cyclotides. Together, several ER resident chaperones, protein disulfide isomerases, a papain-like cysteine protease, and an asparaginyl endopeptidase were identified in the kB1 interactome. We found that overexpression of the identified papain-like cysteine protease resulted in an improvement in the yield of cyclic kB1, while this was not the case for the overexpression of protein disulfide isomerases, despite their interaction being verified using bimolecular fluorescence complementation. Together, these results provide a significant advance in our understanding of the role of auxiliary biosynthetic elements for heterologous cyclotide production in plants.

Estuarine nekton community shows minimal response following large-scale oyster reef habitat loss in Apalachicola Bay, Florida - Gabrielle D. Love; Zachary A. Siders; David A. Gandy; William E. Pine; Shirley Baker; Edward V. Camp (Hydrobiologia, 2024)

Hot and Fresh: Evidence of Climate-Related Suboptimal Water Conditions for Seagrass in a Large Gulf Coast Estuary - Marcus W. Beck; Kerry Flaherty-Walia; Sheila Scolaro; Maya C. Burke; Bradley T. Furman; David J. Karlen; Christopher Pratt; Christopher J. Anastasiou; Edward T. Sherwood (Estuaries and Coasts, 2024)
Seagrasses have long been a focal point for management efforts aimed at restoring ecosystem health in estuaries worldwide. In Tampa Bay, Florida (USA), seagrass coverage has declined since 2016 by nearly a third (11,518 acres), despite sustained reductions of nitrogen loads supportive of light environments for growth. Changing physical water quality conditions related to climate change may be stressing seagrasses beyond their optimal growth ranges, requiring an assessment to determine if this decline can be linked to climate stress. Three ambient water quality datasets of varying sampling designs and coverage were evaluated to characterize physicochemical environments in Tampa Bay and the potential relationships with seagrass change. Tampa Bay has become hotter and fresher with water temperature increasing by 0.03–0.04 °C per year and salinity decreasing by 0.04–0.06 ppt per year, translating to an increase of 1.3 to 1.7 °C and a decrease of 1.6 to 2.6 ppt over the last 50 years. Additionally, the number of days when temperature was above 30 °C or salinity was below 25 ppt has increased on average across all bay segments by 48 and 37 days, respectively, since 1975. These changes varied spatially and seasonally, with the most dramatic changes observed in the upper bay. Generalized Additive Models provided a weight-of-evidence that recent seagrass declines are somewhat associated with hotter and fresher conditions. Trends in warming and increased precipitation in the region are likely to continue, further creating suboptimal conditions for seagrasses in Tampa Bay. These results should compel resource managers to consider the likelihood that reduced resilience of estuarine resources due to shifting ecological baselines driven by additional climate change drivers will complicate long-standing management paradigms. While conventional management approaches that focus on limiting nutrient loads should be continued, their future effectiveness may be confounded by climate change drivers and warrant additional, complementary interventions and continuous monitoring data to support ecosystem health into the future.

Estimating Biogeochemical Rates Using a Computationally Efficient Lagrangian Approach - Edward Gross; Rusty Holleman; Wim Kimmerer; Tamara Kraus; Brian Bergamaschi; Scott Burdick-Yahya; David Senn (Estuaries and Coasts, 2024)
Nutrient concentrations in many estuaries have increased over the past century due to increases in wastewater discharge and increased agricultural intensity, contributing to multiple environmental problems. Numerous biogeochemical and physical processes in estuaries influence nutrient concentrations during transport, resulting in complex spatial and temporal variability and challenges identifying predominant processes and their rates. Mechanistic models which require these rates to quantify biogeochemical processes become complex and difficult to calibrate as the number of processes and parameters grows, owing to the high dimensionality of the parameter space and the computational cost of simultaneously modeling the transport and transformations of constituents. We developed a modeling approach that decouples transport from transformations, enabling fast, data-driven exploration of the parameter space. The approach extracted information including water age, cumulative exposure to specific habitats, and mean water depth exposure from a hydrodynamic model. Using this information, a biogeochemical model was implemented to predict ammonium and nitrate concentrations in a Lagrangian frame. The model performed each simulation in milliseconds on a laptop computer, allowing the fitting of rate parameters for key transformations by optimization. The optimization used fixed station nitrate observations and the model was then validated against high-resolution mapping observations of ammonium and nitrate. The results suggest that the observed spatial and temporal variation can be largely represented with five transformation processes and their associated rates. Dissolved inorganic nitrogen (DIN) losses occurred only in shallow vegetated areas in the model, highlighting that biogeochemical processes in these areas should be included in DIN models.

Pseudomonas stutzeri bloodstream infection is a prevailing community-onset disease with important mortality rates: results from a retrospective observational study in Australia - Juan P. Horcajada; Felicity Edwards; Silvia Fonio; Milagro Montero; Patrick Harris; David L. Paterson; Kevin B. Laupland (Infectious Diseases, 2024)

A systematic review of barriers to implementing net zero energy buildings in Australia - Darcy Brown; Olubukola Tokede; Hong Xian Li; David Edwards (Journal of Cleaner Production, 2024)

Self-swabbing versus assisted swabbing for viral detection by qRT-PCR: the experience from SARS-CoV-2 based on a meta-analysis of six prospectively designed evaluations conducted in a UK setting - Tom Fowler; David Chapman; Matthias E. Futschik; Sarah A. Tunkel; Edward Blandford; Elena Turek; Olumide Kolade; Sergio Souza da Cunha; Andrew Dodgson; Paul Klapper; Malur Sudhanva; Lindsey Davies; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Purpose In April 2020, the UK Government implemented NHS Test and Trace to provide SARS-CoV-2 quantitative reverse transcription polymerase chain reaction (qRT-PCR) testing for the public, with nose-and-throat swabbing for samples performed by trained staff. Self-swabbing (SS) would allow rapid scale-up of testing capacity and access. Six studies were undertaken to determine whether SS was as effective for detecting SARS-CoV-2 as swabbing performed by trained staff. Methods Six prospective studies were conducted between April–October 2020, using six swab/media combinations. Differences between assisted swabbing (AS) and SS were evaluated for concordance, positivity, sensitivity, cycle threshold (Ct) values and void rates. Statistical analysis was performed using 95% confidence intervals (CIs), paired t-tests and model-based methods. Results Overall, 3,253 individuals were recruited (median age 37 years, 49% female), with 2,933 having valid paired qRT-PCR results. Pooled concordance rate was 98% (95% CI: 96%, 99%). Positivity rate differences for SS (8.1%) and AS (8.4%) and differences in pooled sensitivities between SS (86%; 95% CI: 78%, 92%) and AS (91%; 95% CI: 78%, 96%) were nonsignificant. Both types of swabbing led to pooled void rates below 2% and strongly correlated Ct values. Age, sex and previous swabbing experience did not have a significant impact on concordance or sensitivity. Conclusion The UK adopted a policy to promote self-testing for SARS-CoV-2 based on data demonstrating equivalence of SS versus AS. Positive outcomes with SS are likely generalisable to testing for other respiratory pathogens, and we consider self-sampling and self-testing essential for future pandemic preparedness.

Quantification and characterization of microplastics ingested by mangrove oysters across West Africa - Edem Mahu; Tyronne Jude Vanderpuye-Orgle; Charles Mario Boateng; Maurice Oti Edusei; Gabriella Akpah Yeboah; Ernest Obeng Chuku; Paulina Okpei; Isaac Okyere; David Dodoo-Arhin; Edward Akinnigbagbe Akintoye (Environmental Science and Pollution Research, 2024)
Microplastic ingestion by marine organisms presents a challenge to both ecosystem functioning and human health. We characterized microplastic abundance, shape, size, and polymer types ingested by the West African mangrove oyster, Crassostrea tulipa (Lamarck, 1819) sampled from estuaries and lagoons from the Gambia, Sierra Leone, Ghana, Benin, and Nigeria using optical microscopy and Fourier transform infrared (FTIR) techniques. A total of 780 microplastics were isolated in the whole tissues of the 250 oysters ( n = 50 oysters per country). The abundance and distribution of microplastics in the oysters followed the pattern: the Gambia > Ghana > Sierra Leone > Nigeria > Benin. The Tanbi wetlands in the Gambia recorded the highest average of 10.50 ± 6.69 per oyster while the Ouidah lagoon in Benin recorded the lowest average of 1.80 ± 1.90 per oyster. Overall, microplastic numbers varied significantly ( p < 0.05) among the five countries. Microfibers, particularly those within 1001–5000 μm size, dominated the total microplastic count with a few fragments and films. No spherical microplastics were isolated in the oysters. In the Sierra Leone and Benin oysters, fragments and films were absent in the samples. Microplastic between the 1001 and 5000 μm size class dominated the counts, followed by 501–1000 μm, 101–500 μm, and 51–100 μm. Five polymer groups namely polyethylene, polyester, nylon, polypropylene, and polyamide were identified across the five countries, with polyethylene occurring in oysters from all five countries and polyester occurring in all but the oysters from Nigeria. This diversity of polymers suggests varied sources of microplastics ingested by the studied oysters. The absence of microspheres across the five supports findings from other studies that they are the least ingested and highly egested by the oysters. Graphical Abstract

Developmental and therapeutic implications of IL4ra expression for rhabdomyosarcoma - David W. Edwards; Gabrielle M. Kroepfl; Jacob M. Jackson; Sonja Chen; Lisa Hudson-Price; Ganapati Srinivasa; Kavya Kannan; Qianqian Liu; Joel E. Michalek; Charles Keller (Transgenic Research, 2024)

Longitudinal relationships between depressive symptoms, functional impairment, and physical activity in later late life - Lisa Y. Xiong; Madeline Wood Alexander; Hugo Cogo-Moreira; Che-Yuan Wu; Michael Eid; Nathan Herrmann; Damien Gallagher; Jodi D. Edwards; Krista L. Lanctôt; Susan Marzolini; David A. Bennett; Jennifer S. Rabin; et al. (GeroScience, 2024)

Crops production and the contribution of agricultural biomass power generation to Africa's clean energy transition: Analysis of trends from 1990 to 2021 - Augustine Awaafo; Edward A. Awafo; Meisam Mahdavi; Gilbert Akolgo; Francisco Jurado; David Vera; Emmanuel Amankwah (Biomass and Bioenergy, 2024)

Spatial extent predicts Andean epiphyte biodiversity responses to habitat loss and fragmentation across human‐modified landscapes - Edicson Parra‐Sanchez; David P. Edwards (Journal of Biogeography, 2024)
Aim Human‐driven landscape processes such as habitat loss and fragmentation act on biodiversity, but their effects are mediated by the spatial scale at which they are observed. We aim to analyse the scale‐of‐effects (direction and spatial extent) of landscape‐scale processes that best explain species richness and abundance across epiphyte communities. Location Neotropics, Northern Andes, Colombia, Eastern cordillera. Taxon Vascular epiphytes, Orchidaceae. Methods We used field data to unravel the scale‐of‐effect of three landscape processes—habitat loss (forest cover), fragmentation (number of patches) and edge effects (edge density)—on epiphyte biodiversity. Vascular epiphytes were sampled in the understorey across 141 plots within 23 Andean forests in the eastern Colombian cordillera We focused on the community‐level responses (species richness and total abundance) of the hyperdiverse vascular epiphyte communities using generalized linear mixed models to quantify the direction and the spatial extent of the scale‐of‐effects. Results Habitat loss and edge effects act at fine spatial extents (scale‐of‐effects = 200 m), predicting low species richness and abundance across groups. Likewise, fragmentation negatively impacts communities, but operates at larger spatial extents (scale‐of‐effects = 2000–2400 m radius). The detection of these effects is contingent upon the spatial extent and specific landscape processes involved. Models of habitat loss within a spatial extent of 800–1500 m (large confidence intervals), fragmentation below 300 m, and edge effects above 800 m show weak statistical support (marginal r 2 = 0.02–0.1). Thus, the impacts of these landscape processes may be overlooked if studied at inadequate spatial extents. Main Conclusions We showed that habitat loss, fragmentation and edge effects all play a negative role on understorey epiphytic communities, but their detectability is scale dependant. The scale‐of‐effects can assist landscape designs that are beneficial for epiphytic communities, by preserving forest cover, and reducing fragmentation and exposure to edge effects at small scales (200–300 m). Conversely, landscape‐scale actions directed at reducing habitat loss and fragmentation function at larger spatial extents (>2000 m). Selecting a priori or inadequate spatial extents of analysis can obscure the detectability of landscape processes.

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Hot, cold, or just right? An infrared biometric sensor to improve occupant comfort and reduce overcooling in buildings via closed-loop control - Ronnen Levinson; Donghun Kim; Howdy Goudey; Sharon Chen; Hui Zhang; Ali Ghahramani; Charlie Huizenga; Yingdong He; Akihisa Nomoto; Edward Arens; Ana Álvarez Suárez; David Ritter; et al. (Energy and Buildings, 2024)

Effect of a microbial phytase on the growth performance, digestibility and retention in a high plant meal inclusion diet for Atlantic salmon (Salmo salar) - David Edward Terrey; Daniel Arana Braidi; Robert Serwata (Aquaculture International, 2024)
The effect of supplementation of a novel phytase (OptiPhos®; Huvepharma; 750 OTU) to high plant meal inclusion diets for Atlantic salmon ( Salmo salar ) was assessed. Diets were prepared without phytase, with phytase and with supplemental inorganic phosphorus (MCP). After 61 days significant increases in growth, FCR and protein efficiency were seen in diets supplemented with phytase and with MCP over the negative control ( P P P P

Damage to tropical forests caused by cyclones is driven by wind speed but mediated by topographical exposure and tree characteristics - Thomas Ibanez; David Bauman; Shin‐ichiro Aiba; Thomas Arsouze; Peter J. Bellingham; Chris Birkinshaw; Philippe Birnbaum; Timothy J. Curran; Saara J. DeWalt; John Dwyer; Thierry Fourcaud; Janet Franklin; et al. (Global Change Biology, 2024)
Each year, an average of 45 tropical cyclones affect coastal areas and potentially impact forests. The proportion of the most intense cyclones has increased over the past four decades and is predicted to continue to do so. Yet, it remains uncertain how topographical exposure and tree characteristics can mediate the damage caused by increasing wind speed. Here, we compiled empirical data on the damage caused by 11 cyclones occurring over the past 40 years, from 74 forest plots representing tropical regions worldwide, encompassing field data for 22,176 trees and 815 species. We reconstructed the wind structure of those tropical cyclones to estimate the maximum sustained wind speed (MSW) and wind direction at the studied plots. Then, we used a causal inference framework combined with Bayesian generalised linear mixed models to understand and quantify the causal effects of MSW, topographical exposure to wind (EXP), tree size (DBH) and species wood density ( ρ ) on the proportion of damaged trees at the community level, and on the probability of snapping or uprooting at the tree level. The probability of snapping or uprooting at the tree level and, hence, the proportion of damaged trees at the community level, increased with increasing MSW, and with increasing EXP accentuating the damaging effects of cyclones, in particular at higher wind speeds. Higher ρ decreased the probability of snapping and to a lesser extent of uprooting. Larger trees tended to have lower probabilities of snapping but increased probabilities of uprooting. Importantly, the effect of ρ decreasing the probabilities of snapping was more marked for smaller than larger trees and was further accentuated at higher MSW. Our work emphasises how local topography, tree size and species wood density together mediate cyclone damage to tropical forests, facilitating better predictions of the impacts of such disturbances in an increasingly windier world.

Effect of nutrient concentration, dissolved salts, and mineralogy at high temperature column bioleaching of a pyrrhotite-pyrite secondary ore - Carmen Falagán; David W. Dew; Karen A. Hudson-Edwards (Minerals Engineering, 2024)

Consequences of ecological aggregation in general equilibrium analysis of perturbed ecosystems - Stephanie Brockmann; David C. Finnoff; Doran M. Mason; Edward S. Rutherford; Hongyan Zhang (Ecological Economics, 2024)

Transformation of natural habitat disrupts biogeographical patterns of orchid diversity - Edicson Parra-Sanchez; Robert P. Freckleton; Matthew G. Hethcoat; Jose Manuel Ochoa-Quintero; David P. Edwards (Biological Conservation, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

The role of living labs in cultivating inclusive and responsible innovation in precision agriculture - Maaz Gardezi; Halimeh Abuayyash; Paul R. Adler; Juan P. Alvez; Rubaina Anjum; Appala Raju Badireddy; Skye Brugler; Pablo Carcamo; David Clay; Ali Dadkhah; Mary Emery; Joshua W. Faulkner; et al. (Agricultural Systems, 2024)

An innovative diffusion-theory based assessment of inherent barriers in urban green drainage infrastructure systems - Sakibu Seidu; David J. Edwards; De-Graft Owusu-Manu; Joseph I.T. Buertey (Hydrological Sciences Journal, 2024)

Insecticide contamination in organic agriculture: Evidence from a long-term farming systems comparisons trial - Ivonne Kampermann; David Bautze; Millicent Mapili; Martha Musyoka; Edward Karanja; Komi K.M. Fiaboe; Janet Irungu; Noah Adamtey (Crop Protection, 2024)

Assessing and improving the veracity of international trade in captive-bred animals - Oscar Morton; Vincent Nijman; David P. Edwards (Journal of Environmental Management, 2024)

Tree diversity and liana infestation predict acoustic diversity in logged tropical forests - Zachary Chu; Cindy C.P. Cosset; Catherine Finlayson; Patrick G. Cannon; Robert P. Freckleton; Kalsum M. Yusah; David P. Edwards (Biological Conservation, 2024)

Delayed leaf greening involves a major shift in the expression of cytosolic and mitochondrial ribosomes to plastid ribosomes in the highly phosphorus-use-efficient Hakea prostrata (Proteaceae) - Toby Bird; Benjamin J. Nestor; Philipp E. Bayer; Guannan Wang; Albina Ilyasova; Clément E. Gille; Bryce E. H. Soraru; Kosala Ranathunge; Anita A. Severn-Ellis; Ricarda Jost; Wolf-Rüdiger Scheible; Maheshi Dassanayake; et al. (Plant and Soil, 2024)
Background and aims Hakea prostrata (Proteaceae) is a highly phosphorus-use-efficient plant native to southwest Australia. It maintains a high photosynthetic rate at low leaf phosphorus (P) and exhibits delayed leaf greening, a convergent adaptation that increases nutrient-use efficiency. This study aimed to provide broad physiological and gene expression profiles across leaf development, uncovering pathways leading from young leaves as nutrient sinks to mature leaves as low-nutrient, energy-transducing sources. Methods To explore gene expression underlying delayed greening, we analysed a de novo transcriptome for H. prostrata across five stages of leaf development. Photosynthesis and respiration rates, and foliar pigment, P and nitrogen (N) concentrations were determined, including the division of P into five biochemical fractions. Key results Transcripts encoding functions associated with leaf structure generally decreased in abundance across leaf development, concomitant with decreases in foliar concentrations of 85% for anthocyanins, 90% for P and 70% for N. The expression of genes associated with photosynthetic function increased during or after leaf expansion, in parallel with increases in photosynthetic pigments and activity, much later in leaf development than in species that do not have delayed greening. As leaves developed, transcript abundance for cytosolic and mitochondrial ribosomal proteins generally declined, whilst transcripts for chloroplast ribosomal proteins increased. Conclusions There was a much longer temporal separation of leaf cell growth from chloroplast development in H. prostrata than is found in species that lack delayed greening. Transcriptome-guided analysis of leaf development in H. prostrata provided insight into delayed greening as a nutrient-saving strategy in severely phosphorus-impoverished landscapes.

Conflicts and opportunities for commercial tree plantation expansion and biodiversity restoration across Brazil - Gianluca Cerullo; Thomas Worthington; Pedro Brancalion; Joyce Brandão; Francisco d'Albertas; Alison Eyres; Thomas Swinfield; David Edwards; Andrew Balmford (Global Change Biology, 2024)
Substantial global restoration commitments are occurring alongside a rapid expansion in land‐hungry tropical commodities, including to supply increasing demand for wood products. Future commercial tree plantations may deliver high timber yields, shrinking the footprint of production forestry, but there is an as‐yet unquantified risk that plantations may expand into priority restoration areas, with marked environmental costs. Focusing on Brazil—a country of exceptional restoration importance and one of the largest tropical timber producers—we use random forest models and information on the economic, social, and spatial drivers of historic commercial tree plantation expansion to estimate and map the probability of future monoculture tree plantation expansion between 2020 and 2030. We then evaluate potential plantation‐restoration conflicts and opportunities at national and biome‐scales and under different future production and restoration pathways. Our simulations show that of 2.8 Mha of future plantation expansion (equivalent to plantation expansion 2010–2020), ~78,000 ha (3%) is forecast to occur in the top 1% of restoration priority areas for terrestrial vertebrates, with ~547,500 ha (20%) and ~1,300,000 ha (46%) in the top 10% and 30% of priority areas, respectively. Just ~459,000 ha (16%) of expansion is forecast within low‐restoration areas (bottom 30% restoration priorities), and the first 1 Mha of plantation expansion is likely to have disproportionate impacts, with potential restoration‐plantation overlap starkest in the Atlantic Forest but prominent in the Pampas and Cerrado as well. Our findings suggest that robust, coherent land‐use policies must be deployed to ensure that significant trade‐offs between restoration and production objectives are navigated, and that commodity expansion does not undermine the most tractable conservation gains under emerging global restoration agendas. They also highlight the potentially significant role an engaged forestry sector could play in improving biodiversity outcomes in restoration projects in Brazil, and presumably elsewhere.

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

It's time to consider the Arcellinida shell as a weapon - Kenneth Dumack; Enrique Lara; Clément Duckert; Elizaveta Ermolaeva; Ferry Siemensma; David Singer; Valentyna Krashevska; Mariusz Lamentowicz; Edward A.D. Mitchell (European Journal of Protistology, 2024)

Land‐use change from market responses to oil palm intensification in Indonesia - Felix K. S. Lim; Luis Roman Carrasco; David P. Edwards; Jolian McHardy (Conservation Biology, 2024)
Oil palm is a major driver of tropical deforestation. A key intervention proposed to reduce the footprint of oil palm is intensifying production to free up spare land for nature, yet the indirect land‐use implications of intensification through market forces are poorly understood. We used a spatially explicit land‐rent modeling framework to characterize the supply and demand of oil palm in Indonesia under multiple yield improvement and demand elasticity scenarios and explored how shifts in market equilibria alter projections of crop expansion. Oil palm supply was sensitive to crop prices and yield improvements. Across all our scenarios, intensification raised agricultural rents and lowered the effectiveness of reductions in crop expansion. Increased yields lowered oil palm prices, but these price‐drops were not sufficient to prevent further cropland expansion from increased agricultural rents under a range of price elasticities of demand. Crucially, we found that agricultural intensification might only result in land being spared when the demand relationship was highly inelastic and crop prices were very low (i.e., a 70% price reduction). Under this scenario, the extent of land spared (∼0.32 million ha) was countered by the continued establishment of new plantations (∼1.04 million ha). Oil palm intensification in Indonesia could exacerbate current pressures on its imperiled biodiversity and should be deployed with stronger spatial planning and enforcement to prevent further cropland expansion.

Numerical modelling of a 1.5 MW tidal turbine in realistic coupled wave–current sea states for the assessment of turbine hub-depth impacts on mechanical loads - Callum Guy; Edward Hart; Venugopal Vengatesan; David Forehand (Ocean Engineering, 2024)

Canola meal as a supplement for grass-fed beef cattle: Effects on growth rates, carcase and meat quality, and consumer sensory evaluations - Emma E.M. Lynch; Edward H. Clayton; Benjamin W.B. Holman; David L. Hopkins; Rod J. Polkinghorne; Michael A. Campbell (Meat Science, 2024)

Habitat modelling of native freshwater mussels distinguishes river specific differences in the Detroit and St. Clair rivers of the Laurentian Great Lakes - Shay S. Keretz; Daelyn A. Woolnough; Todd J. Morris; Edward F. Roseman; David T. Zanatta (Ecological Modelling, 2024)

Temperature Thresholds for Leaf Damage from Two Extreme Freeze Events (2018 and 2021) Near the Northern Range Limit of Black Mangroves (Avicennia germinans) in Southeastern North America - Simen Kaalstad; Michael J. Osland; Donna J. Devlin; C. Edward Proffitt; Laura C. Feher; Anna R. Armitage; Richard H. Day; Kathleen M. Swanson; Gordon H. Anderson; Brigid Berger; Just Cebrian; Karen L. Cummins; et al. (Estuaries and Coasts, 2024)

Indigenous Peoples' Lands are critical for safeguarding vertebrate diversity across the tropics - Jocelyne S. Sze; Dylan Z. Childs; L. Roman Carrasco; Álvaro Fernández‐Llamazares; Stephen T. Garnett; David P. Edwards (Global Change Biology, 2024)
Indigenous Peoples are long‐term custodians of their lands, but only recently are their contributions to conservation starting to be recognized in biodiversity policy and practice. Tropical forest loss and degradation are lower in Indigenous lands than unprotected areas, yet the role of Indigenous Peoples' Lands (IPL) in biodiversity conservation has not been properly assessed from regional to global scales. Using species distribution ranges of 11,872 tropical forest‐dependent vertebrates to create area of habitat maps, we identified the overlap of these species ranges with IPL and then compared values inside and outside of IPL for species richness, extinction vulnerability, and range‐size rarity. Of assessed vertebrates, at least 76.8% had range overlaps with IPL, on average overlapping ~25% of their ranges; at least 120 species were found only within IPL. Species richness within IPL was highest in South America, while IPL in Southeast Asia had highest extinction vulnerability, and IPL in Dominica and New Caledonia were important for range‐size rarity. Most countries in the Americas had higher species richness within IPL than outside, whereas most countries in Asia had lower extinction vulnerability scores inside IPL and more countries in Africa and Asia had slightly higher range‐size rarity in IPL. Our findings suggest that IPL provide critical support for tropical forest‐dependent vertebrates, highlighting the need for greater inclusion of Indigenous Peoples in conservation target‐setting and program implementation, and stronger upholding of Indigenous Peoples' rights in conservation policy.

Valuing bioeconomic impacts of regulation on nutrient loads mediated by invasive mussels in Lake Michigan - Stephanie Brockmann; David Finnoff; Nicholas Boucher; Doran M. Mason; Edward S. Rutherford; Hongyan Zhang (Journal of Environmental Management, 2023)

Sampling method drives differing detection of responses to land-use change in small mammals - Mariana F. Rocha; Luiz Fernando S. Magnago; Marcelo Passamani; Vinicius Chaga Lopes; Sergio Barbiero Lage; David P. Edwards (Journal for Nature Conservation, 2023)

Hydrodynamic response to bathymetric changes in Tampa Bay, Florida - Jing Chen; Yonggang Liu; Robert H. Weisberg; Steven A. Murawski; Sherryl Gilbert; David F. Naar; Lianyuan Zheng; Matthew Hommeyer; Catherine Dietrick; Mark E. Luther; Cheryl Hapke; Edward Myers; et al. (Deep Sea Research Part II: Topical Studies in Oceanography, 2023)

Approaches to increase the validity of gene family identification using manual homology search tools - Benjamin J. Nestor; Philipp E. Bayer; Cassandria G. Tay Fernandez; David Edwards; Patrick M. Finnegan (Genetica, 2023)
Identifying homologs is an important process in the analysis of genetic patterns underlying traits and evolutionary relationships among species. Analysis of gene families is often used to form and support hypotheses on genetic patterns such as gene presence, absence, or functional divergence which underlie traits examined in functional studies. These analyses often require precise identification of all members in a targeted gene family. Manual pipelines where homology search and orthology assignment tools are used separately are the most common approach for identifying small gene families where accurate identification of all members is important. The ability to curate sequences between steps in manual pipelines allows for simple and precise identification of all possible gene family members. However, the validity of such manual pipeline analyses is often decreased by inappropriate approaches to homology searches including too relaxed or stringent statistical thresholds, inappropriate query sequences, homology classification based on sequence similarity alone, and low-quality proteome or genome sequences. In this article, we propose several approaches to mitigate these issues and allow for precise identification of gene family members and support for hypotheses linking genetic patterns to functional traits.

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Evolution of Neptune at near-infrared wavelengths from 1994 through 2022 - Erandi Chavez; Imke de Pater; Erin Redwing; Edward M. Molter; Michael T. Roman; Andrea Zorzi; Carlos Alvarez; Randy Campbell; Katherine de Kleer; Ricardo Hueso; Michael H. Wong; Elinor Gates; et al. (Icarus, 2023)

Isopropyl alcohol inhalation versus 5-HT3 antagonists for treatment of nausea: a meta-analysis of randomised controlled trials - James S. Kimber; Joshua G. Kovoor; John M. Glynatsis; Samuel J. West; Thi Thien Nhi Mai; Jonathan Henry W. Jacobsen; Christopher D. Ovenden; Stephen Bacchi; Joseph N. Hewitt; Aashray K. Gupta; Suzanne Edwards; Fiona J. Taverner; et al. (European Journal of Clinical Pharmacology, 2023)
Purpose Nausea is a common and unpleasant sensation for which current therapies such as serotonin (5-HT 3 ) antagonists are often ineffective, while also conferring a risk of potential adverse events. Isopropyl alcohol (IPA) has been proposed as a treatment for nausea. We aimed to compare IPA with 5-HT 3 antagonists for the treatment of nausea across all clinical settings. Methods MEDLINE, EMBASE, PubMed, CENTRAL and CINAHL were searched from inception to 17 July 2023 for randomised controlled trials (RCTs) comparing inhaled IPA and a 5-HT 3 antagonist for treatment of nausea. Severity and duration of nausea, rescue antiemetic use, adverse events and patient satisfaction were the outcomes sought. Risk of bias (RoB) was assessed using Cochrane RoB 2. Random-effects model was used for meta-analysis. Combination of meta-analyses and narrative review was used to synthesise findings. The evidence was appraised using GRADE. Results From 1242 records, 4 RCTs were included with 382 participants. Participants receiving IPA had a significantly lower mean time to 50% reduction in nausea (MD − 20.06; 95% CI − 26.26, − 13.85). Nausea score reduction at 30 min was significantly greater in the IPA group (MD 21.47; 95% CI 15.47, 27.47). IPA led to significantly reduced requirement for rescue antiemetics (OR 0.60; 95% CI 0.37, 0.95; p = 0.03). IPA led to no significant difference in patient satisfaction when compared with a 5-HT 3 antagonist. The overall GRADE assessment of evidence quality ranged from very low to low. Conclusion IPA may provide rapid, effective relief of nausea when compared with 5-HT 3 antagonists.

Free-water imaging reveals unique brain microstructural deficits in hispanic individuals with Dementia - Edward Ofori; David E. Vaillancourt; Maria T Greig-Custo; Warren Barker; Kevin Hanson; Steven T. DeKosky; Cynthia S. Garvan; Malek Adjouadi; Todd Golde; David A. Loewenstein; Chad Stecher; Rylan Fowers; et al. (Brain Imaging and Behavior, 2023)

High urinary oxidative DNA damage in wild chimpanzees ranging in proximity of agricultural fields in Sebitoli area, Uganda - Sabrina Krief; Petra Spirhanzlova; Shelly Masi; Chloé Couturier; Eric Okwir; Edward Asalu; Paco Bustamante; David Costantini (Environmental Science and Pollution Research, 2023)

Avian biodiversity losses from grazing of high Andean páramo - Simon C. Mills; Edicson Parra Sanchez; Jacob B. Socolar; Chris Bousfield; Bryn Coffey; Jos Barlow; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; David P. Edwards (Biological Conservation, 2023)

Correction to: Satellite Remote Sensing of Surface Winds, Waves, and Currents: Where are we Now? - Danièle Hauser; Saleh Abdalla; Fabrice Ardhuin; Jean-Raymond Bidlot; Mark Bourassa; David Cotton; Christine Gommenginger; Hayley Evers-King; Harald Johnsen; John Knaff; Samantha Lavender; Alexis Mouche; et al. (Surveys in Geophysics, 2023)

Satellite Remote Sensing of Surface Winds, Waves, and Currents: Where are we Now? - Danièle Hauser; Saleh Abdalla; Fabrice Ardhuin; Jean-Raymond Bidlot; Mark Bourassa; David Cotton; Christine Gommenginger; Hayley Evers-King; Harald Johnsen; John Knaff; Samantha Lavender; Alexis Mouche; et al. (Surveys in Geophysics, 2023)
This review paper reports on the state-of-the-art concerning observations of surface winds, waves, and currents from space and their use for scientific research and subsequent applications. The development of observations of sea state parameters from space dates back to the 1970s, with a significant increase in the number and diversity of space missions since the 1990s. Sensors used to monitor the sea-state parameters from space are mainly based on microwave techniques. They are either specifically designed to monitor surface parameters or are used for their abilities to provide opportunistic measurements complementary to their primary purpose. The principles on which is based on the estimation of the sea surface parameters are first described, including the performance and limitations of each method. Numerous examples and references on the use of these observations for scientific and operational applications are then given. The richness and diversity of these applications are linked to the importance of knowledge of the sea state in many fields. Firstly, surface wind, waves, and currents are significant factors influencing exchanges at the air/sea interface, impacting oceanic and atmospheric boundary layers, contributing to sea level rise at the coasts, and interacting with the sea-ice formation or destruction in the polar zones. Secondly, ocean surface currents combined with wind- and wave- induced drift contribute to the transport of heat, salt, and pollutants. Waves and surface currents also impact sediment transport and erosion in coastal areas. For operational applications, observations of surface parameters are necessary on the one hand to constrain the numerical solutions of predictive models (numerical wave, oceanic, or atmospheric models), and on the other hand to validate their results. In turn, these predictive models are used to guarantee safe, efficient, and successful offshore operations, including the commercial shipping and energy sector, as well as tourism and coastal activities. Long-time series of global sea-state observations are also becoming increasingly important to analyze the impact of climate change on our environment. All these aspects are recalled in the article, relating to both historical and contemporary activities in these fields.

Small is Powerful: Demonstration of the Impact of Nanoformed Piroxicam in a Controlled Clinical Study - Satu Lakio; David J. Smith; Goncalo Andrade; Niklas Sandler; Philip Evans; John McDermott; Chris Roe; Edward Hӕggström (Pharmaceutical Research, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

A genetic Study of the Ghanaian Population Using 15 Autosomal STR Loci - Abban Edward Kofi; David Adjem Agyemang; Anita Ghansah; Gordon A. Awandare; Hashom Mohd Hakim; Hussein Omar Khan; Abd Rashid Nur Haslindawaty; Mohd Yusmaidie Aziz; Geoffrey Keith Chambers; Hisham Atan Edinur (Biochemical Genetics, 2023)

Determining the sustainability of legal wildlife trade - Alice Hughes; Mark Auliya; Sandra Altherr; Brett Scheffers; Jordi Janssen; Vincent Nijman; Chris R. Shepherd; Neil D'Cruze; Emerson Sy; David P. Edwards (Journal of Environmental Management, 2023)

Adaptation and mitigation capacity of wildland forests in the northeastern United States - Edward K. Faison; Danelle Laflower; Luca L. Morreale; David R. Foster; Brian Hall; Emily Johnson; Jonathan R. Thompson (Forest Ecology and Management, 2023)

Factors that influence pastoralists’ estimation of onset and cessation of rains in Rwenzori region in Western Uganda - Michael Robert Nkuba; Raban Chanda; Gagoitseope Mmopelwa; Edward Kato; Akintayo Adedoyin; Godfrey Mujuni; David Lesolle; Margaret Najjingo Mangheni (Environmental Development, 2023)

John Squire: a leader and seminal contributor to experimental and theoretical muscle research for over 50 years - Pradeep K. Luther; Edward P. Morris; David A.D. Parry; Kenneth A. Taylor (Journal of Muscle Research and Cell Motility, 2023)

Evaluating the factors influencing the location strategies of specialty grocers versus traditional supermarkets in the United States - Connor Reed; T. Edward Yu; David Hughes (Applied Geography, 2023)

Evaluation in a porcine wound model and long-term clinical assessment of an autologous heterogeneous skin construct used to close full-thickness wounds - Nicholas Baetz; Pratima Labroo; Marytheresa Ifediba; Devin Miller; Kendall Stauffer; Michael Sieverts; Jessie Nicodemus-Johnson; Eric Chan; Ian Robinson; James Miess; Stephanie Roth; Jenny Irvin; et al. (Tissue and Cell, 2023)

Acute inhalation of tungsten particles results in early signs of cardiac injury - Sage Templeton; Charlotte M. McVeigh; Colin Nguyen; Russell Hunter; David Scieszka; Guy W. Herbert; Edward B. Barr; Rui Liu; Haiwei Gu; Barry E. Bleske; Matthew J. Campen; Alicia M. Bolt (Toxicology Letters, 2023)

Plant genome resequencing and population genomics: Current status and future prospects - Bo Song; Weidong Ning; Di Wei; Mengyun Jiang; Kun Zhu; Xingwei Wang; David Edwards; Damaris A. Odeny; Shifeng Cheng (Molecular Plant, 2023)

Corticospinal excitability and reflex modulation in a contralateral non-stretched muscle following unilateral stretching - Saman Hadjizadeh Anvar; Urs Granacher; Andreas Konrad; Shahab Alizadeh; Robyn Culleton; Chris Edwards; Reza Goudini; David G. Behm (European Journal of Applied Physiology, 2023)

Complement component C1q is an immunological rheostat that regulates Fc:Fc$$γ$$R interactions - Edward C. So; Hua Zhou; Ariana Greenwell; Erin E. Burch; Yaping Ji; Emmanuel Y. Mérigeon; Henrik S. Olsen; Søren M. Bentzen; David S. Block; Xiaoyu Zhang; Scott E. Strome (Immunogenetics, 2023)

Adaptive, multi-paddock, rotational grazing management alters foraging behavior and spatial grazing distribution of free-ranging cattle - David J. Augustine; Sean P. Kearney; Edward J. Raynor; Lauren M. Porensky; Justin D. Derner (Agriculture, Ecosystems & Environment, 2023)

Association of reproductive traits with captive‐ versus wild‐sourced birds in trade - Oscar Morton; Brett R. Scheffers; Torbjørn Haugaasen; David P. Edwards (Conservation Biology, 2023)
The wildlife trade is a billion‐dollar global business, involving millions of people, thousands of species, and hundreds of millions of individual organisms. Unravelling whether trade targets reproductively distinct species and whether this preference varies between captive‐ and wild‐sourced species is a crucial question. We used a comprehensive list of all bird species traded, trade listings and records kept in compliance with the Convention on International Trade in Endangered Species (CITES), and a suite of avian reproductive parameters to examine whether wildlife trade is associated with particular facets of life history and to examine the association between life‐history traits and captive‐ and wild‐sourced traded volumes over time. Across all trade, CITES listing, and CITES trade, large birds were more likely to be traded and listed, but their longevity and age at maturity were not associated with CITES listing or trade. We found species across almost the full range of trait values in both captive and wild trade between 2000 and 2020. Captive trade volumes clearly associated with relatively longer lived and early‐maturing species; these associations remained stable and largely unchanged over time. Trait–volume associations in wild‐sourced trade were more uncertain. Only body mass had a clear association, and it varied from negative to positive over time. Although reproductive traits were important in captive‐sourced trade, species‐level variation dominated trade, with even congeneric species varying greatly in volume despite similar traits. The collection and incorporation of trait data into sustainability assessments of captive breeding facilities are crucial to ensure accurate quotas and guard against laundering.

Effect of indigenous and scientific forecasts on pastoralists’ climate change perceptions in the Rwenzori region, Western Uganda - Michael Robert Nkuba; Raban Chanda; Gagoitseope Mmopelwa; Edward Kato; Margaret Najjingo Mangheni; David Lesolle; Godfrey Mujuni (Climate and Development, 2023)

The phytotoxicity of soil-applied herbicides is enhanced in the first-year post strategic deep tillage - Tom J. Edwards; Stephen L. Davies; Ron J. Yates; Mick Rose; John G. Howieson; Graham O’Hara; Emma J. Steel; David JM Hall (Soil and Tillage Research, 2023)

Feeding the pyramid builders: Early agriculture at Giza in Egypt - Hader Sheisha; David Kaniewski; Nick Marriner; Morteza Djamali; Gamal Younes; Zhongyuan Chen; Gad El-Qady; Amr Saleem; Carla Khater; Alain Véron; Edward Anthony; Mohamed Mustapha Abdelmaguid; et al. (Quaternary Science Reviews, 2023)

Internal endpoint temperature (level of cooking doneness) effects on the fatty acid and mineral profiles of grilled lamb m. longissimus lumborum - Benjamin W.B. Holman; Stephanie M. Fowler; Kristy L. Bailes; Richard G. Meyer; David L. Hopkins; Edward H. Clayton (Meat Science, 2023)

Empowering Food Citizens Through a Coordinated SNAP-Ed Garden-Based Nutrition Education Program - Caramie Edwards; Katie Holland; Amy McClelland; Sarah David; Crystal Bowne; Josh Phelps (Journal of Nutrition Education and Behavior, 2023)

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Evolutionary dynamics and adaptive benefits of deleterious mutations in crop gene pools - Sangam L. Dwivedi; Pat Heslop-Harrison; Charles Spillane; Peter C. McKeown; David Edwards; Irwin Goldman; Rodomiro Ortiz (Trends in Plant Science, 2023)

Sparing old-growth maximises conservation outcomes within selectively logged Amazonian rainforest - Gianluca Cerullo; Filipe França; Tom Finch; Philip Erm; Hannah Griffiths; Julio Louzada; Chris G. Bousfield; Mike R. Massam; Carlos A. Peres; Jos Barlow; Rhys E. Green; David P. Edwards; et al. (Biological Conservation, 2023)

Topography Mediates the Response of Soil CO2 Efflux to Precipitation Over Days, Seasons, and Years - Marissa Kopp; Jason Kaye; Yuting He Smeglin; Thomas Adams; Edward J. Primka; Brosi Bradley; Yuning Shi; David Eissenstat (Ecosystems, 2023)

SIPN South: six years of coordinated seasonal Antarctic sea ice predictions - François Massonnet; Sandra Barreira; Antoine Barthélemy; Roberto Bilbao; Edward Blanchard-Wrigglesworth; Ed Blockley; David H. Bromwich; Mitchell Bushuk; Xiaoran Dong; Helge F. Goessling; Will Hobbs; Doroteaciro Iovino; et al. (Frontiers in Marine Science, 2023)
Antarctic sea ice prediction has garnered increasing attention in recent years, particularly in the context of the recent record lows of February 2022 and 2023. As Antarctica becomes a climate change hotspot, as polar tourism booms, and as scientific expeditions continue to explore this remote continent, the capacity to anticipate sea ice conditions weeks to months in advance is in increasing demand. Spurred by recent studies that uncovered physical mechanisms of Antarctic sea ice predictability and by the intriguing large variations of the observed sea ice extent in recent years, the Sea Ice Prediction Network South (SIPN South) project was initiated in 2017, building upon the Arctic Sea Ice Prediction Network. The SIPN South project annually coordinates spring-to-summer predictions of Antarctic sea ice conditions, to allow robust evaluation and intercomparison, and to guide future development in polar prediction systems. In this paper, we present and discuss the initial SIPN South results collected over six summer seasons (December-February 2017-2018 to 2022-2023). We use data from 22 unique contributors spanning five continents that have together delivered more than 3000 individual forecasts of sea ice area and concentration. The SIPN South median forecast of the circumpolar sea ice area captures the sign of the recent negative anomalies, and the verifying observations are systematically included in the 10-90% range of the forecast distribution. These statements also hold at the regional level except in the Ross Sea where the systematic biases and the ensemble spread are the largest. A notable finding is that the group forecast, constructed by aggregating the data provided by each contributor, outperforms most of the individual forecasts, both at the circumpolar and regional levels. This indicates the value of combining predictions to average out model-specific errors. Finally, we find that dynamical model predictions (i.e., based on process-based general circulation models) generally perform worse than statistical model predictions (i.e., data-driven empirical models including machine learning) in representing the regional variability of sea ice concentration in summer. SIPN South is a collaborative community project that is hosted on a shared public repository. The forecast and verification data used in SIPN South are publicly available in near-real time for further use by the polar research community, and eventually, policymakers.

Uranus ring occultation observations: 1977–2006 - Richard G. French; Colleen A. McGhee-French; Mitchell Gordon; Richard L. Baron; Amanda S. Bosh; Marc W. Buie; Nancy Chanover; Mary Ann Clark; Edward W. Dunham; Linda M. French; Ian S. Glass; Jay D. Goguen; et al. (Icarus, 2023)

Dilated hypertrophic phenotype of the carotid artery is associated with accelerated age-associated central arterial stiffening - Majd AlGhatrif; Edward G. Lakatta; Christopher H. Morrell; Danilo Alunni Fegatelli; Edoardo Fiorillo; Michele Marongiu; David Schlessinger; Francesco Cucca; Angelo Scuteri (GeroScience, 2023)

Plant-based production of an orally active cyclotide for the treatment of multiple sclerosis - Mark A. Jackson; Jing Xie; Linh T. T. Nguyen; Xiaohan Wang; Kuok Yap; Peta J. Harvey; Edward K. Gilding; David J. Craik (Transgenic Research, 2023)
Multiple sclerosis (MS) is a debilitating disease that requires prolonged treatment with often severe side effects. One experimental MS therapeutic currently under development is a single amino acid mutant of a plant peptide termed kalata B1, of the cyclotide family. Like all cyclotides, the therapeutic candidate [T20K]kB1 is highly stable as it contains a cyclic backbone that is cross-linked by three disulfide bonds in a knot-like structure. This stability is much sought after for peptide drugs, which despite exquisite selectivity for their targets, are prone to rapid degradation in human serum. In preliminary investigations, it was found that [T20K]kB1 retains oral activity in experimental autoimmune encephalomyelitis, a model of MS in mice, thus opening up opportunities for oral dosing of the peptide. Although [T20K]kB1 can be synthetically produced, a recombinant production system provides advantages, specifically for reduced scale-up costs and reductions in chemical waste. In this study, we demonstrate the capacity of the Australian native Nicotiana benthamiana plant to produce a structurally identical [T20K]kB1 to that of the synthetic peptide. By optimizing the co-expressed cyclizing enzyme, precursor peptide arrangements, and transgene regulatory regions, we demonstrate a [T20K]kB1 yield in crude peptide extracts of ~ 0.3 mg/g dry mass) in whole plants and close to 1.0 mg/g dry mass in isolated infiltrated leaves. With large-scale plant production facilities coming on-line across the world, the sustainable and cost-effective production of cyclotide-based therapeutics is now within reach.

Community‐based monitoring, assessment and management of data‐limited inland fish stocks in North Rupununi, Guyana - Samuel Shephard; Kevin Edwards; Susan George; Elvis Joseph; Samantha James; Oswin David; Addevi Persaud; L. Cynthia Watson; Nathalie Van Vliet (Fisheries Management and Ecology, 2023)
Inland fisheries are important for food security in communities around the world, especially in developing countries. In North Rupununi, Guyana, the state of exploited stocks is poorly understood, and fishery monitoring and assessment are challenging because diverse fishing gears and target species are distributed across a heterogeneous landscape. This complexity created an opportunity for community‐based monitoring (CBM) to support data‐limited assessment. Standardised CBM was established for the North Rupununi as part of a new inland fisheries management plan initiated by indigenous community groups with support from the government. Quantitative length‐based assessments undertaken for target stocks suggested moderate levels of exploitation consistent with local perception. Our study highlights that local experts and community participants with different levels of training can collect accurate biodiversity data. Further development of CBM is important in North Rupununi. We recommend using local ecological knowledge indicators to track spatial and temporal patterns in exploitation and fish stock status.

Factors associated with farmers’ use of indigenous and scientific climate forecasts in Rwenzori region, Western Uganda - Michael Robert Nkuba; Raban Chanda; Gagoitseope Mmopelwa; Edward Kato; Margaret Najjingo Mangheni; David Lesolle; Akintayo Adedoyin; Godfrey Mujuni (Regional Environmental Change, 2023)

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Bioavailability of dissolved organic matter varies with anthropogenic landcover in the Upper Mississippi River Basin - Derrick R. Vaughn; Anne M. Kellerman; Kimberly P. Wickland; Robert G. Striegl; David C. Podgorski; Jon R. Hawkings; Jaap H. Nienhuis; Mark M. Dornblaser; Edward G. Stets; Robert G.M. Spencer (Water Research, 2023)

The National Conference on Health Disparities Student Research Forum - Marvella E. Ford; Angela M. Malek; Erica Martino; Latecia Abraham-Hilaire; Oluwole Ariyo; Dana Burshell; Gloria Callwood; Laura Campbell; Kimberly Cannady; Courtney Chavis; Brittney Crawford; Andie Edwards; et al. (Journal of Cancer Education, 2023)
The annual National Conference on Health Disparities (NCHD) was launched in 2000. It unites health professionals, researchers, community leaders, and government officials, and is a catalyzing force in developing policies, research interventions, and programs that address prevention, social determinants, health disparities, and health equity. The NCHD Student Research Forum (SRF) was established in 2011 at the Medical University of South Carolina to build high-quality biomedical research presentation capacity in primarily underrepresented undergraduate and graduate/professional students. This paper describes the unique research training and professional development aspects of the NCHD SRF. These include guidance in abstract development, a webinar on presentation techniques and methods, a vibrant student-centric conference, and professional development workshops on finding a mentor and locating scholarship/fellowship funding, networking, and strategies for handling ethical issues in research with mentors. Between 2011 and 2018, 400 undergraduate and graduate/professional students participated in the NCHD SRF. Most students were women (80.5%). Approximately half were African American or black (52.3%), 18.0% were white, and 21.3% were of Hispanic/Latinx ethnicity. The NCHD SRF is unique in several ways. First, it provides detailed instructions on developing a scientific abstract, including content area examples. Second, it establishes a mandatory pre-conference training webinar demonstrating how to prepare a scientific poster. Third, it works with the research mentors, faculty advisors, department chairs, and deans to help identify potential sources of travel funding for students with accepted abstracts. These features make the NCHD SRF different from many other conferences focused on students’ scientific presentations.

Profiling human pathogenic repeat expansion regions by synergistic and multi-level impacts on molecular connections - Cong Fan; Ken Chen; Yukai Wang; Edward V. Ball; Peter D. Stenson; Matthew Mort; Albino Bacolla; Hildegard Kehrer-Sawatzki; John A. Tainer; David N. Cooper; Huiying Zhao (Human Genetics, 2023)

Evolving insights into the epidemiology of Moraxella species bloodstream infection from two decades of surveillance in Queensland, Australia - Jessica Schults; Felicity Edwards; Karina Charles; Adam D. Irwin; Claire M. Rickard; Patrick N. A. Harris; David L. Paterson; Kevin Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Nutrient function over form: Organic and inorganic nitrogen additions have similar effects on lake phytoplankton nutrient limitation - Sabrina N. Volponi; Heather L. Wander; David C. Richardson; Clayton J. Williams; Denise A. Bruesewitz; Shelley Arnott; Jennifer A. Brentrup; Hailee L. Edwards; Holly A. Ewing; Kristen Holeck; Lauren Johnson; Brian S. Kim; et al. (Limnology and Oceanography, 2023)
The concentration of dissolved organic nitrogen (DON) is increasing in many northern hemisphere lakes, yet its use by phytoplankton and fate in the environment seldom have been quantified. We conducted 1 week, in situ, microcosm incubations across 25 lakes in northeastern North America to understand how DON, dissolved inorganic nitrogen (DIN), and dissolved inorganic phosphorus (P) affected phytoplankton biomass. In addition, we tested whether lakes were limited by single macronutrients (N or P) or colimited by both. Phytoplankton biomass in 80% of lakes responded similarly to DON and DIN additions. Of the lakes where N form produced differential responses, the majority of phytoplankton communities exhibited greater biomass accumulation with DON than DIN. Colimitation was the most common type of nutrient limitation among the study lakes, followed by P limitation. Limitation type shifted with N form in 40% of the study lakes, but without consistent patterns explaining how shifts occurred. Regardless of N form, lakes with watersheds more dominated by agriculture and higher total dissolved nitrogen (TDN) tended to show P‐limited phytoplankton responses, while lakes with less agricultural watersheds and lower TDN tended to show colimited phytoplankton responses. Finally, ambient TDN and total phosphorus (TP) nutrient concentrations were stronger predictors of limitation type than ambient TDN : TP ratios. The different contributions of DON and DIN to phytoplankton biomass in some of our study lakes suggest that DON loading from surrounding watersheds may be an overlooked component in predicting phytoplankton productivity and nutrient limitation dynamics in freshwater ecosystems.

Constant-temperature predictions underestimate growth of a fungal amphibian pathogen under individual host thermal profiles - Sasha E. Greenspan; Elizabeth A. Roznik; Lexie Edwards; Richard Duffy; Lee Berger; Deborah S. Bower; David A. Pike; Lin Schwarzkopf; Ross A. Alford (Journal of Thermal Biology, 2023)

Effects of nasal anatomical characteristics and administration parameters on delivery of locally-acting drugs with suspension nasal sprays in adults - Sana Hosseini; Ali Alfaifi; Amir Reza Esmaeili; David Edwards; Theodore Schuman; Worth Longest; Michael Hindle; Laleh Golshahi (Journal of Aerosol Science, 2023)

Structural diversity in salt excreting glands and salinity tolerance in Oryza coarctata, Sporobolus anglicus and Urochondra setulosa - Nuria K. Koteyeva; Elena V. Voznesenskaya; Anna Berim; David R. Gang; Gerald E. Edwards (Planta, 2023)

Long-Term Biophysical Observations and Climate Impacts in US Arctic Marine Ecosystems - Phyllis Stabeno; Shaun Bell; Catherine Berchok; Edward Cokelet; Jessica Cross; Ryan McCabe; Calvin Mordy; James Overland; David Strausz; Margaret Sullivan; Heather Tabisola (Oceanography, 2023)
In 1995, the first of a nearly continuous sequence of biophysical moorings was deployed at a site (M2) on the southeastern Bering Sea shelf. Over the next 15 years, 10 additional mooring sites were initiated. The resultant long-term biophysical mooring array extends over 1,800 km from the southern Bering Sea to the northern Chukchi Sea, covering most of the US Arctic. It provides a full range of oceanographic data for researchers, stakeholders, and managers. In addition, these data sets have been critical for the validation of regional ocean models. The ocean temperature data have quantified regional warming and formed the basis for understanding how warmer temperatures and loss of sea ice are modifying these high-latitude marine ecosystems. Changes observed in the context of observations from the mooring program include delayed spring bloom, low abundances of large crustacean zooplankton and crab species, seabird die-offs, changes in ocean acidification, northward expansion of subarctic fish species, and shifts in the ranges of marine mammal species.

High sensitivity of tropical forest birds to deforestation at lower altitudes - Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Edicson Parra; Diego E. Martínez‐Revelo; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; David P. Edwards (Ecology, 2023)
Habitat conversion is a major driver of tropical biodiversity loss, but its effects are poorly understood in montane environments. While community‐level responses to habitat loss display strong elevational dependencies, it is unclear whether these arise via elevational turnover in community composition and interspecific differences in sensitivity or elevational variation in environmental conditions and proximity to thermal thresholds. Here we assess the relative importance of inter‐ and intraspecific variation across the elevational gradient by quantifying how 243 forest‐dependent bird species vary in sensitivity to landscape‐scale forest loss across a 3000‐m elevational gradient in the Colombian Andes. We find that species that live at lower elevations are strongly affected by loss of forest in the nearby landscape, while those at higher elevations appear relatively unperturbed, an effect that is independent of phylogeny. Conversely, we find limited evidence of intraspecific elevational gradients in sensitivity, with populations displaying similar sensitivities to forest loss, regardless of where they exist in a species' elevational range. Gradients in biodiversity response to habitat loss thus appear to arise via interspecific gradients in sensitivity rather than proximity to climatically limiting conditions.

Streptomyces spiramenti sp. nov., isolated from a deep-sea microbial mat - Rachel M. Loughran; Caitlin M. Diefendorf; Jassmine R. Reill-VanSise; Edward A. Mitchell; Oliver B. Vining; David A. Gallegos; Gregory Miller; Marc J. Koyack; David K. Oline; Orion S. Rivers; Blake Ushijima; Jimmy H. Saw; et al. (Archives of Microbiology, 2022)

Uterine fibroid polygenic risk score (PRS) associates and predicts risk for uterine fibroid - Jacqueline A. Piekos; Jacklyn N. Hellwege; Yanfei Zhang; Eric S. Torstenson; Gail P. Jarvik; Ozan Dikilitas; Iftikhar J. Kullo; Daniel J. Schaid; David R. Crosslin; Sarah A. Pendergrass; Ming Ta Michael Lee; Dan Roden; et al. (Human Genetics, 2022)

Determinants and outcomes of bloodstream infections related to obesity - Felicity Edwards; Kate Glen; Patrick N. A. Harris; David L. Paterson; Kevin B. Laupland (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Although obesity is a major healthcare problem that is increasing in many populations worldwide, there are limited studies that have examined its contribution to infectious diseases morbidity and mortality. The aim of this study was to examine the clinical determinants and outcomes of bloodstream infections among patients with obesity. All adults within the publicly funded healthcare system in Queensland, Australia, identified with a BSI during 2017–2019 were included and the presence of obesity was based on discharge International Classification of Diseases (ICD-10) codes. Clinical features, microbiology, and outcomes were compared among obese and non-obese subjects. A total of 24,602 incident BSI were identified among 21,613 Queensland residents; of which 4,579 (21.2%) and 17,034 (78.8%) were classified as obese or non-obese, respectively. Obese patients were less likely to have community associated infections and were more likely to be younger, female, have higher comorbidity scores, and have bone and joint or soft tissue infections as compared to non-obese subjects. Obese patients had a lower proportion of Escherichia coli BSI and higher proportions of b-haemolytic streptococci. Although obese patients had longer hospital admissions and more repeat incident BSI within 1 year, they had lower overall case fatality. In a logistic regression model, obesity was associated with a lower risk for 30-day case fatality (adjusted odds ratio 0.51, 95% confidence interval 0.45–0.58). Obesity is associated with significant differences in the determinants and outcome of BSI. Increasing rates of obesity is likely to influence the epidemiology of BSI in populations.

Laboratory Measurements of Surface Wave Propagation through Ice Floes in Salt Water - Mark Orzech; Jie Yu; David Wang; Blake Landry; Carlo Zuniga-Zamalloa; Edward Braithwaite; Kathryn Trubac; Callum Gray (Journal of Marine Science and Engineering, 2022)
Surface waves traversing polar marginal ice zones (MIZs) generate a boundary layer immediately below the ice, similar in some respects to the wave boundary layer created at the seabed in shallow water. The wave–ice boundary layer has not yet been thoroughly measured, but it can significantly affect wave attenuation rates. In December 2021, we conducted a laboratory experiment designed to measure such a boundary layer and the associated attenuation, in which monochromatic waves propagated through broken surface ice in a salt water tank. A particle imaging velocimetry (PIV) instrument array was submerged in the tank and used to visualize the fluid motion under the moving ice. The surface was tracked at multiple locations with acoustic sensors and cameras mounted over the tank. A total of 64 trials were completed, each producing 3–6 s of highly resolved velocity time series and 30–40 s of surface elevation data. Preliminary analysis of the data has provided strong evidence of a boundary layer at the water–ice interface. The wave attenuation rates compare well with existing datasets. The vertical profiles of RMS velocities and wave-induced Reynolds stress have trends similar to the theoretical predictions, while the quantitative discrepancies in terms of numerical values are discussed. This is the first of two such experiments; the second is tentatively scheduled for early 2023.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Simulated heat wave events increase CO2 and N2O emissions from cropland and forest soils in an incubation experiment - Zhengfeng An; Edward W. Bork; David Olefeldt; Cameron N. Carlyle; Scott X. Chang (Biology and Fertility of Soils, 2022)

Genomic regions associated with resistance to soybean rust (Phakopsora pachyrhizi) under field conditions in soybean germplasm accessions from Japan, Indonesia and Vietnam - David R. Walker; Samuel C. McDonald; Donna K. Harris; H. Roger Boerma; James W. Buck; Edward J. Sikora; David B. Weaver; David L. Wright; James J. Marois; Zenglu Li (Theoretical and Applied Genetics, 2022)
Key message Eight soybean genomic regions, including six never before reported, were found to be associated with resistance to soybean rust ( Phakopsora pachyrhizi ) in the southeastern USA. Abstract Soybean rust caused by Phakopsora pachyrhizi is one of the most important foliar diseases of soybean [ Glycine max (L.) Merr.]. Although seven Rpp resistance gene loci have been reported, extensive pathotype variation in and among fungal populations increases the importance of identifying additional genes and loci associated with rust resistance. One hundred and ninety-one soybean plant introductions from Japan, Indonesia and Vietnam, and 65 plant introductions from other countries were screened for resistance to P. pachyrhizi under field conditions in the southeastern USA between 2008 and 2015. The results indicated that 84, 69, and 49% of the accessions from southern Japan, Vietnam or central Indonesia, respectively, had negative BLUP values, indicating less disease than the panel mean. A genome-wide association analysis using SoySNP50K Infinium BeadChip data identified eight genomic regions on seven chromosomes associated with SBR resistance, including previously unreported regions of Chromosomes 1, 4, 6, 9, 13, and 15, in addition to the locations of the Rpp3 and Rpp6 loci. The six unreported genomic regions might contain novel Rpp loci. The identification of additional sources of rust resistance and associated genomic regions will further efforts to develop soybean cultivars with broad and durable resistance to soybean rust in the southern USA.

Projected climate in coffee-based farming systems: implications for crop suitability in Uganda - Catherine Mulinde; J. G. Mwanjalolo Majaliwa; Revocatus Twinomuhangi; David Mfitumukiza; Daniel Waiswa; Fredrick Tumwine; Edward Kato; Judith Asiimwe; Winfred N. Nakyagaba; David Mukasa (Regional Environmental Change, 2022)

Predicting larval alewife transport in Lake Michigan using hydrodynamic and Lagrangian particle dispersion models - Mark D. Rowe; Sara E. Prendergast; Karen M. Alofs; David B. Bunnell; Edward S. Rutherford; Eric J. Anderson (Limnology and Oceanography, 2022)
Several species of fish in large lakes and marine environments have a pelagic larval stage, and are subject to variable transport that can ultimately regulate survival and recruitment success. Alewife, Alosa pseudoharengus , are subject to transport by complex coastal currents during their pelagic larval stage (~ 30 d). We assessed backward‐trajectory simulations, consisting of a Lagrangian particle dispersion model linked to the Finite Volume Community Ocean Model, to estimate likely hatch locations of aged larval alewife collected from locations on both the eastern and western sides of Lake Michigan during July 2015. We used four deployments of three satellite‐tracked drifter buoys in coastal waters to assess model skill in estimating the origin of a drifter from its final location. We found that the trajectories of drifters varied greatly, depending on wind events and associated coastal transport processes, including upwelling/downwelling and coastal jet currents. In 2 of 12 cases, the backward trajectory simulations failed to predict the drifter origin, associated with transport of 170 km in a narrow coastal jet current. In the remaining 10 cases, the known drifter origin was within 3.5 km of the spatial patch of predicted possible origins for a scenario of horizontal diffusivity (188 m 2 s −1 ) consistent with the offshore model grid resolution. Modeled backward trajectories estimated that alewife originated from the same side of the lake where they were collected, within ~ 100 km of the collection site. Our paper demonstrates the utility of hydrodynamic models to estimate a region of origin for aged larval fish.

Grazing by an endemic atyid shrimp controls microbial communities in the Hawaiian anchialine ecosystem - Justin C. Havird; Pamela M. Brannock; Reyn M. Yoshioka; Rebecca C. Vaught; Kaile'a Carlson; Collin Edwards; Allison Tracy; Cornelia W. Twining; Yun Zheng; David Chai; Alan E. Wilson; Nelson G. Hairston; et al. (Limnology and Oceanography, 2022)
Animals often shape environmental microbial communities, which can in turn influence animal gut microbiomes. Invasive species in critical habitats may reduce grazing pressure from native species and shift microbial communities. The landlocked coastal ponds, pools, and caves that make up the Hawaiian anchialine ecosystem support an endemic shrimp ( Halocaridina rubra ) that grazes on diverse benthic microbial communities, including orange cyanobacterial‐bacterial crusts and green algal mats. Here, we asked how shrimp: (1) shape the abundance and composition of microbial communities, (2) respond to invasive fishes, and (3) whether their gut microbiomes are affected by environmental microbial communities. We demonstrate that ecologically relevant levels of shrimp grazing significantly reduce epilithon biomass. Shrimp grazed readily and grew well on both orange crusts and green mat communities. However, individuals from orange crusts were larger, despite crusts having reduced concentrations of key fatty acids. DNA profiling revealed shrimp harbor a resident gut microbiome distinct from the environment, which is relatively simple and stable across space (including habitats with different microbial communities) and time (between wild‐caught individuals and those maintained in the laboratory for >2 yr). DNA profiling also suggests shrimp grazing alters environmental microbial community composition, possibly through selective consumption and/or physical interactions. While this work suggests grazing by endemic shrimp plays a key role in shaping microbial communities in the Hawaiian anchialine ecosystem, the hypothesized drastic ecological shifts resulting from invasive fishes may be an oversimplification as shrimp may largely avoid predation. Moreover, environmental microbial communities may have little influence on shrimp gut microbiomes.

Shifts in root dynamics along a hillslope in a mixed, mesic temperate forest - Edward J. Primka; Thomas S. Adams; Alexandra S. Buck; David M. Eissenstat (Plant and Soil, 2022)

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Sustainable development outcomes of livelihood diversification in small‐scale fisheries - Matthew B. Roscher; Edward H. Allison; David J. Mills; Hampus Eriksson; Denis Hellebrandt; Neil L. Andrew (Fish and Fisheries, 2022)
Livelihood diversification is increasingly central to policy advice and investments in rural development and fisheries management. For small‐scale fishing communities in low‐ to middle‐income countries, more diverse livelihoods are generally hypothesized to reduce fishing pressure and vulnerabilities to external shocks and adverse trends while enabling people to construct routes out of poverty. Yet, evidence of impacts from livelihood diversification in small‐scale fisheries remains sparse. Our examination of the peer‐reviewed literature found substantial differences in how livelihood diversification is pursued, and in the realized outcomes from the process of diversification. Studies describing diversified livelihoods were almost as likely to report that livelihoods were not improved or that outcomes were mixed (54% combined) as they were to report improved livelihood outcomes (45%). Furthermore, one of the main theoretical drivers behind the support for diversified livelihoods—ecological conservation benefits—was unexplored in over 70% of studies. Of the minority of studies that did explore ecological outcomes, most reported that ecological conditions had not improved. These findings indicate conceptual ambiguity around livelihood diversification and a lack of empirical evidence supporting its theoretical underpinnings. There remain important questions about the impacts of diversification on multidimensional poverty and ecological conservation. Future research on and investment in diversification should be both more deliberate of what diversification means and more rigorous in the evaluation of its impacts.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Neck Loads During Head-First Entries into Trampoline Dismount Foam Pits: Considerations for Trampoline Park Safety - Tom Whyte; Edward Lind; Adam Richards; David Eager; Lynne E. Bilston; Julie Brown (Annals of Biomedical Engineering, 2022)
Serious cervical spine injuries have been documented from falls into foam pits at trampoline parks. To address the lack of evidence on how foam pits should be designed for mitigating neck injury risk, this study aimed to quantify neck loads during head-first entry into varying foam pit designs. An instrumented Hybrid III anthropomorphic test device was dropped head-first from a height of up to 1.5 m into three differently constructed foam pits, each using a different mechanism to prevent direct contact between the falling person and the floor (foam slab, trampoline or net bed). Measured neck loads were compared to published injury reference values. In the simplest, foam-only pit design, increasing foam depth tended to reduce peak compressive force. At least one injury assessment reference metric was exceeded in all pit conditions tested for 1.5 m falls, most commonly the time-dependent neck compression criterion. The results highlight the importance of adequate foam depth in combination with appropriate pit design in minimizing injury risk. The risk of cervical spine injury may not be reduced sufficiently with current foam pit designs.

High‐resolution water‐quality and ecosystem‐metabolism modeling in lowland rivers - Devanshi Pathak; Michael Hutchins; Lee E. Brown; Matthew Loewenthal; Peter Scarlett; Linda Armstrong; David Nicholls; Mike Bowes; François Edwards; Gareth Old (Limnology and Oceanography, 2022)
High‐resolution monitoring of water quality and ecosystem functioning over large spatial scales in expansive lowland river catchments is challenging. Therefore, we need modeling tools to predict these processes at locations where observations are absent. Here, we present a new approach to estimate ecosystem metabolism underpinned by a high‐resolution, process‐based model of in‐stream flows and water quality. The model overcomes the current challenges in metabolism modeling by accounting for oxygen transport under varying flows and oxygen transformations due to biogeochemical processes. We implement the model in a 62‐km‐long stretch of the River Thames, England, using observations spanning 2 yr. Model outputs suggest that the river is primarily autotrophic from mid‐spring to mid‐summer due to high biomass during low‐flow periods, and is heterotrophic during the rest of the year. Ecosystem respiration in upstream reaches is driven mainly by biochemical oxygen demand, autotrophic respiration, and nitrification processes, whereas downstream sites also show a control of benthic oxygen demand in addition to the aforementioned processes. Using empirical modeling, we analyze the sensitivity of our estimated metabolism rates to multiple environmental stressors. Results demonstrate that empirical models could be useful for rapid river health assessments, but need improvements to reproduce peak metabolism rates. The process‐based model, although more complex than existing in situ approaches to metabolism quantification, allows inference when gaps in continuous observations are present. The model offers additional benefits for predicting metabolism rates under future scenarios of environmental change incorporating multiple stressor effects.

The North American Freshwater Migratory Fish Database ( NAFMFD ): Characterizing the migratory life histories of freshwater fishes of Canada, the United States and Mexico - Emily M. Dean; Arthur R. Cooper; Lizhu Wang; Wesley Daniel; Solomon David; Clayton Ernzen; Keith B. Gido; Edward Hale; Tim J. Haxton; William Kelso; Nancy Leonard; Chris Lido; et al. (Journal of Biogeography, 2022)
Aim Migratory freshwater fishes are those that must access discrete habitats to complete their life cycles. Freshwater fish migrations occur around the world and provide numerous ecosystem services for humans and natural systems; however, many migratory species are in decline globally. A limiting factor to successfully conserve freshwater migratory fishes is that the migratory life histories of many species are unknown or only partially described. To provide researchers with critical and comprehensive information to conserve migratory fishes, we developed the North American Freshwater Migratory Fish Database (NAFMFD). Location Canada, Mexico and the United States. Taxon Freshwater fish. Methods To develop this database, we assigned migratory status, pattern and behaviour to a comprehensive list of freshwater fish species found throughout North America. We assembled the database which included assignments (i.e. migratory status, pattern and behaviour) as well as the sources used to make the assignments. Researchers and managers from across North America reviewed the database for completeness and accuracy on the migratory life histories of fishes. Results The database synthesizes current knowledge of migratory status, pattern and behaviour of native and non‐native freshwater fishes throughout North America, including 1250 species representing 79 families and 325 genera. Results showcase the diversity of migratory life histories of freshwater fishes on the continent, including that at least 25% of North American freshwater fishes are migratory, 23% are non‐migratory and 44% have undetermined migratory status. Main conclusions NAFMFD improves the quality of migratory data accessible to researchers, which supports a more holistic understanding of the threats encountered by migratory fishes, including habitat fragmentation. The approach we used in developing NAFMFD can provide guidance for developing similar databases in other regions. Collectively, our work offers new insights into the range of freshwater fish migratory life histories, stimulating a need to better understand this diversity globally.

Planning Waterways for Added Value: Joint Research by PIANC and IWI - Arjan de Heer; Nicki Schiessel Harvey; David Edwards-May (WASSERWIRTSCHAFT, 2022)

Haplotype mapping uncovers unexplored variation in wild and domesticated soybean at the major protein locus cqProt-003 - Jacob I. Marsh; Haifei Hu; Jakob Petereit; Philipp E. Bayer; Babu Valliyodan; Jacqueline Batley; Henry T. Nguyen; David Edwards (Theoretical and Applied Genetics, 2022)
Key message The major soy protein QTL, cqProt-003, was analysed for haplotype diversity and global distribution, and results indicate 304 bp deletion and variable tandem repeats in protein coding regions are likely causal candidates. Abstract Here, we present association and linkage analysis of 985 wild, landrace and cultivar soybean accessions in a pan genomic dataset to characterize the major high-protein/low-oil associated locus cqProt-003 located on chromosome 20. A significant trait-associated region within a 173 kb linkage block was identified, and variants in the region were characterized, identifying 34 high confidence SNPs, 4 insertions, 1 deletion and a larger 304 bp structural variant in the high-protein haplotype. Trinucleotide tandem repeats of variable length present in the second exon of gene Glyma.20G085100 are strongly correlated with the high-protein phenotype and likely represent causal variation. Structural variation has previously been found in the same gene, for which we report the global distribution of the 304 bp deletion and have identified additional nested variation present in high-protein individuals. Mapping variation at the cqProt-003 locus across demographic groups suggests that the high-protein haplotype is common in wild accessions (94.7%), rare in landraces (10.6%) and near absent in cultivated breeding pools (4.1%), suggesting its decrease in frequency primarily correlates with domestication and continued during subsequent improvement. However, the variation that has persisted in under-utilized wild and landrace populations holds high breeding potential for breeders willing to forego seed oil to maximize protein content. The results of this study include the identification of distinct haplotype structures within the high-protein population, and a broad characterization of the genomic context and linkage patterns of cqProt-003 across global populations, supporting future functional characterization and modification.

Pasteurella species bloodstream infections in Queensland, Australia, 2000–2019 - Kevin B. Laupland; Adam G. Stewart; Felicity Edwards; Patrick Harris; Claire Heney; Narelle George; Sonali Coulter; David L. Paterson (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
Pasteurella species are infrequent but potentially severe causes of bloodstream infection (BSI). The objective of this study was to determine the incidence, risk factors, and outcomes of Pasteurella species BSI in a large Australian population. Retrospective, laboratory-based surveillance was conducted in Queensland, Australia (population ≈ 5 million) during 2000–2019, and clinical and outcome information was established by linkage to state hospital admissions and vital statistics databases. During more than 86 million person-years of surveillance, 272 incident Pasteurella species BSI occurred for an overall age- and sex-standardized annual incidence of 3.3 per million residents. The incidence of Pasteurella species BSI was highest in recent years and older individuals were at greatest risk. The median (interquartile range) Charlson Comorbidity Index was 2 (0–4) with scores of zero, 1, 2, and 3 + observed in 81 (30%), 37 (14%), 44 (16%), and 110 (40%) of cases. The 30-day all-cause case fatality was 9% (24/272) and patients who died had more comorbidities and were less likely to have community-associated disease. Although Pasteurella species are infrequent causes of BSI, older individuals and those with comorbidities are at highest risk. The burden of this disease may be expected to increase with an aging and more comorbid population.

Soil protist function varies with elevation in the Swiss Alps - Florent Mazel; Lucie Malard; Hélène Niculita‐Hirzel; Erika Yashiro; Heidi K. Mod; Edward A. D. Mitchell; David Singer; Aline Buri; Eric Pinto; Nicolas Guex; Enrique Lara; Antoine Guisan (Environmental Microbiology, 2022)
Summary Protists are abundant and play key trophic functions in soil. Documenting how their trophic contributions vary across large environmental gradients is essential to understand and predict how biogeochemical cycles will be impacted by global changes. Here, using amplicon sequencing of environmental DNA in open habitat soil from 161 locations spanning 2600 m of elevation in the Swiss Alps (from 400 to 3000 m), we found that, over the whole study area, soils are dominated by consumers, followed by parasites and phototrophs. In contrast, the proportion of these groups in local communities shows large variations in relation to elevation. While there is, on average, three times more consumers than parasites at low elevation (400–1000 m), this ratio increases to 12 at high elevation (2000–3000 m). This suggests that the decrease in protist host biomass and diversity toward mountains tops impact protist functional composition. Furthermore, the taxonomic composition of protists that infect animals was related to elevation while that of protists that infect plants or of protist consumers was related to soil pH. This study provides a first step to document and understand how soil protist functions vary along the elevational gradient.

Low occurrence of multi‐antimicrobial and heavy metal resistance in Salmonella enterica from wild birds in the United States - Yezhi Fu; Nkuchia M. M'ikanatha; Chris A. Whitehouse; Heather Tate; Andrea Ottesen; Jeffrey M. Lorch; David S. Blehert; Brenda Berlowski‐Zier; Edward G. Dudley (Environmental Microbiology, 2022)
Summary Wild birds are common reservoirs of Salmonella enterica . Wild birds carrying resistant S . enterica may pose a risk to public health as they can spread the resistant bacteria across large spatial scales within a short time. Here, we whole‐genome sequenced 375 S . enterica strains from wild birds collected in 41 U.S. states during 1978–2019 to examine bacterial resistance to antibiotics and heavy metals. We found that Typhimurium was the dominant S . enterica serovar, accounting for 68.3% (256/375) of the bird isolates. Furthermore, the proportions of the isolates identified as multi‐antimicrobial resistant (multi‐AMR: resistant to at least three antimicrobial classes) or multi‐heavy metal resistant (multi‐HMR: resistant to at least three heavy metals) were both 1.87% (7/375). Interestingly, all the multi‐resistant S . enterica ( n = 12) were isolated from water birds or raptors; none of them was isolated from songbirds. Plasmid profiling demonstrated that 75% (9/12) of the multi‐resistant strains carried resistance plasmids. Our study indicates that wild birds do not serve as important reservoirs of multi‐resistant S . enterica strains. Nonetheless, continuous surveillance for bacterial resistance in wild birds is necessary because the multi‐resistant isolates identified in this study also showed close genetic relatedness with those from humans and domestic animals.

Global biogeographic patterns of avian morphological diversity - Emma C. Hughes; David P. Edwards; Jen A. Bright; Elliot J.R. Capp; Christopher R. Cooney; Zoë K. Varley; Gavin H. Thomas (Ecology Letters, 2022)
Understanding the biogeographical patterns, and evolutionary and environmental drivers, underpinning morphological diversity are key for determining its origins and conservation. Using a comprehensive set of continuous morphological traits extracted from museum collections of 8353 bird species, including geometric morphometric beak shape data, we find that avian morphological diversity is unevenly distributed globally, even after controlling for species richness, with exceptionally dense packing of species in hyper‐diverse tropical hotspots. At the regional level, these areas also have high morphological variance, with species exhibiting high phenotypic diversity. Evolutionary history likely plays a key role in shaping these patterns, with evolutionarily old species contributing to niche expansion, and young species contributing to niche packing. Taken together, these results imply that the tropics are both ‘cradles’ and ‘museums’ of phenotypic diversity.

Alcohol intake and risk of pituitary adenoma - David J. Cote; Timothy R. Smith; Ursula B. Kaiser; Edward R. Laws; Meir J. Stampfer (Cancer Causes & Control, 2022)

Quantifying Mesophotic Fish Assemblages of Hawai‘i’s Au‘au Channel: Associations With Benthic Habitats and Depth - Raymond C. Boland; K. David Hyrenbach; Edward E. DeMartini; Frank A. Parrish; John J. Rooney (Frontiers in Marine Science, 2022)
Mesophotic reefs (30–150 m) occur in the tropics and subtropics at depths beyond most scientific diving, thereby making conventional surveys challenging. Towed cameras, submersibles, and mixed-gas divers were used to survey the mesophotic reef fish assemblages and benthic substrates of the Au‘au Channel, between the Hawaiian Islands of Maui and Lāna‘i. Non-parametric multivariate analysis: Non-metric Multidimensional Scaling (NMDS), Hierarchical Cluster Analysis (HCA), Multi-Response Permutation Procedure (MRPP), and Indicator Species Analysis (ISA) were used to determine the association of mesophotic reef fish species with benthic substrates and depth. Between 53 and 115-m depths, 82 species and 10 genera of fish were observed together with 10 types of benthic substrate. Eight species of fish ( Apolemichthys arcuatus , Centropyge potteri, Chaetodon kleinii, Chromis leucura, Chromis verater, Forcipiger sp., Naso hexacanthus , and Parupeneus multifasciatus ) were positively associated with increasing depth, Leptoseris sp. coral cover, and hard-bottom cover, and one species ( Oxycheilinus bimaculatus ) of fish was positively associated with increasing Halimeda sp. algae cover. Fish assemblages associated with rubble were not significantly different from those associated with sand, Montipora coral beds and Leptoseris coral beds, but were distinct from fish assemblages associated with hard bottom. The patterns in the data suggested two depth assemblages, one “upper mesophotic” between 53 and 95 m and the other deeper, possibly part of a “lower mesophotic” assemblage between 96 and 115 m at the edge of the rariphotic and bottomfish complex.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Passive-Sampler-Based Bioavailability Assessment of PCB Congeners Associated with Aroclor-Containing Paint Chips in the Presence of Sediment - Guilherme R. Lotufo; Philip T. Gidley; Andrew D. McQueen; David W. Moore; Deborah A. Edwards; Jeffery Hardenstine; Allen D. Uhler (Archives of Environmental Contamination and Toxicology, 2022)
This is the first investigation of the bioavailability of PCBs associated with paint chips (PC) dispersed in sediment. Bioavailability of PCB-containing PC in sediment was measured using ex situ polyethylene passive samplers (PS) and compared to that of PCBs from field-collected sediments. PC were mixed in freshwater sediment from a relatively uncontaminated site with no known PCB contamination sources and from a contaminated site with non-paint PCB sources. PC

Stratification strength and light climate explain variation in chlorophyll a at the continental scale in a European multilake survey in a heatwave summer - Daphne Donis; Evanthia Mantzouki; Daniel F. McGinnis; Dominic Vachon; Irene Gallego; Hans‐Peter Grossart; Lisette N. de Senerpont Domis; Sven Teurlincx; Laura Seelen; Miquel Lürling; Yvon Verstijnen; Valentini Maliaka; et al. (Limnology and Oceanography, 2021)
To determine the drivers of phytoplankton biomass, we collected standardized morphometric, physical, and biological data in 230 lakes across the Mediterranean, Continental, and Boreal climatic zones of the European continent. Multilinear regression models tested on this snapshot of mostly eutrophic lakes (median total phosphorus [TP] = 0.06 and total nitrogen [TN] = 0.7 mg L −1 ), and its subsets (2 depth types and 3 climatic zones), show that light climate and stratification strength were the most significant explanatory variables for chlorophyll a (Chl a ) variance. TN was a significant predictor for phytoplankton biomass for shallow and continental lakes, while TP never appeared as an explanatory variable, suggesting that under high TP, light, which partially controls stratification strength, becomes limiting for phytoplankton development. Mediterranean lakes were the warmest yet most weakly stratified and had significantly less Chl a than Boreal lakes, where the temperature anomaly from the long‐term average, during a summer heatwave was the highest (+4°C) and showed a significant, exponential relationship with stratification strength. This European survey represents a summer snapshot of phytoplankton biomass and its drivers, and lends support that light and stratification metrics, which are both affected by climate change, are better predictors for phytoplankton biomass in nutrient‐rich lakes than nutrient concentrations and surface temperature.

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Mean sea level and tidal change in Ireland since 1842: a case study of Cork - David T. Pugh; Edmund Bridge; Robin Edwards; Peter Hogarth; Guy Westbrook; Philip L. Woodworth; Gerard D. McCarthy (Ocean Science, 2021)
Knowledge of regional changes in mean sea level and local changes in tides are crucial to inform effective climate adaptation. An essential element is the availability of accurate observations of sea level. Sea level data in the Republic of Ireland, prior to the establishment of the National Tide Gauge Network in the mid-2000s, are limited but belie a wealth of historical data available in archival form. In this study, we digitize records located in Cork Harbour, Ireland, from 1842 and show how short-duration (6–8 weeks), high-quality data with a large interval to the present can accurately inform tidal and mean sea level changes. We consider error sources in detail. We estimate for the main M2 tidal constituent that the accuracy of these historical measurements is 1 % and 2 min for amplitude and phase, respectively, once adjustments for seasonal and nodal effects are made. Our mean sea level estimates are accurate to the 2 cm level, once adjustments for atmospheric and seasonal effects are made. Our results show tidal stability with a 2 % change in the amplitude of the M2 component, 4 min change in the phase over a period of 177 years, and mean sea level rise of 40 cm in the Cork Harbour area from 1842 to 2019, approximately in line with global mean sea level trends plus local glacial isostatic adjustment. More broadly, we show that with careful seasonal, nodal, and atmospheric corrections, together with knowledge of benchmark provenance, these historic, survey-oriented data can accurately inform of sea level changes.

Bacterial Viruses Subcommittee and Archaeal Viruses Subcommittee of the ICTV: update of taxonomy changes in 2021 - Mart Krupovic; Dann Turner; Vera Morozova; Mike Dyall-Smith; Hanna M. Oksanen; Rob Edwards; Bas E. Dutilh; Susan M. Lehman; Alejandro Reyes; Diana P. Baquero; Matthew B. Sullivan; Jumpei Uchiyama; et al. (Archives of Virology, 2021)
In this article, we – the Bacterial Viruses Subcommittee and the Archaeal Viruses Subcommittee of the International Committee on Taxonomy of Viruses (ICTV) – summarise the results of our activities for the period March 2020 – March 2021. We report the division of the former Bacterial and Archaeal Viruses Subcommittee in two separate Subcommittees, welcome new members, a new Subcommittee Chair and Vice Chair, and give an overview of the new taxa that were proposed in 2020, approved by the Executive Committee and ratified by vote in 2021. In particular, a new realm, three orders, 15 families, 31 subfamilies, 734 genera and 1845 species were newly created or redefined (moved/promoted).

Environmental change during the last glacial on an ancient land bridge of southeast Australia - Matthew Adesanya Adeleye; Simon Graeme Haberle; David McWethy; Simon Edward Connor; Janelle Stevenson (Journal of Biogeography, 2021)
Aim The Last Glacial Maximum (LGM) remains an enigmatic period in southeast Australia due to the limited spatial and temporal resolution of its palaeoclimatic records. A major feature of the LGM landscape was the existence of the Bassian Land Bridge, joining Tasmania with the mainland of Australia during periods of low sea level, and potentially facilitating increased biotic movement between these regions. To better understand biogeographical changes on the land bridge and in southeast Australia generally during the LGM, we present a 35 ka‐year palaeoecological record from one of the larger islands of Bass Strait. Location Bass Strait, southeast Australia. Taxon Eucalyptus , Poaceae, Monotoca , Myriophyllum , Zygnemataceae, Botryococcus , Pediastrum . Methods Pollen, charcoal, and non‐pollen palynomorphs were analysed in a 1.75‐m sediment core from truwana/Cape Barren Island, Bass Strait, to reconstruct changes in vegetation, fire regimes and lake levels on the Bassian Land Bridge. Results were then compared to existing palaeoenvironmental studies in the region to develop a broader context of the prevailing land bridge environment and the potential influence on biotic dispersals in Australia during the last glacial period. Results Results suggest a major vegetation shift on the Bassian Land Bridge in response to the establishment of the LGM climate, with grassland expansion at the expense of woodland from ~29–11 ka. Floristic richness, biomass burned and lake levels also markedly decreased through this period, with the driest interval being ~25–18 ka. Dryland herbaceous taxa dispersed between the mainland and Tasmania when the landbridge was fully exposed. Main conclusions In agreement with previous studies, our results show that the dry grassland that dominated southeast Australia (and Southern Hemisphere mid‐latitude areas) during the LGM also extended across the Bassian Land Bridge. The prevailing environment on the land bridge is likely to have exerted a selective influence on biotic dispersals in Australia during glacial periods.

Status and advances in mining for blackleg (Leptosphaeria maculans) quantitative resistance (QR) in oilseed rape (Brassica napus) - Junrey Amas; Robyn Anderson; David Edwards; Wallace Cowling; Jacqueline Batley (Theoretical and Applied Genetics, 2021)
Key message Quantitative resistance (QR) loci discovered through genetic and genomic analyses are abundant in the Brassica napus genome, providing an opportunity for their utilization in enhancing blackleg resistance. Abstract Quantitative resistance (QR) has long been utilized to manage blackleg in Brassica napus (canola, oilseed rape), even before major resistance genes (R-genes) were extensively explored in breeding programmes. In contrast to R-gene-mediated qualitative resistance, QR reduces blackleg symptoms rather than completely eliminating the disease. As a polygenic trait, QR is controlled by numerous genes with modest effects, which exerts less pressure on the pathogen to evolve; hence, its effectiveness is more durable compared to R-gene-mediated resistance. Furthermore, combining QR with major R-genes has been shown to enhance resistance against diseases in important crops, including oilseed rape. For these reasons, there has been a renewed interest among breeders in utilizing QR in crop improvement. However, the mechanisms governing QR are largely unknown, limiting its deployment. Advances in genomics are facilitating the dissection of the genetic and molecular underpinnings of QR, resulting in the discovery of several loci and genes that can be potentially deployed to enhance blackleg resistance. Here, we summarize the efforts undertaken to identify blackleg QR loci in oilseed rape using linkage and association analysis. We update the knowledge on the possible mechanisms governing QR and the advances in searching for the underlying genes. Lastly, we lay out strategies to accelerate the genetic improvement of blackleg QR in oilseed rape using improved phenotyping approaches and genomic prediction tools.

Phylogeography of the wide‐host range panglobal plant pathogen Phytophthora cinnamomi - Shankar K. Shakya; Niklaus J. Grünwald; Valerie J. Fieland; Brian J. Knaus; Jerry E. Weiland; Cristiana Maia; André Drenth; David I. Guest; Edward C.Y. Liew; Colin Crane; Tun‐Tschu Chang; Chuen‐Hsu Fu; et al. (Molecular Ecology, 2021)
Various hypotheses have been proposed regarding the origin of the plant pathogen Phytophthora cinnamomi . P . cinnamomi is a devastating, highly invasive soilborne pathogen associated with epidemics of agricultural, horticultural and forest plantations and native ecosystems worldwide. We conducted a phylogeographic analysis of populations of this pathogen sampled in Asia, Australia, Europe, southern and northern Africa, South America, and North America. Based on genotyping‐by‐sequencing, we observed the highest genotypic diversity in Taiwan and Vietnam, followed by Australia and South Africa. Mating type ratios were in equal proportions in Asia as expected for a sexual population. Simulations based on the index of association suggest a partially sexual, semi‐clonal mode of reproduction for the Taiwanese and Vietnamese populations while populations outside of Asia are clonal. Ancestral area reconstruction provides new evidence supporting Taiwan as the ancestral area, given our sample, indicating that this region might be near or at the centre of origin for this pathogen as speculated previously. The Australian and South African populations appear to be a secondary centre of diversity following migration from Taiwan or Vietnam. Our work also identified two panglobal, clonal lineages PcG1‐A2 and PcG2‐A2 of A2 mating type found on all continents. Further surveys of natural forests across Southeast Asia are needed to definitively locate the actual centre of origin of this important plant pathogen.

The dangers of misrepresenting wildlife trade: response to Natusch et al. 2021 - David P. Edwards; Neil D'Cruze; Sandra Altherr; Alice Hughes; Jordi Janssen; Vincent Nijman; Stesha A. Pasachnik; Brett R. Scheffers; Chris R. Shepherd; Emerson Sy; Mark Auliya (Conservation Biology, 2021)

Cystic fibrosis improves COVID-19 survival and provides clues for treatment of SARS-CoV-2 - Edward H. Abraham; Guido Guidotti; Eliezer Rapaport; David Bower; Jack Brown; Robert J. Griffin; Andrew Donnelly; Ellen D. Waitzkin; Kenon Qamar; Mark A. Thompson; Sukumar Ethirajan; Kent Robinson (Purinergic Signalling, 2021)
Systemic pools of ATP are elevated in individuals homozygous for cystic fibrosis (CF) as evidenced by elevated blood and plasma ATP levels. This elevated ATP level seems to provide benefit in the presence of advanced solid tumors (Abraham et al., Nature Medicine 2(5):593–596, 1996). We published in this journal a paper showing that IV ATP can elevate the depleted ATP pools of advanced cancer patients up to levels found in CF patients with subsequent clinical, biochemical, and quality of life (QOL) improvements (Rapaport et al., Purinergic Signalling 11(2): 251–262, 2015). We hypothesize that the elevated ATP levels seen in CF patients may be benefiting CF patients in another way: by improving their survival after contracting COVID-19. We discuss here the reasoning behind this hypothesis and suggest how these findings might be applied clinically in the general population.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Genotype–Environment mismatch of kelp forests under climate change - Sofie Vranken; Thomas Wernberg; Armin Scheben; Anita Alice Severn‐Ellis; Jacqueline Batley; Philipp Emanuel Bayer; David Edwards; David Wheeler; Melinda Ann Coleman (Molecular Ecology, 2021)
Climate change is increasingly impacting ecosystems globally. Understanding adaptive genetic diversity and whether it will keep pace with projected climatic change is necessary to assess species’ vulnerability and design efficient mitigation strategies such as assisted adaptation. Kelp forests are the foundations of temperate reefs globally but are declining in many regions due to climate stress. A lack of knowledge of kelp's adaptive genetic diversity hinders assessment of vulnerability under extant and future climates. Using 4245 single nucleotide polymorphisms (SNPs), we characterized patterns of neutral and putative adaptive genetic diversity for the dominant kelp in the southern hemisphere ( Ecklonia radiata ) from ~1000 km of coastline off Western Australia. Strong population structure and isolation‐by‐distance was underpinned by significant signatures of selection related to temperature and light. Gradient forest analysis of temperature‐linked SNPs under selection revealed a strong association with mean annual temperature range, suggesting adaptation to local thermal environments. Critically, modelling revealed that predicted climate‐mediated temperature changes will probably result in high genomic vulnerability via a mismatch between current and future predicted genotype–environment relationships such that kelp forests off Western Australia will need to significantly adapt to keep pace with projected climate change. Proactive management techniques such as assisted adaptation to boost resilience may be required to secure the future of these kelp forests and the immense ecological and economic values they support.

Candidate Rlm6 resistance genes against Leptosphaeria. maculans identified through a genome-wide association study in Brassica juncea (L.) Czern - Hua Yang; Nur Shuhadah Mohd Saad; Muhammad Ishaq Ibrahim; Philipp E. Bayer; Ting Xiang Neik; Anita A. Severn-Ellis; Aneeta Pradhan; Soodeh Tirnaz; David Edwards; Jacqueline Batley (Theoretical and Applied Genetics, 2021)

High Genetic Addiction Risk Score (GARS) in Chronically Prescribed Severe Chronic Opioid Probands Attending Multi-pain Clinics: an Open Clinical Pilot Trial - Mark Moran; Kenneth Blum; Jessica Valdez Ponce; Lisa Lott; Marjorie C. Gondré–Lewis; Sampada Badgaiyan; Raymond Brewer; B. William Downs; Philip Fynman; Alexander Weingarten; Jean Lud Cadet; David E. Smith; et al. (Molecular Neurobiology, 2021)
Millions of Americans experience pain daily. In 2017, opioid overdose claimed 64,000 lives increasing to 84,000 lives in 2020, resulting in a decrease in national life expectancy. Chronic opioid use results in dependency, drug tolerance, neuroadaptation, hyperalgesia, potential addictive behaviors, or Reward Deficiency Syndrome (RDS) caused by a hypodopaminergia. Evaluation of pain clinic patients with the Genetic Addiction Risk Score (GARS) test and the Addiction Severity Index (ASI- Media Version V) revealed that GARS scores equal to or greater than 4 and 7 alleles significantly predicted drug and alcohol severity, respectively. We utilized RT-PCR for SNP genotyping and multiplex PCR/capillary electrophoresis for fragment analysis of the role of eleven alleles in a ten-reward gene panel, reflecting the activity of brain reward circuitry in 121 chronic opioid users. The study consisted of 55 males and 66 females averaging ages 54 and 53 years of age, respectively. The patients included Caucasians, African Americans, Hispanics, and Asians. Inclusion criteria mandated that the Morphine Milligram Equivalent (MME) was 30–600 mg/day (males) and 20 to 180 mg/day (females) for treatment of chronic pain over 12 months. Ninety-six percent carried four or more risk alleles, and 73% carried seven or more risk alleles, suggesting a high predictive risk for opioid and alcohol dependence, respectively. These data indicate that chronic, legally prescribed opioid users attending a pain clinic possess high genetic risk for drug and alcohol addiction. Early identification of genetic risk, using the GARS test upon entry to treatment, may prevent iatrogenic induced opioid dependence.

Assessment of the efficacy of six field cleaning protocols for hydrocarbon quantification - Emily C. Pisarski; Edward F. Wirth; Paul L. Pennington; Ian Hartwell; Brian S. Shaddrix; David R. Whitall; Dennis A. Apeti; Gregory Baker (Environmental Science and Pollution Research, 2021)

Recent progress on combining geomorphological and geochronological data with ice sheet modelling, demonstrated using the last British–Irish Ice Sheet - Jeremy C. Ely; Chris D. Clark; Richard C. A. Hindmarsh; Anna L. C. Hughes; Sarah L. Greenwood; Sarah L. Bradley; Edward Gasson; Lauren Gregoire; Niall Gandy; Chris R. Stokes; David Small (Journal of Quaternary Science, 2021)
Palaeo‐ice sheets are important analogues for understanding contemporary ice sheets, offering a record of ice sheet behaviour that spans millennia. There are two main approaches to reconstructing palaeo‐ice sheets. Empirical reconstructions use the available glacial geological and chronological evidence to estimate ice sheet extent and dynamics but lack direct consideration of ice physics. In contrast, numerically modelled simulations implement ice physics, but often lack direct quantitative comparison with empirical evidence. Despite being long identified as a fruitful scientific endeavour, few ice sheet reconstructions attempt to reconcile the empirical and model‐based approaches. To achieve this goal, model‐data comparison procedures are required. Here, we compare three numerically modelled simulations of the former British–Irish Ice Sheet with the following lines of evidence: (a) position and shape of former margin positions, recorded by moraines; (b) former ice‐flow direction and flow‐switching, recorded by flowsets of subglacial bedforms; and (c) the timing of ice‐free conditions, recorded by geochronological data. These model–data comparisons provide a useful framework for quantifying the degree of fit between numerical model simulations and empirical constraints. Such tools are vital for reconciling numerical modelling and empirical evidence, the combination of which will lead to more robust palaeo‐ice sheet reconstructions with greater explicative and ultimately predictive power.

Spatio‐temporal insights into microbiology of the freshwater‐to‐hypersaline, oxic‐hypoxic‐euxinic waters of Ursu Lake - Andreea Baricz; Cecilia Maria Chiriac; Adrian‐Ștefan Andrei; Paul‐Adrian Bulzu; Erika Andrea Levei; Oana Cadar; Karina Paula Battes; Mirela Cîmpean; Marin Șenilă; Adorján Cristea; Vasile Muntean; Mircea Alexe; et al. (Environmental Microbiology, 2021)
Summary Ursu Lake is located in the Middle Miocene salt deposit of Central Romania. It is stratified, and the water column has three distinct water masses: an upper freshwater‐to‐moderately saline stratum (0–3 m), an intermediate stratum exhibiting a steep halocline (3–3.5 m), and a lower hypersaline stratum (4 m and below) that is euxinic (i.e. anoxic and sulphidic). Recent studies have characterized the lake's microbial taxonomy and given rise to intriguing ecological questions. Here, we explore whether the communities are dynamic or stable in relation to taxonomic composition, geochemistry, biophysics, and ecophysiological functions during the annual cycle. We found: (i) seasonally fluctuating, light‐dependent communities in the upper layer (≥0.987–0.990 water‐activity), a stable but phylogenetically diverse population of heterotrophs in the hypersaline stratum (water activities down to 0.762) and a persistent plate of green sulphur bacteria that connects these two (0.958–0.956 water activity) at 3–3.5 to 4 m; (ii) communities that might be involved in carbon‐ and sulphur‐cycling between and within the lake's three main water masses; (iii) uncultured lineages including Acetothermia (OP1), Cloacimonetes (WWE1), Marinimicrobia (SAR406), Omnitrophicaeota (OP3), Parcubacteria (OD1) and other Candidate Phyla Radiation bacteria, and SR1 in the hypersaline stratum (likely involved in the anaerobic steps of carbon‐ and sulphur‐cycling); and (iv) that species richness and habitat stability are associated with high redox‐potentials. Ursu Lake has a unique and complex ecology, at the same time exhibiting dynamic fluctuations and stability, and can be used as a modern analogue for ancient euxinic water bodies and comparator system for other stratified hypersaline systems.

Crop breeding for a changing climate: integrating phenomics and genomics with bioinformatics - Jacob I. Marsh; Haifei Hu; Mitchell Gill; Jacqueline Batley; David Edwards (Theoretical and Applied Genetics, 2021)

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

The Path to an Ecosystem Approach for Forage Fish Management: A Case Study of Atlantic Menhaden - Kristen A. Anstead; Katie Drew; David Chagaris; Amy M. Schueller; Jason E. McNamee; Andre Buchheister; Geneviève Nesslage; Jim H. Uphoff Jr.; Michael J. Wilberg; Alexei Sharov; Micah J. Dean; Jeffrey Brust; et al. (Frontiers in Marine Science, 2021)
Atlantic menhaden ( Brevoortia tyrannus ) support the largest fishery by volume on the United States East Coast, while also playing an important role as a forage species. Managers’ and stakeholders’ increasing concerns about the impact of Atlantic menhaden harvest on ecosystem processes led to an evolution in the assessment and management of this species from a purely single-species approach to an ecosystem approach. The first coastwide stock assessment of Atlantic menhaden for management used a single-species virtual population analysis (VPA). Subsequent assessments used a forward projecting statistical catch-at-age framework that incorporated estimates of predation mortality from a multispecies VPA while analytical efforts continued toward the development of ecosystem models and explicit ecological reference points (ERPs) for Atlantic menhaden. As an interim step while ecosystem models were being developed, a series of ad hoc measures to preserve Atlantic menhaden biomass for predators were used by managers. In August 2020, the Atlantic States Marine Fisheries Commission formally adopted an ecological modeling framework as a tool to set reference points and harvest limits for the Atlantic menhaden that considers their role as a forage fish. This is the first example of a quantitative ecosystem approach to setting reference points on the United States Atlantic Coast and it represents a significant advance for forage fish management. This case study reviews the history of Atlantic menhaden stock assessments and management, outlines the progress on the current implementation of ERPs for this species, and highlights future research and management needs to improve and expand ecosystem-based fisheries management.

Upland burning and grazing as strategies to offset climate-change effects on wetlands - Owen P. McKenna; David A. Renton; David M. Mushet; Edward S. DeKeyser (Wetlands Ecology and Management, 2021)
Wetland ecosystems perform a multitude of services valued by society and provide critical habitat for migratory birds and other wildlife. Despite their importance, wetlands have been lost to different local, regional, and global drivers. Remaining wetlands are extremely sensitive to changing temperature and precipitation regimes. Management of grassland areas in wetland catchments may be an effective strategy for counteracting potentially negative impacts of climate change on wetlands. Our objective was to estimate the effects of climate changes on wetland hydrology, and to explore strategies for increasing surface-water inputs to wetlands. We coupled a field study with process-based simulation modeling of wetland-water levels. We found that climate change could decrease the number of wetlands that hold ponded water during the waterfowl breeding season by 14% under a hot wet scenario or 29% under a hot dry scenario if no upland-management actions were taken. Upland burning reduced pond losses to 9% (hot wet) and 26% (hot dry). Upland grazing resulted in the smallest loss of ponded wetlands, 6% loss under the hot-and-wet scenario and 22% loss under the hot-and-dry scenario. Overall, water inputs could be increased by either burning or grazing of upland vegetation thereby reducing pond losses during the waterfowl breeding season. While field results suggest that both grazing and burning can reduce the vegetative structure that could lead to increases in runoff in grassland catchments, our model simulations indicated that additional actions may be needed for managers to minimize future meteorologically driven water losses.

Changes in gastrointestinal cell integrity after marathon running and exercise-associated collapse - Edward Walter; Oliver R. Gibson; Michael Stacey; Neil Hill; Iain T. Parsons; David Woods (European Journal of Applied Physiology, 2021)

Impact of elevated core temperature on cognition in hot environments within a military context - Edward Tom Ashworth; James David Cotter; Andrew Edward Kilding (European Journal of Applied Physiology, 2021)

Tracing the origins of recent Queensland fruit fly incursions into South Australia, Tasmania and New Zealand - Ángel-David Popa-Báez; Siu Fai Lee; Heng Lin Yeap; Guy Westmore; Peter Crisp; Dongmei Li; Renee Catullo; Emilie C. Cameron; Owain R. Edwards; Phillip W. Taylor; John G. Oakeshott (Biological Invasions, 2021)

Animal‐borne video from a sea turtle reveals novel anti‐predator behaviors - Jenna L. Hounslow; Oliver J. D. Jewell; Sabrina Fossette; Scott Whiting; Anton D. Tucker; Anthony Richardson; David Edwards; Adrian C. Gleiss (Ecology, 2021)

The Essentials of Marine Biotechnology - Ana Rotter; Michéle Barbier; Francesco Bertoni; Atle M. Bones; M. Leonor Cancela; Jens Carlsson; Maria F. Carvalho; Marta Cegłowska; Jerónimo Chirivella-Martorell; Meltem Conk Dalay; Mercedes Cueto; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Coastal countries have traditionally relied on the existing marine resources (e.g., fishing, food, transport, recreation, and tourism) as well as tried to support new economic endeavors (ocean energy, desalination for water supply, and seabed mining). Modern societies and lifestyle resulted in an increased demand for dietary diversity, better health and well-being, new biomedicines, natural cosmeceuticals, environmental conservation, and sustainable energy sources. These societal needs stimulated the interest of researchers on the diverse and underexplored marine environments as promising and sustainable sources of biomolecules and biomass, and they are addressed by the emerging field of marine (blue) biotechnology. Blue biotechnology provides opportunities for a wide range of initiatives of commercial interest for the pharmaceutical, biomedical, cosmetic, nutraceutical, food, feed, agricultural, and related industries. This article synthesizes the essence, opportunities, responsibilities, and challenges encountered in marine biotechnology and outlines the attainment and valorization of directly derived or bio-inspired products from marine organisms. First, the concept of bioeconomy is introduced. Then, the diversity of marine bioresources including an overview of the most prominent marine organisms and their potential for biotechnological uses are described. This is followed by introducing methodologies for exploration of these resources and the main use case scenarios in energy, food and feed, agronomy, bioremediation and climate change, cosmeceuticals, bio-inspired materials, healthcare, and well-being sectors. The key aspects in the fields of legislation and funding are provided, with the emphasis on the importance of communication and stakeholder engagement at all levels of biotechnology development. Finally, vital overarching concepts, such as the quadruple helix and Responsible Research and Innovation principle are highlighted as important to follow within the marine biotechnology field. The authors of this review are collaborating under the European Commission-funded Cooperation in Science and Technology (COST) Action Ocean4Biotech – European transdisciplinary networking platform for marine biotechnology and focus the study on the European state of affairs.

Tropical land-use change alters trait-based community assembly rules for dung beetles and birds - Felicity A. Edwards; David P. Edwards; Keith C. Hamer; Tom M. Fayle (Oecologia, 2021)
Tropical rainforest disturbance and conversion are critical drivers of biodiversity loss. A key knowledge gap is understanding the impacts of habitat modification on mechanisms of community assembly, which are predicted to respond differently between taxa and across spatial scales. We use a null model approach to detect trait assembly of species at local- and landscape-scales, and then subdivide communities with different habitat associations and foraging guilds to investigate whether the detection of assembly mechanisms varies between groups. We focus on two indicator taxa, dung beetles and birds, across a disturbance gradient of primary rainforest, selectively logged rainforest, and oil palm plantations in Borneo, Southeast Asia. Random community assembly was predominant for dung beetles across habitats, whereas trait convergence, indicative of environmental filtering, occurred across the disturbance gradient for birds. Assembly patterns at the two spatial scales were similar. Subdividing for habitat association and foraging guild revealed patterns hidden when focusing on the overall community. Dung beetle forest specialists and habitat generalists showed opposing assembly mechanisms in primary forest, community assembly of habitat generalists for both taxa differed with disturbance intensity, and insectivorous birds strongly influenced overall community assembly relative to other guilds. Our study reveals the sensitivity of community assembly mechanisms to anthropogenic disturbance via a shift in the relative contribution of stochastic and deterministic processes. This highlights the need for greater understanding of how habitat modification alters species interactions and the importance of incorporating species’ traits within assessments.

An update of the Worldwide Integrated Assessment (WIA) on systemic insecticides. Part 2: impacts on organisms and ecosystems - Lennard Pisa; Dave Goulson; En-Cheng Yang; David Gibbons; Francisco Sánchez-Bayo; Edward Mitchell; Alexandre Aebi; Jeroen van der Sluijs; Chris J. K. MacQuarrie; Chiara Giorio; Elizabeth Yim Long; Melanie McField; et al. (Environmental Science and Pollution Research, 2021)
New information on the lethal and sublethal effects of neonicotinoids and fipronil on organisms is presented in this review, complementing the previous Worldwide Integrated Assessment (WIA) in 2015. The high toxicity of these systemic insecticides to invertebrates has been confirmed and expanded to include more species and compounds. Most of the recent research has focused on bees and the sublethal and ecological impacts these insecticides have on pollinators. Toxic effects on other invertebrate taxa also covered predatory and parasitoid natural enemies and aquatic arthropods. Little new information has been gathered on soil organisms. The impact on marine and coastal ecosystems is still largely uncharted. The chronic lethality of neonicotinoids to insects and crustaceans, and the strengthened evidence that these chemicals also impair the immune system and reproduction, highlights the dangers of this particular insecticidal class (neonicotinoids and fipronil), with the potential to greatly decrease populations of arthropods in both terrestrial and aquatic environments. Sublethal effects on fish, reptiles, frogs, birds, and mammals are also reported, showing a better understanding of the mechanisms of toxicity of these insecticides in vertebrates and their deleterious impacts on growth, reproduction, and neurobehaviour of most of the species tested. This review concludes with a summary of impacts on the ecosystem services and functioning, particularly on pollination, soil biota, and aquatic invertebrate communities, thus reinforcing the previous WIA conclusions (van der Sluijs et al. 2015).

Ontogenetic scaling of the gastrointestinal tract of a marsupial foregut fermenter, the western grey kangaroo Macropus fuliginosus melanops - Adam J. Munn; Edward P. Snelling; David A. Taggart; Roger S. Seymour (Journal of Comparative Physiology B, 2021)

The missing pieces for better future predictions in subarctic ecosystems: A Torneträsk case study - Didac Pascual; Jonas Åkerman; Marina Becher; Terry V. Callaghan; Torben R. Christensen; Ellen Dorrepaal; Urban Emanuelsson; Reiner Giesler; Dan Hammarlund; Edward Hanna; Annika Hofgaard; Hongxiao Jin; et al. (Ambio, 2021)
Arctic and subarctic ecosystems are experiencing substantial changes in hydrology, vegetation, permafrost conditions, and carbon cycling, in response to climatic change and other anthropogenic drivers, and these changes are likely to continue over this century. The total magnitude of these changes results from multiple interactions among these drivers. Field measurements can address the overall responses to different changing drivers, but are less capable of quantifying the interactions among them. Currently, a comprehensive assessment of the drivers of ecosystem changes, and the magnitude of their direct and indirect impacts on subarctic ecosystems, is missing. The Torneträsk area, in the Swedish subarctic, has an unrivalled history of environmental observation over 100 years, and is one of the most studied sites in the Arctic. In this study, we summarize and rank the drivers of ecosystem change in the Torneträsk area, and propose research priorities identified, by expert assessment, to improve predictions of ecosystem changes. The research priorities identified include understanding impacts on ecosystems brought on by altered frequency and intensity of winter warming events, evapotranspiration rates, rainfall, duration of snow cover and lake-ice, changed soil moisture, and droughts. This case study can help us understand the ongoing ecosystem changes occurring in the Torneträsk area, and contribute to improve predictions of future ecosystem changes at a larger scale. This understanding will provide the basis for the future mitigation and adaptation plans needed in a changing climate.

Pantropical variability in tree crown allometry - Grace Jopaul Loubota Panzou; Adeline Fayolle; Tommaso Jucker; Oliver L. Phillips; Stephanie Bohlman; Lindsay F. Banin; Simon L. Lewis; Kofi Affum‐Baffoe; Luciana F. Alves; Cécile Antin; Eric Arets; Luzmila Arroyo; et al. (Global Ecology and Biogeography, 2021)
Aim Tree crowns determine light interception, carbon and water exchange. Thus, understanding the factors causing tree crown allometry to vary at the tree and stand level matters greatly for the development of future vegetation modelling and for the calibration of remote sensing products. Nevertheless, we know little about large‐scale variation and determinants in tropical tree crown allometry. In this study, we explored the continental variation in scaling exponents of site‐specific crown allometry and assessed their relationships with environmental and stand‐level variables in the tropics. Location Global tropics. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 87,737 trees distributed among 245 forest and savanna sites across the tropics, we fitted site‐specific allometric relationships between crown dimensions (crown depth, diameter and volume) and stem diameter using power‐law models. Stand‐level and environmental drivers of crown allometric relationships were assessed at pantropical and continental scales. Results The scaling exponents of allometric relationships between stem diameter and crown dimensions were higher in savannas than in forests. We identified that continental crown models were better than pantropical crown models and that continental differences in crown allometric relationships were driven by both stand‐level (wood density) and environmental (precipitation, cation exchange capacity and soil texture) variables for both tropical biomes. For a given diameter, forest trees from Asia and savanna trees from Australia had smaller crown dimensions than trees in Africa and America, with crown volumes for some Asian forest trees being smaller than those of trees in African forests. Main conclusions Our results provide new insight into geographical variability, with large continental differences in tropical tree crown allometry that were driven by stand‐level and environmental variables. They have implications for the assessment of ecosystem function and for the monitoring of woody biomass by remote sensing techniques in the global tropics.

Scenarios for Global Aquaculture and Its Role in Human Nutrition - Jessica A. Gephart; Christopher D. Golden; Frank Asche; Ben Belton; Cecile Brugere; Halley E. Froehlich; Jillian P. Fry; Benjamin S. Halpern; Christina C. Hicks; Robert C. Jones; Dane H. Klinger; David C. Little; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Investigating the potential of Sentinel-1 to detect varying spatial heterogeneity in pasture cover in grasslands - Richard A. Crabbe; David W. Lamb; Clare Edwards (International Journal of Remote Sensing, 2021)

Epidemiology, Clinical Features, and Management of Texas Coral Snake (Micrurus tener) Envenomations Reported to the North American Snakebite Registry - Spencer Greene; Anne-Michelle Ruha; Sharan Campleman; Jeffrey Brent; Paul Wax; Kim Aldy; Peter Akpunonu; Vikhyat S. Bebarta; Gillian A. Beauchamp; Michael C. Beuhler; Mary Billington; William Boroughf; et al. (Journal of Medical Toxicology, 2021)

Spatial and Temporal Influences of Nearshore Hydrography on Fish Assemblages Associated with Energy Platforms in the Northern Gulf of Mexico - Ryan T. Munnelly; David B. Reeves; Edward J. Chesney; Donald M. Baltz (Estuaries and Coasts, 2021)

A global analysis of complexity–biodiversity relationships on marine artificial structures - Elisabeth M. A. Strain; Peter D. Steinberg; Maria Vozzo; Emma L. Johnston; Marco Abbiati; Moises A. Aguilera; Laura Airoldi; J. David Aguirre; Gail Ashton; Maritina Bernardi; Paul Brooks; Benny K. K. Chan; et al. (Global Ecology and Biogeography, 2021)
Aim Topographic complexity is widely accepted as a key driver of biodiversity, but at the patch‐scale, complexity–biodiversity relationships may vary spatially and temporally according to the environmental stressors complexity mitigates, and the species richness and identity of potential colonists. Using a manipulative experiment, we assessed spatial variation in patch‐scale effects of complexity on intertidal biodiversity. Location 27 sites within 14 estuaries/bays distributed globally. Time period 2015–2017. Major taxa studied Functional groups of algae, sessile and mobile invertebrates. Methods Concrete tiles of differing complexity (flat; 2.5‐cm or 5‐cm complex) were affixed at low–high intertidal elevation on coastal defence structures, and the richness and abundance of the colonizing taxa were quantified after 12 months. Results The patch‐scale effects of complexity varied spatially and among functional groups. Complexity had neutral to positive effects on total, invertebrate and algal taxa richness, and invertebrate abundances. However, effects on the abundance of algae ranged from positive to negative, depending on location and functional group. The tidal elevation at which tiles were placed accounted for some variation. The total and invertebrate richness were greater at low or mid than at high intertidal elevations. Latitude was also an important source of spatial variation, with the effects of complexity on total richness and mobile mollusc abundance greatest at lower latitudes, whilst the cover of sessile invertebrates and sessile molluscs responded most strongly to complexity at higher latitudes. Conclusions After 12 months, patch‐scale relationships between biodiversity and habitat complexity were not universally positive. Instead, the relationship varied among functional groups and according to local abiotic and biotic conditions. This result challenges the assumption that effects of complexity on biodiversity are universally positive. The variable effect of complexity has ramifications for community and applied ecology, including eco‐engineering and restoration that seek to bolster biodiversity through the addition of complexity.

Production of a structurally validated cyclotide in rice suspension cells is enabled by a supporting biosynthetic enzyme - Haiou Qu; Mark A. Jackson; Kuok Yap; Peta J. Harvey; Edward K. Gilding; David J. Craik (Planta, 2020)

Volatile Organic Compounds as Insect Repellents and Plant Elicitors: an Integrated Pest Management (IPM) Strategy for Glasshouse Whitefly (Trialeurodes vaporariorum) - Niall J.A. Conboy; Thomas McDaniel; David George; Adam Ormerod; Martin Edwards; Paul Donohoe; Angharad M. R Gatehouse; Colin R. Tosh (Journal of Chemical Ecology, 2020)
The glasshouse whitefly ( Trialeurodes vaporariorum Westwood) is a polyphagous arthropod pest that is of particular detriment to glasshouse grown tomato ( Solanum lycopersicum ) across temperate regions of the world. Control of whiteflies with synthetic pesticides has resulted in the evolution of resistant genotypes and a reduction in natural enemies, thus highlighting the need for environmentally sound control strategies. Volatile organic compounds (VOCs) offer an environmentally benign alternative to synthetic chemical sprays and this study explored the use of VOCs as insect repellents and plant defence elicitors to control whiteflies on tomato in a commercial glasshouse setting. Limonene in the form of a volatile dispenser system was found to successfully repel whitefly from the target crop and increased fruit yield by 32% during a heavy whitefly infestation. Analysis of tomato herbivore induced plant volatiles (HIPVs) led us to select methyl salicylate (MeSA) as the plant elicitor and application of MeSA to un-infested tomato plants was found to successfully reduce whitefly population development and increase yield by 11%, although this difference was marginally statistically significant. Combination of these two methods was also effective but whitefly abundance in combined plots was similar to the standalone limonene treatment across the course of the experiment. All of the VOC based control methods we used had a negative impact on whitefly performance, with more pronounced effects during the first few weeks of infestation. In subsequent laboratory experiments, we found elevated peroxidase (POD) activity and a significant increase in TPX1 and PR1 transcripts in MeSA treated plants. This led us to deduce that MeSA immediately induced plant defences, rather than priming them. We did however see evidence for residual priming, as plants treated with MeSA and infested with whiteflies produced significantly higher levels of POD activity than whitefly infestation alone. Despite the fact that our treatments failed to synergise, our methods can be optimised further, and the effectiveness of the standalone treatments is promising for future studies. In particular, our repellent limonene dispensers were extremely effective at deterring whiteflies and offer a low economic cost and easy to implement whitefly control option. The methods we have used here could be incorporated into current integrated pest management (IPM) systems, a sustainable approach to pest control which will be central to our efforts to manage whitefly populations under glass in the future.

Greater topoclimatic control of above‐ versus below‐ground communities - Heidi K. Mod; Daniel Scherrer; Valeria Di Cola; Olivier Broennimann; Quentin Blandenier; Frank T. Breiner; Aline Buri; Jérôme Goudet; Nicolas Guex; Enrique Lara; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; et al. (Global Change Biology, 2020)
Assessing the degree to which climate explains the spatial distributions of different taxonomic and functional groups is essential for anticipating the effects of climate change on ecosystems. Most effort so far has focused on above‐ground organisms, which offer only a partial view on the response of biodiversity to environmental gradients. Here including both above‐ and below‐ground organisms, we quantified the degree of topoclimatic control on the occurrence patterns of >1,500 taxa and phylotypes along a c. 3,000 m elevation gradient, by fitting species distribution models. Higher model performances for animals and plants than for soil microbes (fungi, bacteria and protists) suggest that the direct influence of topoclimate is stronger on above‐ground species than on below‐ground microorganisms. Accordingly, direct climate change effects are predicted to be stronger for above‐ground than for below‐ground taxa, whereas factors expressing local soil microclimate and geochemistry are likely more important to explain and forecast the occurrence patterns of soil microbiota. Detailed mapping and future scenarios of soil microclimate and microhabitats, together with comparative studies of interacting and ecologically dependent above‐ and below‐ground biota, are thus needed to understand and realistically forecast the future distribution of ecosystems.

Public Perceptions of Mangrove Forests Matter for Their Conservation - Farid Dahdouh-Guebas; Gordon N. Ajonina; A. Aldrie Amir; Dominic A. Andradi-Brown; Irfan Aziz; Thorsten Balke; Edward B. Barbier; Stefano Cannicci; Simon M. Cragg; Marília Cunha-Lignon; David J. Curnick; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Survey, identification and genetic diversity of Phytophthora capsici causing wilt of chilli (Capsicum annuum L.) in Bhutan - Ganja S. Rai; Edward C. Y. Liew; David. I. Guest (European Journal of Plant Pathology, 2020)

Evolution of the African slippery frogs (Anura: Conraua ), including the world’s largest living frog - David C. Blackburn; Stuart V. Nielsen; Michael F. Barej; Joseph Doumbia; Mareike Hirschfeld; N’Goran G. Kouamé; Dwight Lawson; Simon Loader; Caleb Ofori‐Boateng; Edward L. Stanley; Mark‐Oliver Rödel (Zoologica Scripta, 2020)
Although Conraua goliath is well known as the largest living frog species, the diversity and evolution of the genus Conraua across sub‐Saharan Africa remain poorly understood. We present multilocus phylogenetic analyses of the six currently recognized species that provide insights into divergence times, biogeography, body size evolution and undescribed species. An analysis of divergence times demonstrates that crown‐group Conraua arose some time during the latest Oligocene to mid‐Miocene followed by divergence into major lineages in the mid‐Miocene that may reflect the fragmentation of widespread tropical forests in Africa that began at this time. We find three pairs of sister species, C. crassipes + C. beccarii , C. alleni + C. derooi and C. goliath + C. robusta , each of which diverged during the Miocene. These relationships reject phylogenetic hypotheses based solely on biogeography as the geographically peripheral C. beccarii from north‐eastern Africa is nested within western African species and the Central African species do not form a clade. Our species delimitation analyses provide support for undescribed species in C. alleni , C. beccarii and C. derooi , and possibly C. crassipes , suggesting that the current taxonomy substantially underestimates species diversity. There is no clear directional trend of either increasing or decreasing body size in Conraua and the three largest species do not form a clade. With a robust phylogenetic hypothesis in hand, further field‐based studies are needed to understand the evolution of morphology and life history in this charismatic African anuran clade.

Comparison of USACE Three-Factor Wetland Delineations to National Wetland Inventory Maps - Edward Gage; David J. Cooper; Robert Lichvar (Wetlands, 2020)

The Human Gene Mutation Database (HGMD®): optimizing its use in a clinical diagnostic or research setting - Peter D. Stenson; Matthew Mort; Edward V. Ball; Molly Chapman; Katy Evans; Luisa Azevedo; Matthew Hayden; Sally Heywood; David S. Millar; Andrew D. Phillips; David N. Cooper (Human Genetics, 2020)
The Human Gene Mutation Database (HGMD ® ) constitutes a comprehensive collection of published germline mutations in nuclear genes that are thought to underlie, or are closely associated with human inherited disease. At the time of writing (June 2020), the database contains in excess of 289,000 different gene lesions identified in over 11,100 genes manually curated from 72,987 articles published in over 3100 peer-reviewed journals. There are primarily two main groups of users who utilise HGMD on a regular basis; research scientists and clinical diagnosticians. This review aims to highlight how to make the most out of HGMD data in each setting.

Managing Phosphate Rock to Improve Nutrient Uptake, Phosphorus Use Efficiency, and Carrot Yields - Edwin Mwangi; Catherine Ngamau; John Wesonga; Edward Karanja; Martha Musyoka; Felix Matheri; Komi Fiaboe; David Bautze; Noah Adamtey (Journal of Soil Science and Plant Nutrition, 2020)

A review of American lobster (Homarus americanus) records around the British Isles: 2012 to 2018 - Christopher John Barrett; Alastair Cook; David Stone; Chris Evans; Debbie Murphy; Paul Johnson; Marc Thain; Gabrielle Wyn; Mark Grey; Hugh Edwards; Declan Quigley; Paul Douglas Stebbing (Hydrobiologia, 2020)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Effectiveness of beta blockers in patients with and without a history of myocardial infarction - Sanjay Verma; Edward L. Peterson; Bin Liu; Hani N. Sabbah; L. Keoki Williams; David E. Lanfear (European Journal of Clinical Pharmacology, 2020)

White matter microstructure varies with post-traumatic stress severity following medical trauma - Nathaniel G. Harnett; Edward W. Ference; Amy J. Knight; David C. Knight (Brain Imaging and Behavior, 2020)

Coronavirus surveillance of wildlife in the Lao People’s Democratic Republic detects viral RNA in rodents - David J. McIver; Soubanh Silithammavong; Watthana Theppangna; Amethyst Gillis; Bounlom Douangngeun; Kongsy Khammavong; Sinpakone Singhalath; Veasna Duong; Philippe Buchy; Sarah H. Olson; Lucy Keatts; Amanda E. Fine; et al. (Archives of Virology, 2020)

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Quaternary land bridges have not been universal conduits of gene flow - Emilie Cros; Balaji Chattopadhyay; Kritika M. Garg; Nathaniel S. R. Ng; Suzanne Tomassi; Suzan Benedick; David P. Edwards; Frank E. Rheindt (Molecular Ecology, 2020)
Quaternary climate oscillations are a well‐known driver of animal diversification, but their effects are most well studied in areas where glaciations lead to habitat fragmentation. In large areas of the planet, however, glaciations have had the opposite effect, but here their impacts are much less well understood. This is especially true in Southeast Asia, where cyclical changes in land distribution have generated enormous land expansions during glacial periods. In this study, we selected a panel of five songbird species complexes covering a range of ecological specificities to investigate the effects Quaternary land bridges have had on the connectivity of Southeast Asian forest biota. Specifically, we combined morphological and bioacoustic analysis with an arsenal of population genomic and modelling approaches applied to thousands of genome‐wide DNA markers across a total of more than 100 individuals. Our analyses show that species dependent on forest understorey exhibit deep differentiation between Borneo and western Sundaland, with no evidence of gene flow during the land bridges accompanying the last 1–2 ice ages. In contrast, dispersive canopy species and habitat generalists have experienced more recent gene flow. Our results argue that there remains much cryptic species‐level diversity to be discovered in Southeast Asia even in well‐known animal groups such as birds, especially in nondispersive forest understorey inhabitants. We also demonstrate that Quaternary land bridges have not been equally suitable conduits of gene flow for all species complexes and that life history is a major factor in predicting relative population divergence time across Quaternary climate fluctuations.

High dietary sodium augments vascular tone and attenuates low-flow mediated constriction in salt-resistant adults - Ninette Shenouda; Meghan G. Ramick; Shannon L. Lennon; William B. Farquhar; David G. Edwards (European Journal of Applied Physiology, 2020)

Taxonomy of prokaryotic viruses: 2018-2019 update from the ICTV Bacterial and Archaeal Viruses Subcommittee - Evelien M. Adriaenssens; Matthew B. Sullivan; Petar Knezevic; Leonardo J. van Zyl; B. L. Sarkar; Bas E. Dutilh; Poliane Alfenas-Zerbini; Małgorzata Łobocka; Yigang Tong; James Rodney Brister; Andrea I. Moreno Switt; Jochen Klumpp; et al. (Archives of Virology, 2020)

Influence of Indigenous Knowledge and Scientific Climate Forecasts on Arable Farmers’ Climate Adaptation Methods in the Rwenzori region, Western Uganda - Michael Robert Nkuba; Raban Chanda; Gagoitseope Mmopelwa; Edward Kato; Margaret N. Mangheni; David Lesolle (Environmental Management, 2020)

Direct Observation of Low Strain, High Rate Deformation of Cultured Brain Tissue During Primary Blast - Edward W. Vogel; Matthew B. Panzer; Fatima N. Morales; Nevin Varghese; Cameron R. Bass; David F. Meaney; Barclay Morrison (Annals of Biomedical Engineering, 2020)

Soil protist diversity in the Swiss western Alps is better predicted by topo‐climatic than by edaphic variables - Christophe V. W. Seppey; Olivier Broennimann; Aline Buri; Erika Yashiro; Eric Pinto‐Figueroa; David Singer; Quentin Blandenier; Edward A. D. Mitchell; Hélène Niculita‐Hirzel; Antoine Guisan; Enrique Lara (Journal of Biogeography, 2020)
Aim Trends in spatial patterns of diversity in macroscopic organisms can be well predicted from correlative models, using topo‐climatic variables for plants and animals allowing inference over large scales. By contrast, diversity in soil microorganisms is generally considered as mostly driven by edaphic variables and, therefore, difficult to extrapolate on a large spatial scale based on predictive models. Here, we compared the power of topo‐climatic versus edaphic variables for predicting the diversity of various soil protist groups at the regional scale. Location Swiss western Alps. Taxa Full protist community and nine clades belonging respectively to three functional groups: parasites (Apicomplexa, Peronosporomycetes and Phytomyxea), phagotrophs (Sarcomonadea, Tubulinea and Spirotrichea) and phototrophs (Chlorophyta, Trebouxiophyceae and Diatomeae). Methods We extracted soil DNA from 178 sites along a wide range of elevations with a random‐stratified sampling design. We defined protist Operational Taxonomic Units assemblages by metabarcoding of the V4 region of the rRNA small subunit gene. We assessed and modelled the diversity (Shannon index) patterns of all above‐mentioned taxonomic groups based on topo‐climatic (topography, slope southness, slope steepness and average summer temperature) and edaphic (soil temperature, relative humidity, pH, electroconductivity, phosphorus percentage, carbon/nitrogen, loss on ignition and shale percentage) variables in Generalized Additive Models (GAM). Results The respective significance of topo‐climatic and edaphic variables varied among taxonomic and—to a certain extent—functional groups: while many variables explained significantly the diversity of the three phototrophs this was less the case for the three parasites. Topo‐climatic variables had a better predictive power than edaphic variables, yet predictive power varied among taxonomic groups. Main conclusions Topo‐climatic variables (particularly slope steepness and summer temperature if we consider their significance in the GAMs) were, on average, better predictors of protist diversity at the landscape scale than edaphic variables. However, the predictive power of these variables on diversity differed considerably among taxonomic groups; such relationships may be due to direct and/or indirect (e.g. biotic) influences (like with parasitic taxa, where low predictive power is most likely explained by the absence of information on the hosts’ distribution). Future prospects include using such spatial models to predict hotspots of diversity and disease outbreaks.

The Importance of Bottom-Up Approaches to International Cooperation in Ocean Science: The Iron Story - Edward Urban; Andrew Bowie; Philip Boyd; Kristen Buck; Maeve Lohan; Sylvia Sander; Reiner Schlitzer; Alessandro Tagliabue; David Turner (Oceanography, 2020)

Not a melting pot: Plant species aggregate in their non‐native range - Gisela C. Stotz; James F. Cahill; Jonathan A. Bennett; Cameron N. Carlyle; Edward W. Bork; Diana Askarizadeh; Sandor Bartha; Carl Beierkuhnlein; Bazartseren Boldgiv; Leslie Brown; Marcelo Cabido; Giandiego Campetella; et al. (Global Ecology and Biogeography, 2020)
Aim Plant species continue to be moved outside of their native range by human activities. Here, we aim to determine whether, once introduced, plants assimilate into native communities or whether they aggregate, thus forming mosaics of native‐ and alien‐rich communities. Alien species might aggregate in their non‐native range owing to shared habitat preferences, such as their tendency to establish in high‐biomass, species‐poor areas. Location Twenty‐two herbaceous grasslands in 14 countries, mainly in the temperate zone. Time period 2012–2016. Major taxa studied Plants. Methods We used a globally coordinated survey. Within this survey, we found 46 plant species, predominantly from Eurasia, for which we had co‐occurrence data in their native and non‐native ranges. We tested for differences in co‐occurrence patterns of 46 species between their native (home) and non‐native (away) range. We also tested whether species had similar habitat preferences, by testing for differences in total biomass and species richness of the patches that species occupy in their native and non‐native ranges. Results We found the same species to show different patterns of association depending on whether they were in their native or non‐native range. Alien species were negatively associated with native species; instead, they aggregated with other alien species in species‐poor, high‐biomass communities in their non‐native range compared with their native range. Main conclusions The strong differences between the native (home) and non‐native (away) range in species co‐occurrence patterns are evidence that the way in which species associate with resident communities in their non‐native range is not species dependent, but is instead a property of being away from their native range. These results thus highlight that species might undergo important ecological changes when introduced away from their native range. Overall, we show origin‐dependent associations that result in novel communities, in which alien‐rich patches exist within a mosaic of native‐dominated communities.

Identification and QTL mapping of resistance to Turnip yellows virus (TuYV) in oilseed rape, Brassica napus - Dieter Hackenberg; Elvis Asare-Bediako; Adam Baker; Peter Walley; Carol Jenner; Shannon Greer; Lawrence Bramham; Jacqueline Batley; David Edwards; Regine Delourme; Guy Barker; Graham Teakle; et al. (Theoretical and Applied Genetics, 2020)
Key message Partially dominant resistance to Turnip yellows virus associated with one major QTL was identified in the natural allotetraploid oilseed rape cultivar Yudal. Abstract Turnip yellows virus (TuYV) is transmitted by the peach-potato aphid ( Myzus persicae ) and causes severe yield losses in commercial oilseed rape crops ( Brassica napus ). There is currently only one genetic resource for resistance to TuYV available in brassica, which was identified in the re-synthesised B. napus line ‘R54’. In our study, 27 mostly homozygous B. napus accessions, either doubled-haploid (DH) or inbred lines, representing a diverse subset of the B. napus genepool, were screened for TuYV resistance/susceptibility. Partial resistance to TuYV was identified in the Korean spring oilseed rape, B. napus variety Yudal, whilst the dwarf French winter oilseed rape line Darmor- bzh was susceptible. QTL mapping using the established Darmor- bzh × Yudal DH mapping population (DYDH) revealed one major QTL explaining 36% and 18% of the phenotypic variation in two independent experiments. A DYDH line was crossed to Yudal, and reciprocal backcross (BC 1 ) populations from the F 1 with either the susceptible or resistant parent revealed the dominant inheritance of the TuYV resistance. The QTL on ChrA04 was verified in the segregating BC 1 population. A second minor QTL on ChrC05 was identified in one of the two DYDH experiments, and it was not observed in the BC 1 population. The TuYV resistance QTL in ‘R54’ is within the QTL interval on Chr A04 of Yudal; however, the markers co-segregating with the ‘R54’ resistance are not conserved in Yudal, suggesting an independent origin of the TuYV resistances. This is the first report of the QTL mapping of TuYV resistance in natural B. napus .

Relationships among white-tailed deer density, harvest, and landscape metrics in TN, USA - Heidi L. Adams; Robert E. Kissell; Daryl Ratajczak; Edward L. Warr; Roger D. Applegate; Lynn Barrett; Tabitha Lavacot; David Graves (European Journal of Wildlife Research, 2020)
Landscape and harvest indices are frequently used to represent white-tailed deer ( Odocoileus virginianus ) density. However, the relationship between deer density and specific landscape indices is unclear. Harvest is another metric often used to estimate deer density. Our objective was to model the relationship among deer density, landscape metrics, and harvest density of deer in TN, USA. We estimated deer density across 11 regions in 2011 using distance sampling techniques. We developed 18 a priori models to assess relationships among deer density, harvest density, and landscape metrics. Estimates of deer density ranged from 1.85 to 19.99 deer/km 2 . Deer density was best predicted by harvest density and harvest density + percent woody area. However, harvest density was the only important variable in predicting deer density (Σω i = 0.700). Results of this study emphasize the significance of harvest density in deer management. While the importance of harvest as a management tool for deer is likely to increase as landscapes are fragmented and urbanized, specific management guidelines should be based upon deer densities and landscape metrics when they are important.

Secondary forest fragments offer important carbon and biodiversity cobenefits - Fabio A. R. Matos; Luiz F. S. Magnago; Carlos Aquila Chan Miranda; Luis F. T. de Menezes; Markus Gastauer; Nathália V. H. Safar; Carlos E. G. R. Schaefer; Mônica P. da Silva; Marcelo Simonelli; Felicity A. Edwards; Sebastião V. Martins; João A. A. Meira‐Neto; et al. (Global Change Biology, 2020)
Tropical forests store large amounts of carbon and high biodiversity, but are being degraded at alarming rates. The emerging global Forest and Landscape Restoration (FLR) agenda seeks to limit global climate change by removing carbon dioxide from the atmosphere through the growth of trees. In doing so, it may also protect biodiversity as a free cobenefit, which is vital given the massive shortfall in funding for biodiversity conservation. We investigated whether natural forest regeneration on abandoned pastureland offers such cobenefits, focusing for the first time on the recovery of taxonomic diversity (TD), phylogenetic diversity (PD) and functional diversity (FD) of trees, including the recovery of threatened and endemic species richness, within isolated secondary forest (SF) fragments. We focused on the globally threatened Brazilian Atlantic Forest, where commitments have been made to restore 1 million hectares under FLR. Three decades after land abandonment, regenerating forests had recovered ~20% (72 Mg/ha) of the above‐ground carbon stocks of a primary forest (PF), with cattle pasture containing just 3% of stocks relative to PFs. Over this period, SF recovered ~76% of TD, 84% of PD and 96% of FD found within PFs. In addition, SFs had on average recovered 65% of threatened and ~30% of endemic species richness of primary Atlantic forest. Finally, we find positive relationships between carbon stock and tree diversity recovery. Our results emphasize that SF fragments offer cobenefits under FLR and other carbon‐based payments for ecosystem service schemes (e.g. carbon enhancements under REDD+). They also indicate that even isolated patches of SF could help to mitigate climate change and the biodiversity extinction crisis by recovering species of high conservation concern and improving landscape connectivity.

Nitric oxide mediates oxylipin production and grazing defense in diatoms - Matthew D. Johnson; Bethanie R. Edwards; David J. Beaudoin; Benjamin A. S. Van Mooy; Assaf Vardi (Environmental Microbiology, 2020)
Summary Diatom blooms are important features of productive marine ecosystems and are known to support higher trophic levels. However, when stressed or wounded, diatoms can produce oxylipin molecules known to inhibit the reproduction and development of copepods and decrease microzooplankton growth rates. Using oxylipin chemical treatments, lipidomic analysis and functional genomic approaches, we provide evidence that nitric oxide (NO) and oxylipin signalling pathways in diatoms respond to protist grazers, resulting in increased defence fitness and survival. Exposure of the diatom Phaeodactylum tricornutum to the dinoflagellate Oxyrrhis marina resulted in NO production by P . tricornutum and pronounced change in its dissolved oxylipin profile. Experimentally elevating levels of NO also resulted in increased oxylipin production, and lower overall grazing rates. Furthermore, O . marina preferentially grazed on P . tricornutum prey with lower levels of NO, suggesting that this molecule and its effect on oxylipin pathways play a key role in prey selection. Exposure of O . marina grazing on P . tricornutum to exogenous oxylipins also decreased grazing rates, which is consistent with a grazing deterrence role for these molecules. These results suggest that NO and oxylipin production help to structure diatom communities, in part by modulating interactions with microzooplankton predators.

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Diffusion magnetic resonance imaging-derived free water detects neurodegenerative pattern induced by interferon-γ - Marcelo Febo; Pablo D. Perez; Carolina Ceballos-Diaz; Luis M. Colon-Perez; Huadong Zeng; Edward Ofori; Todd E. Golde; David E. Vaillancourt; Paramita Chakrabarty (Brain Structure and Function, 2020)

Respiratory and non-respiratory symptoms associated with pesticide management practices among farmers in Ghana’s most important vegetable hub - Reginald Quansah; John R. Bend; Frederick Ato Armah; Felix Bonney; Joshua Aseidu; David Oscar Yawson; Michael Osei Adu; Isaac Luginaah; David Kofi Essumang; Abukari Abdul-Rahaman; Samuel Cobbina; Samuel Iddi; et al. (Environmental Monitoring and Assessment, 2019)

Frag SAD : A database of diversity and species abundance distributions from habitat fragments - Jonathan M. Chase; Mario Liebergesell; Alban Sagouis; Felix May; Shane A. Blowes; Åke Berg; Enrico Bernard; Berry J. Brosi; Marc W. Cadotte; Luis Cayuela; Adriano G. Chiarello; Jean‐Francois Cosson; et al. (Ecology, 2019)
Habitat destruction is the single greatest anthropogenic threat to biodiversity. Decades of research on this issue have led to the accumulation of hundreds of data sets comparing species assemblages in larger, intact, habitats to smaller, more fragmented, habitats. Despite this, little synthesis or consensus has been achieved, primarily because of non‐standardized sampling methodology and analyses of notoriously scale‐dependent response variables (i.e., species richness). To be able to compare and contrast the results of habitat fragmentation on species’ assemblages, it is necessary to have the underlying data on species abundances and sampling intensity, so that standardization can be achieved. To accomplish this, we systematically searched the literature for studies where abundances of species in assemblages (of any taxa) were sampled from many habitat patches that varied in size. From these, we extracted data from several studies, and contacted authors of studies where appropriate data were collected but not published, giving us 117 studies that compared species assemblages among habitat fragments that varied in area. Less than one‐half (41) of studies came from tropical forests of Central and South America, but there were many studies from temperate forests and grasslands from all continents except Antarctica. Fifty‐four of the studies were on invertebrates (mostly insects), but there were several studies on plants (15), birds (16), mammals (19), and reptiles and amphibians (13). We also collected qualitative information on the length of time since fragmentation. With data on total and relative abundances (and identities) of species, sampling effort, and affiliated meta‐data about the study sites, these data can be used to more definitively test hypotheses about the role of habitat fragmentation in altering patterns of biodiversity. There are no copyright restrictions. Please cite this data paper and the associated Dryad data set if the data are used in publications.

Mapping Tasmania's cultural landscapes: Using habitat suitability modelling of archaeological sites as a landscape history tool - Penelope J. Jones; Grant J. Williamson; David M. J. S. Bowman; Edward C. Lefroy (Journal of Biogeography, 2019)
Aim Understanding past distributions of people across the landscape is key to understanding how people used, affected and related to the natural environment. Here, we use habitat suitability modelling to represent the landscape distribution of Tasmanian Aboriginal archaeological sites and assess the implications for patterns of past human activity. Location Tasmania, Australia. Methods We developed a RandomForest ‘habitat suitability' model of site records in the Tasmanian Aboriginal Heritage Register. We applied a best‐effort bias correction, considered 31 predictor variables relating to climate, topography and resource proximity, and used a variable selection procedure to optimize the final model. Model uncertainty was assessed via bootstrapping and we ran an analogous MaxEnt model as a cross‐validation exercise. Results The results from the RandomForest and MaxEnt models are highly congruent. The strongest environmental predictors of site occurrence include distance to coast, elevation, soil clay content, topographic roughness and distance to inland water. The highest habitat suitability scores are distributed across a wide range of environments in central, northern and eastern Tasmania, including coastal areas, inland water body margins and forests and savannas in the drier parts of Tasmania. With the exception of coastal areas much of western Tasmania has low habitat suitability scores, consistent with theories of low‐density Holocene Tasmanian Aboriginal settlement in this region. Main conclusions Our modelling suggests Tasmanian Aboriginal people occupied a heterogeneity of habitats but targeted coastal areas around the whole island, and drier, less steep and/or open forest and savanna environments in the central lowlands . The western interior was identified as being rarely used by Aboriginal people in the Holocene, with the exception of isolated pockets of habitat; yet whether this is a true reflection of Aboriginal‐resourceuse demands increased archaeological surveys, particularly in the Tasmanian Wilderness World Heritage Area.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The impact of secondary forest regeneration on ground-dwelling ant communities in the Tropical Andes - Matthew G. Hethcoat; Bethany J. King; Fernando Fernandez Castiblanco; Claudia M. Ortiz-Sepúlveda; Fabian Camilo Prada Achiardi; Felicity A. Edwards; Claudia Medina; James J. Gilroy; Torbjørn Haugaasen; David P. Edwards (Oecologia, 2019)

Uncertainty in geomorphological responses to climate change - Stephan Harrison; Tim Mighall; David A. Stainforth; Philip Allen; Mark Macklin; Edward Anderson; Jasper Knight; Dmitri Mauquoy; David Passmore; Brice Rea; Matteo Spagnolo; Sarah Shannon (Climatic Change, 2019)

DNA of diverse adenoviruses detected in Cameroonian rodent and shrew species - Joseph Diffo; Valantine Ngum Ndze; Nkom Felix Ntumvi; Jean-Michel Takuo; Moctar M. M. Mouiche; Ubald Tamoufe; Julius Nwobegahay; Matthew LeBreton; Amethyst Gillis; Bradley S. Schneider; Joseph M. Fair; Corina Monagin; et al. (Archives of Virology, 2019)

A dual rescaled Mitscherlich model of the simultaneous savings in phosphorus and zinc fertiliser from arbuscular mycorrhizal fungal colonisation of linseed (Linum usitatissimum L.) - Nicole P. Seymour; David G. Edwards; John P. Thompson (Plant and Soil, 2019)

Nitrogen leaching losses and balances in conventional and organic farming systems in Kenya - Martha W. Musyoka; Noah Adamtey; Anne W. Muriuki; David Bautze; Edward N. Karanja; Monica Mucheru-Muna; Komi K. M. Fiaboe; Georg Cadisch (Nutrient Cycling in Agroecosystems, 2019)

Combining supervised run interval training or moderate-intensity continuous training with the diabetes prevention program on clinical outcomes - Nicole M. Gilbertson; Joan A. Mandelson; Kathryn Hilovsky; Jeremy D. Akers; Trent A. Hargens; David L. Wenos; Elizabeth S. Edwards (European Journal of Applied Physiology, 2019)

Phosphate‐limited ocean regions select for bacterial populations enriched in the carbon–phosphorus lyase pathway for phosphonate degradation - Oscar A. Sosa; Daniel J. Repeta; Edward F. DeLong; Mohammad D. Ashkezari; David M. Karl (Environmental Microbiology, 2019)
Summary In tropical and subtropical oceanic surface waters phosphate scarcity can limit microbial productivity. However, these environments also have bioavailable forms of phosphorus incorporated into dissolved organic matter (DOM) that microbes with the necessary transport and hydrolysis metabolic pathways can access to supplement their phosphorus requirements. In this study we evaluated how the environment shapes the abundance and taxonomic distribution of the bacterial carbon–phosphorus (C–P) lyase pathway, an enzyme complex evolved to extract phosphate from phosphonates. Phosphonates are organophosphorus compounds characterized by a highly stable C–P bond and are enriched in marine DOM. Similar to other known bacterial adaptions to low phosphate environments, C–P lyase was found to become more prevalent as phosphate concentrations decreased. C–P lyase was particularly enriched in the Mediterranean Sea and North Atlantic Ocean, two regions that feature sustained periods of phosphate depletion. In these regions, C–P lyase was prevalent in several lineages of Alphaproteobacteria ( Pelagibacter , SAR116, Roseobacter and Rhodospirillales ), Gammaproteobacteria, and Actinobacteria . The global scope of this analysis supports previous studies that infer phosphonate catabolism via C–P lyase is an important adaptive strategy implemented by bacteria to alleviate phosphate limitation and expands the known geographic extent and taxonomic affiliation of this metabolic pathway in the ocean.

Reducing sea level rise with submerged barriers and dams in Greenland - Julian David Hunt; Edward Byers (Mitigation and Adaptation Strategies for Global Change, 2019)

Dispersal limitations and historical factors determine the biogeography of specialized terrestrial protists - David Singer; Edward A. D. Mitchell; Richard J. Payne; Quentin Blandenier; Clément Duckert; Leonardo D. Fernández; Bertrand Fournier; Cristián E. Hernández; Gustaf Granath; Håkan Rydin; Luca Bragazza; Natalia G. Koronatova; et al. (Molecular Ecology, 2019)
Recent studies show that soil eukaryotic diversity is immense and dominated by micro‐organisms. However, it is unclear to what extent the processes that shape the distribution of diversity in plants and animals also apply to micro‐organisms. Major diversification events in multicellular organisms have often been attributed to long‐term climatic and geological processes, but the impact of such processes on protist diversity has received much less attention as their distribution has often been believed to be largely cosmopolitan. Here, we quantified phylogeographical patterns in Hyalosphenia papilio , a large testate amoeba restricted to Holarctic Sphagnum ‐dominated peatlands, to test if the current distribution of its genetic diversity can be explained by historical factors or by the current distribution of suitable habitats. Phylogenetic diversity was higher in Western North America, corresponding to the inferred geographical origin of the H. papilio complex, and was lower in Eurasia despite extensive suitable habitats. These results suggest that patterns of phylogenetic diversity and distribution can be explained by the history of Holarctic Sphagnum peatland range expansions and contractions in response to Quaternary glaciations that promoted cladogenetic range evolution, rather than the contemporary distribution of suitable habitats. Species distributions were positively correlated with climatic niche breadth, suggesting that climatic tolerance is key to dispersal ability in H. papilio . This implies that, at least for large and specialized terrestrial micro‐organisms, propagule dispersal is slow enough that historical processes may contribute to their diversification and phylogeographical patterns and may partly explain their very high overall diversity.

Modeling potential impacts of three benthic invasive species on the Lake Erie food web - Hongyan Zhang; Edward S. Rutherford; Doran M. Mason; Marion E. Wittmann; David M. Lodge; Xinhua Zhu; Timothy B. Johnson; Andrew Tucker (Biological Invasions, 2019)

Land‐sparing agriculture sustains higher levels of avian functional diversity than land sharing - Patrick G. Cannon; James J. Gilroy; Joseph A. Tobias; Alex Anderson; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2019)
The ecological impacts of meeting rising demands for food production can potentially be mitigated by two competing land‐use strategies: off‐setting natural habitats through intensification of existing farmland (land sparing), or elevating biodiversity within the agricultural matrix via the integration of “wildlife‐friendly” habitat features (land sharing). However, a key unanswered question is whether sparing or sharing farming would best conserve functional diversity, which can promote ecosystem stability and resilience to future land‐use change. Focusing on bird communities in tropical cloud forests of the Colombian Andes, we test the performance of each strategy in conserving functional diversity. We show that multiple components of avian functional diversity in farmland are positively related to the proximity and extent of natural forest. Using landscape and community simulations, we also show that land‐sparing agriculture conserves greater functional diversity and predicts higher abundance of species supplying key ecological functions than land sharing, with sharing becoming progressively inferior with increasing isolation from remnant forest. These results suggest low‐intensity agriculture is likely to conserve little functional diversity unless large blocks of adjacent natural habitat are protected, consistent with land sparing. To ensure the retention of functionally diverse ecosystems, we urgently need to implement mechanisms for increasing farmland productivity whilst protecting spared land.

Securing a Just Space for Small-Scale Fisheries in the Blue Economy - Philippa J. Cohen; Edward H. Allison; Neil L. Andrew; Joshua Cinner; Louisa S. Evans; Michael Fabinyi; Len R. Garces; Stephen J. Hall; Christina C. Hicks; Terry P. Hughes; Svein Jentoft; David J. Mills; et al. (Frontiers in Marine Science, 2019)

Advancing Research for the Management of Long-Lived Species: A Case Study on the Greenland Shark - Jena E. Edwards; Elizabeth Hiltz; Franziska Broell; Peter G. Bushnell; Steven E. Campana; Jørgen S. Christiansen; Brynn M. Devine; Jeffrey J. Gallant; Kevin J. Hedges; M. Aaron MacNeil; Bailey C. McMeans; Julius Nielsen; et al. (Frontiers in Marine Science, 2019)

Quantitation of Purines from Pigeon Guano and Implications for Cryptococcus neoformans Survival During Infection - Jessica L. Chitty; David J. Edwards; Avril A. B. Robertson; Mark S. Butler; John A. Duley; Matthew A. Cooper; James A. Fraser (Mycopathologia, 2019)

The U.S. Climate Resilience Toolkit: evidence of progress - Edward P. Gardiner; David D. Herring; James F. Fox (Climatic Change, 2019)

Advancing Marine Biogeochemical and Ecosystem Reanalyses and Forecasts as Tools for Monitoring and Managing Ecosystem Health - Katja Fennel; Marion Gehlen; Pierre Brasseur; Christopher W. Brown; Stefano Ciavatta; Gianpiero Cossarini; Alessandro Crise; Christopher A. Edwards; David Ford; Marjorie A. M. Friedrichs; Marilaure Gregoire; Emlyn Jones; et al. (Frontiers in Marine Science, 2019)

A differential k-mer analysis pipeline for comparing RNA-Seq transcriptome and meta-transcriptome datasets without a reference - Chon-Kit Kenneth Chan; Nedeljka Rosic; Michał T. Lorenc; Paul Visendi; Meng Lin; Paulina Kaniewska; Brett J. Ferguson; Peter M. Gresshoff; Jacqueline Batley; David Edwards (Functional & Integrative Genomics, 2019)

Antibiotic misuse in respiratory tract infections in children and adults—a prospective, multicentre study (TAILORED Treatment) - Chantal B. van Houten; Asi Cohen; Dan Engelhard; John P. Hays; Roger Karlsson; Edward Moore; David Fernández; Racheli Kreisberg; Laurence V. Collins; Wouter de Waal; Karin M. de Winter-de Groot; Tom F. W. Wolfs; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Pharmacokinetics and safety of glecaprevir and pibrentasvir in HCV-negative subjects with hepatic impairment - Matthew P. Kosloski; Haoyu Wang; David Pugatch; Federico J. Mensa; Edward Gane; Eric Lawitz; Thomas C. Marbury; Richard A. Preston; Jens Kort; Wei Liu (European Journal of Clinical Pharmacology, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Corrigendum: Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2019)

Impacts of tropical forest disturbance on species vital rates - Cindy C.P. Cosset; James J. Gilroy; David P. Edwards (Conservation Biology, 2019)
Tropical forests are experiencing enormous threats from deforestation and habitat degradation. Much knowledge of the impacts of these land‐use changes on tropical species comes from studies examining patterns of richness and abundance. Demographic vital rates (survival, reproduction, and movement) can also be affected by land‐use change in a way that increases species vulnerability to extirpation, but in many cases these impacts may not be manifested in short‐term changes in abundance or species richness. We conducted a literature review to assess current knowledge and research effort concerning how land‐use change affects species vital rates in tropical forest vertebrates. We found a general paucity of empirical research on demography across taxa and regions, with some biases toward mammals and birds and land‐use transitions, including fragmentation and agriculture. There is also considerable between‐species variation in demographic responses to land‐use change, which could reflect trait‐based differences in species sensitivity, complex context dependencies (e.g., between‐region variation), or inconsistency in methods used in studies. Efforts to improve understanding of anthropogenic impacts on species demography are underway, but there is a need for increased research effort to fill knowledge gaps in understudied tropical regions and taxa. The lack of information on demographic impacts of anthropogenic disturbance makes it difficult to draw definite conclusions about the magnitude of threats to tropical ecosystems under anthropogenic pressures. Thus, determining conservation priorities and improving conservation effectiveness remains a challenge.

A Computational Cardiac Model for the Adaptation to Pulmonary Arterial Hypertension in the Rat - Reza Avazmohammadi; Emilio A. Mendiola; João S. Soares; David S. Li; Zhiqiang Chen; Samer Merchant; Edward W. Hsu; Peter Vanderslice; Richard A. F. Dixon; Michael S. Sacks (Annals of Biomedical Engineering, 2019)

The western Mediterranean region provided the founder population of domesticated narrow-leafed lupin - Mahsa Mousavi-Derazmahalleh; Bruno Nevado; Philipp E. Bayer; Dmitry A. Filatov; James K. Hane; David Edwards; William Erskine; Matthew N. Nelson (Theoretical and Applied Genetics, 2018)

Abundance and Distribution of Reef-Associated Fishes Around Small Oil and Gas Platforms in the Northern Gulf of Mexico’s Hypoxic Zone - David B. Reeves; Edward J. Chesney; Ryan T. Munnelly; Donald M. Baltz; Brian D. Marx (Estuaries and Coasts, 2018)

Correction to: A Semi-passive Planar Manipulandum for Upper-Extremity Rehabilitation - Chih-Kang Chang; Edward P. Washabaugh; Andrew Gwozdziowski; C. David Remy; Chandramouli Krishnan (Annals of Biomedical Engineering, 2018)

Subregional variability in the response of New England vegetation to postglacial climate change - W. Wyatt Oswald; David R. Foster; Bryan N. Shuman; Elaine D. Doughty; Edward K. Faison; Brian R. Hall; Barbara C. S. Hansen; Matts Lindbladh; Adriana Marroquin; Sarah A. Truebe (Journal of Biogeography, 2018)
Aim We analysed a dataset composed of multiple palaeoclimate and lake‐sediment pollen records from New England to explore how postglacial changes in the composition and spatial patterns of vegetation were controlled by regional‐scale climate change, a subregional environmental gradient, and landscape‐scale variations in soil characteristics. Location The 120,000‐km 2 study area includes parts of Vermont and New Hampshire in the north, where sites are 150–200 km from the Atlantic Ocean, and spans the coastline from southeastern New York to Cape Cod and the adjacent islands, including Block Island, the Elizabeth Islands, Nantucket, and Martha's Vineyard. Methods We analysed pollen records from 29 study sites, using multivariate cluster analysis to visualize changes in the composition and spatial patterns of vegetation during the last 14,000 years. The pollen data were compared with temperature and precipitation reconstructions. Results Boreal forest featuring Picea and Pinus banksiana was present across the region when conditions were cool and dry 14,000–12,000 calibrated 14 C years before present (ybp). Pinus strobus became regionally dominant as temperatures increased between 12,000 and 10,000 ybp. The composition of forests in inland and coastal areas diverged in response to further warming after 10,000 ybp, when Quercus and Pinus rigida expanded across southern New England, whereas conditions remained cool enough in inland areas to maintain Pinus strobus . Increasing precipitation allowed Tsuga canadensis , Fagus grandifolia , and Betula to replace Pinus strobus in inland areas during 9,000–8,000 ybp, and also led to the expansion of Carya across the coastal part of the region beginning at 7,000–6,000 ybp. Abrupt cooling at 5,500–5,000 ybp caused sharp declines in Tsuga in inland areas and Quercus at some coastal sites, and the populations of those taxa remained low until they recovered around 3,000 ybp in response to rising precipitation. Throughout most of the Holocene, sites underlain by sandy glacial deposits were occupied by Pinus rigida and Quercus . Main conclusions Postglacial changes in the composition and spatial pattern of New England forests were controlled by long‐term trends and abrupt shifts in temperature and precipitation, as well as by the environmental gradient between coastal and inland parts of the region. Substrate and soil moisture shaped landscape‐scale variations in forest composition.

Climatically driven changes in primary production propagate through trophic levels - David C. Stoner; Joseph O. Sexton; David M. Choate; Jyothy Nagol; Heather H. Bernales; Steven A. Sims; Kirsten E. Ironside; Kathleen M. Longshore; Thomas C. Edwards (Global Change Biology, 2018)
Climate and land‐use change are the major drivers of global biodiversity loss. Their effects are particularly acute for wide‐ranging consumers, but little is known about how these factors interact to affect the abundance of large carnivores and their herbivore prey. We analyzed population densities of a primary and secondary consumer (mule deer, Odocoileus hemionus , and mountain lion, Puma concolor ) across a climatic gradient in western North America by combining satellite‐based maps of plant productivity with estimates of animal abundance and foraging area derived from Global Positioning Systems telemetry data (GPS). Mule deer density exhibited a positive, linear relationship with plant productivity ( r 2 = 0.58), varying by a factor of 18 across the climate‐vegetation gradient (range: 38–697 individuals/100 km 2 ). Mountain lion home range size decreased in response to increasing primary productivity and consequent changes in the abundance of their herbivore prey (range: 20–450 km 2 ). This pattern resulted in a strong, positive association between plant productivity and mountain lion density ( r 2 = 0.67). Despite varying densities, the ratio of prey to predator remained constant across the climatic gradient (mean ± SE = 363 ± 29 mule deer/mountain lion), suggesting that the determinacy of the effect of primary productivity on consumer density was conserved across trophic levels. As droughts and longer term climate changes reduce the suitability of marginal habitats, consumer home ranges will expand in order for individuals to meet basic nutritional requirements. These changes portend decreases in the abundance of large‐bodied, wide‐ranging wildlife through climatically driven reductions in carrying capacity, as well as increased human–wildlife interactions stemming from anthropogenic land use and habitat fragmentation.

The DRD2 Taq1A A1 Allele May Magnify the Risk of Alzheimer’s in Aging African-Americans - Kenneth Blum; Rajendra D. Badgaiyan; Georgia M. Dunston; David Baron; Edward J. Modestino; Thomas McLaughlin; Bruce Steinberg; Mark S. Gold; Marjorie C. Gondré-Lewis (Molecular Neurobiology, 2018)

A Semi-passive Planar Manipulandum for Upper-Extremity Rehabilitation - Chih-Kang Chang; Edward P. Washabaugh; Andrew Gwozdziowski; C. David Remy; Chandramouli Krishnan (Annals of Biomedical Engineering, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Comparative, collaborative, and integrative risk governance for emerging technologies - Igor Linkov; Benjamin D. Trump; Elke Anklam; David Berube; Patrick Boisseasu; Christopher Cummings; Scott Ferson; Marie-Valentine Florin; Bernard Goldstein; Danail Hristozov; Keld Alstrup Jensen; Georgios Katalagarianakis; et al. (Environment Systems and Decisions, 2018)

Converging and emerging threats to health security - C. Raina MacIntyre; Thomas Edward Engells; Matthew Scotch; David James Heslop; Abba B. Gumel; George Poste; Xin Chen; Wesley Herche; Kathleen Steinhöfel; Samsung Lim; Alex Broom (Environment Systems and Decisions, 2018)

Review: The distribution, flow, and quality of Grand Canyon Springs, Arizona (USA) - Benjamin W. Tobin; Abraham E. Springer; David K. Kreamer; Edward Schenk (Hydrogeology Journal, 2018)

Exploring the genetic and adaptive diversity of a pan-Mediterranean crop wild relative: narrow-leafed lupin - Mahsa Mousavi-Derazmahalleh; Philipp E. Bayer; Bruno Nevado; Bhavna Hurgobin; Dmitry Filatov; Andrzej Kilian; Lars G. Kamphuis; Karam B. Singh; Jens D. Berger; James K. Hane; David Edwards; William Erskine; et al. (Theoretical and Applied Genetics, 2018)

The phase diagrams of KCaF3 and NaMgF3 by ab initio simulations - Clément Jakymiw; Lidunka Vočadlo; David P. Dobson; Edward Bailey; Andrew R. Thomson; John P. Brodholt; Ian G. Wood; Alex Lindsay-Scott (Physics and Chemistry of Minerals, 2018)

Taxonomy of prokaryotic viruses: 2017 update from the ICTV Bacterial and Archaeal Viruses Subcommittee - Evelien M. Adriaenssens; Johannes Wittmann; Jens H. Kuhn; Dann Turner; Matthew B. Sullivan; Bas E. Dutilh; Ho Bin Jang; Leonardo J. van Zyl; Jochen Klumpp; Malgorzata Lobocka; Andrea I. Moreno Switt; Janis Rumnieks; et al. (Archives of Virology, 2018)

Environmental filtering and phylogenetic clustering correlate with the distribution patterns of cryptic protist species - David Singer; Anush Kosakyan; Christophe V. W. Seppey; Amandine Pillonel; Leonardo D. Fernández; Diego Fontaneto; Edward A. D. Mitchell; Enrique Lara (Ecology, 2018)
The community composition of any group of organisms should theoretically be determined by a combination of assembly processes including resource partitioning, competition, environmental filtering, and phylogenetic legacy. Environmental DNA studies have revealed a huge diversity of protists in all environments, raising questions about the ecological significance of such diversity and the degree to which they obey to the same rules as macroscopic organisms. The fast‐growing cultivable protist species on which hypotheses are usually experimentally tested represent only a minority of the protist diversity. Addressing these questions for the lesser known majority can only be inferred through observational studies. We conducted an environmental DNA survey of the genus Nebela , a group of closely related testate (shelled) amoeba species, in different habitats within Sphagnum ‐dominated peatlands. Identification based on the mitochondrial cytochrome c oxidase 1 gene, allowed species‐level resolution as well as phylogenetic reconstruction. Community composition varied strongly across habitats and associated environmental gradients. Species showed little overlap in their realized niche, suggesting resource partitioning, and a strong influence of environmental filtering driving community composition. Furthermore, phylogenetic clustering was observed in the most nitrogen‐poor samples, supporting phylogenetic inheritance of adaptations in the group of N. guttata . This study showed that the studied free‐living unicellular eukaryotes follow to community assembly rules similar to those known to determine plant and animal communities; the same may be true for much of the huge functional and taxonomic diversity of protists.

Extra-pair parentage and personality in a cooperatively breeding bird - Hannah A Edwards; Hannah L Dugdale; David S Richardson; Jan Komdeur; Terry Burke (Behavioral Ecology and Sociobiology, 2018)

Tropical forests are thermally buffered despite intensive selective logging - Rebecca A. Senior; Jane K. Hill; Suzan Benedick; David P. Edwards (Global Change Biology, 2018)
Tropical rainforests are subject to extensive degradation by commercial selective logging. Despite pervasive changes to forest structure, selectively logged forests represent vital refugia for global biodiversity. The ability of these forests to buffer temperature‐sensitive species from climate warming will be an important determinant of their future conservation value, although this topic remains largely unexplored. Thermal buffering potential is broadly determined by: (i) the difference between the “macroclimate” (climate at a local scale, m to ha) and the “microclimate” (climate at a fine‐scale, mm to m, that is distinct from the macroclimate); (ii) thermal stability of microclimates (e.g. variation in daily temperatures); and (iii) the availability of microclimates to organisms. We compared these metrics in undisturbed primary forest and intensively logged forest on Borneo, using thermal images to capture cool microclimates on the surface of the forest floor, and information from dataloggers placed inside deadwood, tree holes and leaf litter. Although major differences in forest structure remained 9–12 years after repeated selective logging, we found that logging activity had very little effect on thermal buffering, in terms of macroclimate and microclimate temperatures, and the overall availability of microclimates. For 1°C warming in the macroclimate, temperature inside deadwood, tree holes and leaf litter warmed slightly more in primary forest than in logged forest, but the effect amounted to

Exposure to Sublethal Ammonia Concentrations Alters the Duration and Intensity of Agonistic Interactions in the Crayfish, Orconectes rusticus - David D. Edwards; Katie L. Klotz; Paul A. Moore (Bulletin of Environmental Contamination and Toxicology, 2018)

Vulnerability of grazing and confined livestock in the Northern Great Plains to projected mid- and late-twenty-first century climate - Justin Derner; David Briske; Matt Reeves; Tami Brown-Brandl; Miranda Meehan; Dana Blumenthal; William Travis; David Augustine; Hailey Wilmer; Derek Scasta; John Hendrickson; Jerry Volesky; et al. (Climatic Change, 2018)

Relationships between landscape pattern metrics, vertical structure and surface urban Heat Island formation in a Colorado suburb - Edward A. Gage; David J. Cooper (Urban Ecosystems, 2017)

Copy number variation and disease resistance in plants - Aria Dolatabadian; Dhwani Apurva Patel; David Edwards; Jacqueline Batley (Theoretical and Applied Genetics, 2017)

Quantifying rock fall probabilities and their temporal distribution associated with weather seasonality - Renato Macciotta; Michael Hendry; David M. Cruden; Andrée Blais-Stevens; Tom Edwards (Landslides, 2017)

Asynchrony among local communities stabilises ecosystem function of metacommunities - Kevin R. Wilcox; Andrew T. Tredennick; Sally E. Koerner; Emily Grman; Lauren M. Hallett; Meghan L. Avolio; Kimberly J. La Pierre; Gregory R. Houseman; Forest Isbell; David Samuel Johnson; Juha M. Alatalo; Andrew H. Baldwin; et al. (Ecology Letters, 2017)
Temporal stability of ecosystem functioning increases the predictability and reliability of ecosystem services, and understanding the drivers of stability across spatial scales is important for land management and policy decisions. We used species‐level abundance data from 62 plant communities across five continents to assess mechanisms of temporal stability across spatial scales. We assessed how asynchrony (i.e. different units responding dissimilarly through time) of species and local communities stabilised metacommunity ecosystem function. Asynchrony of species increased stability of local communities, and asynchrony among local communities enhanced metacommunity stability by a wide range of magnitudes (1–315%); this range was positively correlated with the size of the metacommunity. Additionally, asynchronous responses among local communities were linked with species’ populations fluctuating asynchronously across space, perhaps stemming from physical and/or competitive differences among local communities. Accordingly, we suggest spatial heterogeneity should be a major focus for maintaining the stability of ecosystem services at larger spatial scales.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Erratum to: A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)

Biomarkers of Acute Stroke Etiology (BASE) Study Methodology - Edward C. Jauch; Andrew D. Barreto; Joseph P. Broderick; Doug M. Char; Brett L. Cucchiara; Thomas G. Devlin; Alison J. Haddock; William J. Hicks; Brian C. Hiestand; Glen C. Jickling; Jeff June; David S. Liebeskind; et al. (Translational Stroke Research, 2017)

A multi-stage genome-wide association study of uterine fibroids in African Americans - Jacklyn N. Hellwege; Janina M. Jeff; Lauren A. Wise; C. Scott Gallagher; Melissa Wellons; Katherine E. Hartmann; Sarah F. Jones; Eric S. Torstenson; Scott Dickinson; Edward A. Ruiz-Narváez; Nadin Rohland; Alexander Allen; et al. (Human Genetics, 2017)
Uterine fibroids are benign tumors of the uterus affecting up to 77% of women by menopause. They are the leading indication for hysterectomy, and account for $34 billion annually in the United States. Race/ethnicity and age are the strongest known risk factors. African American (AA) women have higher prevalence, earlier onset, and larger and more numerous fibroids than European American women. We conducted a multi-stage genome-wide association study (GWAS) of fibroid risk among AA women followed by in silico genetically predicted gene expression profiling of top hits. In Stage 1, cases and controls were confirmed by pelvic imaging, genotyped and imputed to 1000 Genomes. Stage 2 used self-reported fibroid and GWAS data from 23andMe, Inc. and the Black Women’s Health Study. Associations with fibroid risk were modeled using logistic regression adjusted for principal components, followed by meta-analysis of results. We observed a significant association among 3399 AA cases and 4764 AA controls at rs739187 (risk-allele frequency = 0.27) in CYTH4 (OR (95% confidence interval) = 1.23 (1.16–1.30), p value = 7.82 × 10 −9 ). Evaluation of the genetic association results with MetaXcan identified lower predicted gene expression of CYTH4 in thyroid tissue as significantly associated with fibroid risk ( p value = 5.86 × 10 −8 ). In this first multi-stage GWAS for fibroids among AA women, we identified a novel risk locus for fibroids within CYTH4 that impacts gene expression in thyroid and has potential biological relevance for fibroids.

Asymmetric responses of primary productivity to precipitation extremes: A synthesis of grassland precipitation manipulation experiments - Kevin R. Wilcox; Zheng Shi; Laureano A. Gherardi; Nathan P. Lemoine; Sally E. Koerner; David L. Hoover; Edward Bork; Kerry M. Byrne; James Cahill; Scott L. Collins; Sarah Evans; Anna K. Gilgen; et al. (Global Change Biology, 2017)
Climatic changes are altering Earth's hydrological cycle, resulting in altered precipitation amounts, increased interannual variability of precipitation, and more frequent extreme precipitation events. These trends will likely continue into the future, having substantial impacts on net primary productivity ( NPP ) and associated ecosystem services such as food production and carbon sequestration. Frequently, experimental manipulations of precipitation have linked altered precipitation regimes to changes in NPP . Yet, findings have been diverse and substantial uncertainty still surrounds generalities describing patterns of ecosystem sensitivity to altered precipitation. Additionally, we do not know whether previously observed correlations between NPP and precipitation remain accurate when precipitation changes become extreme. We synthesized results from 83 case studies of experimental precipitation manipulations in grasslands worldwide. We used meta‐analytical techniques to search for generalities and asymmetries of aboveground NPP ( ANPP ) and belowground NPP ( BNPP ) responses to both the direction and magnitude of precipitation change. Sensitivity (i.e., productivity response standardized by the amount of precipitation change) of BNPP was similar under precipitation additions and reductions, but ANPP was more sensitive to precipitation additions than reductions; this was especially evident in drier ecosystems. Additionally, overall relationships between the magnitude of productivity responses and the magnitude of precipitation change were saturating in form. The saturating form of this relationship was likely driven by ANPP responses to very extreme precipitation increases, although there were limited studies imposing extreme precipitation change, and there was considerable variation among experiments. This highlights the importance of incorporating gradients of manipulations, ranging from extreme drought to extreme precipitation increases into future climate change experiments. Additionally, policy and land management decisions related to global change scenarios should consider how ANPP and BNPP responses may differ, and that ecosystem responses to extreme events might not be predicted from relationships found under moderate environmental changes.

Transcriptome and proteome dynamics in chemostat culture reveal how Campylobacter jejuni modulates metabolism, stress responses and virulence factors upon changes in oxygen availability - Edward J. Guccione; John J. Kendall; Andrew Hitchcock; Nitanshu Garg; Michael A. White; Francis Mulholland; Robert K. Poole; David J. Kelly (Environmental Microbiology, 2017)
Summary Campylobacter jejuni , the most frequent cause of food‐borne bacterial gastroenteritis worldwide, is a microaerophile that has to survive high environmental oxygen tensions, adapt to oxygen limitation in the intestine and resist host oxidative attack. Here, oxygen‐dependent changes in C . jejuni physiology were studied at constant growth rate using carbon (serine)‐limited continuous chemostat cultures. We show that a perceived aerobiosis scale can be calibrated by the acetate excretion flux, which becomes zero when metabolism is fully aerobic (100% aerobiosis). Transcriptome changes in a downshift experiment from 150% to 40% aerobiosis revealed many novel oxygen‐regulated genes and highlighted re‐modelling of the electron transport chains. A label‐free proteomic analysis showed that at 40% aerobiosis, many proteins involved in host colonisation (e.g., PorA, CadF, FlpA, CjkT) became more abundant. PorA abundance increased steeply below 100% aerobiosis. In contrast, several citric‐acid cycle enzymes, the peptide transporter CstA, PEB1 aspartate/glutamate transporter, LutABC lactate dehydrogenase and PutA proline dehydrogenase became more abundant with increasing aerobiosis. We also observed a co‐ordinated response of oxidative stress protection enzymes and Fe‐S cluster biogenesis proteins above 100% aerobiosis. Our approaches reveal key virulence factors that respond to restricted oxygen availability and specific transporters and catabolic pathways activated with increasing aerobiosis.

Assessment of the Neuroprotective Effects of Arginine-Rich Protamine Peptides, Poly-Arginine Peptides (R12-Cyclic, R22) and Arginine–Tryptophan-Containing Peptides Following In Vitro Excitotoxicity and/or Permanent Middle Cerebral Artery Occlusion in Rats - Bruno P. Meloni; Diego Milani; Jane L. Cross; Vince W. Clark; Adam B. Edwards; Ryan S. Anderton; David J. Blacker; Neville W. Knuckey (NeuroMolecular Medicine, 2017)

Diversity and Inclusion in Conservation: A Proposal for a Marine Diversity Network - Nicola S. Smith; Isabelle M. Côté; Lourdes Martinez-Estevez; Edward J. Hind-Ozan; Angela L. Quiros; Nathan Johnson; Stephanie J. Green; Leslie Cornick; David Shiffman; Luis Malpica-Cruz; Allison Gleason Besch; Nikita Shiel-Rolle (Frontiers in Marine Science, 2017)

The Significant Surface-Water Connectivity of “Geographically Isolated Wetlands” - Aram J. K. Calhoun; David M. Mushet; Laurie C. Alexander; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Stephen C. Richter; Susan C. Walls (Wetlands, 2017)

The Human Gene Mutation Database: towards a comprehensive repository of inherited mutation data for medical research, genetic diagnosis and next-generation sequencing studies - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Evans; Matthew Hayden; Sally Heywood; Michelle Hussain; Andrew D. Phillips; David N. Cooper (Human Genetics, 2017)

Dose effects of New Zealand blackcurrant on substrate oxidation and physiological responses during prolonged cycling - Matthew David Cook; Stephen David Myers; Mandy Lucinda Gault; Victoria Charlotte Edwards; Mark Elisabeth Theodorus Willems (European Journal of Applied Physiology, 2017)

Markers of physiological stress during exercise under conditions of normoxia, normobaric hypoxia, hypobaric hypoxia, and genuine high altitude - David Richard Woods; John Paul O’Hara; Christopher John Boos; Peter David Hodkinson; Costas Tsakirides; Neil Edward Hill; Darren Jose; Amanda Hawkins; Kelly Phillipson; Antonia Hazlerigg; Nicola Arjomandkhah; Liam Gallagher; et al. (European Journal of Applied Physiology, 2017)

Cerebello-cerebral connectivity in the developing brain - Kay Pieterman; Dafnis Batalle; Jeroen Dudink; J-Donald Tournier; Emer J. Hughes; Madeleine Barnett; Manon J. Benders; A. David Edwards; Freek E. Hoebeek; Serena J. Counsell (Brain Structure and Function, 2017)

Taxonomy of prokaryotic viruses: 2016 update from the ICTV bacterial and archaeal viruses subcommittee - Evelien M. Adriaenssens; Mart Krupovic; Petar Knezevic; Hans-Wolfgang Ackermann; Jakub Barylski; J. Rodney Brister; Martha R. C. Clokie; Siobain Duffy; Bas E. Dutilh; Robert A. Edwards; Francois Enault; Ho Bin Jang; et al. (Archives of Virology, 2017)

High-Speed Laser Image Analysis of Plume Angles for Pressurised Metered Dose Inhalers: The Effect of Nozzle Geometry - Yang Chen; Paul M. Young; Seamus Murphy; David F. Fletcher; Edward Long; David Lewis; Tanya Church; Daniela Traini (AAPS PharmSciTech, 2017)

Sensory and motor cortex function contributes to symptom severity in spinocerebellar ataxia type 6 - Nyeonju Kang; Evangelos A. Christou; Roxana G. Burciu; Jae Woo Chung; Jesse C. DeSimone; Edward Ofori; Tetsuo Ashizawa; Sankarasubramon H. Subramony; David E. Vaillancourt (Brain Structure and Function, 2017)

Source-Sink Dynamics: a Neglected Problem for Landscape-Scale Biodiversity Conservation in the Tropics - James J. Gilroy; David P. Edwards (Current Landscape Ecology Reports, 2017)

By their own devices: invasive Argentine ants have shifted diet without clear aid from symbiotic microbes - Yi Hu; David A. Holway; Piotr Łukasik; Linh Chau; Adam D. Kay; Edward G. LeBrun; Katie A. Miller; Jon G. Sanders; Andrew V. Suarez; Jacob A. Russell (Molecular Ecology, 2017)
The functions and compositions of symbiotic bacterial communities often correlate with host ecology. Yet cause–effect relationships and the order of symbiont vs. host change remain unclear in the face of ancient symbioses and conserved host ecology. Several groups of ants exemplify this challenge, as their low‐nitrogen diets and specialized symbioses appear conserved and ancient. To address whether nitrogen‐provisioning symbionts might be important in the early stages of ant trophic shifts, we studied bacteria from the Argentine ant, Linepithema humile – an invasive species that has transitioned towards greater consumption of sugar‐rich, nitrogen‐poor foods in parts of its introduced range. Bacteria were present at low densities in most L. humile workers, and among those yielding quality 16S rRNA amplicon sequencing data, we found just three symbionts to be common and dominant. Two, a Lactobacillus and an Acetobacteraceae species, were shared between native and introduced populations. The other, a Rickettsia , was found only in two introduced supercolonies. Across an eight‐year period of trophic reduction in one introduced population, we found no change in symbionts, arguing against a relationship between natural dietary change and microbiome composition. Overall, our findings thus argue against major changes in symbiotic bacteria in association with the invasion and trophic shift of L. humile . In addition, genome content from close relatives of the identified symbionts suggests that just one can synthesize most essential amino acids; this bacterium was only modestly abundant in introduced populations, providing little support for a major role of nitrogen‐provisioning symbioses in Argentine ant's dietary shift.

Visualising the relationships between synoptic circulation type and air quality in Sydney, a subtropical coastal‐basin environment - Ningbo Jiang; Yvonne Scorgie; Melissa Hart; Matthew L. Riley; Jagoda Crawford; Paul J. Beggs; Grant C. Edwards; Lisa Chang; David Salter; Giovanni Di Virgilio (International Journal of Climatology, 2017)
Ozone and particle pollution are of concern for the Sydney basin, in particular during warm months (November to March) when pollution levels can exceed national standards. Previous studies on the relationship between synoptic circulation and air quality focused on high pollution days or aggregated air quality conditions over the region as a whole. This study provides both temporal and spatial analyses of the synoptic processes affecting warm‐month ozone and particle pollution in Sydney. A warm‐month synoptic catalogue was developed by applying the self‐organising map method to the NCEP/NCAR geopotential height reanalysis for south‐east Australia. The catalogue was linked to mesoscale meteorological features such as drainage flows and sea breezes, and subsequently to the spatial variability in air quality across the Sydney basin. The typical synoptic types commonly associated with high or low ozone and PM 10 levels, as well as variations in visibility, were identified. The results suggest that, due to Sydney's subtropical coastal‐basin environment, the interaction between meso‐ and synoptic‐scale features determine local air quality conditions in the region, rather than the synoptic conditions alone. Emissions from bushfires appear to have considerable impacts on the synoptic modulation to visibility and PM 10 levels, with such impacts tending to be more at a local scale. In contrast, no comparable impacts were found for ozone pollution. For ozone and visibility, the probability for an exceedance day under some synoptic types varied considerably over time, implying that there might have been a shift in the role of synoptic modulation to local air quality associated with changes in air emissions profiles. This study provides a leap in our understanding of the relationship between synoptic circulation and air quality in a coastal‐basin environment. The results are useful for improving air quality forecasting in Sydney, with the methodology developed readily applicable to similar regions elsewhere.

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Cardiovascular function during supine rest in endurance-trained males with New Zealand blackcurrant: a dose–response study - Matthew David Cook; Stephen David Myers; Mandy Lucinda Gault; Victoria Charlotte Edwards; Mark Elisabeth Theodorus Willems (European Journal of Applied Physiology, 2017)

The city as a refuge for insect pollinators - Damon M. Hall; Gerardo R. Camilo; Rebecca K. Tonietto; Jeff Ollerton; Karin Ahrné; Mike Arduser; John S. Ascher; Katherine C. R. Baldock; Robert Fowler; Gordon Frankie; Dave Goulson; Bengt Gunnarsson; et al. (Conservation Biology, 2017)
Research on urban insect pollinators is changing views on the biological value and ecological importance of cities. The abundance and diversity of native bee species in urban landscapes that are absent in nearby rural lands evidence the biological value and ecological importance of cities and have implications for biodiversity conservation. Lagging behind this revised image of the city are urban conservation programs that historically have invested in education and outreach rather than programs designed to achieve high‐priority species conservation results. We synthesized research on urban bee species diversity and abundance to determine how urban conservation could be repositioned to better align with new views on the ecological importance of urban landscapes. Due to insect pollinators’ relatively small functional requirements—habitat range, life cycle, and nesting behavior—relative to larger mammals, we argue that pollinators put high‐priority and high‐impact urban conservation within reach. In a rapidly urbanizing world, transforming how environmental managers view the city can improve citizen engagement and contribute to the development of more sustainable urbanization.

Raman spectroscopic analysis of the effect of the lichenicolous fungus Xanthoriicola physciae on its lichen host - Howell G.M. Edwards; Mark R.D. Seaward; Tom F. Preece; Susana E. Jorge-Villar; David L. Hawksworth (Symbiosis, 2017)

A novel QTL associated with dwarf bunt resistance in Idaho 444 winter wheat - Jianli Chen; Mary J. Guttieri; Junli Zhang; David Hole; Edward Souza; Blair Goates (Theoretical and Applied Genetics, 2016)

Lysozyme activity of the R uminococcus champanellensis cellulosome - Sarah Moraïs; Darrell W. Cockburn; Yonit Ben‐David; Nicole M. Koropatkin; Eric C. Martens; Sylvia H. Duncan; Harry J. Flint; Itzhak Mizrahi; Edward A. Bayer (Environmental Microbiology, 2016)
Summary Ruminococcus champanellensis is a keystone species in the human gut that produces an intricate cellulosome system of various architectures. A variety of cellulosomal enzymes have been identified, which exhibit a range of hydrolytic activities on lignocellulosic substrates. We describe herein a unique R. champanellensis scaffoldin, ScaK, which is expressed during growth on cellobiose and comprises a cohesin module and a family 25 glycoside hydrolase (GH25). The GH25 is non‐autolytic and exhibits lysozyme‐mediated lytic activity against several bacterial species. Despite the narrow acidic pH curve, the enzyme is active along a temperature range from 2 to 85°C and is stable at very high temperatures for extended incubation periods. The ScaK cohesin was shown to bind selectively to the dockerin of a monovalent scaffoldin (ScaG), thus enabling formation of a cell‐free cellulosome, whereby ScaG interacts with a divalent scaffodin (ScaA) that bears the enzymes either directly or through additional monovalent scaffoldins (ScaC and ScaD). The ScaK cohesin also interacts with the dockerin of a protein comprising multiple Fn3 domains that can potentially promote adhesion to carbohydrates and the bacterial cell surface. A cell‐free cellulosomal GH25 lysozyme may provide a bacterial strategy to both hydrolyze lignocellulose and repel eventual food competitors and/or cheaters.

The emergence of molecular profiling and omics techniques in seagrass biology; furthering our understanding of seagrasses - Peter A. Davey; Mathieu Pernice; Gaurav Sablok; Anthony Larkum; Huey Tyng Lee; Agnieszka Golicz; David Edwards; Rudy Dolferus; Peter Ralph (Functional & Integrative Genomics, 2016)

Intramuscular MAPK signaling following high volume and high intensity resistance exercise protocols in trained men - Adam M. Gonzalez; Jay R. Hoffman; Jeremy R. Townsend; Adam R. Jajtner; Carleigh H. Boone; Kyle S. Beyer; Kayla M. Baker; Adam J. Wells; Gerald T. Mangine; Edward H. Robinson; David D. Church; Leonardo P. Oliveira; et al. (European Journal of Applied Physiology, 2016)

Biogeographic gradients in ecosystem processes of the invasive ecosystem engineer Phragmites australis - A. Randall Hughes; Forest R. Schenck; Jeanne Bloomberg; Torrance C. Hanley; Dongmei Feng; Tarik C. Gouhier; R. Edward Beighley; David L. Kimbro (Biological Invasions, 2016)

Parametric Modeling of the Mouse Left Ventricular Myocardial Fiber Structure - Samer S. Merchant; Arnold David Gomez; James L. Morgan; Edward W. Hsu (Annals of Biomedical Engineering, 2016)

Prioritization of knowledge‐needs to achieve best practices for bottom trawling in relation to seabed habitats - Michel J Kaiser; Ray Hilborn; Simon Jennings; Ricky Amaroso; Michael Andersen; Kris Balliet; Eric Barratt; Odd A Bergstad; Stephen Bishop; Jodi L Bostrom; Catherine Boyd; Eduardo A Bruce; et al. (Fish and Fisheries, 2016)
Management and technical approaches that achieve a sustainable level of fish production while at the same time minimizing or limiting the wider ecological effects caused through fishing gear contact with the seabed might be considered to be ‘best practice’. To identify future knowledge‐needs that would help to support a transition towards the adoption of best practices for trawling, a prioritization exercise was undertaken with a group of 39 practitioners from the seafood industry and management, and 13 research scientists who have an active research interest in bottom‐trawl and dredge fisheries. A list of 108 knowledge‐needs related to trawl and dredge fisheries was developed in conjunction with an ‘expert task force’. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge‐need. The top 25 knowledge‐needs are presented, as scored separately by practitioners and scientists. There was considerable consistency in the priorities identified by these two groups. The top priority knowledge‐need to improve current understanding on the distribution and extent of different habitat types also reinforced the concomitant need for the provision and access to data on the spatial and temporal distribution of all forms of towed bottom‐fishing activities. Many of the other top 25 knowledge‐needs concerned the evaluation of different management approaches or implementation of different fishing practices, particularly those that explore trade‐offs between effects of bottom trawling on biodiversity and ecosystem services and the benefits of fish production as food.

Mapping adipose and muscle tissue expression quantitative trait loci in African Americans to identify genes for type 2 diabetes and obesity - Satria P. Sajuthi; Neeraj K. Sharma; Jeff W. Chou; Nicholette D. Palmer; David R. McWilliams; John Beal; Mary E. Comeau; Lijun Ma; Jorge Calles-Escandon; Jamehl Demons; Samantha Rogers; Kristina Cherry; et al. (Human Genetics, 2016)

Persistent CSF but not plasma HIV RNA is associated with increased risk of new-onset moderate-to-severe depressive symptoms; a prospective cohort study - Edward R. Hammond; Rosa M. Crum; Glenn J. Treisman; Shruti H. Mehta; David B. Clifford; Ronald J. Ellis; Benjamin B. Gelman; Igor Grant; Scott L. Letendre; Christina M. Marra; Susan Morgello; David M. Simpson; et al. (Journal of NeuroVirology, 2016)

Variability in the response of amphipods and macroinvertebrate assemblage structure to prolonged drought in forested upland streams - Samantha J. Imberger; Christopher J. Walsh; Edward Tsyrlin; David G. Kerr; Monica Tewman (Biodiversity and Conservation, 2016)

Genomic insights into the carbohydrate catabolism of Cairneyella variabilis gen. nov. sp. nov., the first reports from a genome of an ericoid mycorrhizal fungus from the southern hemisphere - David J. Midgley; Carly P. Rosewarne; Paul Greenfield; Dongmei Li; Cassandra J. Vockler; Catherine J. Hitchcock; Nicole A. Sawyer; Robyn Brett; Jacqueline Edwards; John I. Pitt; Nai Tran-Dinh (Mycorrhiza, 2016)

The impact of tropical forest logging and oil palm agriculture on the soil microbiome - Binu M. Tripathi; David P. Edwards; Lucas William Mendes; Mincheol Kim; Ke Dong; Hyoki Kim; Jonathan M. Adams (Molecular Ecology, 2016)
Selective logging and forest conversion to oil palm agriculture are rapidly altering tropical forests. However, functional responses of the soil microbiome to these land‐use changes are poorly understood. Using 16S rRNA gene and shotgun metagenomic sequencing, we compared composition and functional attributes of soil biota between unlogged, once‐logged and twice‐logged rainforest, and areas converted to oil palm plantations in Sabah, Borneo. Although there was no significant effect of logging history, we found a significant difference between the taxonomic and functional composition of both primary and logged forests and oil palm. Oil palm had greater abundances of genes associated with DNA , RNA , protein metabolism and other core metabolic functions, but conversely, lower abundance of genes associated with secondary metabolism and cell–cell interactions, indicating less importance of antagonism or mutualism in the more oligotrophic oil palm environment. Overall, these results show a striking difference in taxonomic composition and functional gene diversity of soil microorganisms between oil palm and forest, but no significant difference between primary forest and forest areas with differing logging history. This reinforces the view that logged forest retains most features and functions of the original soil community. However, networks based on strong correlations between taxonomy and functions showed that network complexity is unexpectedly increased due to both logging and oil palm agriculture, which suggests a pervasive effect of both land‐use changes on the interaction of soil microbes.

Search for an astronomical site in Kenya (SASKYA) using climate reanalyses and high-resolution meteorological model data - Edward Graham; Richard Vaughan; David A. H. Buckley; Koi Tirima (Theoretical and Applied Climatology, 2016)

Taxonomy of prokaryotic viruses: update from the ICTV bacterial and archaeal viruses subcommittee - Mart Krupovic; Bas E. Dutilh; Evelien M. Adriaenssens; Johannes Wittmann; Finn K. Vogensen; Mathew B. Sullivan; Janis Rumnieks; David Prangishvili; Rob Lavigne; Andrew M. Kropinski; Jochen Klumpp; Annika Gillis; et al. (Archives of Virology, 2016)

Biophysical controls on dissolved organic carbon concentrations of Alaskan coastal temperate rainforest streams - David V. D’Amore; Rick T. Edwards; Frances E. Biles (Aquatic Sciences, 2016)

Compositional Analysis of Biomass Reference Materials: Results from an Interlaboratory Study - David W. Templeton; Edward J. Wolfrum; James H. Yen; Katherine E. Sharpless (BioEnergy Research, 2016)

Soil microorganisms behave like macroscopic organisms: patterns in the global distribution of soil euglyphid testate amoebae - Enrique Lara; Ludovic Roussel‐Delif; Bertrand Fournier; David M. Wilkinson; Edward A. D. Mitchell (Journal of Biogeography, 2016)
Aim Patterns of α‐ and β‐diversity of soil protist communities and the factors that shape them remain largely unknown. We undertook a world‐wide survey of forest litter to investigate the patterns of diversity in a group of testate amoebae. We aimed to assess: (1) whether there is a latitudinal gradient in α‐diversity, and (2) whether β‐diversity was correlated solely with environmental factors commonly used in soil biology research or if it was also independently explained by geographical barriers. Location World‐wide. Methods We studied the diversity of Euglyphida, a common group of testate amoebae, in 35 samples of forest litter and moss samples from a global survey, using small subunit rRNA gene sequences. We assessed the relationship between sample α‐diversity and latitude using generalized additive models ( GAM ). Furthermore, we determined the relationships between community composition and geographical models (distance‐based Moran's Eigenvector Maps – db‐ MEM ) using Generalized UniFrac distances ( GU niFrac). We also investigated the relationship between individual measured soil parameters, WorldClim data and diversity (alpha plus beta) using both raw data and synthetic variables obtained through principal components analysis. Results We recorded 245 phylotypes belonging to 6 out of 7 known Euglyphida families, plus four novel deep clades. Euglyphid α‐diversity was positively correlated with temperature and negatively with latitude and litter C/N ratio. Euglyphida community structure was correlated with the spatial eigenvector Db‐ MEM 31, independently of all measured environmental variables. Db‐ MEM 31 corresponds to a natural barrier constituted by the Northern Hemisphere desert belt. Beta diversity was correlated with other environmental variables, such as pH , isothermality and temperature in the coldest month of the year. Main conclusions Soil euglyphid α‐diversity displays a latitudinal gradient, and β‐diversity is not only correlated with climatic and physicochemical parameters but also with geographical barriers. Such patterns of diversity were until recently believed to be characteristic only for macroscopic organisms.

Developing a Field-Tested Wetland Indicator Rating for Blue Spruce (Picea Pungens) in the Southern Rocky Mountains - Edward A. Gage; David J. Cooper; Betsy Bultema; Cristina McKernan; Robert Lichvar (Wetlands, 2016)

A bio-economic ‘war game’ model to simulate plant disease incursions and test response strategies at the landscape scale - David C. Cook; Jean-Philippe Aurambout; Oscar N. Villalta; Shuang Liu; Jacqueline Edwards; Savi Maharaj (Food Security, 2016)

Enzymatic profiling of cellulosomal enzymes from the human gut bacterium, R uminococcus champanellensis , reveals a fine‐tuned system for cohesin‐dockerin recognition - Sarah Moraïs; Yonit Ben David; Lizi Bensoussan; Sylvia H. Duncan; Nicole M. Koropatkin; Eric C. Martens; Harry J. Flint; Edward A. Bayer (Environmental Microbiology, 2016)
Summary R uminococcus champanellensis is considered a keystone species in the human gut that degrades microcrystalline cellulose efficiently and contains the genetic elements necessary for cellulosome production. The basic elements of its cellulosome architecture, mainly cohesin and dockerin modules from scaffoldins and enzyme‐borne dockerins, have been characterized recently. In this study, we cloned, expressed and characterized all of the glycoside hydrolases that contain a dockerin module. Among the 25 enzymes, 10 cellulases, 4 xylanases, 3 mannanases, 2 xyloglucanases, 2 arabinofuranosidases, 2 arabinanases and one β‐glucanase were assessed for their comparative enzymatic activity on their respective substrates. The dockerin specificities of the enzymes were examined by ELISA , and 80 positives out of 525 possible interactions were detected. Our analysis reveals a fine‐tuned system for cohesin–dockerin specificity and the importance of diversity among the cohesin–dockerin sequences. Our results imply that cohesin–dockerin pairs are not necessarily assembled at random among the same specificity types, as generally believed for other cellulosome‐producing bacteria, but reveal a more organized cellulosome architecture. Moreover, our results highlight the importance of the cellulosome paradigm for cellulose and hemicellulose degradation by R . champanellensis in the human gut.

Metformin and prostate cancer mortality: a meta-analysis - Konrad H. Stopsack; David R. Ziehr; Jennifer R. Rider; Edward L. Giovannucci (Cancer Causes & Control, 2016)

Enigmatic spheres from the Upper Triassic Lockatong Formation, Newark Basin of eastern Pennsylvania: evidence for microbial activity in marginal-lacustrine strandline deposits - Edward L. Simpson; David L. Fillmore; Michael J. Szajna; Emily Bogner; Margariete G. Malenda; Kelsey M. Livingston; Brian Hartline (Palaeobiodiversity and Palaeoenvironments, 2015)

Differences in Ecosystem Carbon Distribution and Nutrient Cycling Linked to Forest Tree Species Composition in a Mid-Successional Boreal Forest - April M. Melvin; Michelle C. Mack; Jill F. Johnstone; A. David McGuire; Helene Genet; Edward A. G. Schuur (Ecosystems, 2015)

Identification of milling and baking quality QTL in multiple soft wheat mapping populations - Antonio Cabrera; Mary Guttieri; Nathan Smith; Edward Souza; Anne Sturbaum; Duc Hua; Carl Griffey; Marla Barnett; Paul Murphy; Herb Ohm; Jim Uphaus; Mark Sorrells; et al. (Theoretical and Applied Genetics, 2015)

Defining adult bonefish (Albula vulpes) movement corridors around Grand Bahama in the Bahamian Archipelago - Karen J. Murchie; Aaron D. Shultz; Jeffrey A. Stein; Steven J. Cooke; Justin Lewis; Jason Franklin; Greg Vincent; Edward J. Brooks; Julie E. Claussen; David P. Philipp (Environmental Biology of Fishes, 2015)

Seascape drivers of M acrocystis pyrifera population genetic structure in the northeast P acific - Mattias L. Johansson; Filipe Alberto; Daniel C. Reed; Peter T. Raimondi; Nelson C. Coelho; Mary A. Young; Patrick T. Drake; Christopher A. Edwards; Kyle Cavanaugh; Jorge Assis; Lydia B. Ladah; Tom W. Bell; et al. (Molecular Ecology, 2015)
At small spatial and temporal scales, genetic differentiation is largely controlled by constraints on gene flow, while genetic diversity across a species' distribution is shaped on longer temporal and spatial scales. We assess the hypothesis that oceanographic transport and other seascape features explain different scales of genetic structure of giant kelp, M acrocystis pyrifera . We followed a hierarchical approach to perform a microsatellite‐based analysis of genetic differentiation in M acrocystis across its distribution in the northeast P acific. We used seascape genetic approaches to identify large‐scale biogeographic population clusters and investigate whether they could be explained by oceanographic transport and other environmental drivers. We then modelled population genetic differentiation within clusters as a function of oceanographic transport and other environmental factors. Five geographic clusters were identified: A laska/ C anada, central C alifornia, continental S anta B arbara, C alifornia C hannel I slands and mainland southern C alifornia/ B aja C alifornia peninsula. The strongest break occurred between central and southern C alifornia, with mainland S anta B arbara sites forming a transition zone between the two. Breaks between clusters corresponded approximately to previously identified biogeographic breaks, but were not solely explained by oceanographic transport. An isolation‐by‐environment ( IBE ) pattern was observed where the northern and southern C hannel I slands clustered together, but not with closer mainland sites, despite the greater distance between them. The strongest environmental association with this IBE pattern was observed with light extinction coefficient, which extends suitable habitat to deeper areas. Within clusters, we found support for previous results showing that oceanographic connectivity plays an important role in the population genetic structure of M acrocystis in the Northern hemisphere.

The novel mu-opioid antagonist, GSK1521498, reduces ethanol consumption in C57BL/6J mice - Tamzin L. Ripley; Sandra Sanchez-Roige; Edward T. Bullmore; Manolo Mugnaini; Kay Maltby; Sam R. Miller; David R. Wille; Pradeep Nathan; David N. Stephens (Psychopharmacology, 2015)

The Effect of Active Pharmaceutical Ingredients on Aerosol Electrostatic Charges from Pressurized Metered Dose Inhalers - Yang Chen; Paul M. Young; David F. Fletcher; Hak Kim Chan; Edward Long; David Lewis; Tanya Church; Daniela Traini (Pharmaceutical Research, 2015)

Science–policy processes for transboundary water governance - Derek Armitage; Rob C. de Loë; Michelle Morris; Tom W. D. Edwards; Andrea K. Gerlak; Roland I. Hall; Dave Huitema; Ray Ison; David Livingstone; Glen MacDonald; Naho Mirumachi; Ryan Plummer; et al. (Ambio, 2015)

Would protecting tropical forest fragments provide carbon and biodiversity cobenefits under REDD +? - Luiz Fernando S. Magnago; Ainhoa Magrach; William F. Laurance; Sebastião V. Martins; João Augusto A. Meira‐Neto; Marcelo Simonelli; David P. Edwards (Global Change Biology, 2015)
Tropical forests store vast amounts of carbon and are the most biodiverse terrestrial habitats, yet they are being converted and degraded at alarming rates. Given global shortfalls in the budgets required to prevent carbon and biodiversity loss, we need to seek solutions that simultaneously address both issues. Of particular interest are carbon‐based payments under the Reducing Emissions from Deforestation and Forest Degradation ( REDD +) mechanism to also conserve biodiversity at no additional cost. One potential is for REDD + to protect forest fragments, especially within biomes where contiguous forest cover has diminished dramatically, but we require empirical tests of the strength of any carbon and biodiversity cobenefits in such fragmented systems. Using the globally threatened Atlantic Forest landscape, we measured above‐ground carbon stocks within forest fragments spanning 13 to 23 442 ha in area and with different degrees of isolation. We related these stocks to tree community structure and to the richness and abundance of endemic and IUCN Red‐listed species. We found that increasing fragment size has a positive relationship with above‐ground carbon stock and with abundance of IUCN Red‐listed species and tree community structure. We also found negative relationships between distance from large forest block and tree community structure, endemic species richness and abundance, and IUCN Red‐listed species abundance. These resulted in positive congruence between carbon stocks and Red‐listed species, and the abundance and richness of endemic species, demonstrating vital cobenefits. As such, protecting forest fragments in hotspots of biodiversity, particularly larger fragments and those closest to sources, offers important carbon and biodiversity cobenefits. More generally, our results suggest that macroscale models of cobenefits under REDD + have likely overlooked key benefits at small scales, indicating the necessity to apply models that include finer‐grained assessments in fragmented landscapes rather than using averaged coarse‐grained cells.

Ruminococcal cellulosome systems from rumen to human - Yonit Ben David; Bareket Dassa; Ilya Borovok; Raphael Lamed; Nicole M. Koropatkin; Eric C. Martens; Bryan A. White; Annick Bernalier‐Donadille; Sylvia H. Duncan; Harry J. Flint; Edward A. Bayer; Sarah Moraïs (Environmental Microbiology, 2015)
Summary A cellulolytic fiber‐degrading bacterium, R uminococcus champanellensis , was isolated from human faecal samples, and its genome was recently sequenced. Bioinformatic analysis of the R . champanellensis genome revealed numerous cohesin and dockerin modules, the basic elements of the cellulosome, and manual sequencing of partially sequenced genomic segments revealed two large tandem scaffoldin‐coding genes that form part of a gene cluster. Representative R . champanellensis dockerins were tested against putative cohesins, and the results revealed three different cohesin–dockerin binding profiles which implied two major types of cellulosome architectures: (i) an intricate cell‐bound system and (ii) a simplistic cell‐free system composed of a single cohesin‐containing scaffoldin. The cell‐bound system can adopt various enzymatic architectures, ranging from a single enzyme to a large enzymatic complex comprising up to 11 enzymes. The variety of cellulosomal components together with adaptor proteins may infer a very tight regulation of its components. The cellulosome system of the human gut bacterium R . champanellensis closely resembles that of the bovine rumen bacterium R uminococcus flavefaciens . The two species contain orthologous gene clusters comprising fundamental components of cellulosome architecture. Since R . champanellensis is the only human colonic bacterium known to degrade crystalline cellulose, it may thus represent a keystone species in the human gut.

The Influence of Land Cover, Vertical Structure, and Socioeconomic Factors on Outdoor Water Use in a Western US City - Edward Gage; David J. Cooper (Water Resources Management, 2015)

Increasing In-Row Spacing Enhances Potato Virus Y and Potato Leafroll Virus Spread in Potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale; Ian MacRae (American Journal of Potato Research, 2015)

Chromosomal genomics facilitates fine mapping of a Russian wheat aphid resistance gene - Helena Staňková; Miroslav Valárik; Nora L. V. Lapitan; Paul J. Berkman; Jacqueline Batley; David Edwards; Ming-Cheng Luo; Zuzana Tulpová; Marie Kubaláková; Nils Stein; Jaroslav Doležel; Hana Šimková (Theoretical and Applied Genetics, 2015)

The contribution of trees to ecosystem methane emissions in a temperate forested wetland - Sunitha R. Pangala; Edward R.C. Hornibrook; David J. Gowing; Vincent Gauci (Global Change Biology, 2015)
Wetland‐adapted trees are known to transport soil‐produced methane ( CH 4 ), an important greenhouse gas to the atmosphere, yet seasonal variations and controls on the magnitude of tree‐mediated CH 4 emissions remain unknown for mature forests. We examined the spatial and temporal variability in stem CH 4 emissions in situ and their controls in two wetland‐adapted tree species ( Alnus glutinosa and Betula pubescens ) located in a temperate forested wetland. Soil and herbaceous plant‐mediated CH 4 emissions from hollows and hummocks also were measured, thus enabling an estimate of contributions from each pathway to total ecosystem flux. Stem CH 4 emissions varied significantly between the two tree species, with Alnus glutinosa displaying minimal seasonal variations, while substantial seasonal variations were observed in Betula pubescens . Trees from each species emitted similar quantities of CH 4 from their stems regardless of whether they were situated in hollows or hummocks. Soil temperature and pore‐water CH 4 concentrations best explained annual variability in stem emissions, while wood‐specific density and pore‐water CH 4 concentrations best accounted for between‐species variations in stem CH 4 emission. Our study demonstrates that tree‐mediated CH 4 emissions contribute up to 27% of seasonal ecosystem CH 4 flux in temperate forested wetland, with the largest relative contributions occurring in spring and winter. Tree‐mediated CH 4 emissions currently are not included in trace gas budgets of forested wetland. Further work is required to quantify and integrate this transport pathway into CH 4 inventories and process‐based models.

A pan‐Arctic synthesis of CH 4 and CO 2 production from anoxic soil incubations - Claire C. Treat; Susan M. Natali; Jessica Ernakovich; Colleen M. Iversen; Massimo Lupascu; Anthony David McGuire; Richard J. Norby; Taniya Roy Chowdhury; Andreas Richter; Hana Šantrůčková; Christina Schädel; Edward A. G. Schuur; et al. (Global Change Biology, 2015)
Permafrost thaw can alter the soil environment through changes in soil moisture, frequently resulting in soil saturation, a shift to anaerobic decomposition, and changes in the plant community. These changes, along with thawing of previously frozen organic material, can alter the form and magnitude of greenhouse gas production from permafrost ecosystems. We synthesized existing methane (CH 4 ) and carbon dioxide (CO 2 ) production measurements from anaerobic incubations of boreal and tundra soils from the geographic permafrost region to evaluate large‐scale controls of anaerobic CO 2 and CH 4 production and compare the relative importance of landscape‐level factors (e.g., vegetation type and landscape position), soil properties (e.g., pH, depth, and soil type), and soil environmental conditions (e.g., temperature and relative water table position). We found fivefold higher maximum CH 4 production per gram soil carbon from organic soils than mineral soils. Maximum CH 4 production from soils in the active layer (ground that thaws and refreezes annually) was nearly four times that of permafrost per gram soil carbon, and CH 4 production per gram soil carbon was two times greater from sites without permafrost than sites with permafrost. Maximum CH 4 and median anaerobic CO 2 production decreased with depth, while CO 2 :CH 4 production increased with depth. Maximum CH 4 production was highest in soils with herbaceous vegetation and soils that were either consistently or periodically inundated. This synthesis identifies the need to consider biome, landscape position, and vascular/moss vegetation types when modeling CH 4 production in permafrost ecosystems and suggests the need for longer‐term anaerobic incubations to fully capture CH 4 dynamics. Our results demonstrate that as climate warms in arctic and boreal regions, rates of anaerobic CO 2 and CH 4 production will increase, not only as a result of increased temperature, but also from shifts in vegetation and increased ground saturation that will accompany permafrost thaw.

Geographically Isolated Wetlands: Rethinking a Misnomer - David M. Mushet; Aram J. K. Calhoun; Laurie C. Alexander; Matthew J. Cohen; Edward S. DeKeyser; Laurie Fowler; Charles R. Lane; Megan W. Lang; Mark C. Rains; Susan C. Walls (Wetlands, 2015)

High-resolution skim genotyping by sequencing reveals the distribution of crossovers and gene conversions in Cicer arietinum and Brassica napus - Philipp E. Bayer; Pradeep Ruperao; Annaliese S. Mason; Jiri Stiller; Chon-Kit Kenneth Chan; Satomi Hayashi; Yan Long; Jinling Meng; Tim Sutton; Paul Visendi; Rajeev K. Varshney; Jacqueline Batley; et al. (Theoretical and Applied Genetics, 2015)

An ant–plant by-product mutualism is robust to selective logging of rain forest and conversion to oil palm plantation - Tom M. Fayle; David P. Edwards; William A. Foster; Kalsum M. Yusah; Edgar C. Turner (Oecologia, 2015)

Impacts on the metabolome of down-regulating polyphenol oxidase in potato tubers - Louise Vida Traill Shepherd; Colin James Alexander; Christine Anne Hackett; Diane McRae; Julia Anne Sungurtas; Susan Ramsay Verrall; Jennifer Anne Morris; Peter Edward Hedley; David Rockhold; William Belknap; Howard Vivian Davies (Transgenic Research, 2015)

Climate change implications in the northern coastal temperate rainforest of North America - Colin S. Shanley; Sanjay Pyare; Michael I. Goldstein; Paul B. Alaback; David M. Albert; Colin M. Beier; Todd J. Brinkman; Rick T. Edwards; Eran Hood; Andy MacKinnon; Megan V. McPhee; Trista M. Patterson; et al. (Climatic Change, 2015)

Females Exceed Males in Mercury Concentrations of Burbot Lota lota - Charles P. Madenjian; Martin A. Stapanian; Peter A. Cott; David P. Krabbenhoft; William H. Edwards; Lynn M. Ogilvie; Justin G. Mychek-Londer; John F. DeWild (Archives of Environmental Contamination and Toxicology, 2015)

The Effect of Actuator Nozzle Designs on the Electrostatic Charge Generated in Pressurised Metered Dose Inhaler Aerosols - Yang Chen; Paul M. Young; David F. Fletcher; Hak Kim Chan; Edward Long; David Lewis; Tanya Church; Daniela Traini (Pharmaceutical Research, 2015)

Microbial taxonomy in the post-genomic era: Rebuilding from scratch? - Cristiane C. Thompson; Gilda R. Amaral; Mariana Campeão; Robert A. Edwards; Martin F. Polz; Bas E. Dutilh; David W. Ussery; Tomoo Sawabe; Jean Swings; Fabiano L. Thompson (Archives of Microbiology, 2015)

Minimizing the biodiversity impact of Neotropical oil palm development - James J. Gilroy; Graham W. Prescott; Johann S. Cardenas; Pamela González del Pliego Castañeda; Andrés Sánchez; Luis E. Rojas‐Murcia; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2015)
Oil palm agriculture is rapidly expanding in the Neotropics, at the expense of a range of natural and seminatural habitats. A key question is how this expansion should be managed to reduce negative impacts on biodiversity. Focusing on the Llanos of Colombia, a mixed grassland–forest system identified as a priority zone for future oil palm development, we survey communities of ants, dung beetles, birds and herpetofauna occurring in oil palm plantations and the other principal form of agriculture in the region – improved cattle pasture – together with those of surrounding natural forests. We show that oil palm plantations have similar or higher species richness across all four taxonomic groups than improved pasture. For dung beetles, species richness in oil palm was equal to that of forest, whereas the other three taxa had highest species richness in forests. Hierarchical modelling of species occupancy probabilities indicated that oil palm plantations supported a higher proportion of species characteristic of forests than did cattle pastures. Across the bird community, occupancy probabilities within oil palm were positively influenced by increasing forest cover in a surrounding 250 m radius, whereas surrounding forest cover did not strongly influence the occurrence of other taxonomic groups in oil palm. Overall, our results suggest that the conversion of existing improved pastures to oil palm has limited negative impacts on biodiversity. As such, existing cattle pastures of the Colombian Llanos could offer a key opportunity to meet governmental targets for oil palm development without incurring significant biodiversity costs. Our results also highlight the value of preserving remnant forests within these agricultural landscapes, protecting high biodiversity and exporting avian ‘spill‐over’ effects into oil palm plantations.

Effect of scale on trait predictors of species responses to agriculture - James J. Gilroy; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Conservation Biology, 2015)
Species persistence in human‐altered landscapes can depend on factors operating at multiple spatial scales. To understand anthropogenic impacts on biodiversity, it is useful to examine relationships between species traits and their responses to land‐use change. A key knowledge gap concerns whether these relationships vary depending on the scale of response under consideration. We examined how local‐ and large‐scale habitat variables influence the occupancy dynamics of a bird community in cloud forest zones in the Colombian Chocó‐Andes. Using data collected across a continuum of forest and agriculture, we examined which traits best predict species responses to local variation in farmland and which traits best predict species responses to isolation from contiguous forest. Global range size was a strong predictor of species responses to agriculture at both scales; widespread species were less likely to decline as local habitat cover decreased and as distance from forest increased. Habitat specialization was a strong predictor of species responses only at the local scale. Open‐habitat species were particularly likely to increase as pasture increased, but they were relatively insensitive to variation in distance to forest. Foraging plasticity and flocking behavior were strong predictors of species responses to distance from forest, but not their responses to local habitat. Species with lower plasticity in foraging behaviors and obligate flock‐following species were more likely to decline as distance from contiguous forest increased. For species exhibiting these latter traits, persistence in tropical landscapes may depend on the protection of larger contiguous blocks of forest, rather than the integration of smaller‐scale woodland areas within farmland. Species listed as threatened or near threatened on the International Union for Conservation of Nature Red List were also more likely to decline in response to both local habitat quality and isolation from forest relative to least‐concern species, underlining the importance of contiguous forests for threatened taxa.

Real-Time Mobile Detection of Drug Use with Wearable Biosensors: A Pilot Study - Stephanie Carreiro; David Smelson; Megan Ranney; Keith J. Horvath; R. W. Picard; Edwin D. Boudreaux; Rashelle Hayes; Edward W. Boyer (Journal of Medical Toxicology, 2015)

Gene loss in the fungal canola pathogen Leptosphaeria maculans - Agnieszka A. Golicz; Paula A. Martinez; Manuel Zander; Dhwani A. Patel; Angela P. Van De Wouw; Paul Visendi; Timothy L. Fitzgerald; David Edwards; Jacqueline Batley (Functional & Integrative Genomics, 2015)

Design Control for Clinical Translation of 3D Printed Modular Scaffolds - Scott J. Hollister; Colleen L. Flanagan; David A. Zopf; Robert J. Morrison; Hassan Nasser; Janki J. Patel; Edward Ebramzadeh; Sophia N. Sangiorgio; Matthew B. Wheeler; Glenn E. Green (Annals of Biomedical Engineering, 2015)

Tolerance of wheat to vegetative stage soil waterlogging is conditioned by both constitutive and adaptive QTL - Diana C. Ballesteros; R. Esten Mason; Christopher K. Addison; M. Andrea Acuña; M. Nelly Arguello; Nithya Subramanian; Randall Galen Miller; Haley Sater; Edward E. Gbur; David Miller; Carl A. Griffey; Marla D. Barnett; et al. (Euphytica, 2015)

Evidence‐based conservation: reply to Tepedino et al. - Gretchen Lebuhn; Sam Droege; Edward F. Connor; Barbara Gemmill‐Herren; Simon G. Potts; Robert L. Minckley; Robert P. Jean; Emanuel Kula; David W. Roubik; Karen W. Wright; Gordon Frankie; Frank Parker (Conservation Biology, 2015)

Use of structured expert judgment to forecast invasions by bighead and silver carp in Lake Erie - Marion E. Wittmann; Roger M. Cooke; John D. Rothlisberger; Edward S. Rutherford; Hongyan Zhang; Doran M. Mason; David M. Lodge (Conservation Biology, 2015)
Identifying which nonindigenous species will become invasive and forecasting the damage they will cause is difficult and presents a significant problem for natural resource management. Often, the data or resources necessary for ecological risk assessment are incomplete or absent, leaving environmental decision makers ill equipped to effectively manage valuable natural resources. Structured expert judgment (SEJ) is a mathematical and performance‐based method of eliciting, weighting, and aggregating expert judgments. In contrast to other methods of eliciting and aggregating expert judgments (where, for example, equal weights may be assigned to experts), SEJ weights each expert on the basis of his or her statistical accuracy and informativeness through performance measurement on a set of calibration variables. We used SEJ to forecast impacts of nonindigenous Asian carp ( Hypophthalmichthys spp.) in Lake Erie, where it is believed not to be established. Experts quantified Asian carp biomass, production, and consumption and their impact on 4 fish species if Asian carp were to become established. According to experts, in Lake Erie Asian carp have the potential to achieve biomass levels that are similar to the sum of biomasses for several fishes that are harvested commercially or recreationally. However, the impact of Asian carp on the biomass of these fishes was estimated by experts to be small, relative to long term average biomasses, with little uncertainty. Impacts of Asian carp in tributaries and on recreational activities, water quality, or other species were not addressed. SEJ can be used to quantify key uncertainties of invasion biology and also provide a decision‐support tool when the necessary information for natural resource management and policy is not available. El Uso de Juicio Experto Estructurado para Predecir Invasiones de Carpas Asiáticas en el Lago Erie

Risks of large-scale use of systemic insecticides to ecosystem functioning and services - Madeleine Chagnon; David Kreutzweiser; Edward A.D. Mitchell; Christy A. Morrissey; Dominique A. Noome; Jeroen P. Van der Sluijs (Environmental Science and Pollution Research, 2015)

Operationalizing resilience for adaptive coral reef management under global environmental change - Kenneth R.N. Anthony; Paul A. Marshall; Ameer Abdulla; Roger Beeden; Chris Bergh; Ryan Black; C. Mark Eakin; Edward T. Game; Margaret Gooch; Nicholas A.J. Graham; Alison Green; Scott F. Heron; et al. (Global Change Biology, 2015)
Cumulative pressures from global climate and ocean change combined with multiple regional and local‐scale stressors pose fundamental challenges to coral reef managers worldwide. Understanding how cumulative stressors affect coral reef vulnerability is critical for successful reef conservation now and in the future. In this review, we present the case that strategically managing for increased ecological resilience (capacity for stress resistance and recovery) can reduce coral reef vulnerability (risk of net decline) up to a point. Specifically, we propose an operational framework for identifying effective management levers to enhance resilience and support management decisions that reduce reef vulnerability. Building on a system understanding of biological and ecological processes that drive resilience of coral reefs in different environmental and socio‐economic settings, we present an Adaptive Resilience‐Based management ( ARBM ) framework and suggest a set of guidelines for how and where resilience can be enhanced via management interventions. We argue that press‐type stressors (pollution, sedimentation, overfishing, ocean warming and acidification) are key threats to coral reef resilience by affecting processes underpinning resistance and recovery, while pulse‐type (acute) stressors (e.g. storms, bleaching events, crown‐of‐thorns starfish outbreaks) increase the demand for resilience. We apply the framework to a set of example problems for Caribbean and Indo‐Pacific reefs. A combined strategy of active risk reduction and resilience support is needed, informed by key management objectives, knowledge of reef ecosystem processes and consideration of environmental and social drivers. As climate change and ocean acidification erode the resilience and increase the vulnerability of coral reefs globally, successful adaptive management of coral reefs will become increasingly difficult. Given limited resources, on‐the‐ground solutions are likely to focus increasingly on actions that support resilience at finer spatial scales, and that are tightly linked to ecosystem goods and services.

Fire in Australian savannas: from leaf to landscape - Jason Beringer; Lindsay B. Hutley; David Abramson; Stefan K. Arndt; Peter Briggs; Mila Bristow; Josep G. Canadell; Lucas A. Cernusak; Derek Eamus; Andrew C. Edwards; Bradley J. Evans; Benedikt Fest; et al. (Global Change Biology, 2015)
Savanna ecosystems comprise 22% of the global terrestrial surface and 25% of Australia (almost 1.9 million km 2 ) and provide significant ecosystem services through carbon and water cycles and the maintenance of biodiversity. The current structure, composition and distribution of Australian savannas have coevolved with fire, yet remain driven by the dynamic constraints of their bioclimatic niche. Fire in Australian savannas influences both the biophysical and biogeochemical processes at multiple scales from leaf to landscape. Here, we present the latest emission estimates from Australian savanna biomass burning and their contribution to global greenhouse gas budgets. We then review our understanding of the impacts of fire on ecosystem function and local surface water and heat balances, which in turn influence regional climate. We show how savanna fires are coupled to the global climate through the carbon cycle and fire regimes. We present new research that climate change is likely to alter the structure and function of savannas through shifts in moisture availability and increases in atmospheric carbon dioxide, in turn altering fire regimes with further feedbacks to climate. We explore opportunities to reduce net greenhouse gas emissions from savanna ecosystems through changes in savanna fire management.

Erosion rates as a potential bottom‐up control of forest structural characteristics in the Sierra Nevada Mountains - David T. Milodowski; Simon M. Mudd; Edward T. A. Mitchard (Ecology, 2015)
The physical characteristics of landscapes place fundamental constraints on vegetation growth and ecosystem function. In actively eroding landscapes, many of these characteristics are controlled by long‐term erosion rates: increased erosion rates generate steeper topography and reduce the depth and extent of weathering, limiting moisture storage capacity and impacting nutrient availability. Despite the potentially important bottom‐up control that erosion rates place on substrate characteristics, the relationship between the two is largely unexplored. We investigate spatial variations in aboveground biomass (AGB) across a structurally diverse mixed coniferous/deciduous forest with an order of magnitude erosion‐rate gradient in the Northern Californian Sierra Nevada, USA, using high resolution LiDAR data and field plots. Mean basin slope, a proxy for erosion rate, accounts for 32% of variance in AGB within our field area ( P

Laboratory bioassay for canola (Brassica napus) allelopathy - Md. Asaduzzaman; Min An; James Edward Pratley; David John Luckett; Deirdre Lemerle (Journal of Crop Science and Biotechnology, 2014)

A high-throughput SNP array in the amphidiploid species Brassica napus shows diversity in resistance genes - Jessica Dalton-Morgan; Alice Hayward; Salman Alamery; Reece Tollenaere; Annaliese S. Mason; Emma Campbell; Dhwani Patel; Michał T. Lorenc; Bin Yi; Yan Long; Jinling Meng; Rosy Raman; et al. (Functional & Integrative Genomics, 2014)

Recovery of precision grasping after motor cortex lesion does not require forced use of the impaired hand in macaca mulatta - Warren G. Darling; Robert J. Morecraft; Diane L. Rotella; Marc A. Pizzimenti; Jizhi Ge; Kimberly S. Stilwell-Morecraft; Hongyu Zhang; Hesham Soliman; Dave Seecharan; Ian Edwards; David McNeal; Randolph J. Nudo; et al. (Experimental Brain Research, 2014)

Characterization of Regional Deformation and Material Properties of the Intact Explanted Vein by microCT and Computational Analysis - Arnold David Gomez; Huashan Zou; Yan-Ting Shiu; Edward W. Hsu (Cardiovascular Engineering and Technology, 2014)

Long Time Series in US Fisheries Oceanography - Sam McClatchie; Janet Duffy-Anderson; John Field; Ralf Goericke; Dave Griffith; David Hanisko; Jonathan Hare; Joanne Lyczkowski-Shultz; William Peterson; William Watson; Edward Weber; Glenn Zapfe (Oceanography, 2014)

Horizon scanning for invasive alien species with the potential to threaten biodiversity in Great Britain - Helen E. Roy; Jodey Peyton; David C. Aldridge; Tristan Bantock; Tim M. Blackburn; Robert Britton; Paul Clark; Elizabeth Cook; Katharina Dehnen‐Schmutz; Trevor Dines; Michael Dobson; François Edwards; et al. (Global Change Biology, 2014)
Invasive alien species ( IAS ) are considered one of the greatest threats to biodiversity, particularly through their interactions with other drivers of change. Horizon scanning, the systematic examination of future potential threats and opportunities, leading to prioritization of IAS threats is seen as an essential component of IAS management. Our aim was to consider IAS that were likely to impact on native biodiversity but were not yet established in the wild in Great Britain. To achieve this, we developed an approach which coupled consensus methods (which have previously been used for collaboratively identifying priorities in other contexts) with rapid risk assessment. The process involved two distinct phases: Preliminary consultation with experts within five groups (plants, terrestrial invertebrates, freshwater invertebrates, vertebrates and marine species) to derive ranked lists of potential IAS. Consensus‐building across expert groups to compile and rank the entire list of potential IAS. Five hundred and ninety‐one species not native to Great Britain were considered. Ninety‐three of these species were agreed to constitute at least a medium risk (based on score and consensus) with respect to them arriving, establishing and posing a threat to native biodiversity. The quagga mussel, Dreissena rostriformis bugensis , received maximum scores for risk of arrival, establishment and impact; following discussions the unanimous consensus was to rank it in the top position. A further 29 species were considered to constitute a high risk and were grouped according to their ranked risk. The remaining 63 species were considered as medium risk, and included in an unranked long list. The information collated through this novel extension of the consensus method for horizon scanning provides evidence for underpinning and prioritizing management both for the species and, perhaps more importantly, their pathways of arrival. Although our study focused on Great Britain, we suggest that the methods adopted are applicable globally.

Novel Nystatin A1 derivatives exhibiting low host cell toxicity and antifungal activity in an in vitro model of oral candidosis - Joanna Boros-Majewska; Natalia Salewska; Edward Borowski; Sławomir Milewski; Sladjana Malic; Xiao-Qing Wei; Anthony J. Hayes; Melanie J. Wilson; David W. Williams (Medical Microbiology and Immunology, 2014)

Real Exposure: Field Measurement of Chemical Plumes in Headwater Streams - David D. Edwards; Paul A. Moore (Archives of Environmental Contamination and Toxicology, 2014)

Range‐wide multilocus phylogeography of the red fox reveals ancient continental divergence, minimal genomic exchange and distinct demographic histories - Mark J. Statham; James Murdoch; Jan Janecka; Keith B. Aubry; Ceiridwen J. Edwards; Carl D. Soulsbury; Oliver Berry; Zhenghuan Wang; David Harrison; Malcolm Pearch; Louise Tomsett; Judith Chupasko; et al. (Molecular Ecology, 2014)
Widely distributed taxa provide an opportunity to compare biogeographic responses to climatic fluctuations on multiple continents and to investigate speciation. We conducted the most geographically and genomically comprehensive study to date of the red fox ( Vulpes vulpes ), the world's most widely distributed wild terrestrial carnivore. Analyses of 697 bp of mitochondrial sequence in ~1000 individuals suggested an ancient Middle Eastern origin for all extant red foxes and a 400 kya ( SD = 139 kya) origin of the primary North American (Nearctic) clade. Demographic analyses indicated a major expansion in Eurasia during the last glaciation (~50 kya), coinciding with a previously described secondary transfer of a single matriline (Holarctic) to North America. In contrast, North American matrilines (including the transferred portion of Holarctic clade) exhibited no signatures of expansion until the end of the Pleistocene (~12 kya). Analyses of 11 autosomal loci from a subset of foxes supported the colonization time frame suggested by mt DNA (and the fossil record) but, in contrast, reflected no detectable secondary transfer, resulting in the most fundamental genomic division of red foxes at the Bering Strait. Endemic continental Y‐chromosome clades further supported this pattern. Thus, intercontinental genomic exchange was overall very limited, consistent with long‐term reproductive isolation since the initial colonization of North America. Based on continental divergence times in other carnivoran species pairs, our findings support a model of peripatric speciation and are consistent with the previous classification of the North American red fox as a distinct species, V. fulva .

Archaeological Evidence of Validity of Fish Populations on Unexploited Reefs as Proxy Targets for Modern Populations - KEN LONGENECKER; YVONNE L. CHAN; ROBERT J. TOONEN; DAVID B. CARLON; TERRY L. HUNT; ALAN M. FRIEDLANDER; EDWARD E. DEMARTINI (Conservation Biology, 2014)
Reef‐fish management and conservation is hindered by a lack of information on fish populations prior to large‐scale contemporary human impacts. As a result, relatively pristine sites are often used as conservation baselines for populations near sites affected by humans. This space‐for‐time approach can only be validated by sampling assemblages through time. We used archaeological remains to evaluate whether the remote, uninhabited Northwestern Hawaiian Islands (NWHI) might provide a reasonable proxy for a lightly exploited baseline in the Main Hawaiian Islands (MHI). We used molecular and morphological techniques to describe the taxonomic and size composition of the scarine parrotfish catches present in 2 archaeological assemblages from the MHI, compared metrics of these catches with modern estimates of reproductive parameters to evaluate whether catches represented by the archaeological material were consistent with sustainable fishing, and evaluated overlap between size structures represented by the archaeological material and modern survey data from the MHI and the NWHI to assess whether a space‐for‐time substitution is reasonable. The parrotfish catches represented by archaeological remains were consistent with sustainable fishing because they were dominated by large, mature individuals whose average size remained stable from prehistoric (AD approximately 1400–1700) through historic (AD 1700–1960) periods. The ancient catches were unlike populations in the MHI today. Overlap between the size structure of ancient MHI catches and modern survey data from the NWHI or the MHI was an order of magnitude greater for the NWHI comparison, a result that supports the validity of using the NWHI parrotfish data as a proxy for the MHI before accelerated, heavy human impacts in modern times. Evidencia Arqueológica de la Validez de Poblaciones de Peces en Arrecifes Sin Explotar como Objetivos de Apoderamiento para Poblaciones Actuales

Distinct dissolved organic matter sources induce rapid transcriptional responses in coexisting populations of P rochlorococcus , P elagibacter and the OM60 clade - Adrian K. Sharma; Jamie W. Becker; Elizabeth A. Ottesen; Jessica A. Bryant; Solange Duhamel; David M. Karl; Otto X. Cordero; Daniel J. Repeta; Edward F. DeLong (Environmental Microbiology, 2014)
Summary A considerable fraction of the E arth's organic carbon exists in dissolved form in seawater. To investigate the roles of planktonic marine microbes in the biogeochemical cycling of this dissolved organic matter ( DOM ), we performed controlled seawater incubation experiments and followed the responses of an oligotrophic surface water microbial assemblage to perturbations with DOM derived from an axenic culture of P rochlorococcus , or high‐molecular weight DOM concentrated from nearby surface waters. The rapid transcriptional responses of both P rochlorococcus and P elagibacter populations suggested the utilization of organic nitrogen compounds common to both DOM treatments. Along with these responses, both populations demonstrated decreases in gene transcripts associated with nitrogen stress, including those involved in ammonium acquisition. In contrast, responses from low abundance organisms of the NOR5/OM60 gammaproteobacteria were observed later in the experiment, and included elevated levels of gene transcripts associated with polysaccharide uptake and oxidation. In total, these results suggest that numerically dominant oligotrophic microbes rapidly acquire nitrogen from commonly available organic sources, and also point to an important role for carbohydrates found within the DOM pool for sustaining the less abundant microorganisms in these oligotrophic systems.

Can tidal perturbations associated with sea level variations in the western Pacific Ocean be used to understand future effects of tidal evolution? - Adam T. Devlin; David A. Jay; Stefan A. Talke; Edward Zaron (Ocean Dynamics, 2014)

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Optimizing carbon storage and biodiversity protection in tropical agricultural landscapes - James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Charlotte Wheeler; Claudia A. Medina Uribe; Torbjørn Haugaasen; David P. Edwards (Global Change Biology, 2014)
With the rapidly expanding ecological footprint of agriculture, the design of farmed landscapes will play an increasingly important role for both carbon storage and biodiversity protection. Carbon and biodiversity can be enhanced by integrating natural habitats into agricultural lands, but a key question is whether benefits are maximized by including many small features throughout the landscape (‘land‐sharing’ agriculture) or a few large contiguous blocks alongside intensive farmland (‘land‐sparing’ agriculture). In this study, we are the first to integrate carbon storage alongside multi‐taxa biodiversity assessments to compare land‐sparing and land‐sharing frameworks. We do so by sampling carbon stocks and biodiversity (birds and dung beetles) in landscapes containing agriculture and forest within the Colombian Chocó‐Andes, a zone of high global conservation priority. We show that woodland fragments embedded within a matrix of cattle pasture hold less carbon per unit area than contiguous primary or advanced secondary forests (>15 years). Farmland sites also support less diverse bird and dung beetle communities than contiguous forests, even when farmland retains high levels of woodland habitat cover. Landscape simulations based on these data suggest that land‐sparing strategies would be more beneficial for both carbon storage and biodiversity than land‐sharing strategies across a range of production levels. Biodiversity benefits of land‐sparing are predicted to be similar whether spared lands protect primary or advanced secondary forests, owing to the close similarity of bird and dung beetle communities between the two forest classes. Land‐sparing schemes that encourage the protection and regeneration of natural forest blocks thus provide a synergy between carbon and biodiversity conservation, and represent a promising strategy for reducing the negative impacts of agriculture on tropical ecosystems. However, further studies examining a wider range of ecosystem services will be necessary to fully understand the links between land‐allocation strategies and long‐term ecosystem service provision.

Amphiphilic triblock copolymers with PEGylated hydrocarbon structures as environmentally friendly marine antifouling and fouling-release coatings - Zhaoli Zhou; David R. Calabrese; Warren Taylor; John A. Finlay; Maureen E. Callow; James A. Callow; Daniel Fischer; Edward J. Kramer; Christopher K. Ober (Biofouling, 2014)

The Influence of Actuator Materials and Nozzle Designs on Electrostatic Charge of Pressurised Metered Dose Inhaler (pMDI) Formulations - Yang Chen; Paul M. Young; David F. Fletcher; Hak Kim Chan; Edward Long; David Lewis; Tanya Church; Daniela Traini (Pharmaceutical Research, 2014)

Computational Identification and Comparative Analysis of miRNAs in Wheat Group 7 Chromosomes - Pingchuan Deng; Xiaojun Nie; Le Wang; Licao Cui; Peixun Liu; Wei Tong; Siddanagouda S. Biradar; David Edwards; Paul Berkman; Hana Šimková; Jaroslav Doležel; Mincheng Luo; et al. (Plant Molecular Biology Reporter, 2014)

The global contribution of forage fish to marine fisheries and ecosystems - Ellen K Pikitch; Konstantine J Rountos; Timothy E Essington; Christine Santora; Daniel Pauly; Reg Watson; Ussif R Sumaila; P Dee Boersma; Ian L Boyd; David O Conover; Philippe Cury; Selina S Heppell; et al. (Fish and Fisheries, 2014)
Forage fish play a pivotal role in marine ecosystems and economies worldwide by sustaining many predators and fisheries directly and indirectly. We estimate global forage fish contributions to marine ecosystems through a synthesis of 72 published E copath models from around the world. Three distinct contributions of forage fish were examined: (i) the ecological support service of forage fish to predators in marine ecosystems, (ii) the total catch and value of forage fisheries and (iii) the support service of forage fish to the catch and value of other commercially targeted predators. Forage fish use and value varied and exhibited patterns across latitudes and ecosystem types. Forage fish supported many kinds of predators, including fish, seabirds, marine mammals and squid. Overall, forage fish contribute a total of about $16.9 billion USD to global fisheries values annually, i.e. 20% of the global ex‐vessel catch values of all marine fisheries combined. While the global catch value of forage fisheries was $5.6 billion, fisheries supported by forage fish were more than twice as valuable ($11.3 billion). These estimates provide important information for evaluating the trade‐offs of various uses of forage fish across ecosystem types, latitudes and globally. We did not estimate a monetary value for supportive contributions of forage fish to recreational fisheries or to uses unrelated to fisheries, and thus the estimates of economic value reported herein understate the global value of forage fishes.

Improving the science-policy dialogue to meet the challenges of biodiversity conservation: having conversations rather than talking at one-another - Juliette C. Young; Kerry A. Waylen; Simo Sarkki; Steve Albon; Ian Bainbridge; Estelle Balian; James Davidson; David Edwards; Roddy Fairley; Ceri Margerison; Davy McCracken; Roger Owen; et al. (Biodiversity and Conservation, 2014)

Molecular epidemiology of R abbit H aemorrhagic D isease V irus in A ustralia: when one became many - John Kovaliski; Ron Sinclair; Greg Mutze; David Peacock; Tanja Strive; Joana Abrantes; Pedro J. Esteves; Edward C. Holmes (Molecular Ecology, 2014)
R abbit H aemorrhagic D isease V irus ( RHDV ) was introduced into A ustralia in 1995 as a biological control agent against the wild E uropean rabbit ( O ryctolagus cuniculus ). We evaluated its evolution over a 16‐year period (1995–2011) by examining 50 isolates collected throughout A ustralia, as well as the original inoculum strains. Phylogenetic analysis of capsid protein VP 60 sequences of the A ustralian isolates, compared with those sampled globally, revealed that they form a monophyletic group with the inoculum strains ( CAPM V‐351 and RHDV 351 INOC ). Strikingly, despite more than 3000 rereleases of RHDV 351 INOC since 1995, only a single viral lineage has sustained its transmission in the long‐term, indicative of a major competitive advantage. In addition, we find evidence for widespread viral gene flow, in which multiple lineages entered individual geographic locations, resulting in a marked turnover of viral lineages with time, as well as a continual increase in viral genetic diversity. The rate of RHDV evolution recorded in A ustralia −4.0 (3.3–4.7) × 10 −3 nucleotide substitutions per site per year – was higher than previously observed in RHDV , and evidence for adaptive evolution was obtained at two VP 60 residues. Finally, more intensive study of a single rabbit population (Turretfield) in S outh A ustralia provided no evidence for viral persistence between outbreaks, with genetic diversity instead generated by continual strain importation.

Microhabitats reduce animal's exposure to climate extremes - Brett R. Scheffers; David P. Edwards; Arvin Diesmos; Stephen E. Williams; Theodore A. Evans (Global Change Biology, 2014)
Extreme weather events, such as unusually hot or dry conditions, can cause death by exceeding physiological limits, and so cause loss of population. Survival will depend on whether or not susceptible organisms can find refuges that buffer extreme conditions. Microhabitats offer different microclimates to those found within the wider ecosystem, but do these microhabitats effectively buffer extreme climate events relative to the physiological requirements of the animals that frequent them? We collected temperature data from four common microhabitats (soil, tree holes, epiphytes, and vegetation) located from the ground to canopy in primary rainforests in the Philippines. Ambient temperatures were monitored from outside of each microhabitat and from the upper forest canopy, which represent our macrohabitat controls. We measured the critical thermal maxima ( CT max ) of frog and lizard species, which are thermally sensitive and inhabit our microhabitats. Microhabitats reduced mean temperature by 1–2 °C and reduced the duration of extreme temperature exposure by 14–31 times. Microhabitat temperatures were below the CT max of inhabitant frogs and lizards, whereas macrohabitats consistently contained lethal temperatures. Microhabitat temperatures increased by 0.11–0.66 °C for every 1 °C increase in macrohabitat temperature, and this nonuniformity in temperature change influenced our forecasts of vulnerability for animal communities under climate change. Assuming uniform increases of 6 °C, microhabitats decreased the vulnerability of communities by up to 32‐fold, whereas under nonuniform increases of 0.66 to 3.96 °C, microhabitats decreased the vulnerability of communities by up to 108‐fold. Microhabitats have extraordinary potential to buffer climate and likely reduce mortality during extreme climate events. These results suggest that predicted changes in distribution due to mortality and habitat shifts that are derived from macroclimatic samples and that assume uniform changes in microclimates relative to macroclimates may be overly pessimistic. Nevertheless, even nonuniform temperature increases within buffered microhabitats would still threaten frogs and lizards.

The Human Gene Mutation Database: building a comprehensive mutation repository for clinical and molecular genetics, diagnostic testing and personalized genomic medicine - Peter D. Stenson; Matthew Mort; Edward V. Ball; Katy Shaw; Andrew D. Phillips; David N. Cooper (Human Genetics, 2014)
The Human Gene Mutation Database (HGMD ® ) is a comprehensive collection of germline mutations in nuclear genes that underlie, or are associated with, human inherited disease. By June 2013, the database contained over 141,000 different lesions detected in over 5,700 different genes, with new mutation entries currently accumulating at a rate exceeding 10,000 per annum. HGMD was originally established in 1996 for the scientific study of mutational mechanisms in human genes. However, it has since acquired a much broader utility as a central unified disease-oriented mutation repository utilized by human molecular geneticists, genome scientists, molecular biologists, clinicians and genetic counsellors as well as by those specializing in biopharmaceuticals, bioinformatics and personalized genomics. The public version of HGMD ( https://www.hgmd.cf.ac.uk ) is freely available to registered users from academic institutions/non-profit organizations whilst the subscription version (HGMD Professional) is available to academic, clinical and commercial users under license via BIOBASE GmbH.

Haptoglobin (HP) and Haptoglobin-related protein (HPR) copy number variation, natural selection, and trypanosomiasis - Robert J. Hardwick; Anne Ménard; Manuela Sironi; Jacqueline Milet; André Garcia; Claude Sese; Fengtang Yang; Beiyuan Fu; David Courtin; Edward J. Hollox (Human Genetics, 2014)

Longitudinal decline of lower extremity muscle power in healthy and mobility-limited older adults: influence of muscle mass, strength, composition, neuromuscular activation and single fiber contractile properties - Kieran F. Reid; Evan Pasha; Gheorghe Doros; David J. Clark; Carolynn Patten; Edward M. Phillips; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2014)

Land‐sharing versus land‐sparing logging: reconciling timber extraction with biodiversity conservation - David P. Edwards; James J. Gilroy; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; David J. R. Andrews; Mia A. Derhé; Teegan D. S. Docherty; Wayne W. Hsu; Simon L. Mitchell; Takahiro Ota; Leah J. Williams; et al. (Global Change Biology, 2014)
Selective logging is a major driver of rainforest degradation across the tropics. Two competing logging strategies are proposed to meet timber demands with the least impact on biodiversity: land sharing, which combines timber extraction with biodiversity protection across the concession; and land sparing, in which higher intensity logging is combined with the protection of intact primary forest reserves. We evaluate these strategies by comparing the abundances and species richness of birds, dung beetles and ants in Borneo, using a protocol that allows us to control for both timber yield and net profit across strategies. Within each taxonomic group, more species had higher abundances with land‐sparing than land‐sharing logging, and this translated into significantly higher species richness within land‐sparing concessions. Our results are similar when focusing only on species found in primary forest and restricted in range to Sundaland, and they are independent of the scale of sampling. For each taxonomic group, land‐sparing logging was the most promising strategy for maximizing the biological value of logging operations.

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

Characterization of STR/microsatellite primers for the Gila monster, Heloderma suspectum screened from paired-end Illumina shotgun sequencing - Michael R. Hess; Taylor Edwards; David A. Edmunds; Kevin E. Bonine (Conservation Genetics Resources, 2013)

Acetochlor Persistence in Surface and Subsurface Soil Samples - Rubem S. Oliveira; William C. Koskinen; Carrie D. Graff; James L. Anderson; David J. Mulla; Edward A. Nater; Diego G. Alonso (Water, Air, & Soil Pollution, 2013)

Seasonal abundance, philopatry and demographic structure of Caribbean reef shark (Carcharhinus perezi) assemblages in the north-east Exuma Sound, The Bahamas - Edward J. Brooks; David W. Sims; Andy J. Danylchuk; Katherine A. Sloman (Marine Biology, 2013)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Reliable, verifiable and efficient monitoring of biodiversity via metabarcoding - Yinqiu Ji; Louise Ashton; Scott M. Pedley; David P. Edwards; Yong Tang; Akihiro Nakamura; Roger Kitching; Paul M. Dolman; Paul Woodcock; Felicity A. Edwards; Trond H. Larsen; Wayne W. Hsu; et al. (Ecology Letters, 2013)
To manage and conserve biodiversity, one must know what is being lost, where, and why, as well as which remedies are likely to be most effective. Metabarcoding technology can characterise the species compositions of mass samples of eukaryotes or of environmental DNA . Here, we validate metabarcoding by testing it against three high‐quality standard data sets that were collected in Malaysia (tropical), China (subtropical) and the United Kingdom (temperate) and that comprised 55,813 arthropod and bird specimens identified to species level with the expenditure of 2,505 person‐hours of taxonomic expertise. The metabarcode and standard data sets exhibit statistically correlated alpha‐ and beta‐diversities, and the two data sets produce similar policy conclusions for two conservation applications: restoration ecology and systematic conservation planning. Compared with standard biodiversity data sets, metabarcoded samples are taxonomically more comprehensive, many times quicker to produce, less reliant on taxonomic expertise and auditable by third parties, which is essential for dispute resolution.

Trophic Flexibility and the Persistence of Understory Birds in Intensively Logged Rainforest - DAVID P. EDWARDS; PAUL WOODCOCK; ROB J. NEWTON; FELICITY A. EDWARDS; DAVID J. R. ANDREWS; TEEGAN D. S. DOCHERTY; SIMON L. MITCHELL; TAKAHIRO OTA; SUZAN BENEDICK; SIMON H. BOTTRELL; KEITH C. HAMER (Conservation Biology, 2013)
Effects of logging on species composition in tropical rainforests are well known but may fail to reveal key changes in species interactions. We used nitrogen stable‐isotope analysis of 73 species of understory birds to quantify trophic responses to repeated intensive logging of rainforest in northern Borneo and to test 4 hypotheses: logging has significant effects on trophic positions and trophic‐niche widths of species, and the persistence of species in degraded forest is related to their trophic positions and trophic‐niche widths in primary forest. Species fed from higher up the food chain and had narrower trophic‐niche widths in degraded forest. Species with narrow trophic‐niche widths in primary forest were less likely to persist after logging, a result that indicates a higher vulnerability of dietary specialists to local extinction following habitat disturbance. Persistence of species in degraded forest was not related to a species’ trophic position. These results indicate changes in trophic organization that were not apparent from changes in species composition and highlight the importance of focusing on trophic flexibility over the prevailing emphasis on membership of static feeding guilds. Our results thus support the notion that alterations to trophic organization and interactions within tropical forests may be a pervasive and functionally important hidden effect of forest degradation. Flexibilidad Trófica y la Persistencia de Aves de Sotobosque en un Bosque Lluvioso Talado Intensivamente

Identifying genetic diversity of avirulence genes in Leptosphaeria maculans using whole genome sequencing - Manuel Zander; Dhwani A. Patel; Angela Van de Wouw; Kaitao Lai; Michal T. Lorenc; Emma Campbell; Alice Hayward; David Edwards; Harsh Raman; Jacqueline Batley (Functional & Integrative Genomics, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Estimation of impulse response between electromyogram signals for use in conduction delay distribution estimation - Tahsin Hassan; Kyle C. D. McIntosh; David A. Gabriel; Edward A. Clancy (Medical & Biological Engineering & Computing, 2013)

Transcriptional profiling of Zea mays roots reveals roles for jasmonic acid and terpenoids in resistance against Phytophthora cinnamomi - Jane Alisa Allardyce; James Edward Rookes; Hashmath Inayath Hussain; David Miles Cahill (Functional & Integrative Genomics, 2013)

Attenuation of cocaine and heroin seeking by μ-opioid receptor antagonism - Chiara Giuliano; Trevor W. Robbins; David R. Wille; Edward T. Bullmore; Barry J. Everitt (Psychopharmacology, 2013)

Dispersal limitation, speciation, environmental filtering and niche differentiation influence forest tree communities in West Polynesia - Janet Franklin; Gunnar Keppel; Edward L. Webb; Joshua O. Seamon; Sergio J. Rey; David W. Steadman; Susan K. Wiser; Donald R. Drake (Journal of Biogeography, 2013)
Aim Regional patterns of forest composition in West Polynesia were analysed to determine the relative importance of dispersal limitation, speciation, environmental filtering and biotic interactions. Location West Polynesia (Fiji, Tonga, Samoa). Methods We applied clustering and indicator species analysis to presence/absence data for 397 tree taxa in 338 forest plots to detect groups of plots sharing similar species composition. Patterns of plot composition and co‐occurrence of congeneric species were compared between archipelagos for evidence of dispersal limitation, speciation, and environmental filtering versus competitive displacement or niche differentiation across the three archipelagos at the local (plot) and regional scales. Results Dispersal limitation was evident in the compositional segregation of inland rain forests across the three archipelagos, whereas compositional overlap was widespread for coastal forests, which are composed of species dispersed by water. Within genera, species numbers attenuated from Fiji to Tonga to Samoa, but speciation also contributed to compositional differences in all three island groups. Environmental filtering was suggested by the distinct composition of both secondary and mature inland rain forest versus coastal forest. At the local scale, however, clumping of congeners, which might suggest fine‐scale environmental filtering, was observed for only a minority of inland forest genera. Most genera showed either overdispersion, suggesting competitive displacement or niche differentiation, or patterns not significantly different from random. Main conclusions Well‐established biogeographical patterns of dispersal limitation and speciation contribute to West Polynesian tree diversity at the community scale. Environmental filtering and competitive displacement further structure forest communities; the evidence from this study suggests that environmental filtering is more important at a landscape scale, while competitive displacement may be more important at a local scale, although their relative importance varies considerably among taxa.

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

Noninvasive diffusive optical imaging of the auditory response to birdsong in the zebra finch - James V. Lee; Edward L. Maclin; Kathy A. Low; Gabriele Gratton; Monica Fabiani; David F. Clayton (Journal of Comparative Physiology A, 2013)

The nature and formation of cristobalite at the Soufrière Hills volcano, Montserrat: implications for the petrology and stability of silicic lava domes - Claire J. Horwell; Ben J. Williamson; Edward W. Llewellin; David E. Damby; Jennifer S. Le Blond (Bulletin of Volcanology, 2013)

Detecting Insect Pollinator Declines on Regional and Global Scales - Gretchen Lebuhn; Sam Droege; Edward F. Connor; Barbara Gemmill‐Herren; Simon G. Potts; Robert L. Minckley; Terry Griswold; Robert Jean; Emanuel Kula; David W. Roubik; Jim Cane; Karen W. Wright; et al. (Conservation Biology, 2013)
Recently there has been considerable concern about declines in bee communities in agricultural and natural habitats. The value of pollination to agriculture, provided primarily by bees, is >$200 billion/year worldwide, and in natural ecosystems it is thought to be even greater. However, no monitoring program exists to accurately detect declines in abundance of insect pollinators; thus, it is difficult to quantify the status of bee communities or estimate the extent of declines. We used data from 11 multiyear studies of bee communities to devise a program to monitor pollinators at regional, national, or international scales. In these studies, 7 different methods for sampling bees were used and bees were sampled on 3 different continents. We estimated that a monitoring program with 200–250 sampling locations each sampled twice over 5 years would provide sufficient power to detect small (2–5%) annual declines in the number of species and in total abundance and would cost U.S.$2,000,000. To detect declines as small as 1% annually over the same period would require >300 sampling locations. Given the role of pollinators in food security and ecosystem function, we recommend establishment of integrated regional and international monitoring programs to detect changes in pollinator communities. Detección de Declinaciones de Insectos Polinizadores a Escalas Regional y Global

Fire in the Air: Biomass Burning Impacts in a Changing Climate - Melita Keywood; Maria Kanakidou; Andreas Stohl; Frank Dentener; Giacomo Grassi; C. P. Meyer; Kjetil Torseth; David Edwards; Anne M. Thompson; Ulrike Lohmann; John Burrows (Critical Reviews in Environmental Science and Technology, 2013)

Genetic and physical mapping of flowering time loci in canola (Brassica napus L.) - Harsh Raman; Rosy Raman; Paul Eckermann; Neil Coombes; Sahana Manoli; Xiaoxiao Zou; David Edwards; Jinling Meng; Roslyn Prangnell; Jiri Stiller; Jacqueline Batley; David Luckett; et al. (Theoretical and Applied Genetics, 2013)

Accessing complex crop genomes with next-generation sequencing - David Edwards; Jacqueline Batley; Rod J. Snowdon (Theoretical and Applied Genetics, 2013)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Diabetes and risk of pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium - Joanne W. Elena; Emily Steplowski; Kai Yu; Patricia Hartge; Geoffrey S. Tobias; Michelle J. Brotzman; Stephen J. Chanock; Rachael Z. Stolzenberg-Solomon; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Kathy Helzlsouer; Eric J. Jacobs; et al. (Cancer Causes & Control, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Microstructure characteristics during hydrate formation and dissociation revealed by X-ray tomographic microscopy - Stephan A. Klapp; Frieder Enzmann; Peter Walz; Thomas Huthwelker; Jürgen Tuckermann; J.-Oliver Schwarz; Thomas Pape; Edward T. Peltzer; Rajmund Mokso; David Wangner; Federica Marone; Michael Kersten; et al. (Geo-Marine Letters, 2012)

Resistance to Aphids, Late Blight and Viruses in Somatic Fusions and Crosses of Solanum tuberosum L. and Solanum bulbocastanum Dun - Jeffrey A. Davis; Edward B. Radcliffe; Christian A. Thill; David W. Ragsdale (American Journal of Potato Research, 2012)

Gene expression changes of interconnected spared cortical neurons 7 days after ischemic infarct of the primary motor cortex in the rat - Edward T. R. Urban; Scott D. Bury; H. Scott Barbay; David J. Guggenmos; Yafeng Dong; Randolph J. Nudo (Molecular and Cellular Biochemistry, 2012)

Reliability and variability of sleep and activity as biomarkers of ageing in Drosophila - Sofocles Koudounas; Edward W. Green; David Clancy (Biogerontology, 2012)

Impacts of logging and rehabilitation on invertebrate communities in tropical rainforests of northern Borneo - David P. Edwards; Amy R. Backhouse; Charlotte Wheeler; Chey Vun Khen; Keith C. Hamer (Journal of Insect Conservation, 2012)

Comparison of techniques used to count single-celled viable phytoplankton - Mia K. Steinberg; Matthew R. First; Edward J. Lemieux; Lisa A. Drake; Bruce N. Nelson; David M. Kulis; Donald M. Anderson; Nicholas A. Welschmeyer; Penny R. Herring (Journal of Applied Phycology, 2012)

Impact of predatory carabids on below- and above-ground pests and yield in strawberry - Jana C. Lee; David L. Edwards (BioControl, 2012)

Ferumoxytol-Enhanced MRI to Image Inflammation Within Human Brain Arteriovenous Malformations: a Pilot Investigation - David M. Hasan; Matthew Amans; Tarik Tihan; Christopher Hess; Yi Guo; Soonmee Cha; Hua Su; Alastair J. Martin; Michael T. Lawton; Edward A. Neuwelt; David A. Saloner; William L. Young (Translational Stroke Research, 2012)

Molecular mapping of qualitative and quantitative loci for resistance to Leptosphaeria maculans causing blackleg disease in canola (Brassica napus L.) - Rosy Raman; Belinda Taylor; Steve Marcroft; Jiri Stiller; Paul Eckermann; Neil Coombes; Ata Rehman; Kurt Lindbeck; David Luckett; Neil Wratten; Jacqueline Batley; David Edwards; et al. (Theoretical and Applied Genetics, 2012)

Muscle power failure in mobility-limited older adults: preserved single fiber function despite lower whole muscle size, quality and rate of neuromuscular activation - Kieran F. Reid; Gheorghe Doros; David J. Clark; Carolynn Patten; Robert J. Carabello; Gregory J. Cloutier; Edward M. Phillips; Lisa S. Krivickas; Walter R. Frontera; Roger A. Fielding (European Journal of Applied Physiology, 2012)

Breeding success of four male life history types of spring Chinook Salmon spawning in an artificial stream - Steve L. Schroder; Curtis M. Knudsen; Todd N. Pearsons; Todd W. Kassler; Edward P. Beall; Sewall F. Young; David E. Fast (Environmental Biology of Fishes, 2012)

Assessing trophic position from nitrogen isotope ratios: effective calibration against spatially varying baselines - Paul Woodcock; David P. Edwards; Rob J. Newton; Felicity A. Edwards; Chey Vun Khen; Simon H. Bottrell; Keith C. Hamer (The Science of Nature, 2012)

Plasma folate, methylenetetrahydrofolate reductase (MTHFR), and colorectal cancer risk in three large nested case–control studies - Jung Eun Lee; Esther K. Wei; Charles S. Fuchs; David J. Hunter; I-Min Lee; Jacob Selhub; Meir J. Stampfer; Walter C. Willett; Jing Ma; Edward Giovannucci (Cancer Causes & Control, 2012)

Soil C erosion and burial in cropland - A. J. VandenBygaart; DAVID Kroetsch; EDWARD G. Gregorich; DAVID Lobb (Global Change Biology, 2012)
Erosion influences the lateral and vertical distribution of soil in agricultural landscapes. A better understanding of the effects of erosion and redistribution on soil organic carbon ( C ) within croplands would improve our knowledge of how management practices may affect global C dynamics. In this study, the vertical and lateral distribution of soil organic C was characterized to evaluate the amounts and timescales of soil organic C movement, deposition and burial over the last 50 years in different agroecosystems across C anada. There was strong evidence that a substantial portion of eroded sediment and soil organic C was deposited as colluvium close to its source area, thereby burying the original topsoil. The deepest aggraded profile was in a potato field and contained over 70 cm of deposited soil indicating an accumulation rate of 152 Mg ha yr −1 ; aggraded profiles in other sites had soil deposition rates of 40–90 Mg ha −1 yr −1 . The largest stock of soil organic C was 463 Mg ha −1 (to 60 cm depth) and soil C deposition ranged from about 2 to 4 Mg ha −1 yr −1 across all sites. A distinct feature observed in the aggraded profiles at every site was the presence of a large increase in soil organic C concentration near the bottom of the A horizon; the concentration of this C was greater than that at the soil surface. Compared to aggraded profiles, the SOC concentration in eroded profiles did not differ with depth, suggesting that dynamic replacement of soil organic C had occurred in eroded soils. A large amount of soil organic C is buried in depositional areas of C anadian croplands; mineralization of this stock of C appears to have been constrained since burial, but it may be vulnerable to future loss by management practices, land use change and a warming climate.

Preliminary Efforts Directed Toward the Detection of Craving of Illicit Substances: The iHeal Project - Edward W. Boyer; Rich Fletcher; Richard J. Fay; David Smelson; Douglas Ziedonis; Rosalind W. Picard (Journal of Medical Toxicology, 2012)

Agronomic diversity of naked barley (Hordeum vulgare L.): a potential resource for breeding new food barley for Europe - Edward Dickin; Katherine Steele; Gareth Edwards-Jones; David Wright (Euphytica, 2012)

Volcanic Eruptions in the Deep Sea - Kenneth Rubin; S. Adam Soule; William Chadwick; Daniel Fornari; David Clague; Robert Embley; Edward Baker; Michael Perfit; David Caress; Robert Dziak (Oceanography, 2012)

Sequencing wheat chromosome arm 7BS delimits the 7BS/4AL translocation and reveals homoeologous gene conservation - Paul J. Berkman; Adam Skarshewski; Sahana Manoli; Michał T. Lorenc; Jiri Stiller; Lars Smits; Kaitao Lai; Emma Campbell; Marie Kubaláková; Hana Šimková; Jacqueline Batley; Jaroslav Doležel; et al. (Theoretical and Applied Genetics, 2012)

Predicting regional spread of non-native species using oceanographic models: validation and identification of gaps - David G. Delaney; Paul K. Edwards; Brian Leung (Marine Biology, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Effect of cold acclimatization on exercise economy in the cold - Matthew D. Muller; Chul-Ho Kim; David M. Bellar; Edward J. Ryan; Yongsuk Seo; Sarah M. Muller; Ellen L. Glickman (European Journal of Applied Physiology, 2012)

Modelling the effect of size on the aerial dispersal of microorganisms - David M. Wilkinson; Symeon Koumoutsaris; Edward A. D. Mitchell; Isabelle Bey (Journal of Biogeography, 2012)
Aim We investigate the long‐standing question of whether the small size of microbes allows most microbial species to colonize all suitable sites around the globe or whether their ranges are limited by opportunities for dispersal. In this study we use a modelling approach to investigate the effect of size on the probability of between‐continent dispersal using virtual microorganisms in a global model of the Earth’s atmosphere. Location Global. Methods We use a computer model of global atmospheric circulation to investigate the effect of microbe size (effective diameters of 9, 20, 40 and 60 μm) on the probability of aerial dispersal. Results We found that for smaller microbes, once airborne, dispersal is remarkably successful over a 1‐year period. The most striking results are the extensive within‐hemisphere distribution of virtual microbes of 9 and 20 μm diameter and the lack of dispersal between the Northern and Southern Hemispheres during the year‐long time‐scale of our simulations. Main conclusions Above a diameter of 20 μm wind dispersal of virtual microbes between continents becomes increasingly unlikely, and it does not occur at all (within our simulated 1‐year period) for those of 60 μm diameter. Within our simulation, the success of small microbes in long‐distance dispersal is due both to their greater abundance and to their longer time in the atmosphere – once airborne – compared with larger microbes.

Effects of biotic disturbances on forest carbon cycling in the U nited S tates and C anada - Jeffrey A. Hicke; Craig D. Allen; Ankur R. Desai; Michael C. Dietze; Ronald J. Hall; Edward H. (Ted) Hogg; Daniel M. Kashian; David Moore; Kenneth F. Raffa; Rona N. Sturrock; James Vogelmann (Global Change Biology, 2012)
Forest insects and pathogens are major disturbance agents that have affected millions of hectares in N orth A merica in recent decades, implying significant impacts to the carbon ( C ) cycle. Here, we review and synthesize published studies of the effects of biotic disturbances on forest C cycling in the U nited S tates and C anada. Primary productivity in stands was reduced, sometimes considerably, immediately following insect or pathogen attack. After repeated growth reductions caused by some insects or pathogens or a single infestation by some bark beetle species, tree mortality occurred, altering productivity and decomposition. In the years following disturbance, primary productivity in some cases increased rapidly as a result of enhanced growth by surviving vegetation, and in other cases increased slowly because of lower forest regrowth. In the decades following tree mortality, decomposition increased as a result of the large amount of dead organic matter. Net ecosystem productivity decreased immediately following attack, with some studies reporting a switch to a C source to the atmosphere, and increased afterward as the forest regrew and dead organic matter decomposed. Large variability in C cycle responses arose from several factors, including type of insect or pathogen, time since disturbance, number of trees affected, and capacity of remaining vegetation to increase growth rates following outbreak. We identified significant knowledge gaps, including limited understanding of carbon cycle impacts among different biotic disturbance types (particularly pathogens), their impacts at landscape and regional scales, and limited capacity to predict disturbance events and their consequences for carbon cycling. We conclude that biotic disturbances can have major impacts on forest C stocks and fluxes and can be large enough to affect regional C cycling. However, additional research is needed to reduce the uncertainties associated with quantifying biotic disturbance effects on the N orth A merican C budget.

Migratory flyway and geographical distance are barriers to the gene flow of influenza virus among North American birds - Tommy Tsan‐Yuk Lam; Hon S. Ip; Elodie Ghedin; David E. Wentworth; Rebecca A. Halpin; Timothy B. Stockwell; David J. Spiro; Robert J. Dusek; James B. Bortner; Jenny Hoskins; Bradley D. Bales; Dan R. Yparraguirre; et al. (Ecology Letters, 2012)
Ecology Letters (2011) 14 : 24–33 Abstract Despite the importance of migratory birds in the ecology and evolution of avian influenza virus (AIV), there is a lack of information on the patterns of AIV spread at the intra‐continental scale. We applied a variety of statistical phylogeographic techniques to a plethora of viral genome sequence data to determine the strength, pattern and determinants of gene flow in AIV sampled from wild birds in North America. These analyses revealed a clear isolation‐by‐distance of AIV among sampling localities. In addition, we show that phylogeographic models incorporating information on the avian flyway of sampling proved a better fit to the observed sequence data than those specifying homogeneous or random rates of gene flow among localities. In sum, these data strongly suggest that the intra‐continental spread of AIV by migratory birds is subject to major ecological barriers, including spatial distance and avian flyway.

Advanced Molecular Biologic Techniques in Toxicologic Disease - Jeanine Ward; Gyongyi Szabo; David McManus; Edward Boyer (Journal of Medical Toxicology, 2011)

MHC region and risk of systemic lupus erythematosus in African American women - Edward A. Ruiz-Narvaez; Patricia A. Fraser; Julie R. Palmer; L. Adrienne Cupples; David Reich; Ying A. Wang; John D. Rioux; Lynn Rosenberg (Human Genetics, 2011)

Web 2.0 collaborations address uncertainty in climate reconstructions of the past millennium - David Morrill Anderson; Bruce A. Bauer; Charles R. Buckner; Edward Gille; Wendy S. Gross; Michael Hartman; Carrie Morrill; Anju M. Shah; Eugene R. Wahl (Earth Science Informatics, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

New Choices and Challenges for Regulated Private Forests: The “Alternate Plan” Option - Roje S. Gootee; Keith A. Blatner; Matthew S. Carroll; David M. Baumgartner; Edward P. Weber (Journal of Forestry, 2011)
The state of Washington has developed a policy instrument that substantially amends traditional “top-down” private forest regulation. Called the “Alternate Plan” option, it gives landowners unusual new flexibility in designing forest management projects for their property. Projects may depart from any of the state's established Forest Practices Rules, if the property owner can satisfactorily show that a customized proposal would provide equivalent environmental protection. The state provides a prompt review and decision and then supervises project implementation and monitors compliance with the approved project specifications. We interviewed 109 stakeholders involved in the design, use, and implementation of this innovative program. From this data we evaluate the functional advantages and challenges inherent in this new regulatory approach, suggest modifications to improve its effectiveness, and discuss policymaking implications.

Influence of insects and fungal pathogens on individual and population parameters of Cirsium arvense in its native and introduced ranges - Michael G. Cripps; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler; Grant R. Edwards (Biological Invasions, 2011)

Equitable regulation of private forests - Roje S. Gootee; Keith A. Blatner; David M. Baumgartner; Matthew S. Carroll; Edward P. Weber (Small-scale Forestry, 2011)

Developmental and growth defects in mice with combined deficiency of CK2 catalytic genes - Esther Landesman-Bollag; Anna Belkina; Beth Hovey; Edward Connors; Charles Cox; David C. Seldin (Molecular and Cellular Biochemistry, 2011)

Precalibrating an intermediate complexity climate model - Neil R. Edwards; David Cameron; Jonathan Rougier (Climate Dynamics, 2011)

Antioxidant and NF-κB inhibitory constituents isolated from Morchella esculenta - Jeong-Ah Kim; Edward Lau; David Tay; Esperanza J. Carcache De Blanco (Natural Product Research, 2011)

Low Temperature Geothermal Applications as Enablers of Sustainable Development: Practical Case Studies from Australia and UK - Edward Oldmeadow; Dora Marinova; David Birks; Steven Whittall; Stuart Brown (Water Resources Management, 2011)

Resistance to the Translation Initiation Inhibitor Silvestrol is Mediated by ABCB1/P-Glycoprotein Overexpression in Acute Lymphoblastic Leukemia Cells - Sneha V. Gupta; Ellen J. Sass; Melanie E. Davis; Ryan B. Edwards; Gerard Lozanski; Nyla A. Heerema; Amy Lehman; Xiaoli Zhang; David Jarjoura; John C. Byrd; Li Pan; Kenneth K. Chan; et al. (The AAPS Journal, 2011)

Validity of the Actical for estimating free-living physical activity - Scott E. Crouter; Diane M. DellaValle; Magdalene Horton; Jere D. Haas; Edward A. Frongillo; David R. Bassett (European Journal of Applied Physiology, 2011)

Shotgun Proteomic Analysis of Emiliania huxleyi, a Marine Phytoplankton Species of Major Biogeochemical Importance - Bethan M. Jones; Richard J. Edwards; Paul J. Skipp; C. David O’Connor; M. Debora Iglesias-Rodriguez (Marine Biotechnology, 2011)

Pain and thermal sensation in the cold: the effect of interval versus continuous exercise - Matthew D. Muller; Sarah M. Muller; Edward J. Ryan; David M. Bellar; Chul-Ho Kim; Ellen L. Glickman (European Journal of Applied Physiology, 2011)

“Dead Zone” dynamics in Lake Erie: the importance of weather and sampling intensity for calculated hypolimnetic oxygen depletion rates - Joseph D. Conroy; Leon Boegman; Hongyan Zhang; William J. Edwards; David A. Culver (Aquatic Sciences, 2011)

CyberShake: A Physics-Based Seismic Hazard Model for Southern California - Robert Graves; Thomas H. Jordan; Scott Callaghan; Ewa Deelman; Edward Field; Gideon Juve; Carl Kesselman; Philip Maechling; Gaurang Mehta; Kevin Milner; David Okaya; Patrick Small; et al. (Pure and Applied Geophysics, 2011)

The Role of the Everglades Mangrove Ecotone Region (EMER) in Regulating Nutrient Cycling and Wetland Productivity in South Florida - Victor H. Rivera-Monroy; Robert R. Twilley; Stephen E. Davis; Daniel L. Childers; Marc Simard; Randolph Chambers; Rudolf Jaffe; Joseph N. Boyer; David T. Rudnick; Keqi Zhang; Edward Castañeda-Moya; Sharon M. L. Ewe; et al. (Critical Reviews in Environmental Science and Technology, 2011)

Dissecting quantitative resistance against blast disease using heterogeneous inbred family lines in rice - Yan Liu; Xiao Yuan Zhu; Shaohong Zhang; Marichu Bernardo; Jeremy Edwards; David W. Galbraith; Jan Leach; Gaisheng Zhang; Bin Liu; Hei Leung (Theoretical and Applied Genetics, 2011)

Practical considerations optically sensing rhodamine WT in water impacted by municipal biosolids - Mark Edwards; Edward Topp; Patricia Bolton; David R. Lapen (Environmental Monitoring and Assessment, 2011)

Host migration impacts on the phylogeography of Lyme Borreliosis spirochaete species in Europe - Stephanie A. Vollmer; Antra Bormane; Ruth E. Dinnis; Frederik Seelig; Andrew D. M. Dobson; David M. Aanensen; Marianne C. James; Michael Donaghy; Sarah E. Randolph; Edward J. Feil; Klaus Kurtenbach; Gabriele Margos (Environmental Microbiology, 2011)
Summary The geographic patterns of transmission opportunities of vector‐borne zoonoses are determined by a complex interplay between the migration patterns of the host and the vector. Here we examine the impact of host migration on the spread of a tick‐borne zoonotic disease, using Lyme Borreliosis (LB) spirochaetal species in Europe. We demonstrate that the migration of the LB species is dependent on and limited by the migration of their respective hosts. We note that populations of Borrelia spp. associated with birds ( Borrelia garinii and B. valaisiana ) show limited geographic structuring between countries compared with those associated with small mammals ( Borrelia afzelii ), and we argue that this can be explained by higher rates of migration in avian hosts. We also show the presence of B. afzelii strains in England and, through the use of the multi‐locus sequence analysis scheme, reveal that the strains are highly structured. This pattern in English sites is very different from that observed at the continental sites, and we propose that these may be recent introductions.

Pulmonary Immunization of Guinea Pigs with Diphtheria CRM-197 Antigen as Nanoparticle Aggregate Dry Powders Enhance Local and Systemic Immune Responses - Pavan Muttil; Brian Pulliam; Lucila Garcia-Contreras; John Kevin Fallon; Chenchen Wang; Anthony James Hickey; David A. Edwards (The AAPS Journal, 2010)

The biology and ecology of the ocean sunfish Mola mola: a review of current knowledge and future research perspectives - Edward C. Pope; Graeme C. Hays; Tierney M. Thys; Thomas K. Doyle; David W. Sims; Nuno Queiroz; Victoria J. Hobson; Lukas Kubicek; Jonathan D. R. Houghton (Reviews in Fish Biology and Fisheries, 2010)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

Estimating the Value of Non‐Use Benefits from Small Changes in the Provision of Ecosystem Services - ADAM DUTTON; GARETH EDWARDS‐JONES; DAVID W. MACDONALD (Conservation Biology, 2010)
The unit of trade in ecosystem services is usually the use of a proportion of the parcels of land associated with a given service. Valuing small changes in the provision of an ecosystem service presents obstacles, particularly when the service provides non‐use benefits, as is the case with conservation of most plants and animals. Quantifying non‐use values requires stated‐preference valuations. Stated‐preference valuations can provide estimates of the public's willingness to pay for a broad conservation goal. Nevertheless, stated‐preference valuations can be expensive and do not produce consistent measures for varying levels of provision of a service. Additionally, the unit of trade, land use, is not always linearly related to the level of ecosystem services the land might provide. To overcome these obstacles, we developed a method to estimate the value of a marginal change in the provision of a non‐use ecosystem service—in this case conservation of plants or animals associated with a given land‐cover type. Our method serves as a tool for calculating transferable valuations of small changes in the provision of ecosystem services relative to the existing provision. Valuation is achieved through stated‐preference investigations, calculation of a unit value for a parcel of land, and the weighting of this parcel by its ability to provide the desired ecosystem service and its effect on the ability of the surrounding land parcels to provide the desired service. We used the water vole ( Arvicola terrestris ) as a case study to illustrate the method. The average present value of a meter of water vole habitat was estimated at UK£12, but the marginal value of a meter (based on our methods) could range between £0 and £40 or more .

Intakes of vitamins A, C, and E and use of multiple vitamin supplements and risk of colon cancer: a pooled analysis of prospective cohort studies - Yikyung Park; Donna Spiegelman; David J. Hunter; Demetrius Albanes; Leif Bergkvist; Julie E. Buring; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Lisa Harnack; Ikuko Kato; Vittorio Krogh; et al. (Cancer Causes & Control, 2010)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

Immunization of Guinea Pigs with Novel Hepatitis B Antigen as Nanoparticle Aggregate Powders Administered by the Pulmonary Route - Pavan Muttil; Cecilia Prego; Lucila Garcia-Contreras; Brian Pulliam; John Kevin Fallon; Chenchen Wang; Anthony James Hickey; David Edwards (The AAPS Journal, 2010)

First Results of the Regional Earthquake Likelihood Models Experiment - Danijel Schorlemmer; J. Douglas Zechar; Maximilian J. Werner; Edward H. Field; David D. Jackson; Thomas H. Jordan (Pure and Applied Geophysics, 2010)

Co-regulation of dark and light reactions in three biochemical subtypes of C4 species - Olavi Kiirats; David M. Kramer; Gerald E. Edwards (Photosynthesis Research, 2010)

Effects of parameter error on Cooper-Jacob drawdown estimates - David A. Edwards (Hydrogeology Journal, 2010)

Alcohol intake and pancreatic cancer: a pooled analysis from the pancreatic cancer cohort consortium (PanScan) - Dominique S. Michaud; Alina Vrieling; Li Jiao; Julie B. Mendelsohn; Emily Steplowski; Shannon M. Lynch; Jean Wactawski-Wende; Alan A. Arslan; H. Bas Bueno-de-Mesquita; Charles S. Fuchs; Myron Gross; Kathy Helzlsouer; et al. (Cancer Causes & Control, 2010)

Enemy release does not increase performance of Cirsium arvense in New Zealand - Michael G. Cripps; Grant R. Edwards; Graeme W. Bourdôt; David J. Saville; Hariet L. Hinz; Simon V. Fowler (Plant Ecology, 2010)

The influence of interval versus continuous exercise on thermoregulation, torso hemodynamics, and finger dexterity in the cold - Matthew D. Muller; Edward J. Ryan; David M. Bellar; Chul-Ho Kim; Robert P. Blankfield; Sarah M. Muller; Ellen L. Glickman (European Journal of Applied Physiology, 2010)

The WAMME regional model intercomparison study - Leonard M. Druyan; Jinming Feng; Kerry H. Cook; Yongkang Xue; Matthew Fulakeza; Samson M. Hagos; Abdourahamane Konaré; Wilfran Moufouma-Okia; David P. Rowell; Edward K. Vizy; Seidou Sanda Ibrah (Climate Dynamics, 2010)

Choosing What to Believe About Forests: Differences Between Professional and Non-Professional Evaluative Criteria - Roje S. Gootee; Keith A. Blatner; David M. Baumgartner; Matthew S. Carroll; Edward P. Weber (Small-scale Forestry, 2010)

Wireless Technologies, Ubiquitous Computing and Mobile Health: Application to Drug Abuse Treatment and Compliance with HIV Therapies - Edward W. Boyer; David Smelson; Richard Fletcher; Douglas Ziedonis; Rosalind W. Picard (Journal of Medical Toxicology, 2010)

Formulation Development and In Vivo Evaluation of a New Dry Powder Formulation of Albuterol Sulphate in Beagle Dogs - Philip J. Kuehl; Edward G. Barrett; Jacob D. McDonald; Karin Rudolph; David Vodak; Dan Dobry; David Lyon (Pharmaceutical Research, 2010)

Molecular keys unlock the mysteries of variable survival responses of blue crabs to hypoxia - Geoffrey W. Bell; David B. Eggleston; Edward J. Noga (Oecologia, 2010)

Biological consequences of invasion by reed canary grass (Phalaris arundinacea) - Greg Spyreas; Brian W. Wilm; Allen E. Plocher; David M. Ketzner; Jeffrey W. Matthews; James L. Ellis; Edward J. Heske (Biological Invasions, 2010)

World phylogeography and male-mediated gene flow in the sandbar shark, Carcharhinus plumbeus - DAVID S. PORTNOY; JAN R. MCDOWELL; EDWARD J. HEIST; JOHN A. MUSICK; JOHN E. GRAVES (Molecular Ecology, 2010)

The high value of logged tropical forests: lessons from northern Borneo - Nicholas J. Berry; Oliver L. Phillips; Simon L. Lewis; Jane K. Hill; David P. Edwards; Noel B. Tawatao; Norhayati Ahmad; David Magintan; Chey V. Khen; M. Maryati; Robert C. Ong; Keith C. Hamer (Biodiversity and Conservation, 2010)

Local people value environmental services provided by forested parks - Navjot S. Sodhi; Tien Ming Lee; Cagan H. Sekercioglu; Edward L. Webb; Dewi M. Prawiradilaga; David J. Lohman; Naomi E. Pierce; Arvin C. Diesmos; Madhu Rao; Paul R. Ehrlich (Biodiversity and Conservation, 2010)

Population synchrony of a native fish across three Laurentian Great Lakes: evaluating the effects of dispersal and climate - David B. Bunnell; Jean V. Adams; Owen T. Gorman; Charles P. Madenjian; Stephen C. Riley; Edward F. Roseman; Jeffrey S. Schaeffer (Oecologia, 2010)

Spotlight: Northwest Rota-1 Seamount - William Chadwick; Robert Embley; Edward Baker; Joseph Resing; John Lupton; Katharine Cashman; Robert Dziak; Verna Tunnicliffe; David Butterfield; Yoshihiko Tamura (Oceanography, 2010)

Abundances of crenarchaeal amoA genes and transcripts in the Pacific Ocean - Matthew J. Church; Brenner Wai; David M. Karl; Edward F. DeLong (Environmental Microbiology, 2010)
Summary Planktonic Crenarchaea are thought to play a key role in chemolithotrophic ammonia oxidation, a critical step of the marine nitrogen (N) cycle. In this study, we examined the spatial distributions of ammonia‐oxidizing Crenarchaea across a large (∼5200 km) region of the central Pacific Ocean. Examination of crenarchaeal 16S rRNA, ammonia monooxygenase subunit A ( amoA ) genes, and amoA transcript abundances provided insight into their spatial distributions and activities. Crenarchaeal gene abundances increased three to four orders of magnitude with depth between the upper ocean waters and dimly lit waters of the mesopelagic zone. The resulting median value of the crenarchaeal amoA : 16S rRNA gene ratio was 1.3, suggesting the majority of Crenarchaea in the epi‐ and mesopelagic regions of the Pacific Ocean have the metabolic machinery for ammonia oxidation. Crenarchaeal amoA transcript abundances typically increased one to two orders of magnitude in the transitional zone separating the epipelagic waters from the mesopelagic (100–200 m), before decreasing into the interior of the mesopelagic zone. The resulting gene copy normalized transcript abundances revealed elevated amoA expression in the upper ocean waters (0–100 m) where crenarchaeal abundances were low, with transcripts decreasing into the mesopelagic zone as crenarchaeal gene abundances increased. These results suggest ammonia‐oxidizing Crenarchaea are active contributors to the N cycle throughout the epi‐ and mesopelagic waters of the Pacific Ocean.

Reduction of fumarate, mesaconate and crotonate by Mfr, a novel oxygen‐regulated periplasmic reductase in Campylobacter jejuni - Edward Guccione; Andrew Hitchcock; Stephen J. Hall; Francis Mulholland; Neil Shearer; Arnoud H. M. Van Vliet; David J. Kelly (Environmental Microbiology, 2010)
Summary Methylmenaquinol : fumarate reductase (Mfr) is a newly recognized type of fumarate reductase present in some ε‐proteobacteria, where the active site subunit (MfrA) is localized in the periplasm, but for which a physiological role has not been identified. We show that the Campylobacter jejuni mfrABE operon is transcribed from a single promoter, with the mfrA gene preceded by a small open reading‐frame ( mfrX ) encoding a C. jejuni ‐specific polypeptide of unknown function. The growth characteristics and enzyme activities of mutants in the mfrA and menaquinol : fumarate reductase A ( frdA ) genes show that the cytoplasmic facing Frd enzyme is the major fumarate reductase under oxygen limitation. The Mfr enzyme is shown to be necessary for maximal rates of growth by fumarate respiration and rates of fumarate reduction in intact cells measured by both viologen assays and 1 H‐NMR were slower in an mfrA mutant. As periplasmic fumarate reduction does not require fumarate/succinate antiport, Mfr may allow more efficient adaptation to fumarate‐dependent growth. However, a further rationale for the periplasmic location of Mfr is suggested by the observation that the enzyme also reduces the fumarate analogues mesaconate and crotonate; fermentation products of anaerobes with which C. jejuni shares its gut environment, that are unable to be transported into the cell. Both MfrA and MfrB subunits were localized in the periplasm by immunoblotting and 2D‐gel electrophoresis, but an mfrE mutant accumulated unprocessed MfrA in the cytoplasm, suggesting a preassembled MfrABE holoenzyme has to be recognized by the TAT system for translocation to occur. Gene expression studies in chemostat cultures following an aerobic‐anaerobic shift showed that mfrA is highly upregulated by oxygen limitation, as would be experienced in vivo . Our results indicate that in addition to a role in fumarate respiration, Mfr allows C. jejuni to reduce analogous substrates specifically present in the host gut environment.

Payments for Ecosystem Services as a Framework for Community‐Based Conservation in Northern Tanzania - FRED NELSON; CHARLES FOLEY; LARA S. FOLEY; ABRAHAM LEPOSO; EDWARD LOURE; DAVID PETERSON; MIKE PETERSON; THAD PETERSON; HASSAN SACHEDINA; ANDREW WILLIAMS (Conservation Biology, 2010)
Payments for ecosystem services (PES) are an increasingly promoted approach to conservation. These approaches seek to develop financial mechanisms that create economic incentives for the maintenance of ecosystems and associated biodiversity by rewarding those who are responsible for provision of ecological services. There are, however, few cases in which such schemes have been used as a strategy for conserving wildlife in developing countries and very few operational examples of such schemes of any sort in sub‐Saharan Africa. In savannah ecosystems, large mammal populations generally depend on seasonal use of extensive areas and are widely declining as a result of habitat loss, overexploitation, and policies that limit local benefits from wildlife. Community‐based conservation strategies seek to create local incentives for conserving wildlife, but often have limited impact as a result of persistent institutional barriers that limit local rights and economic benefits. In northern Tanzania, a consortium of tourism operators is attempting to address these challenges through an agreement with a village that possesses part of a key wildlife dispersal area outside Tarangire National Park. The operators pay the community to enforce voluntary restrictions on agricultural cultivation and permanent settlement in a defined area of land. The initiative represents a potentially cost‐effective framework for community‐based conservation in an ecologically important area and is helping to reconcile historically conflicting local and national interests relative to land tenure, pastoralist livelihoods, and conservation. Wider adaptation of payments for ecosystem services approaches to settings where sustaining wildlife populations depends on local stewardship may help address current challenges facing conservation outside state‐protected areas in savannah ecosystems in sub‐Saharan Africa and other parts of the world.

Ecosystem Services as a Common Language for Coastal Ecosystem‐Based Management - ELISE F. GRANEK; STEPHEN POLASKY; CARRIE V. KAPPEL; DENISE J. REED; DAVID M. STOMS; EVAMARIA W. KOCH; CHRIS J. KENNEDY; LORI A. CRAMER; SALLY D. HACKER; EDWARD B. BARBIER; SHANKAR ASWANI; MARY RUCKELSHAUS; et al. (Conservation Biology, 2010)
Ecosystem‐based management is logistically and politically challenging because ecosystems are inherently complex and management decisions affect a multitude of groups. Coastal ecosystems, which lie at the interface between marine and terrestrial ecosystems and provide an array of ecosystem services to different groups, aptly illustrate these challenges. Successful ecosystem‐based management of coastal ecosystems requires incorporating scientific information and the knowledge and views of interested parties into the decision‐making process. Estimating the provision of ecosystem services under alternative management schemes offers a systematic way to incorporate biogeophysical and socioeconomic information and the views of individuals and groups in the policy and management process. Employing ecosystem services as a common language to improve the process of ecosystem‐based management presents both benefits and difficulties. Benefits include a transparent method for assessing trade‐offs associated with management alternatives, a common set of facts and common currency on which to base negotiations, and improved communication among groups with competing interests or differing worldviews. Yet challenges to this approach remain, including predicting how human interventions will affect ecosystems, how such changes will affect the provision of ecosystem services, and how changes in service provision will affect the welfare of different groups in society. In a case study from Puget Sound, Washington, we illustrate the potential of applying ecosystem services as a common language for ecosystem‐based management.

Urothelial carcinoma: Stem cells on the edge - William D. Brandt; William Matsui; Jonathan E. Rosenberg; Xiaobing He; Shizhang Ling; Edward M. Schaeffer; David M. Berman (Cancer and Metastasis Reviews, 2009)

A limited innate immune response is induced by a replication-defective herpes simplex virus vector following delivery to the murine central nervous system - Zane Zeier; J Santiago Aguilar; Cecilia M Lopez; GB Devi-Rao; Zachary L Watson; Henry V Baker; Edward K Wagner; David C Bloom (Journal of NeuroVirology, 2009)

The evolution of intermediate castration virulence and ant coexistence in a spatially structured environment - András Szilágyi; István Scheuring; David P. Edwards; Jerome Orivel; Douglas W. Yu (Ecology Letters, 2009)
Ecology Letters (2009) 12: 1306–1316 Abstract Theory suggests that spatial structuring should select for intermediate levels of virulence in parasites, but empirical tests are rare and have never been conducted with castration (sterilizing) parasites. To test this theory in a natural landscape, we construct a spatially explicit model of the symbiosis between the ant‐plant Cordia nodosa and its two, protecting ant symbionts, Allomerus and Azteca . Allomerus is also a castration parasite, preventing fruiting to increase colony fecundity. Limiting the dispersal of Allomerus and host plant selects for intermediate castration virulence. Increasing the frequency of the mutualist, Azteca , selects for higher castration virulence in Allomerus , because seeds from Azteca ‐inhabited plants are a public good that Allomerus exploits. These results are consistent with field observations and, to our knowledge, provide the first empirical evidence supporting the hypothesis that spatial structure can reduce castration virulence and the first such evidence in a natural landscape for either mortality or castration virulence.

The Value of Rehabilitating Logged Rainforest for Birds - DAVID P. EDWARDS; FELICITY A. ANSELL; ABDUL H. AHMAD; REUBEN NILUS; KEITH C. HAMER (Conservation Biology, 2009)
The recent advent of carbon crediting has led to a rapid rise in biosequestration projects that seek to remove carbon from the atmosphere through afforestation and forest rehabilitation. Such projects also present an important potential opportunity to reverse biodiversity losses resulting from deforestation and forest degradation, but the biodiversity benefits of different forms of biosequestration have not been considered adequately. We captured birds in mist nets to examine the effects of rehabilitation of logged forest on birds in Sabah, Borneo, and to test the hypothesis that rehabilitation restores avian assemblages within regenerating forest to a condition closer to that seen in unlogged forest. Species richness and diversity were similar in unlogged and rehabilitated forest, but significantly lower in naturally regenerating forest. Rehabilitation resulted in a relatively rapid recovery of populations of insectivores within logged forest, especially those species that forage by sallying, but had a marked adverse effect on frugivores and possibly reduced the overall abundance of birds within regenerating forest. In view of these results, we advocate increased management for heterogeneity within rehabilitated forests, but we strongly urge an increased role for forest rehabilitation in the design and implementation of a biodiversity‐friendly carbon‐offsetting market.

Genotypes of Brassica rapa respond differently to plant-induced variation in air CO2 concentration in growth chambers with standard and enhanced venting - Christine E. Edwards; Monia S. H. Haselhorst; Autumn M. McKnite; Brent E. Ewers; David G. Williams; Cynthia Weinig (Theoretical and Applied Genetics, 2009)

The roles of tolerance in the evolution, maintenance and breakdown of mutualism - David P. Edwards (The Science of Nature, 2009)

Rapid effects of hypoxia on H+ homeostasis in articular chondrocytes - John S. Gibson; David McCartney; Joanna Sumpter; Thomas P. A. Fairfax; Peter I. Milner; Hannah L. Edwards; Robert J. Wilkins (Pflügers Archiv - European Journal of Physiology, 2009)

Are adolescents more vulnerable to drug addiction than adults? Evidence from animal models - Nicole L. Schramm-Sapyta; Q. David Walker; Joseph M. Caster; Edward D. Levin; Cynthia M. Kuhn (Psychopharmacology, 2009)

Linking stream and landscape trajectories in the southern Appalachians - Edward P. Gardiner; Andrew B. Sutherland; Rebecca J. Bixby; Mark C. Scott; Judy L. Meyer; Gene S. Helfman; E. Fred Benfield; Cathy M. Pringle; Paul V. Bolstad; David N. Wear (Environmental Monitoring and Assessment, 2009)

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

A record of Lateglacial and early Holocene environmental and ecological change from southwestern Connecticut, USA - W. Wyatt Oswald; David R. Foster; Elaine D. Doughty; Edward K. Faison (Journal of Quaternary Science, 2009)
Analyses of a sediment core from Highstead Swamp in southwestern Connecticut, USA, reveal Lateglacial and early Holocene ecological and hydrological changes. Lateglacial pollen assemblages are dominated by Picea and Pinus subg. Pinus , and the onset of the Younger Dryas (YD) cold interval is evidenced by higher abundance of Abies and Alnus viridis subsp. crispa . As climate warmed at the end of the YD, Picea and Abies declined and Pinus strobus became the dominant upland tree species. A shift from lacustrine sediment to organic peat at the YD–Holocene boundary suggests that the lake that existed in the basin during the Lateglacial interval developed into a swamp in response to reduced effective moisture. A change in wetland vegetation from Myrica gale to Alnus incana subsp. rugosa and Sphagnum is consistent with this interpretation of environmental changes at the beginning of the Holocene. Copyright © 2009 John Wiley & Sons, Ltd.

Formulation and Pharmacokinetics of Self-Assembled Rifampicin Nanoparticle Systems for Pulmonary Delivery - Jean C. Sung; Danielle J. Padilla; Lucila Garcia-Contreras; Jarod L. VerBerkmoes; David Durbin; Charles A. Peloquin; Katharina J. Elbert; Anthony J. Hickey; David A. Edwards (Pharmaceutical Research, 2009)

Biochemical properties and biodegradation of dissolved organic matter from soils - Susan R. Bowen; Edward G. Gregorich; David W. Hopkins (Biology and Fertility of Soils, 2009)

Intestinal Lymphatic Transport Enhances the Post-Prandial Oral Bioavailability of a Novel Cannabinoid Receptor Agonist Via Avoidance of First-Pass Metabolism - Natalie L. Trevaskis; David M. Shackleford; William N. Charman; Glenn A. Edwards; Anne Gardin; Silke Appel-Dingemanse; Olivier Kretz; Bruno Galli; Christopher J. H. Porter (Pharmaceutical Research, 2009)

Planter Skips and Impaired Stand Favors Potato Virus Y Spread in Potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2009)

Estuarine Ecosystem Response Captured Using a Synoptic Climatology - David G. Kimmel; W. David Miller; Lawrence W. Harding; Edward D. Houde; Michael R. Roman (Estuaries and Coasts, 2009)

Enhanced Resistance to Control Potato Tuberworm by Combining Engineered Resistance, Avidin, and Natural Resistance Derived from, Solanum Chacoense - Susannah G. Cooper; David S. Douches; Kelly Zarka; Edward J. Grafius (American Journal of Potato Research, 2009)

Border Treatment to Reduce Insecticide Use in Seed Potato Production: Biological, Economic, and Managerial Analysis - Matthew W. Carroll; Edward B. Radcliffe; Ian V. MacRae; David W. Ragsdale; Kent D. Olson; Thaddee Badibanga (American Journal of Potato Research, 2009)

Photoperiod insensitive Ppd-A1a mutations in tetraploid wheat (Triticum durum Desf.) - Edward P. Wilhelm; Adrian S. Turner; David A. Laurie (Theoretical and Applied Genetics, 2009)

Metagenomic and stable isotopic analyses of modern freshwater microbialites in Cuatro Ciénegas, Mexico - Mya Breitbart; Ana Hoare; Anthony Nitti; Janet Siefert; Matthew Haynes; Elizabeth Dinsdale; Robert Edwards; Valeria Souza; Forest Rohwer; David Hollander (Environmental Microbiology, 2009)
Summary Ancient biologically mediated sedimentary carbonate deposits, including stromatolites and other microbialites, provide insight into environmental conditions on early Earth. The primary limitation to interpreting these records is our lack of understanding regarding microbial processes and the preservation of geochemical signatures in contemporary microbialite systems. Using a combination of metagenomic sequencing and isotopic analyses, this study describes the identity, metabolic potential and chemical processes of microbial communities from living microbialites from Cuatro Ciénegas, Mexico. Metagenomic sequencing revealed a diverse, redox‐dependent microbial community associated with the microbialites. The microbialite community is distinct from other marine and freshwater microbial communities, and demonstrates extensive environmental adaptation. The microbialite metagenomes contain a large number of genes involved in the production of exopolymeric substances and the formation of biofilms, creating a complex, spatially structured environment. In addition to the spatial complexity of the biofilm, microbial activity is tightly controlled by sensory and regulatory systems, which allow for coordination of autotrophic and heterotrophic processes. Isotopic measurements of the intracrystalline organic matter demonstrate the importance of heterotrophic respiration of photoautotrophic biomass in the precipitation of calcium carbonate. The genomic and stable isotopic data presented here significantly enhance our evolving knowledge of contemporary biomineralization processes, and are directly applicable to studies of ancient microbialites.

Colorado Potato Beetle Resistance to Insecticides - Andrei Alyokhin; Mitchell Baker; David Mota-Sanchez; Galen Dively; Edward Grafius (American Journal of Potato Research, 2008)

Sub‐millennial climate shifts in the western Mediterranean during the last glacial period recorded in a speleothem from Mallorca, Spain - Edward J. Hodge; David A. Richards; Peter L. Smart; Angel Ginés; David P. Mattey (Journal of Quaternary Science, 2008)
Very few high‐resolution and directly dated terrestrial archives of the last glacial period exist for the western Mediterranean region, yet this is a key locality for recording sub‐millennial North Atlantic and Mediterranean climate change. Here, we present evidence of effective precipitation changes based on growth history and δ 13 C of calcite in a Mallorcan stalagmite that grew between 112 and 48 ka. Effective precipitation in Mallorca appears to have been sensitive to proximal sea surface temperature variations and at certain times, ca. 76 ka for example, changed rapidly from moist to arid conditions in only a few centuries. A sea‐level highstand during Marine Isotope Stage (MIS) 5a interrupted growth. Regrowth started promptly after this, but effective precipitation decreased markedly for much of the later part of MIS 5a, and also for shorter periods correlative with Heinrich events H8 (ca. 90 ka) and H6 (ca. 65 ka), with growth ceasing during H5 (ca. 48 ka). Arid episodes in Mallorca appear to be expressions of extremely cold periods recorded further north in Europe and occur contemporaneously with rapid decreases in Greenland temperature. Copyright © 2008 John Wiley & Sons, Ltd.

Association of the TCF7L2 polymorphism with colorectal cancer and adenoma risk - Aditi Hazra; Charles S. Fuchs; Andrew T. Chan; Edward L. Giovannucci; David J. Hunter (Cancer Causes & Control, 2008)

Tolerating castration by hiding flowers in plain sight - David P. Edwards; Douglas W. Yu (Behavioral Ecology and Sociobiology, 2008)

Antiproliferative compounds of Artabotrys madagascariensis from the Madagascar rainforest - Brian T. Murphy; Shugeng Cao; Peggy J. Brodie; James S. Miller; Fidy Ratovoson; Chris Birkinshaw; Etienne Rakotobe; Vincent E. Rasamison; Karen Tendyke; Edward M. Suh; David G. I. Kingston (Natural Product Research, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Heterologous expression of pyruvate decarboxylase in Geobacillus thermoglucosidasius - Ann H. Thompson; David J. Studholme; Edward M. Green; David J. Leak (Biotechnology Letters, 2008)

A meta-analysis of studies investigating the effects of lead exposure on nerve conduction - Edward F. Krieg; David W. Chrislip; W. Stephen Brightwell (Archives of Toxicology, 2008)

TCR-MHC docking orientation: natural selection, or thymic selection? - Edward J. Collins; David S. Riddle (Immunologic Research, 2008)

Relationship of predation potential to mortality of Calanus finmarchicus on Georges Bank, northwest Atlantic - Mark D. Ohman; Edward G. Durbin; Jeffrey A. Runge; Barbara K. Sullivan; David B. Field (Limnology and Oceanography, 2008)
Based on 29 cruises on Georges Bank between January and June, conducted as part of the U.S. Global Ocean Ecosystem Dynamics program, we describe seasonal and spatial variability of early life history mortality for the planktonic copepod Calanus finmarchicus and relate mortality to an index of predation potential from a suite of suspension‐feeding predators. Emphasis is placed on the earliest life history phase wherein peak mortality occurs. Instantaneous mortality rates for a combined egg‐through‐nauplius‐3 stage show a recurrent seasonal pattern of a modest elevation in January followed by a seasonal peak in May of all 5 study yr. Spatial differences exist in mortality rates, with a higher probability of mortality on the southern flank in winter and a pronounced seasonal maximum on the bank crest in May. Three hypotheses associated, respectively, with egg hatching success, advection, and invertebrate predation were evaluated to account for the seasonal and spatial mortality patterns. Variations in egg‐hatching success are inconsistent with the observed seasonal patterns of loss. Off‐bank advection, particularly on the southern flank, appears to be the dominant loss term in January. Apart from this winter period, egg mortality is associated with predation potential. Comparison of an index of daily rates of egg loss with an index of consumption rates of eggs by suspended hydroids, hydromedusae, and five species of planktonic copepods show general agreement between mortality and predation in both seasonal variation and spatial patterns. Of the predator taxa, late copepodid and adult C. finmarchicus , supplemented by planktonic hydroids, appear to have the largest quantitative predation effect.

Carbon allocation in boreal black spruce forests across regions varying in soil temperature and precipitation - JASON G. VOGEL; BEN P. BOND‐LAMBERTY; EDWARD A. G. SCHUUR; STITH T. GOWER; MICHELLE C. MACK; KARI E. B. O'CONNELL; DAVID W. VALENTINE; ROGER W. RUESS (Global Change Biology, 2008)
A common hypothesis for northern ecosystems is that low soil temperatures inhibit plant productivity. To address this hypothesis, we reviewed how separate components of ecosystem carbon (C) cycling varied along a soil temperature gradient for nine well‐drained, relatively productive boreal black spruce ( Picea mariana Mill. [B.S.P.]) forests in Alaska, USA, and Saskatchewan and Manitoba, Canada. Annual soil temperature [expressed as soil summed degree days (SDD)] was positively correlated with aboveground net primary productivity (ANPP), while negatively correlated with total belowground carbon flux (TBCF). The partitioning of C to ANPP at the expense of root processes represented a nearly 1 : 1 tradeoff across the soil temperature gradient, which implied that the amount of C cycling through these black spruce ecosystems was relatively insensitive to variation in SDD. Moreover, the rate at which C accumulated in the ecosystem since the last stand replacing fire was unrelated to SDD, but SDD was positively correlated to the ratio of spruce‐biomass : forest‐floor‐mass. Thus, plant partitioning of C and the distribution of ecosystem C were apparently affected by soil temperature, although across regions, precipitation co‐varied with soil temperature. These two factors likely correlated with one another because of precipitation's influence on soil heat balance, suggesting that a soil temperature–precipitation interaction could be responsible for the shifts in C allocation. Nonetheless, our results highlight that for this boreal ecosystem, ANPP and TBCF can be negatively correlated. In tropical and temperate forests, TBCF and ANPP have been reported as positively correlated, and our results may reflect the unique interactions between soil temperature, forest floor accumulation, rooting depth, and nutrient availability that characterize the black spruce forest type.

Return of Salmon-Derived Nutrients from the Riparian Zone to the Stream during a Storm in Southeastern Alaska - Jason B. Fellman; Eran Hood; Rick T. Edwards; David V. D’Amore (Ecosystems, 2008)

Extensive polymorphism and geographical variation at a positively selected MHC class II B gene of the lesser kestrel ( Falco naumanni ) - MIGUEL ALCAIDE; SCOTT V. EDWARDS; JUAN J. NEGRO; DAVID SERRANO; JOSÉ L. TELLA (Molecular Ecology, 2008)
Understanding the selective forces that shape genetic variation in natural populations remains a high priority in evolutionary biology. Genes at the major histocompatibility complex (MHC) have become excellent models for the investigation of adaptive variation and natural selection because of their crucial role in fighting off pathogens. Here we present one of the first data sets examining patterns of MHC variation in wild populations of a bird of prey, the lesser kestrel, Falco naumanni . We report extensive polymorphism at the second exon of a putatively functional MHC class II gene, Fana‐ DAB*1. Overall, 103 alleles were isolated from 121 individuals sampled from Spain to Kazakhstan. Bayesian inference of diversifying selection suggests that several amino acid sites may have experienced strong positive selection (ω = 4.02 per codon). The analysis also suggests a prominent role of recombination in generating and maintaining MHC diversity (ρ = 4 Nc = 0.389 per codon, θ = 0.017 per codon). Both the Fana ‐DAB*1 locus and a set of eight polymorphic microsatellite markers revealed an isolation‐by‐distance pattern across the Western Palaearctic ( r = 0.67; P = 0.01 and r = 0.50; P = 0.04, respectively). Nonetheless, geographical variation at the MHC contrasts with relatively uniform distributions in the frequencies of microsatellite alleles. In addition, we found lower fixation rates in the MHC than those predicted by genetic drift after controlling for neutral mitochondrial sequences. Our results therefore underscore the role of balancing selection as well as spatial variations in parasite‐mediated selection regimes in shaping MHC diversity when gene flow is limited.

Preparation and in Vivo Evaluation of a Dry Powder for Inhalation of Capreomycin - Jennifer Fiegel; Lucila Garcia-Contreras; Matthew Thomas; Jarod VerBerkmoes; Katharina Elbert; Anthony Hickey; David Edwards (Pharmaceutical Research, 2008)

Sediment quality triad assessment of an industrialized estuary of the northeastern USA - Timothy J. Iannuzzi; Tina N. Armstrong; Edward R. Long; Jacqueline Iannuzzi; David F. Ludwig (Environmental Monitoring and Assessment, 2008)

Asymmetric larval competition in the parasitoid wasp Nasonia vitripennis: a role in sex allocation? - Edward M. Sykes; Tabitha M. Innocent; Ido Pen; David M. Shuker; Stuart A. West (Behavioral Ecology and Sociobiology, 2008)

Measurement of copepod predation on nauplii using qPCR of the cytochrome oxidase I gene - Edward G. Durbin; Maria C. Casas; Tatiana A. Rynearson; David C. Smith (Marine Biology, 2008)

Macroinvertebrate drift density in relation to abiotic factors in the Missouri River - Christopher H. Hay; Thomas G. Franti; David B. Marx; Edward J. Peters; Larry W. Hesse (Hydrobiologia, 2008)

Exploring the Submarine Ring of Fire: Mariana Arc - Western Pacific - Robert Embley; Edward Baker; David Butterfield; William Chadwick; John Lupton; Joseph Resing; Cornel de Ronde; Ko-ichi Nakamura; Verena Tunnicliffe; John Dower; Susan Merle (Oceanography, 2007)

External mechanical compression reduces regional arterial stiffness - Kevin S. Heffernan; David G. Edwards; Lindy Rossow; Sae Young Jae; Bo Fernhall (European Journal of Applied Physiology, 2007)

The reference genetic linkage map for the multinational Brassica rapa genome sequencing project - Su Ryun Choi; Graham R. Teakle; Prikshit Plaha; Jeong Hee Kim; Charlotte J. Allender; Elena Beynon; Zhong Yun Piao; Pilar Soengas; Tae Ho Han; Graham J. King; Guy C. Barker; Paul Hand; et al. (Theoretical and Applied Genetics, 2007)

A biological consequence of reducing Arctic ice cover: arrival of the Pacific diatom Neodenticula seminae in the North Atlantic for the first time in 800 000 years - PHILIP C. REID; DAVID G. JOHNS; MARTIN EDWARDS; MICHEL STARR; MICHEL POULIN; PAULI SNOEIJS (Global Change Biology, 2007)
The Continuous Plankton Recorder survey has monitored plankton in the Northwest Atlantic at monthly intervals since 1962, with an interegnum between 1978 and 1990. In May 1999, large numbers of the Pacific diatom Neodenticula seminae were found in Continuous Plankton Recorder (CPR) samples in the Labrador Sea as the first record in the North Atlantic for more than 800 000 years. The event coincided with modifications in Arctic hydrography and circulation, increased flows of Pacific water into the Northwest Atlantic and in the previous year the exceptional occurrence of extensive ice‐free water to the North of Canada. These observations indicate that N. seminae was carried in a pulse of Pacific water in 1998/early 1999 via the Canadian Arctic Archipelago and/or Fram Strait. The species occurred previously in the North Atlantic during the Pleistocene from∼1.2 to∼0.8 Ma as recorded in deep sea sediment cores. The reappearance of N. seminae in the North Atlantic is an indicator of the scale and speed of changes that are taking place in the Arctic and North Atlantic oceans as a consequence of regional climate warming. Because of the unusual nature of the event it appears that a threshold has been passed, marking a change in the circulation between the North Pacific and North Atlantic Oceans via the Arctic. Trans‐Arctic migrations from the Pacific into the Atlantic are likely to occur increasingly over the next 100 years as Arctic ice continues to melt affecting Atlantic biodiversity and the biological pump with consequent feedbacks to the carbon cycle.

Asymmetric larval competition in the parasitoid wasp Nasonia vitripennis: a role in sex allocation? - Edward M. Sykes; Tabitha M. Innocent; Ido Pen; David M. Shuker; Stuart A. West (Behavioral Ecology and Sociobiology, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Effects of acute fatigue on the volitional and magnetically-evoked electromechanical delay of the knee flexors in males and females - Claire Minshull; Nigel Gleeson; Michelle Walters-Edwards; Roger Eston; David Rees (European Journal of Applied Physiology, 2007)

Improved drought tolerance of transgenic Zea mays plants that express the glutamate dehydrogenase gene (gdhA) of E. coli - David A. Lightfoot; Rajsree Mungur; Rafiqa Ameziane; Scott Nolte; Lynn Long; Karen Bernhard; Andrew Colter; Karen Jones; M. J. Iqbal; Edward Varsa; Brian Young (Euphytica, 2007)

Tree-ring reconstructed megadroughts over North America since a.d. 1300 - David W. Stahle; Falko K. Fye; Edward R. Cook; R. Daniel Griffin (Climatic Change, 2007)

The roles of sensory traps in the origin, maintenance, and breakdown of mutualism - David P. Edwards; Douglas W. Yu (Behavioral Ecology and Sociobiology, 2007)

Modeling and Prediction of Marine Microbial Populations in the Genomic Era - Raleigh Hood; Edward Laws; Michael Follows; David Siegel (Oceanography, 2007)

Anoxia-induced changes in reactive oxygen species and cyclic nucleotides in the painted turtle - Matthew Edward Pamenter; Michael David Richards; Leslie Thomas Buck (Journal of Comparative Physiology B, 2007)

Resistance to green peach aphid,Myzus persicae (Sulzer), and potato aphid,Macrosiphum euphorbiae (Thomas), in potato cultivars - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2007)

Post‐glacial changes in spatial patterns of vegetation across southern New England - W. Wyatt Oswald; Edward K. Faison; David R. Foster; Elaine D. Doughty; Brian R. Hall; Barbara C. S. Hansen (Journal of Biogeography, 2007)
Aim We analysed lake‐sediment pollen records from eight sites in southern New England to address: (1) regional variation in ecological responses to post‐glacial climatic changes, (2) landscape‐scale vegetational heterogeneity at different times in the past, and (3) environmental and ecological controls on spatial patterns of vegetation. Location The eight study sites are located in southern New England in the states of Massachusetts and Connecticut. The sites span a climatic and vegetational gradient from the lowland areas of eastern Massachusetts and Connecticut to the uplands of north‐central and western Massachusetts. Tsuga canadensis and Fagus grandifolia are abundant in the upland area, while Quercus , Carya and Pinus species have higher abundances in the lowlands. Methods We collected sediment cores from three lakes in eastern and north‐central Massachusetts (Berry East, Blood and Little Royalston Ponds). Pollen records from those sites were compared with previously published pollen data from five other sites. Multivariate data analysis (non‐metric multi‐dimensional scaling) was used to compare the pollen spectra of these sites through time. Results Our analyses revealed a sequence of vegetational responses to climate changes occurring across southern New England during the past 14,000 calibrated radiocarbon years before present (cal yr bp ). Pollen assemblages at all sites were dominated by Picea and Pinus banksiana between 14,000 and 11,500 cal yr bp ; by Pinus strobus from 11,500 to 10,500 cal yr bp ; and by P. strobus and Tsuga between 10,500 and 9500 cal yr bp . At 9500–8000 cal yr bp , however, vegetation composition began to differentiate between lowland and upland sites. Lowland sites had higher percentages of Quercus pollen, whereas Tsuga abundance was higher at the upland sites. This spatial heterogeneity strengthened between 8000 and 5500 cal yr bp , when Fagus became abundant in the uplands and Quercus pollen percentages increased further in the lowland records. The differentiation of upland and lowland vegetation zones remained strong during the mid‐Holocene Tsuga decline (5500–3500 cal yr bp ), but the pattern weakened during the late‐Holocene (3500–300 cal yr bp ) and European‐settlement intervals. Within‐group similarity declined in response to the uneven late‐Holocene expansion of Castanea , while between‐group similarity increased due to homogenization of the regional vegetation by forest clearance and ongoing disturbances. Main conclusions The regional gradient of vegetation composition across southern New England was first established between 9500 and 8000 cal yr bp . The spatial heterogeneity of the vegetation may have arisen at that time in response to the development or strengthening of the regional climatic gradient. Alternatively, the differentiation of upland and lowland vegetation types may have occurred as the climate ameliorated and an increasing number of species arrived in the region, arranging themselves in progressively more complex vegetation patterns across relatively stationary environmental gradients. The emergence of a regional vegetational gradient in southern New England may be a manifestation of the increasing number of species and more finely divided resource gradient.

Quantitative distribution of presumptive archaeal and bacterial nitrifiers in Monterey Bay and the North Pacific Subtropical Gyre - Tracy J. Mincer; Matthew J. Church; Lance Trent Taylor; Christina Preston; David M. Karl; Edward F. DeLong (Environmental Microbiology, 2007)
Summary The recent isolation of the ammonia‐oxidizing crenarchaeon Nitrosopumilus maritimus has expanded the known phylogenetic distribution of nitrifying phenotypes beyond the domain Bacteria . To further characterize nitrification in the marine environment and explore the potential crenarchaeal contribution to this process, we quantified putative nitrifying genes and phylotypes in picoplankton genomic libraries and environmental DNA samples from coastal and open ocean habitats. Betaproteobacteria ammonia monooxygenase subunit A ( amoA ) gene copy numbers were low or undetectable, in stark contrast to crenarchaeal amoA‐ like genes that were broadly distributed and reached up to 6 × 10 4 copies ml −1 . Unexpectedly, in the North Pacific Subtropical Gyre, a deeply branching crenarchaeal group related to a hot spring clade (pSL12) was at times abundant below the euphotic zone. Quantitative data suggested that the pSL12 relatives also contain archaeal amoA ‐like genes. In both coastal and open ocean habitats, close relatives of known nitrite‐oxidizing Nitrospina species were well represented in genomic DNA libraries and quantitative PCR profiles. Planktonic Nitrospina depth distributions correlated with those of Crenarchaea . Overall, the data suggest that amoA ‐containing Crenarchaea are more phylogenetically diverse than previously reported. Additionally, distributional patterns of planktonic Crenarchaea and Nitrospina species suggest potential metabolic interactions between these groups in the ocean's water column.

A high resolution green area index for modelling the seasonal dynamics of CO2 exchange in peatland vascular plant communities - David Wilson; Jukka Alm; Terhi Riutta; Jukka Laine; Kenneth A. Byrne; Edward P. Farrell; Eeva-Stiina Tuittila (Plant Ecology, 2007)

Guidelines on nicotine dose selection for in vivo research - Shannon G. Matta; David J. Balfour; Neal L. Benowitz; R. Thomas Boyd; Jerry J. Buccafusco; Anthony R. Caggiula; Caroline R. Craig; Allan C. Collins; M. Imad Damaj; Eric C. Donny; Phillip S. Gardiner; Sharon R. Grady; et al. (Psychopharmacology, 2007)

The Arabidopsis stearoyl-acyl carrier protein-desaturase family and the contribution of leaf isoforms to oleic acid synthesis - Aardra Kachroo; John Shanklin; Edward Whittle; Ludmila Lapchyk; David Hildebrand; Pradeep Kachroo (Plant Molecular Biology, 2006)

Assistive navigational devices that incorporate principles of spatial cognition and imagery - Geoffrey Edwards; Alison F. Eardley; Francine Malouin; Marlène Viger; Reda Yaagoubi; David Lambiel (Cognitive Processing, 2006)

CADMUS: use of affordances in cognitive modeling for wayfinding - Pierre-Emmanuel Michon; David Duguay; Geoffrey Edwards (Cognitive Processing, 2006)

Genetic identification of units for conservation in tomato frogs, genus Dyscophus - Ylenia Chiari; Pablo Orozco-terWengel; Miguel Vences; David R. Vieites; Augustin Sarovy; Jasmin E. Randrianirina; Axel Meyer; Edward Louis (Conservation Genetics, 2006)

The auxin-induced K+ channel gene Zmk1 in maize functions in coleoptile growth and is required for embryo development - Katrin Philippar; Kai Büchsenschütz; David Edwards; Julia Löffler; Hartwig Lüthen; Erhard Kranz; Keith J. Edwards; Rainer Hedrich (Plant Molecular Biology, 2006)

Empirical Bayes estimation of gene-specific effects in micro-array research - Jode W. Edwards; Grier P. Page; Gary Gadbury; Moonseong Heo; Tsuyoshi Kayo; Richard Weindruch; David B. Allison (Functional & Integrative Genomics, 2006)

Indirect effects of algae on coral: algae‐mediated, microbe‐induced coral mortality - Jennifer E. Smith; Morrigan Shaw; Rob A. Edwards; David Obura; Olga Pantos; Enric Sala; Stuart A. Sandin; Steven Smriga; Mark Hatay; Forest L. Rohwer (Ecology Letters, 2006)
Declines in coral cover are generally associated with increases in the abundance of fleshy algae. In many cases, it remains unclear whether algae are responsible, directly or indirectly, for coral death or whether they simply settle on dead coral surfaces. Here, we show that algae can indirectly cause coral mortality by enhancing microbial activity via the release of dissolved compounds. When coral and algae were placed in chambers together but separated by a 0.02 μ m filter, corals suffered 100% mortality. With the addition of the broad‐spectrum antibiotic ampicillin, mortality was completely prevented. Physiological measurements showed complementary patterns of increasing coral stress with proximity to algae. Our results suggest that as human impacts increase and algae become more abundant on reefs a positive feedback loop may be created whereby compounds released by algae enhance microbial activity on live coral surfaces causing mortality of corals and further algal growth.

O6-Methylguanine-DNA Methyltransferase Leu84Phe and Ile143Val Polymorphisms and Risk of Colorectal Cancer in the Nurses’ Health Study and Physicians’ Health Study (United States) - Gregory J. Tranah; James Bugni; Edward Giovannucci; Jing Ma; Charles Fuchs; Lisa Hines; Leona Samson; David J. Hunter (Cancer Causes & Control, 2006)

hAT element population genetics in Anopheles gambiae s.l. in Mozambique - David A. O’Brochta; Ramanand A. Subramanian; Jamison Orsetti; Edward Peckham; Nicole Nolan; Peter Arensburger; Peter W. Atkinson; Derek J. Charlwood (Genetica, 2006)

An ethoxylated alkyl phosphate (anionic surfactant) for the promotion of activities of proteases and its potential use in the enzymatic processing of wool - Qinghua Zhang; Edward Smith; Jinsong Shen; David Bishop (Biotechnology Letters, 2006)

A Case Study on the Effects of Heterogeneous Soil Moisture on Mesoscale Boundary-Layer Structure in the Southern Great Plains, U.S.A. Part I: Simple Prognostic Model - Ankur R. Desai; Kenneth J. Davis; Christoph J. Senff; Syed Ismail; Edward V. Browell; David R. Stauffer; Brian P. Reen (Boundary-Layer Meteorology, 2006)

Relationship of intertidal surface sediment chlorophyll concentration to hyperspectral reflectance and chlorophyll fluorescence - Jacco C. Kromkamp; Edward P. Morris; Rodney M. Forster; Claire Honeywill; Scott Hagerthey; David M. Paterson (Estuaries and Coasts, 2006)

Determination of a Human Hepatic Microsomal Scaling Factor for Predicting in Vivo Drug Clearance - Nancy Hakooz; Kiyomi Ito; Helen Rawden; Helen Gill; Lynn Lemmers; Alan R. Boobis; Robert J. Edwards; David J. Carlile; Brian G. Lake; J. Brian Houston (Pharmaceutical Research, 2006)

Genetic Susceptibility to Prostate Cancer: Prostate-specific Antigen and its Interaction with the Androgen Receptor (United States) - Weiva Sieh; Karen L. Edwards; Annette L. Fitzpatrick; Sengkeo L. Srinouanprachanh; Fred M. Farin; Stephanie A. Monks; Richard A. Kronmal; David L. Eaton (Cancer Causes & Control, 2006)

Sources of Sediment in Lake Pepin on the Upper Mississippi River in Response to Holocene Climatic Changes - David W. Kelley; Stefanie A. Brachfeld; Edward A. Nater; Herbert E. Wright (Journal of Paleolimnology, 2006)

A single operon-encoded form of the acetyl-CoA decarbonylase/synthase multienzyme complex responsible for synthesis and cleavage of acetyl-CoA in Methanosarcina thermophila - David A. Grahame; Simonida Gencic; Edward DeMoll (Archives of Microbiology, 2005)

Intercellular adhesion molecule-1 and childhood asthma - Yu-Fen Li; Yo-Hsuang Tsao; W. James Gauderman; David V. Conti; Edward Avol; Louis Dubeau; Frank D. Gilliland (Human Genetics, 2005)

Mental maze solving: directional fMRI tuning and population coding in the superior parietal lobule - Pavlos Gourtzelidis; Charidimos Tzagarakis; Scott M. Lewis; David A. Crowe; Edward Auerbach; Trenton A. Jerde; Kâmil Uğurbil; Apostolos P. Georgopoulos (Experimental Brain Research, 2005)

Bacterial Biofilm Development on Hydroxyapatite-Coated Glass - David Elliott; Jonathan Pratten; Mark Edwards; Jonathan Crowther; Aviva Petrie; Michael Wilson (Current Microbiology, 2005)

Sex differences in the perception of affective facial expressions: Do men really lack emotional sensitivity? - Barbara Montagne; Roy P. C. Kessels; Elisa Frigerio; Edward H. F. de Haan; David I. Perrett (Cognitive Processing, 2005)

Soybean aphid,Aphis glycines Matsumura, a new vector ofPotato virus Y in potato - Jeffrey A. Davis; Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2005)

Isopentenyl-diphosphate isomerase is essential for viability of Caenorhabditis elegans - John Yochem; David H. Hall; Leslie R. Bell; Edward M. Hedgecock; Robert K. Herman (Molecular Genetics and Genomics, 2005)

Characterization of photosynthetic electron transport in bundle sheath cells of maize. I. Ascorbate effectively stimulates cyclic electron flow around PSI - Boris Ivanov; Kozi Asada; David M. Kramer; Gerald Edwards (Planta, 2005)

Influence of bedrock geology and tree species composition on stream nitrate concentrations in mid-appalachian forested watersheds - Karl W.J. Williard; David R. Dewalle; Pamela J. Edwards (Water, Air, & Soil Pollution, 2005)

Genetic analysis and mapping of resistance to lettuce dieback: a soilborne disease caused by tombusviruses - Rebecca C. Grube; William M. Wintermantel; Paul Hand; Rami Aburomia; David A. C. Pink; Edward J. Ryder (Theoretical and Applied Genetics, 2005)

NMI-1182, a gastro-protective cyclo-oxygenase-inhibiting nitric oxide donor - James L. Ellis; Michael E. Augustyniak; Edward D. Cochran; Richard A. Earl; David S. Garvey; Laura J. Gordon; David R. Janero; Subhash P. Khanapure; L. Gordon Letts; Terry L. Melim; Madhavi G. Murty; David J. Schwalb; et al. (Inflammopharmacology, 2005)

Empirical Bayes estimation of gene-specific effects in micro-array research - Jode W. Edwards; Grier P. Page; Gary Gadbury; Moonseong Heo; Tsuyoshi Kayo; Richard Weindruch; David B. Allison (Functional & Integrative Genomics, 2005)

Constraints on willow seedling survival in a Rocky Mountain Montane floodplain - Edward A. Gage; David J. Cooper (Wetlands, 2004)

Dietary intake of Cruciferous vegetables, Glutathione S-transferase (GST) polymorphisms and lung cancer risk in a Caucasian population - Lisa I. Wang; Edward L. Giovannucci; David Hunter; Donna Neuberg; Li Su; David C. Christiani (Cancer Causes & Control, 2004)

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

EMD 281014, a specific and potent 5HT2 antagonist in humans: a dose-finding PET study - David Mamo; Ewen Sedman; Joachim Tillner; Edward M. Sellers; Myroslava K. Romach; Shitij Kapur (Psychopharmacology, 2004)

A gene-driven ENU-based approach to generating an allelic series in any gene - Mohamed Mohideen Quwailid; Alison Hugill; Neil Dear; Lucie Vizor; Sara Wells; Emma Horner; Shelly Fuller; Jessica Weedon; Hamish McMath; Paul Woodman; David Edwards; David Campbell; et al. (Mammalian Genome, 2004)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

Assessing the toxicity and teratogenicity of pond water in north-central minnesota to amphibians - Christine Bridges; Edward Little; David Gardiner; James Petty; James Huckins (Environmental Science and Pollution Research, 2004)

QTL controlling partial resistance to Stagonospora nodorum leaf blotch in winter wheat cultivar Alba - Edward Arseniuk; Pawel C. Czembor; Andrzej Czaplicki; Qijian Song; Perry B. Cregan; David L. Hoffman; Peter P. Ueng (Euphytica, 2004)

New Fluorescence Parameters for the Determination of QA Redox State and Excitation Energy Fluxes - David M. Kramer; Giles Johnson; Olavi Kiirats; Gerald E. Edwards (Photosynthesis Research, 2004)

Root production is determined by radiation flux in a temperate grassland community - Everard J. Edwards; David G. Benham; Louise A. Marland; Alastair H. Fitter (Global Change Biology, 2004)
Accurate knowledge of the response of root turnover to a changing climate is needed to predict growth and produce carbon cycle models. A soil warming system and shading were used to vary soil temperature and received radiation independently in a temperate grassland dominated by Holcus lanatus L. Minirhizotrons allowed root growth and turnover to be examined non‐destructively. In two short‐term (8 week) experiments, root responses to temperature were seasonally distinct. Root number increased when heating was applied during spring, but root death increased during autumnal heating. An experiment lasting 12 months demonstrated that any positive response to temperature was short‐lived and that over a full growing season, soil warming led to a reduction in root number and mass due to increased root death during autumn and winter. Root respiration was also insensitive to soil temperature over much of the year. In contrast, root growth was strongly affected by incident radiation. Root biomass, length, birth rate, number and turnover were all reduced by shading. Photosynthesis in H. lanatus exhibited some acclimation to shading, but assimilation rates at growth irradiance were still lower in shaded plants. The negative effects of shading and soil warming on roots were additive. Comparison of root data with environmental measurements demonstrated a number of positive relationships with photosynthetically active radiation, but not with soil temperature. This was true both across the entire data set and within a shade treatment. These results demonstrate that root growth is unlikely to be directly affected by increased soil temperatures as a result of global warming, at least in temperate areas, and that predictions of net primary productivity should not be based on a positive root growth response to temperature.

GROWTH, IMMORTALIZATION, AND DIFFERENTIATION POTENTIAL OF NORMAL ADULT HUMAN PROXIMAL TUBULE CELLS - DAVID E. OROSZ; PHILIP G. WOOST; ROBERT J. KOLB; MARGARET B. FINESILVER; WENWU JIN; PHYLLIS S. FRISA; CHEE-KEONG CHOO; CHUNG-FAI YAU; KWOK-WAH CHAN; MARTIN I. RESNICK; JANICE G. DOUGLAS; JOHN C. EDWARDS; et al. (In Vitro Cellular & Developmental Biology - Animal, 2004)

Growth, immortalization, and differentiation potential of normal adult human proximal tubule cells - David Orosz; Martin Resnick; Jurgen Wehland; Janice Douglas; John Edwards; James Jacobberger; Ulrich Hopfer; Philip Woost; Robert Kolb; Margaret Finesilver; Wenwu Jin; Phyllis Frisa; et al. (In Vitro Cellular & Developmental Biology - Animal, 2004)

Impact of soil warming and shading on colonization and community structure of arbuscular mycorrhizal fungi in roots of a native grassland community - Andreas Heinemeyer; Karyn P. Ridgway; Everard J. Edwards; David G. Benham; J. Peter W. Young; Alastair H. Fitter (Global Change Biology, 2004)
Arbuscular mycorrhizal (AM) fungi have a major influence on the structure, responses and below‐ground C allocation of plant communities. Our lack of understanding of the response of AM fungi to factors such as light and temperature is an obstacle to accurate prediction of the impact of global climate change on ecosystem functioning. In order to investigate this response, we divided a grassland site into 24 plots, each either unshaded or partly shaded with soil either unheated or heated by 3°C at 2 cm depth. In both short‐term studies in spring and autumn, and in a 1‐year‐long study, we measured root length colonization (L R C) by AM and non‐AM fungi. For selected root samples, DNA sequences were amplified by PCR with fungal‐specific primers for part of the small sub‐unit (SSU) rRNA gene. In spring, the total L R C increased over 6 weeks from 12% to 25%. Shading significantly reduced AM but increased non‐AM fungal colonization, while soil warming had no effect. In the year‐long study, colonization by AM fungi peaked in summer, whereas non‐AM colonization peaked in autumn, when there was an additive effect of shading and soil warming that reduced AM but increased non‐AM fungi. Stepwise regression revealed that light received within the 7 days prior to sampling was the most significant factor in determining AM L R C and that mean temperature was the most important influence on non‐AM L R C. Loglinear analysis confirmed that there were no seasonal or treatment effects on the host plant community. Ten AM fungal sequence types were identified that clustered into two families of the Glomales, Glomaceae and Gigasporaceae. Three other sequence types were of non‐AM fungi, all Ascomycotina. AM sequence types showed seasonal variation and shading impacts: loglinear regression analysis revealed changes in the AM fungal community with time, and a reduction of one Glomus sp. under shade, which corresponded to a decrease in the abundance of Trifolium repens. We suggest that further research investigating any impacts of climate change on ecosystem functioning must not only incorporate their natural AM fungal communities but should also focus on niche separation and community dynamics of AM fungi.

Preparing for Climatic Change: The Water, Salmon, and Forests of the Pacific Northwest - Philip W. Mote; Edward A. Parson; Alan F. Hamlet; William S. Keeton; Dennis Lettenmaier; Nathan Mantua; Edward L. Miles; David W. Peterson; David L. Peterson; Richard Slaughter; Amy K. Snover (Climatic Change, 2003)

Effects of Land Cover on Stream Ecosystems: Roles of Empirical Models and Scaling Issues - David L. Strayer; R. Edward Beighley; Lisa C. Thompson; Shane Brooks; Christer Nilsson; Gilles Pinay; Robert J. Naiman (Ecosystems, 2003)

Immunization with a vaccine that combines the expression of MUC1 and B7 co-stimulatory molecules prolongs the survival of mice and delays the appearance of mouse mammary tumors - Vitaly Vasilevko; Anahit Ghochikyan; Nadya Sadzikava; Irina Petrushina; Mike Tran; Edward P. Cohen; Patrick J. Kesslak; David H. Cribbs; Garth L. Nicolson; Michael G. Agadjanyan (Clinical & Experimental Metastasis, 2003)

Genetic analysis of resistance to Type-1 Diabetes in ALR/Lt mice, a NOD-related strain with defenses against autoimmune-mediated diabetogenic stress - Clayton E. Mathews; Robert T. Graser; Rebecca J. Bagley; Jason W. Caldwell; Renhua Li; Gary A. Churchill; David V. Serreze; Edward H. Leiter (Immunogenetics, 2003)

Intestinal Lymphatic Transport of Halofantrine Occurs After Oral Administration of a Unit-Dose Lipid-Based Formulation to Fasted Dogs - Shui-Mei Khoo; David M. Shackleford; Christopher J. H. Porter; Glenn A. Edwards; William N. Charman (Pharmaceutical Research, 2003)

The Tagliamento River: A model ecosystem of European importance - Klement Tockner; James V. Ward; David B. Arscott; Peter J. Edwards; Johannes Kollmann; Angela M. Gurnell; Geoffrey E. Petts; Bruno Maiolini (Aquatic Sciences, 2003)

Tuna schools/aggregations in surface longline data 1993–98 - David S. Kirby; Edward R. Abraham; Michael J. Uddstrom; Hudson Dean (New Zealand Journal of Marine and Freshwater Research, 2003)
Exploratory data analysis of a high‐resolution (hook‐by‐hook), 6‐year time series (1993–98) of observed longline catch data for tunas was used to investigate fine‐scale spatial patterns along individual sets that may be indicative of social behaviour (i.e., schooling) and/or the response of individual fish to favourable extrinsic conditions (i.e., aggregation). Methods of spatial data analysis (i.e., nearest neighbour analysis) that have previously been applied in various other sciences (e.g., forestry and astronomy) were used. Results indicate strong clustering of individual tunas at characteristic scales within the set. Mean Nearest Neighbour Distances (NNDs) were between 100 and 200 m, compared with NNDs of 200–700 m predicted by a heterogeneous Poisson process on the same spatial domain. The results suggest that these adult tunas were either schooling or aggregating at the time of capture; this may therefore be related either to social behaviour or to sub‐mesoscale oceanographic features. An aggregation index was derived from the NNDs, giving a classification method that may be used for similar data and the development of empirical models attempting to relate patterns in fish catch distributions to environmental variables. The success of such models will ultimately depend on elucidating the ecological processes reflected in oceanographic features at biologically meaningful spatial scales.

Abundance and distribution of planktonic Archaea and Bacteria in the waters west of the Antarctic Peninsula - Matthew J. Church; Edward F. DeLong; Hugh W. Ducklow; Markus B. Karner; Christina M. Preston; David M. Karl (Limnology and Oceanography, 2003)
Polyribonucleotide probes targeting planktonic archaeal (Group I and II) and bacterial rRNA revealed that Archaea comprised a significant fraction of total prokaryote cell abundance in the marine waters west of the Antarctic Peninsula. Determinations of Archaea and Bacteria cell abundances were made during two research cruises to the Palmer Long‐Term Ecological Research region during the austral winter and summer of 1999. During the austral summer, surface water abundances of Group I (GI) Archaea were generally low, averaging 4.7 x 10 3 cells ml −1 and accounting for 1% of the total picoplankton assemblage. The abundance of GI Archaea increased significantly with depth, averaging 2.1 X 10 4 cells ml −1 and comprising 9–39% of the total picoplankton abundance in the meso‐ (150–1,000 m) and bathypelagic (1,000–3,500 m) circumpolar deep water (CDW). Relative to summertime distributions, GI cells were more evenly distributed throughout the water column during the winter, averaging 10% of the picoplankton in the surface waters and 13% in the CDW. Surface water GI abundance increased 44% between the summer and winter, coincident with a fivefold decrease in GI abundance in the deeper waters. The abundance of Group II (GII) Archaea was persistently 5 cells ml −1 and comprised 89% of the total picoplankton assemblage. Generally, GI Archaea varied seasonally in the deeper waters, whereas bacterial abundance varied more in the upper waters. The observed variability in bacterial and archaeal abundance suggests that these two groups of marine picoplankton are dynamic components of Southern Ocean microbial food webs.

Signal that reboxetine use is linked with symptoms of peripheral ischaemia (Raynaud's syndrome) - David W. J. Clark; Ana-Maria Correa-Nunes; I. Ralph Edwards (European Journal of Clinical Pharmacology, 2003)

Cloning, characterization and regulation of a family of phi class glutathione transferases from wheat - Ian Cummins; David O'Hagan; Istvan Jablonkai; David J. Cole; Alain Hehn; Danièle Werck-Reichhart; Robert Edwards (Plant Molecular Biology, 2003)

Haplotype diversity in the interleukin-4 gene is not associated with HIV-1 transmission and AIDS progression - William S. Modi; Thomas R. O'Brien; David Vlahov; Susan Buchbinder; Edward Gomperts; John Phair; Stephen J. O'Brien; Cheryl Winkler (Immunogenetics, 2003)

Reduced hybrid cluster proteins (HCP) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at high resolution using synchrotron radiation - David Aragão; Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Ming Y. Liu; Carlos Frazão; Lígia M. Saraiva; António V. Xavier; Jean LeGall; Walter M. A. M. van Dongen; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2003)

Effects of ultraviolet radiation on toad early life stages - Edward E. Little; Robin D. Calfee; David L. Fabacher; Cynthia Carey; Vicki S. Blazer; Elizabeth M. Middleton (Environmental Science and Pollution Research, 2003)

Minisatellite DNA profiling detects lineages and parentage in the endangered kakapo (Strigops habroptilus) despite low microsatellite DNA variation - Hilary C. Miller; David M. Lambert; Craig D. Millar; Bruce C. Robertson; Edward O. Minot (Conservation Genetics, 2003)

Understanding Climatic Impacts, Vulnerabilities, and Adaptation in the United States: Building a Capacity for Assessment - Edward A. Parson; Robert W. Corell; Eric J. Barron; Virginia Burkett; Anthony Janetos; Linda Joyce; Thomas R. Karl; Michael C. MacCracken; Jerry Melillo; M. Granger Morgan; David S. Schimel; Thomas Wilbanks (Climatic Change, 2003)

Molecular diversity among marine picophytoplankton as revealed by psbA analyses - Gil Zeidner; Christina M. Preston; Edward F. Delong; Ramon Massana; Anton F. Post; David J. Scanlan; Oded Béjà (Environmental Microbiology, 2003)
Summary Photosynthetic microorganisms play a crucial role in the marine environment. In vast areas of the oceans, marine primary productivity is performed by cells smaller than 2–3 µm (picoplankton). Here, we report on molecular analyses of the conserved photosynthetic psbA gene (coding for protein D1 of photosystem II reaction centre) as a diversity indicator of naturally occurring marine oxygenic picophytoplankton. The psbA genes proved to be good indicators of the presence of a wide variety of photosynthetic marine microbial groups, including new cyanobacterial groups and eukaryotic algae (prasinophytes). Furthermore, using environmental bacterial artificial chromosome (BAC) libraries, we were able to correlate psbA genes with small subunit rRNAs and, therefore, to confirm their phylogenetic affiliation.

Nitrous oxide emission from agricultural drainage waters - David S. Reay; Keith A. Smith; Anthony C. Edwards (Global Change Biology, 2003)
Uncertainty about the amounts of the greenhouse gas nitrous oxide (N 2 O), which arise from N leaching from agricultural soils, predominantly as nitrate (NO 3 – ), is large. To date, the bulk of studies of N 2 O in aquatic systems have relied upon measurement of dissolved N 2 O concentrations at wide spatial intervals (of the order of km) down a stream, river or estuary. When we combined a fine‐scale (m) assessment of N 2 O concentrations in agricultural drainage water with novel measurement of net N 2 O emission from the same drainage system, we found that dissolved N 2 O in agricultural drainage water was very rapidly lost to the atmosphere, while dissolved NO 3 – in the same water was conserved. Consequently, the N 2 O emission factor (as a proportion of the nitrate‐N present, the IPCC's ‘EF 5 ’) fell by a factor of more than 5 within only 100 m. Direct measurement of N 2 O emission from the drainage water confirmed the disappearance of N 2 O as being due to emission from water to the atmosphere, rather than in situ consumption by denitrification. Our findings indicate that making widely spaced measurements of dissolved N 2 O concentration and/or emissions from the water surface will not take account of this much more dynamic behaviour over short distances. Realistic assessment of the ‘indirect’ agricultural emissions of N 2 O from leached N will necessitate much more intensive sampling of the whole drainage system, from ditch to stream to river to estuary, accompanied by measurements of in‐stream production. The quantities of N 2 O actually released in the ditches gave values for EF 5‐g (the IPCC's emission factor for N 2 O from surface drainage and groundwaters) of between 0.02 and 0.03%, compared with the IPCC value of 1.5%. For the latter to be realistic, the quantity of N 2 O required to be formed after the initial entry of water into the drainage system would need to exceed the initial load by the order of 50‐fold.

Aphid-transmitted potato viruses: The importance of understanding vector biology - Edward B. Radcliffe; David W. Ragsdale (American Journal of Potato Research, 2002)

Effects of aerobic fitness training on human cortical function - Arthur F. Kramer; Stanley Colcombe; Kirk Erickson; Artem Belopolsky; Edward McAuley; Neal J. Cohen; Andrew Webb; Gerald J. Jerome; David X. Marquez; Tracey M. Wszalek (Journal of Molecular Neuroscience, 2002)

Probing the Diversity of the Arabidopsis glutathione S-Transferase Gene Family - Ulrich Wagner; Robert Edwards; David P. Dixon; Felix Mauch (Plant Molecular Biology, 2002)

On birth and death in the sea - Mark D. Ohman; Jeffrey A. Runge; Edward G. Durbin; David B. Field; Barbara Niehoff (Hydrobiologia, 2002)

Hybrid cluster proteins (HCPs) from Desulfovibrio desulfuricans ATCC 27774 and Desulfovibrio vulgaris (Hildenborough): X-ray structures at 1.25 Å resolution using synchrotron radiation - Sofia Macedo; Edward P. Mitchell; Célia V. Romão; Serena J. Cooper; Ricardo Coelho; Ming Y. Liu; António V. Xavier; Jean LeGall; Susan Bailey; David C. Garner; Wilfred R. Hagen; Miguel Teixeira; et al. (JBIC Journal of Biological Inorganic Chemistry, 2002)

Chronic inhibition of α4β2 nicotinic receptors in the ventral hippocampus of rats: impacts on memory and nicotine response - David Arthur; Edward Levin (Psychopharmacology, 2002)

Ecosystem response to bivalve density reduction: management implications - Richard Dame; David Bushek; Dennis Allen; Alan Lewitus; Don Edwards; Eric Koepfler; Leah Gregory (Aquatic Ecology, 2002)

Early Detection of G + C Differences in Bacterial Species Inferred from the Comparative Analysis of the Two Completely Sequenced Helicobacter pylori Strains - Matthew Bellgard; David Schibeci; Edward Trifonov; Takashi Gojobori (Journal of Molecular Evolution, 2001)

Canine TCOF1; cloning, chromosome assignment and genetic analysis in dogs with different head types - Kim E. Haworth; Ira Islam; Matthew Breen; Wendy Putt; Eleni Makrinou; Matthew Binns; David Hopkinson; Yvonne Edwards (Mammalian Genome, 2001)

TUMOR-ASSOCIATED ANTIGEN EXPRESSION AND GROWTH REQUIREMENTS PREDICT TUMORIGENESIS IN SQUAMOUS CELL CARCINOMA - EDWARD R. SAUTER; DAVID TICHANSKY; E. ELIZABETH FURTH; MEENHARD HERLYN (In Vitro Cellular & Developmental Biology - Animal, 2001)

Changes in primary DNA sequence complexity influence the phenotypic consequences of mutations in human gene regulatory regions - Michael Krawczak; Nadia Chuzhanova; Peter Stenson; Bent Johansen; Edward Ball; David Cooper (Human Genetics, 2000)

Incorporation of the intracellular elemental correlation pattern into simulation models of phytoplankton uptake and population dynamics - Vladimir Krivtsov; Edward Bellinger; David Sigee (Journal of Applied Phycology, 2000)

Nociceptin/orphanin FQ (N/OFQ) induces a quasi-morphine abstinence syndrome in the rat - David H. Malin; J. Ronald Lake; William D. Moon; Debora Moy; Ana L. Montellano; Edward Moy; Tracy D. Campbell; Maurice V. Bell; Dana Bryant; Laura M. Harrison; David K. Grandy (Psychopharmacology, 2000)

Comparative toxicity of trivalent and pentavalent inorganic and methylated arsenicals in rat and human cells - Miroslav Styblo; Luz M. Del Razo; Libia Vega; Dori R. Germolec; Edward L. LeCluyse; Geraldine A. Hamilton; William Reed; Changqing Wang; William R. Cullen; David J. Thomas (Archives of Toxicology, 2000)

Renal effects of cyclooxygenase inhibitors in volume-depleted dogs - David P. Brooks; Jerry Adams; P. Dennis DePalma; Edward F. Webb; Robert H. Palmer; Don E. Griswold (Inflammopharmacology, 2000)

Microsatellite primers for the kakapo (Strigops habroptilus) and their utility in other parrots - Bruce C. Robertson; Edward O. Minot; David M. Lambert (Conservation Genetics, 2000)

Factors influencing the induction of diapausing egg production in the calanoid copepod Diaptomus leptopus - David W. Piercey; Edward J. Maly (Aquatic Ecology, 2000)

Surface pollen‐vegetation relationships on the Atlantic seaboard: South Uist, Scotland - Barbara A. Brayshay; David D. Gilbertson; Martin Kent*; Kevin J. Edwards; Peter Wathern; Ruth E. Weaver (Journal of Biogeography, 2000)
Studies of modern pollen rain from remote islands have raised a number of interesting issues concerning the spatial precision of present‐day pollen spectra in relation to their parent plant community types. This paper examines the relationships and degree of correlation between a sequence of contemporary vegetation types, environments and their associated surface pollen spectra from a transect across the island of South Uist in the Outer Hebrides of Scotland. Paired data on both contemporary vegetation and associated surface pollen assemblages have been collected and analysed using methods of numerical classification and ordination. In general terms, the modern pollen rain on South Uist reflects the major changes in vegetation pattern and the major community types fairly closely. The major boundary between the alkaline machair sand dune communities and the various acidic upland vegetation types is particularly clear. However, both variability in the vegetation and the effects of the strong prevailing westerly and south‐westerly winds tend to blur the boundaries of the various communities within each of these larger categories. On average 86.6% of the palynomorphs come from in‐community quadrat sources, while only 1.3% are from off‐island sources. The limited present‐day tree distribution on the transect is discussed in the context of the more widespread distribution of arboreal pollen. Overall, there is a strong numerical correspondence between vegetation, pollen and environmental variables. The various problems inherent in examining surface pollen spectra are reviewed.

Formulation and Physical Characterization of Large Porous Particles for Inhalation - Rita Vanbever; Jeffrey D. Mintzes; Jue Wang; Jacquelyn Nice; Donghao Chen; Richard Batycky; Robert Langer; David A. Edwards (Pharmaceutical Research, 1999)

Dimerisation of maize glutathione transferases in recombinant bacteria - David P. Dixon; David J. Cole; Robert Edwards (Plant Molecular Biology, 1999)

Molecular sexing of individual kakapo, Strigops habroptilus Aves, from faeces - Bruce C. Robertson; Edward O. Minot; David M. Lambert (Molecular Ecology, 1999)

Parametric and Nonparametric Nonlinear System Identification of Lung Tissue Strip Mechanics - Huichin Yuan; David T. Westwick; Edward P. Ingenito; Kenneth R. Lutchen; Béla Suki (Annals of Biomedical Engineering, 1999)

Tolerance of an Albino Fish to Ultraviolet-B Radiation - David L. Fabacher; Edward E. Little; Gary K. Ostrander (Environmental Science and Pollution Research, 1999)

Technique to Determine Inspiratory Impedance during Mechanical Ventilation: Implications for Flow Limited Patients - David W. Kaczka; Edward P. Ingenito; Kenneth R. Lutchen (Annals of Biomedical Engineering, 1999)

Large Porous Particles for Sustained Protection from Carbachol-Induced Bronchoconstriction in Guinea Pigs - Abdellaziz Ben-Jebria; Donghao Chen; Mary Lou Eskew; Rita Vanbever; Robert Langer; David A. Edwards (Pharmaceutical Research, 1999)

An example of intron junctional sliding in the gene families encoding squalene monooxygenase homologues in Arabidopsis thaliana and Brassica napus* - Ulrike A. Schäfer; Darwin W. Reed; David G. Hunter; Kening Yao; Alan M. Weninger; Edward W.T. Tsang; Martin J.T. Reaney; Samuel L. MacKenzie; Patrick S. Covello (Plant Molecular Biology, 1999)

Callinectin, an Antibacterial Peptide from Blue Crab, Callinectes sapidus, Hemocytes - Lester Khoo; David W. Robinette; Edward J. Noga (Marine Biotechnology, 1999)

Isolation and characterization of an Arabidopsis thaliana C-8,7 sterol isomerase: functional and structural similarities to mammalian C-8,7 sterol isomerase/emopamil-binding protein - Robert J. Grebenok; Thomas E. Ohnmeiss; Alvin Yamamoto; Edward D. Huntley; David W. Galbraith; Dean Della Penna (Plant Molecular Biology, 1998)

Permeability of Articular Cartilage to Matrix Metalloprotease Inhibitors - Sean X. Peng; Edward C. VonBargen; David M. Bornes; Stanislaw Pikul (Pharmaceutical Research, 1998)

Erratum - David L. Fabacher; Edward E. Little (Environmental Science and Pollution Research, 1998)

Photoprotective substance occurs primarily in outer layers of fish skin - David L. Fabacher; Edward E. Little (Environmental Science and Pollution Research, 1998)

Effects of climate change on nitrogen dynamics in upland soils. 1. A transplant approach - Philip Ineson; Kenneth Taylor; Anthony F. Harrison; Janet Poskitt; David G. Benham; Edward Tipping; Colin Woof (Global Change Biology, 1998)
The impact of climate change on N leaching from hill land plant/soil systems was investigated using a transplant technique involving the movement of intact lysimeter cores of three contrasting soil types down an altitudinal gradient at Great Dun Fell, Cumbria. Air and soil temperatures and precipitation were monitored at four elevations down an altitudinal transect using automatic weather stations for a period of two years. The altitudinal sequence of air temperature followed the anticipated pattern, providing mean annual temperatures at the four locations of 3.4, 5.0, 6.3 and 8.1 °C. Lapse rates of both mean air and soil temperatures over the altitudinal range 171–845 m were 6.6 (1993) and 7.0 °C km –1 (1994). Soil monthly temperature gradients for a particular soil type for each of the two years showed a seasonal range of 6.0 and 7.4 °C km –1 , respectively, and for air temperature of 4.3 and 3.1 °C km –1 . Precipitation gradients showed the expected general increase with altitude, but were less predictable. Inorganic nitrogen leaching was studied in lysimeter leachates with climatic amelioration resulting in dramatic reductions in leachate nitrate concentrations and associated total concentrations of inorganic nitrogen. Decreases in leachate nitrate concentrations were observed for all three soil types studied. Soils receiving supplemented rainfall also showed decreased N concentrations, suggesting that temperature was the main controlling factor responsible for the observed reductions. Increased N uptake by the vegetation, in response to the increases in temperature, is considered to be critical in controlling soil solution chemistry at these sites.

Purification, regulation and cloning of a glutathione transferase (GST) from maize resembling the auxin-inducible type-III GSTs - David P. Dixon; David J. Cole; Robert Edwards (Plant Molecular Biology, 1998)

Mapping to Chromosomes 1 and 12 of mouse homologs of human protein tyrosine phosphatase, receptor-type, related genes encoding pancreatic beta cell autoantigens - Edward H. Leiter; Hideki Tsumura; David V. Serreze; Harold D. Chapman; Daniel U. Rabin; Michael S. Lan; Abner L. Notkins (Mammalian Genome, 1997)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The quaternary glacial history of the Lahul Himalaya, northern India - Lewis A. Owen; Edward Derbyshire; Shaun Richardson; Dougie I. Benn; David J. A. Evans; Wishart A. Mitchell (Journal of Quaternary Science, 1996)

The quaternary glacial history of the Lahul Himalaya, northern India - Lewis A. Owen; Edward Derbyshire; Shaun Richardson; Dougie I. Benn; David J. A. Evans; Wishart A. Mitchell (Journal of Quaternary Science, 1996)

Potato leafroll virus spread in differentially resistant potato cultivars under varying aphid densities - Christina D. DiFonzo; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1995)

New Sensor Technology for In Situ Measurements of Ocean Chemistry - David Walt; Edward Urban (Oceanography, 1995)

Induction of hepatic microsomal CYP4A activity and of peroxisomal β-oxidation by two non-steroidal anti-inflammatory drugs - Eleni Rekka; Edward O. Ayalogu; David F. V. Lewis; Gordon G. Gibson; Costas Ioannides (Archives of Toxicology, 1994)

Use of enzyme-linked immunosorbent assay to detect potato leafroll virus in field grown potato, cv. Russet Burbank - Kathy L. Flanders; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1990)

Use of enzyme-linked immunosorbent assay to detect potato leafroll virus in field grown potato, cv. Russet Burbank - Kathy L. Flanders; David W. Ragsdale; Edward B. Radcliffe (American Journal of Potato Research, 1990)

Regulation of sulfate assimilation in Cytophaga johnsonae - David F. Gilmore; Walter Godchaux; Edward R. Leadbetter (Archives of Microbiology, 1989)

Replacement of potassium ions by ammonium ions in different micro-organisms grown in potassium-limited chemostat culture - Edward T. Buurman; Jill Pennock; David W. Tempest; M. Joost Teixeira de Mattos; Oense M. Neijssel (Archives of Microbiology, 1989)

Queen number and the production of sexuals in the fire ant, Solenopsis invicta (Hymenoptera: Formicidae) - Edward L. Vargo; David J. C. Fletcher (Behavioral Ecology and Sociobiology, 1986)

Human succinate dehydrogenase: Biochemical and genetic characterization - Marie-Anne Shaw; Yvonne Edwards; David A. Hopkinson (Biochemical Genetics, 1981)

Characterization of human carbonic anhydrase III from skeletal muscle - Nicholas Carter; Stephen Jeffery; Alan Shiels; Yvonne Edwards; Terry Tipler; David A. Hopkinson (Biochemical Genetics, 1979)

Analytical methodology for the determination of Kepone® residues in fish, shellfish, and Hi-Vol air filters - David W. Hodgson; Edward J. Kantor; J. Bruce Mann (Archives of Environmental Contamination and Toxicology, 1978)

DNA synthesis by Escherichia coli B/r/l synchronized and grown under conditions of slow growth - David Edward Buckley; Gerasimos Demetriou Anagnostopoulos (Archives of Microbiology, 1976)

Growth of Escherichia coli B/r/l in a semi-continuous system designed for the synchronization of cell division - David Edward Buckley; Gerasimos Demetriou Anagnostopoulos (Archives of Microbiology, 1975)

Identification of maize seedling mutants lacking starch accumulation capacity - Edward L. Cox; David B. Dickinson (Biochemical Genetics, 1971)